Theoretical reduction of the incidence of colorectal cancer in Colombia from reduction in the population exposure to tobacco, alcohol, excess weight and sedentary lifestyle: a modelling study - de Vries, Esther; Torres, Miguel Zamir; Rojas, Martha Patricia; Díaz, Gustavo; Herrán, Oscar Fernando (BMJ Open, 2020)
Aims To determine the potential impact fraction of alcohol and tobacco consumption, high body mass index and low physical activity on colorectal cancer burden in Colombia for the period 2016–2050. Methods Based on age-specific and sex-specific data on colorectal cancer incidence, data from population-based surveys for the exposure data and population projections, the macrosimulation model Prevent V.3.01 was used to model expected colorectal cancer incidence for the period 2016–2050. Baseline models were those where exposure levels were not subject to change because of interventions. Two intervention scenarios were specified: one with elimination of exposure to the risk factor as of 2017 and a second one where over a 10-year period the current prevalence data gradually declined until they reach 90% of the 2016 levels. Results Under the reference scenarios, a total number of 274 637 colorectal cancers would be expected to occur in the period 2016–2050. Under the scenario of 10% gradual decline in the prevalence of alcohol and tobacco consumption, physical inactivity and high body mass index, a total of 618, 488, 2954 and 2086 new cases, respectively, would be avoided. Under scenarios of elimination, these numbers of avoided cases would be 6908 (elimination alcohol), 6104 (elimination tobacco), 16 637 (optimizing physical inactivity) and 25 089 (all on ideal weight). Conclusions In order to reduce the burden of colorectal cancer, it is important to take measures to halt the current trends of increasing sedentary behaviour and overweight in the Colombian population. Proportionally, alcohol and tobacco consumption are less important population risk factors for colorectal cancer.

Colorectal cancer, screening and primary care: A mini literature review - Hadjipetrou, Athanasios; Anyfantakis, Dimitrios; Galanakis, Christos G; Kastanakis, Miltiades; Kastanakis, Serafim (World Journal of Gastroenterology, 2017)

Colorectal cancer - Kuipers, Ernst J.; Grady, William M.; Lieberman, David; Seufferlein, Thomas; Sung, Joseph J.; Boelens, Petra G.; van de Velde, Cornelis J. H.; Watanabe, Toshiaki (Nature Reviews Disease Primers, 2015)

Gut microbiota and colorectal cancer - Gao, R.; Gao, Z.; Huang, L.; Qin, H. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Annual Report to the Nation on the Status of Cancer, Part 2: Patient Economic Burden Associated With Cancer Care - Yabroff, K Robin; Mariotto, Angela; Tangka, Florence; Zhao, Jingxuan; Islami, Farhad; Sung, Hyuna; Sherman, Recinda L; Henley, S Jane; Jemal, Ahmedin; Ward, Elizabeth M (JNCI: Journal of the National Cancer Institute, 2021)
Abstract Background The American Cancer Society, National Cancer Institute, Centers for Disease Control and Prevention, and North American Association of Central Cancer Registries provide annual information about cancer occurrence and trends in the United States. Part 1 of this annual report focuses on national cancer statistics. This study is part 2, which quantifies patient economic burden associated with cancer care. Methods We used complementary data sources, linked Surveillance, Epidemiology, and End Results-Medicare, and the Medical Expenditure Panel Survey to develop comprehensive estimates of patient economic burden, including out-of-pocket and patient time costs, associated with cancer care. The 2000-2013 Surveillance, Epidemiology, and End Results-Medicare data were used to estimate net patient out-of-pocket costs among adults aged 65 years and older for the initial, continuing, and end-of-life phases of care for all cancer sites combined and separately for the 21 most common cancer sites. The 2008-2017 Medical Expenditure Panel Survey data were used to calculate out-of-pocket costs and time costs associated with cancer among adults aged 18-64 years and 65 years and older. Results Across all cancer sites, annualized net out-of-pocket costs for medical services and prescriptions drugs covered through a pharmacy benefit among adults aged 65 years and older were highest in the initial ($2200 and $243, respectively) and end-of-life phases ($3823 and $448, respectively) and lowest in the continuing phase ($466 and $127, respectively), with substantial variation by cancer site. Out-of-pocket costs were generally higher for patients diagnosed with later-stage disease. Net annual time costs associated with cancer were $304.3 (95% confidence interval = $257.9 to $350.9) and $279.1 (95% confidence interval = $215.1 to $343.3) for adults aged 18-64 years and ≥65 years, respectively, with higher time costs among more recently diagnosed survivors. National patient economic burden, including out-of-pocket and time costs, associated with cancer care was projected to be $21.1 billion in 2019. Conclusions This comprehensive study found that the patient economic burden associated with cancer care is substantial in the United States at the national and patient levels.

The implications of out-of-pocket cost of cancer treatment in the USA: a critical appraisal of the literature - Bestvina, Christine M; Zullig, Leah L; Yousuf Zafar, S (Future Oncology, 2014)
ABSTRACT Advances in cancer diagnosis and treatment have led to increased societal costs and out-of-pocket patient cost. We reviewed the literature on the impact of out-of-pocket cancer care costs on the patient experience, and described efforts made to address these costs. A critical appraisal of articles published in the USA from 2004 to 2014 was performed. The literature revealed that even insured patients receiving anticancer therapy are vulnerable to financial distress, which can impel patients to borrow money, deplete their savings, or engage in cost-coping strategies including nonadherence to prescribed treatment. Additional research is required to define financial distress risk factors, patient–physician communication of the costs of cancer care, and supportive care models for patients and survivors with substantial financial burdens.

Past, present, and future of global health financing: a review of development assistance, government, out-of-pocket, and other private spending on health for 195 countries, 1995–2050 - Chang, Angela Y.; Cowling, Krycia; Micah, Angela E.; Chapin, Abigail; Chen, Catherine S.; Ikilezi, Gloria; Sadat, Nafis; Tsakalos, Golsum; Wu, Junjie; Younker, Theodore; Zhao, Yingxi; Zlavog, Bianca S.; et al. (The Lancet, 2019)

Cómo Enfrentar La Creciente Carga Del Cáncer En Colombia: Desafíos Y Oportunidades - López, Dr Jairo Aguilera

Heart Failure in Women - Bozkurt, Biykem; Khalaf, Shaden (Methodist DeBakey Cardiovascular Journal, 2017)

ANATOMY OF THE ATTACHMENTS OF THE DIAPHRAGM: THEIR RELATION TO THE PROBLEMS OF THE SURGERY OF DIAPHRAGMATIC HERNIA - Rives, J. D.; Baker, D. D.; Orleans, New (Annals of Surgery, 1942)

Anatomy of the Crura of the Diaphragm and the Surgery of Hiatus Hernia - Collis, J. L.; Kelly, T. D.; Wiley, A. M. (Thorax, 1954)

The management of hiatal hernia: an update on diagnosis and treatment - Sfara, Alice; Dumitrașcu, Dan L (Medicine and Pharmacy Reports, 2019)
Background and aim. Hiatal hernia (HH) occurs quite frequently in the general population and is characterized by a wide range of non-specific symptoms, most of them related to gastroesophageal reflux disease. Treatment can be challenging at times, depending on the existence of complications. The most recent guideline regarding the management of hiatal hernia was released by the Society of American Gastrointestinal and Endoscopic Surgeons (SAGES) in the year 2013. This review aims to present  the most recent updates on the diagnosis and management of hiatal hernia for clinical practitioners. Methods. The PubMed database was screened for publications using the terms: “hiatal hernia”, “paraesophageal hernia”, “management”, “treatment”, “hiatal repair”. A literature review of contemporary and latest studies was completed. The studies that we looked into include prospective, randomized trials, systematic reviews, clinical reviews and original articles. The information was compiled in narrative review format. Results. This narrative review presents new data on the diagnosis and management of hiatal hernia. While the diagnostic pathway has remained virtually unchanged, new data have come to light regarding the surgical treatment of hiatal hernia. We present the imaging methods used for its diagnosis, as well as the medical and surgical treatment currently available. Conclusions. In the last five years, there has been vast research in the field of hiatal hernia management, especially regarding the surgical treatment. However, unanswered questions still remain and solid updates on the guidelines have yet to be formulated. To address this, more randomized studies need to be done on subsets of patients, stratified by age, gender, symptoms and comorbidities.

Diaphragmatic dysfunction - Ricoy, J.; Rodríguez-Núñez, N.; Álvarez-Dobaño, J.M.; Toubes, M.E.; Riveiro, V.; Valdés, L. (Pulmonology, 2019)

Anatomía clínica - Pró, Eduardo Adrián (Editorial Médica Panamericana, 2014)

Efficacy and safety of modified bilateral thoracoscopy-assisted Nuss procedure in adult patients with pectus excavatum - Cheng, Y.-L.; Lee, S.-C.; Huang, T.-W.; Wu, C.-T. (European Journal of Cardio-thoracic Surgery, 2008)
Cited By :50
Cited By :50
Cited By :50
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Femenino; Humanos; Masculino; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Toracoscopía/métodos; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adulto; Estudios Prospectivos; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Adulto Joven; Esternón/cirugía; Estudios de Seguimiento; Toracoscopía/efectos adversos; Antiinflamatorios no Esteroideos/uso terapéutico

Minimally Invasive Repair for Pectus Excavatum in Adults - Teh, S.H.; Hanna, A.M.; Pham, T.H.; Lee, A.; Deschamps, C.; Stavlo, P.; Moir, C. (Annals of Thoracic Surgery, 2008)
Cited By :25
Cited By :25
Cited By :25
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Resultado del Tratamiento; Adulto; Dolor Postoperatorio/etiología; Procedimientos Quirúrgicos Mínimamente Invasivos; Complicaciones Posoperatorias/etiología; Tórax Paradójico/cirugía

Is epidural anesthesia truly the best pain management strategy after minimally invasive pectus excavatum repair? - St Peter, S.D.; Weesner, K.A.; Sharp, R.J.; Sharp, S.W.; Ostlie, D.J.; Holcomb III, G.W. (Journal of Pediatric Surgery, 2008)
Cited By :45
Cited By :45
Cited By :45
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Toracoscopía/métodos; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Tórax en Embudo/diagnóstico; Tiempo de Internación; Satisfacción del Paciente; Dimensión del Dolor; Estudios de Seguimiento; Anestesia Intravenosa/métodos; Dolor Postoperatorio/fisiopatología; Anestesia Epidural/métodos; Factores de Tiempo; Sensibilidad y Especificidad; Probabilidad

Pain Quality After Pediatric Pectus Excavatum Repair - Manworren, Renee C. B.; Di Franco, Maria Victoria; Mishra, Trishla; Kaduwela, Naomi (Pain Management Nursing: Official Journal of the American Society of Pain Management Nurses, 2022)
BACKGROUND: Neuropathic pain medications are included in multimodal postoperative analgesic strategies, but quality of perioperative pain is rarely assessed. AIMS: The purpose of this study was to describe adolescents' pain experiences after thoracoscopic pectus excavatum repair (Nuss procedure) using the Adolescent Pediatric Pain Tool. DESIGN: This prospective descriptive longitudinal study was designed to test the hypothesis that pain quality descriptors reported are consistent with neuropathic pain. METHODS: A convenience sample of 23 adolescents aged 12 to 17 years from a single urban, university affiliated, nonprofit children's hospital consented to self-report pain using the Adolescent Pediatric Pain Tool before and during hospitalization, and up to 14 months after Nuss procedure. Visual analytic techniques were used to analyze reported pain intensity, location, and affective, evaluative, sensory, and temporal qualities. RESULTS: Postoperative pain quality, intensity, number of sites, and surface area decreased over time. Word clouds illustrated that neuropathic sensory and temporal pain quality descriptors increased in frequency 2 to 6 weeks after surgery and were the predominant descriptors 2 to 4 months after surgery. Dot matrix charts illustrated an inconsistent relationship of pain quality and intensity with pain surface area. CONCLUSIONS: Pain quality should be assessed with valid, reliable, and developmentally appropriate tools. Visual analytics help illustrate pain quality at single points in time and longitudinally and may be helpful in guiding postoperative pain treatment.
Keywords: Humans; Adolescent; Child; Funnel Chest; Longitudinal Studies; Neuralgia; Pain, Postoperative; Retrospective Studies; Treatment Outcome

Postoperative pain following minimally invasive repair of pectus excavatum: A descriptive study - Ganescu, Olivia; Emil, Sherif; Saint-Martin, Christine; Guadagno, Elena; Laberge, Jean-Martin; LaRusso, Kathryn; Frigon, Chantal (Journal of Pediatric Surgery, 2022)
BACKGROUND: Minimally Invasive Repair of Pectus Excavatum (MIRPE) is associated with significant postoperative pain. The objective of our study was to characterize the severity and duration of this pain, and to investigate possible associations with pectus severity. METHODS: We conducted a retrospective cohort study of pediatric patients who underwent MIRPE from January 2014 to April 2018. Pectus excavatum (PE) severity was determined with 3 indices measured from computed tomography: Depression Index (DI), Correction Index (CI), and Haller index (HI). Mean pain scores for every 6-hour period and the presence of pain and intake of analgesics during follow-up were extracted from the medical record. RESULTS: The cohort included 57 patients with a mean age of 15.9 ± 1.3 years. All 3 severity indices were positively correlated, with a correlation coefficient of 0.8 between the DI and CI. The requirement for 2 bars was significantly associated with higher indices (95% CI:0.18-0.63, p = 0.01). Pain was managed with thoracic epidural analgesia for all but one patient. Growth linear modeling identified five different pain trajectory subgroups of patients up to post-operative day 5. None of the tested predictors (age, gender, body image, physical activity level, DI, CI, HI, difference deformity-epidural level) were significantly associated with class membership. Persistent pain at one-year follow-up was present in 18% of patients, all with severe deformity (DI≥0.8). CONCLUSION: Pain trajectory and intensity after MIRPE can be classified into discrete patterns but are not influenced by PE severity. Severe deformity seems to predict persistent pain at one year.
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Humanos; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Dolor Postoperatorio/epidemiología; Adolescent; Dolor Postoperatorio/etiología; Tórax en Embudo; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Analgésicos; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Depression index; Level III; Minimally invasive repair; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Persistent post surgical pain; Post-operative pain; Retrospective Study; Severity deformity

Intraoperative intercostal nerve cryoablation During the Nuss procedure reduces length of stay and opioid requirement: A randomized clinical trial - Graves, Claire E.; Moyer, Jarrett; Zobel, Michael J.; Mora, Roberto; Smith, Derek; O'Day, Maura; Padilla, Benjamin E. (Journal of Pediatric Surgery, 2019)
PURPOSE: Minimally-invasive repair of pectus excavatum by the Nuss procedure is associated with significant postoperative pain, prolonged hospital stay, and high opiate requirement. We hypothesized that intercostal nerve cryoablation during the Nuss procedure reduces hospital length of stay (LOS) compared to thoracic epidural analgesia. DESIGN: This randomized clinical trial evaluated 20 consecutive patients undergoing the Nuss procedure for pectus excavatum between May 2016 and March 2018. Patients were randomized evenly via closed-envelope method to receive either cryoanalgesia or thoracic epidural analgesia. Patients and physicians were blinded to study arm until immediately preoperatively. SETTING: Single institution, UCSF-Benioff Children's Hospital. PARTICIPANTS: 20 consecutive patients were recruited from those scheduled for the Nuss procedure. Exclusion criteria were age < 13 years, chest wall anomaly other than pectus excavatum, previous repair or other thoracic surgery, and chronic use of pain medications. MAIN OUTCOMES AND MEASURES: Primary outcome was postoperative LOS. Secondary outcomes included total operative time, total/daily opioid requirement, inpatient/outpatient pain score, and complications. Primary outcome data were analyzed by the Mann-Whitney U-test for nonparametric continuous variables. Other continuous variables were analyzed by two-tailed t-test, while categorical data were compared via Chi-squared test, with alpha = 0.05 for significance. RESULTS: 20 patients were randomized to receive either cryoablation (n = 10) or thoracic epidural (n = 10). Mean operating room time was 46.5 min longer in the cryoanalgesia group (p = 0.0001). Median LOS decreased by 2 days in patients undergoing cryoablation, to 3 days from 5 days (Mann-Whitney U, p = 0.0001). Cryoablation patients required significantly less inpatient opioid analgesia with a mean decrease of 416 mg oral morphine equivalent per patient (p = 0.0001), requiring 52%-82% fewer milligrams on postoperative days 1-3 (p < 0.01 each day). There was no difference in mean pain score between the groups at any point postoperatively, up to one year, and no increased incidence of neuropathic pain in the cryoablation group. No complications were noted in the cryoablation group; among patients with epidurals, one patient experienced a symptomatic pneumothorax and another had urinary retention. CONCLUSIONS AND RELEVANCE: Intercostal nerve cryoablation during the Nuss procedure decreases hospital length of stay and opiate requirement versus thoracic epidural analgesia, while offering equivalent pain control. TYPE OF STUDY: Treatment study. LEVEL OF EVIDENCE: Level I.
Cited By :55
Cited By :55
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Humanos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgésicos Opioides/uso terapéutico; Criocirugía; Criocirugía/métodos; Nervios Intercostales/cirugía; Criocirugía/efectos adversos; Tiempo de Internación/estadística & datos numéricos; Procedimientos Ortopédicos/efectos adversos; Criocirugía/estadística & datos numéricos; Procedimientos Ortopédicos/estadística & datos numéricos; Procedimientos Ortopédicos/métodos; Funnel Chest; Pain, Postoperative; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Orthopedic Procedures; Thoracoscopic

Percutaneous Cryoanalgesia: A New Strategy for Pain Management in Pectus Excavatum Surgery - Velayos, María; Alonso, Mercedes; Delgado-Miguel, Carlos; Estefanía-Fernández, Karla; Muñoz-Serrano, Antonio J.; Santamaría, Manuel V. López; Reinoso-Barbero, Francisco; De La Torre, Carlos A. (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2022)
INTRODUCTION: In recent years, pain protocols for pectus excavatum (PE) have incorporated cryoanalgesia through thoracoscopic approach. Since 2019, ultrasound-guided percutaneous cryoanalgesia (PCr) has been applied at our institution, either on the same day as the Nuss procedure or 48 hours before surgery. We carried out a preliminary retrospective review of patients with PE in whom PCr prior to surgery was performed at our institution between 2019 and 2021. MATERIALS AND METHODS: Two groups were evaluated: PCr on the same day (PCrSD) and PCr 48 hours before surgery (PCr48). Despite PCr, patients were treated with "patient-controlled analgesia" (PCA) with opioids for at least 24 hours, switching to conventional intravenous analgesia and oral analgesia in the following days. Demographic, clinical-radiological variables, PCA opioid use, pain grade according to the visual analog scale (VAS), and length of stay (LOS) were compared between the groups. A total of 20 patients were included (12 with PCrSD and 8 with PCr48), without significant differences in demographics or clinical-radiological variables. The overall median time of PCr was 65 minutes (55-127), with no differences between the groups. RESULTS: PCr48 group presented with significantly lower median number of hours of continuous PCA (24 vs. 32 hours; p = 0.031), lower median number of rescue boluses (11 vs. 18; p = 0.042), lower median VAS in the early postoperative hours (2 vs. 5.5; p = 0.043), and lower median LOS (3.5 vs. 5 days). CONCLUSION: PCr performed 48 hours prior to surgery is more effective in terms of PCA requirements, VAS, and LOS when compared with cryoanalgesia on the same day.
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Manejo del Dolor; Tórax en Embudo/cirugía; Analgésicos Opioides; Tórax en Embudo; Analgesia Controlada por el Paciente; Dolor Postoperatorio; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Analgesia, Patient-Controlled; Pain Management

Same day discharge for pectus excavatum-is it possible? - Rettig, R. Luke; Rudikoff, Andrew G.; Lo, Hoi Yee Annie; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: The use of intercostal nerve cryoablation (INC) has been an effective modality for treating pain in patients undergoing pectus excavatum (PE) repair. This study sought to evaluate if PE patients undergoing Nuss procedures with INC and intercostal nerve block (INB) could safely be discharged the same day of surgery. METHODS: A prospective study with IRB approval of 15 consecutive patients undergoing PE Nuss repair with INC, INB, and an enhanced recovery after surgery (ERAS) protocol was conducted. The primary outcome measure was hospital length of stay (LOS) in hours. Secondary variables included same day discharge, postoperative complications, emergency department (ED) visits, urgent care (UC) visits, opioid use, and return to the operating room (OR). RESULTS: LOS averaged 11.9 h amongst 15 patients. Ten patients (66.7%) went home on postoperative day (POD) 0, and the rest went home on POD 1. No patients stayed in the hospital due to pain. Reasons for failure to discharge included urinary retention, drowsiness, vomiting, and anxiety, but not pain. No patients were readmitted to the ED. One patient visited UC for constipation. One patient had bar migration requiring return to the OR for revision. Ten (66.7%) patients did not use opioids after discharge. CONCLUSIONS: Same day discharge is feasible and safe in PE patients undergoing Nuss procedure with INC and INB. INC with INB can adequately control pain without significant complications. Same day discharge can be safely considered for PE patients undergoing Nuss procedure with INC with INB. TYPE OF STUDY: Prognosis study LEVEL-OF-EVIDENCE RATING: Level II.
Cited By :4
Cited By :4
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Intercostal nerve cryoablation; Enhanced recovery after surgery (ERAS); Patient Discharge; Pectus excavatum repair; Prospective Studies; Same day discharge

Impact of Cryoablation on Pectus Excavatum Repair in Pediatric Patients - Clark, Rachael A.; Jacobson, Jillian C.; Singhal, Amogh; Alder, Adam C.; Chung, Dai H.; Pandya, Samir R. (Journal of the American College of Surgeons, 2022)
BACKGROUND: Minimally invasive repair of pectus excavatum (MIRPE) involves placement of a transthoracic, retrosternal support bar under thoracoscopic guidance. Despite its minimally invasive technical approach, postoperative pain is a significant morbidity that often results in increased length of stay. Multi-modal pain control strategies have been used in the past with limited success. Recently, the use of intraoperative intercostal nerve cryoablation (CA) has been added. In the present study, we aim to evaluate the effects of CA on postoperative pain control, opioid requirements, and perioperative outcomes. STUDY DESIGN: A single-center, retrospective chart review of all patients (less than 18 years old) who underwent MIRPE from 2009 to 2020 was performed. CA was started in June 2018. Data collection included demographics, preoperative characteristics, intraoperative findings, and postoperative outcomes. We hypothesized that CA would be associated with improved pain scores, lower doses of total inpatient opioid requirement, and shorter length of stay (LOS). RESULTS: One hundred sixty-one patients met inclusion criteria: 75 underwent intraoperative CA and 86 underwent MIRPE without CA (NCA group). CA significantly decreased median LOS from 4 days in NCA to 2 days; the use of CA was the only significant predictor of LOS on linear regression. CA was also associated with decreased total PCA, intravenous opioid, and oral opioid dosages. There was no difference in inpatient pain scores and a slight increase in mean procedure time. However, CA was associated with significantly decreased postoperative complications. CONCLUSIONS: The use of cryoablation during MIRPE significantly decreases LOS, perioperative opioid requirements, and postoperative complications, with a minimal increase in operative time. Cryoablation is an effective pain control modality in the surgical management of chest wall deformities in children.
Keywords: Humans; Adolescente; Estudios Retrospectivos; Humanos; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Adolescent; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Tórax en Embudo; Analgésicos Opioides/uso terapéutico; Criocirugía; Criocirugía/métodos; Complicaciones Posoperatorias/cirugía; Criocirugía/efectos adversos; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Tórax en Embudo/complicaciones; Tórax en Embudo/tratamiento farmacológico; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Postoperative Complications

Same-day discharge following the Nuss repair: A comparison - Rettig, R. Luke; Rudikoff, Andrew G.; Annie Lo, Hoi Yee; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: Intercostal Nerve Cryoablation (INC) has significantly improved pain control following the Nuss repair of pectus excavatum (PE). This study sought to evaluate patients undergoing the Nuss repair with INC compared to the Nuss repair with an ERAS protocol, INC, and intercostal nerve blocks (INB). METHODS: In June 2020, a new protocol was implemented involving surgery, anesthesia, nursing, physical therapy, and child life with the goal of safe same day discharge for patients undergoing the Nuss repair. They were compared to a control group who underwent the Nuss repair with INC alone in 2017-2019. The primary outcome measure was hospital length of stay (LOS) in hours, secondary outcomes were number of patients discharged on postoperative day (POD) 0, and returns to the emergency department (ED), urgent care (UC), and operating room (OR). RESULTS: The characteristics between the groups were the same (Table 1). The mean LOS was 11.8 h in the INB group versus 58.2 h in the INC group, p < 0.01. 10 of 15 patients in the INB group went home on POD 0 (average of 5.5 h postop), versus 0 patients in the INC only group, p < 0.01. Five patients in the INB stayed overnight. Two patients stayed owing to anxiety, one owing to urinary retention, one owing to nausea, and one owing to drowsiness. None stayed for pain control. Four patients in the INC group returned to the ED for pain control, versus 0 in the INB group, and 1 patient in the INB returned to UC for constipation. CONCLUSIONS: The majority of patients undergoing the Nuss repair of PE with a multidisciplinary regimen of pre and postoperative nursing education, precise intraoperative anesthesia care, performance of direct vision INB and INC, as well as careful surgery can go home on the day of surgery without adverse outcomes or unanticipated returns to the hospital. LEVEL-OF-EVIDENCE: Level II.
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Dolor Postoperatorio/etiología; Tórax en Embudo; Alta del Paciente; Anestesia de Conducción; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Intercostal nerve cryoablation; Enhanced recovery after surgery (ERAS); Patient Discharge; Pectus excavatum repair; Same day discharge; Anesthesia, Conduction; Intercostal nerve block

Do health beliefs affect pain perception after pectus excavatum repair? - Sujka, Joseph; St Peter, Shawn; Mueller, Claudia M. (Pediatric Surgery International, 2018)
PURPOSE: The pain experience is highly variable among patients. Psychological mindsets, in which individuals view a particular characteristic as either fixed or changeable, have been demonstrated to influence people's actions and perceptions in a variety of settings including school, sports, and interpersonal. The purpose of this study was to determine if health mindsets influence the pain scores and immediate outcomes of post-operative surgical patients. METHODS: As part of a multi-institutional, prospective, randomized clinical trial involving patients undergoing a minimally invasive pectus excavatum repair of pectus excavatum, patients were surveyed to determine whether they had a fixed or growth health mindset. Their post-operative pain was followed prospectively and scored on a Visual Analog Scale and outcomes were measured according to time to oral pain medication use. RESULTS: Fifty patients completed the Health Beliefs survey, 17 had a fixed mindset (8 epidural, 9 PCA) and 33 had a growth mindset (17 epidural, 16 PCA). Patients with a growth mindset had lower post-operative pain scores than patients with a fixed mindset although pain medication use was not different. CONCLUSION: This is the first usage of health mindsets as a means to characterize the perception of pain in the post-operative period. Mindset appears to make a difference in how patients perceive and report their pain. Interventions to improve a patient's mindset could be effective in the future to improve pain control and patient satisfaction.
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Periodo Posoperatorio; Adolescent; Female; Male; Dolor Postoperatorio/prevención & control; Estudios Prospectivos; Satisfacción del Paciente; Dimensión del Dolor; Toracoplastia/métodos; Actitud Frente a la Salud; Dolor Postoperatorio/psicología; Percepción del Dolor/fisiología; Tórax en Embudo/psicología; Funnel Chest; Pain, Postoperative; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesia, Patient-Controlled; Prospective Studies; Attitude to Health; Fixed; Growth; Mindset; Pain Measurement; Pain Perception; Pain scores; Patient Satisfaction; Postoperative Period; Thoracoplasty; Visual Analog Scale

Postoperative management of pediatric patients undergoing minimally invasive repair of pectus excavatum: Where are we now? - Kirupaharan, Sawmmiya; Briatico, Daniel; Robinson, Tessa; Fitzgerald, Peter; Walton, J. Mark (Journal of Pediatric Surgery, 2022)
PURPOSE: Minimally invasive repair of pectus excavatum (MIRPE) often leads to a painful and challenging recovery period. This study aims to describe the postoperative management of pediatric patients undergoing MIRPE and compare postoperative outcomes between patients using different routes of postoperative analgesia. METHODS: Retrospective chart review of pediatric patients who underwent MIRPE from July 2003 to September 2019 at a single pediatric tertiary care center. Data on pain management and course of hospital stay were ascertained. Descriptive statistics, Mann-Whitney U and Pearson Chi-Square tests were used to analyze data. A p-value <0.05 was considered significant. RESULTS: Of the 115 patients identified, 58 (50.4%) managed pain postoperatively using thoracic epidural and 57 (49.6%) used intravenous patient-controlled analgesia (IVPCA). The transition from the predominant use of epidural to IVPCA for MIRPE occurred between 2012 and 2013. Higher pain scores were reported by the IVPCA group at 6 h (p<0.001) and 12 h (p<0.001) postoperative. Patients using IVPCA had lower postoperative opioid consumption (p<0.001) and switched to oral opioids sooner than the epidural group (p<0.001). Fewer patients in the IVPCA group required urinary catheterization (p<0.001). Patients using IVPCA had a shorter hospital stay (4 days [IQR 4-5]) compared to the epidural group (5.5 [IQR 5-6]; p<0.001). Readmission was comparable at 3.48% in the total sample. CONCLUSION: Patients using intravenous patient-controlled analgesia reported higher pain scores however, this route of analgesia was associated with shorter hospital stay. Prospective studies designed to address moderator variables are required to confirm findings and develop standardized recovery protocols.
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Analgésicos Opioides; Dolor Postoperatorio/etiología; Tórax en Embudo; Estudios Prospectivos; Tórax en Embudo/etiología; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Analgesia, Patient-Controlled; Prospective Studies; MIRPE; Pain management; Quality improvement

Neurolysis for analgesia following pectus repair in a national cohort - Pecoraro, Anthony R.; Hunter, Chelsea E.; Colgate, Cameron L.; Landman, Matthew P. (Journal of Pediatric Surgery, 2022)
INTRODUCTION: Pectus excavatum and pectus carinatum are the most common chest wall deformities of childhood. Surgical repair can be complicated by post-operative analgesic challenges. Thoracic epidural analgesia, patient-controlled analgesia, and multimodal pain control are among the most common strategies. We sought to define the current utilization of intraoperative thoracic neurolysis, hypothesizing that this would minimize length of stay (LOS) and post-operative narcotic use with relatively higher proportion of non-narcotic post-operative analgesia. METHODS: We performed a retrospective review of the Pediatric Health Information System (PHIS) database between 2017 and 2020. We first identified patients who underwent a pectus repair via ICD-10-PCS codes. We used ICD-10-PCS codes 01580ZZ and 01584ZZ to identify those patients who underwent concomitant thoracic neurolysis. Statistical analyses were performed using R; p value less than 0.05 was considered significant. RESULTS: We identified 2979 patients who underwent a pectus repair. 184 underwent a concomitant thoracic nerve destruction procedure (6.7%); 13 were performed in 2017 (2.01%), 76 in 2018 (10.7%), and 84 in 2019 (9.6%). LOS was shorter in those patients who underwent neurolysis (mean=2.55 vs 3.73 days, SD=1.33 vs 1.78 days, p<0.001). There were fewer post-operative ICU admissions in neurolysis patients (3/184 vs. 193/2795, p = 0.003). The cost of procedures that included a neurolysis were higher, though not significantly so (mean=$24,885.64 vs $22,200.59). CONCLUSION: Thoracic neurolysis may be a useful analgesic strategy, expediating post-operative discharge and potentially obviating the need for intensive care. Further larger-scale prospective trials should be considered to further elucidate the role of this analgesia method. LEVEL OF EVIDENCE: Level III.
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Analgesia Epidural/métodos; Dolor Postoperatorio/etiología; Tórax en Embudo; Tiempo de Internación; Estudios Prospectivos; Analgésicos; Analgésicos no Narcóticos; Pared Torácica; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Pectus excavatum; Length of Stay; Prospective Studies; Analgesia, Epidural; Analgesics, Non-Narcotic; Cryoanalgesia; Neurolysis; Thoracic Wall

Cryoanalgesia is Associated With Decreased Postoperative Opioid Use in Minimally Invasive Repair of Pectus Excavatum - Arshad, Seyed A.; Ferguson, Dalya M.; Garcia, Elisa I.; Hebballi, Nutan B.; Buchanan, Allison C.; Tsao, KuoJen (The Journal of Surgical Research, 2022)
BACKGROUND: Postoperative pain control is challenging after pectus excavatum repair. We aimed to understand the impact that cryoanalgesia had on opioid utilization and outcomes of pediatric patients undergoing minimally invasive repair of pectus excavatum (MIRPE). METHODS: A single-center retrospective cohort study was conducted of all patients (< 18 y) who underwent MIRPE (2011-2019). Patients receiving cryoanalgesia were compared to those who did not. The primary outcome was total postoperative, inpatient, opioid use, measured as milligrams of oral morphine equivalents per kilogram (OME/kg). Univariate and multivariable analyses were performed. RESULTS: Of 35 patients, 20 received cryoanalgesia (57%). Baseline characteristics were similar. Patients who received cryoanalgesia had a lower opioid requirement: median 2.3 mg OME/kg (IQR 1.2-3.1), versus 4.9 mg OME/kg (IQR 2.9-5.8), P < 0.001. Accounting for receipt of cryoanalgesia, epidural, and/or patient-controlled analgesia, cryoanalgesia was associated with a 3.3 mg OME/kg reduction in opioid use (P < 0.001). Median length of stay (LOS) was shorter in cryoanalgesia patients: 3.1 d (IQR 2.3-3.4), versus 5.1 d (IQR 4.3-5.4), P < 0.001. Complications within 90 d were similar between groups. CONCLUSIONS: Cryoanalgesia is an effective adjunctive pain control modality for patients undergoing MIRPE. Use of cryoanalgesia was associated with lower postoperative opioid requirements and shorter LOS, without increased short-term complications, and should be considered for enhanced recovery after MIRPE.
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Niño; Tórax en Embudo/cirugía; Analgésicos Opioides; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Tórax en Embudo; Analgésicos Opioides/uso terapéutico; Dolor Postoperatorio/cirugía; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryoanalgesia; Length of stay; Minimally invasive repair of pectus excavatum; Pain control

Short and long term outcomes of using cryoablation for postoperative pain control in patients after pectus excavatum repair - Fraser, James A.; Briggs, Kayla B.; Svetanoff, Wendy Jo; Aguayo, Pablo; Juang, David; Fraser, Jason D.; Snyder, Charles L.; Oyetunji, Tolulope A.; St Peter, Shawn D. (Journal of Pediatric Surgery, 2022)
INTRODUCTION: We report the findings of a three-year prospective observational study elucidating long-term symptoms and complications of patients who underwent minimally invasive pectus excavatum repair with intercostal nerve cryoablation with specific attention to postoperative pain control associated with the cryoablation technique. METHODS: Surveys were administered to patients who underwent bar placement for pectus excavatum with intercostal nerve cryoablation from 2017 to 2021 regarding pain scores, pain medication usage, and limitations to activity beginning on the day of surgery, on the day of discharge, and at two-week and three-month follow-up. RESULTS: Of 110 patients, forty-eight (44%) completed the discharge survey; sharp pain and pressure on the first postoperative night were the most described pain characteristics, most frequently in the middle of the chest. On follow-up, 55% of patients reported tolerable residual pain at two weeks and 41% at three months, with 25% requiring intermittent pain medication at three months. There were three readmissions for inadequate pain control and 110 calls to the surgery clinic by three-month follow-up, most commonly for persistent pain and frequent popping sensation with movement. DISCUSSION: Although cryoablation is an excellent pain control modality, these data suggest that patients underreport functional symptoms and experience more frequent discomfort and alteration of daily living activities.
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Tórax en Embudo/diagnóstico; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Tórax en Embudo; Criocirugía; Criocirugía/métodos; Nervios Intercostales/cirugía; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Cryosurgery; Intercostal Nerves; Intercostal cryoablation; Nuss bar; Thoracoscopy

Ultrasound-guided erector spinae plane block versus thoracic epidural analgesia: Postoperative pain management after Nuss repair for pectus excavatum - Bliss, David P.; Strandness, Thomas B.; Derderian, Sarkis C.; Kaizer, Alexander M.; Partrick, David A. (Journal of Pediatric Surgery, 2022)
AIM OF THE STUDY: Postoperative pain management is a significant challenge in patients undergoing Nuss repair for pectus excavatum chest wall deformity. Therapeutic anesthetic options primarily include patient-controlled intravenous analgesia, thoracic epidural analgesia (TEA), and cryoanalgesia. However, TEA is limited to inpatient use and both TEA and cryoanalgesia can result in neurologic injury. The novel technique of ultrasound-guided erector spinae plane regional analgesia has been used recently in our patients undergoing the Nuss repair and has shown impressive pain relief, but without the potential complications of other modalities. Erector spinae plane block (ESPB) postoperative pain management outcomes were studied as compared to TEA. METHODS: Thirty consecutive patients with severe pectus excavatum undergoing Nuss repair and placement of ultrasound-guided ESPB were each paired to a historical cohort control patient with TEA postoperative pain management. The cohort patient match was defined by age (± 2 years), gender, and CT pectus index (± 15%). Study variables included hospital length of stay (LOS), pain scores, and pain medication usage. RESULTS: Pain scores as measured by area under the curve per hour (Day 1: 2.72 (SD = 1.37) vs. 3.90 (SD = 1.81), P = 0.006; Day 2: 2.83 (SD = 1.32) vs. 3.97 (SD = 1.82), P = 0.007) and oral morphine equivalent (OME) pain medication usage (Day 1: 11.9 (SD = 4.9) vs 56.0 (SD = 32.2), P < 0.001; Day 2: 14.7 (SD = 7.1) vs. 38.0 (SD = 21.7), P < 0.001) were higher for the first two postoperative days in the ESPB group. However, mean hospital LOS was nearly one day shorter for ESPB patients (3.78 (SD = 0.82) vs. 2.90 (SD = 0.87), P < 0.001) who were discharged home with the catheter in place until removal, typically at 5-7 days postoperatively. CONCLUSION: Ultrasound-guided ESPB is thus a feasible, safe, and effective alternative to TEA in postoperative pain management after Nuss repair and results in decreased hospital stay. LEVEL OF EVIDENCE: III.
Cited By :5
Cited By :5
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Humanos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Bloqueo Nervioso; Tórax en Embudo; Ultrasonografía Intervencional; Funnel Chest; Pain, Postoperative; Analgesia, Epidural; Erector spinae plane block; Nerve Block; Nuss repair; Ultrasonography, Interventional

Epidural analgesia versus intravenous patient-controlled analgesia following minimally invasive pectus excavatum repair: a systematic review and meta-analysis - Stroud, Andrea M.; Tulanont, Darena D.; Coates, Thomasena E.; Goodney, Philip P.; Croitoru, Daniel P. (Journal of Pediatric Surgery, 2014)
BACKGROUND/PURPOSE: The minimally invasive pectus excavatum repair (MIPER) is a painful procedure. The ideal approach to postoperative analgesia is debated. We performed a systematic review and meta-analysis to assess the efficacy and safety of epidural analgesia compared to intravenous Patient Controlled Analgesia (PCA) following MIPER. METHODS: We searched MEDLINE (1946-2012) and the Cochrane Library (inception-2012) for randomized controlled trials (RCT) and cohort studies comparing epidural analgesia to PCA for postoperative pain management in children following MIPER. We calculated weighted mean differences (WMD) for numeric pain scores and summarized secondary outcomes qualitatively. RESULTS: Of 699 studies, 3 RCTs and 3 retrospective cohorts met inclusion criteria. Compared to PCA, mean pain scores were modestly lower with epidural immediately (WMD -1.04, 95% CI -2.11 to 0.03, p=0.06), 12 hours (WMD -1.12; 95% CI -1.61 to -0.62, p<0.001), 24 hours (WMD -0.51, 95%CI -1.05 to 0.02, p=0.06), and 48 hours (WMD -0.85, 95% CI -1.62 to -0.07, p=0.03) after surgery. We found no statistically significant differences between secondary outcomes. CONCLUSIONS: Epidural analgesia may provide superior pain control but was comparable with PCA for secondary outcomes. Better designed studies are needed. Currently the analgesic technique should be based on patient preference and institutional resources.
Cited By :48
Cited By :48
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Niño; Tórax en Embudo/cirugía; Analgesia Epidural; Dolor Postoperatorio/prevención & control; Tiempo de Internación; Analgesia Controlada por el Paciente; Analgesia Epidural/efectos adversos; Tempo Operativo; Procedimientos Quirúrgicos Mínimamente Invasivos; Analgesia Controlada por el Paciente/economía; Analgesia Controlada por el Paciente/efectos adversos; Analgesia Epidural/economía; Análisis Costo-Beneficio; Proyectos de Investigación/normas; Analgesia; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Length of Stay; Analgesia, Patient-Controlled; Analgesia, Epidural; Pain control; Cost-Benefit Analysis; Epidural; Minimally invasive pectus excavatum repair; Nuss; Operative Time; Research Design

Outcomes Using Cryoablation for Postoperative Pain Control in Children Following Minimally Invasive Pectus Excavatum Repair - Sujka, Joseph; Benedict, Leo Andrew; Fraser, Jason D.; Aguayo, Pablo; Millspaugh, Daniel L.; St Peter, Shawn D. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2018)
PURPOSE: Pain is the main factor that determines the postoperative course for patients undergoing pectus bar placement. Cryoablation of the intercostal nerves has been suggested to mitigate this pain. We instituted a protocol for using intercostal cryoablation and report our early results compared to our immediately previous cohort. MATERIALS AND METHODS: A retrospective study was conducted on patients undergoing minimally invasive repair for pectus excavatum between January 1, 2017, and August 21, 2017. Demographic data, anthropometrics, operative times, type and duration of patient analgesia, and postoperative length of stay were collected. Descriptive statistics were performed with all means reported ± standard deviations. Comparisons between groups were analyzed on STATA using T-tests with a P value <.05 determined as significant. RESULTS: Twenty-eight patients were treated for pectus excavatum during the study period with 9 (32%) undergoing cryoablation. Mean number of rib spaces ablated was 5 ± 0.53 with no reported intraoperative complications. Mean operative time was 30 minutes longer in the cryoablation group (P = .00). Days to only oral pain medication was shorter in the cryoablation group, (1.22 ± 0.66 day versus 2.63 ± 0.68 day, P = .00). Length of stay, in days, was shorter in the cryoablation group (1.4 ± 0.72 days versus 4.0 ± 1.0 days, P = .00). There were no reported complications from cryoablation or bar placement during the study period. Days to discontinuation of oral narcotics were less in the cryoablation group (8.2 ± 7.0 versus 18.2 ± 10.4, P = .00). CONCLUSION: Cryoablation after pectus bar placement dramatically decreases narcotic usage and postoperative length of stay.
Cited By :19
Cited By :19
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Tórax en Embudo/cirugía; Adolescent; Female; Male; Criocirugía/métodos; Dolor Postoperatorio/cirugía; Nervios Intercostales/cirugía; Tempo Operativo; Tiempo de Internación/estadística & datos numéricos; Analgésicos/uso terapéutico; Estudios de Cohortes; Narcóticos/uso terapéutico; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Minimally Invasive Surgical Procedures; Cryosurgery; Intercostal Nerves; Length of Stay; Operative Time; Cohort Studies; cryoablation; epidural; minimally invasive; Narcotics; patient-controlled anesthesia; pectus excavatum

Postoperative pain control following minimally invasive correction of pectus excavatum in pediatric patients: A systematic review - Archer, Victoria; Robinson, Tessa; Kattail, Deepa; Fitzgerald, Peter; Walton, J. Mark (Journal of Pediatric Surgery, 2020)
PURPOSE: Surgery for pectus excavatum is associated with significant postoperative pain. The aim of this study was to summarize the current literature regarding postoperative pain control for pediatric patients undergoing minimally invasive repair of pectus excavatum (MIRPE). METHODS: A systematic search of Medline, Embase, PubMed, CINAHL, Web of Science, and the Cochrane Library for randomized controlled trials (RCT) comparing methods of pain control in pediatric patients undergoing MIRPE was conducted. Studies were restricted to the English language. RESULTS: After screening 1304 references, 9 randomized control trials (RCTs) enrolling 485 patients were included. The average age was 11.9 years (±3.1). Pain scores were decreased with ropivacaine compared to bupivacaine-based epidurals. In studies comparing ketamine to opioid based patient-controlled anesthesia (PCA) pumps, the results were variable. Intercostal and paravertebral nerve blocks had decreased pain scores in 75% of the studies compared to opioid-based PCA. Opioid consumption was decreased in 50% of the trials assessing ketamine-based infusions and 75% of the studies comparing intercostal and paravertebral nerve blocks. Nausea was decreased in several of the ketamine-based infusion and intercostal and paravertebral nerve block studies. CONCLUSION: Ketamine-including infusions or paravertebral and intercostal nerve blocks may represent superior methods of postoperative pain control for MIRPE. Further work is needed to confirm results. LEVEL OF EVIDENCE: 2A [1].
Cited By :11
Cited By :11
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Humanos; Niño; Tórax en Embudo/cirugía; Adolescent; Analgésicos Opioides/uso terapéutico; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Analgésicos/uso terapéutico; Bupivacaína/uso terapéutico; Ketamina/uso terapéutico; Child; Funnel Chest; Pain, Postoperative; Analgesics; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesics, Opioid; Bupivacaine; Ketamine; MIRPE: minimally invasive repair of pectus excavatum; Pain; Pediatric; Postoperative

Pectus patient information website has improved access to care and patient reported outcomes - Tikka, Theofano; Webb, Joanne; Agostini, Paula; Kerr, Amy; Mannion, Glenn; Steyn, Richard S.; Bishay, Ehab; Kalkat, Maninder S.; Rajesh, Pala B.; Naidu, Babu (Journal of Cardiothoracic Surgery, 2016)
BACKGROUND: Pectus is the most common congenital disorder. Awareness amongst primary care physicians and the general public is poor. NHS commissioning bodies plan to withdraw funding for this surgery because they deem a lack of sufficient evidence of benefit. The purpose of this study is to assess the effects of introducing a patient information website on referral and activity patterns and on patients reported outcomes. METHODS: We produced an innovative information website, www.pectus.co.uk , accessible to the general public, providing information about pectus deformities; management options and advice about surgery. Referral patterns and number of cases where studied before and after the introduction of the website in 2010. Patients' satisfaction post-op was assessed using the Brompton's single step questionnaire (SSQ). RESULTS: The website had considerable traffic with 2179 hits in 2012, 4983 in 2013 and 7416 in 2014. This has led to 1421 contacts and 372 email enquiries. These emails have resulted in an increased number of patients who have been assessed and go on to have surgery. We asked 59 pectus excavatum patients who were operated from 2008 to 2014 to complete the SSQ. We received 32 replies. Eighty-four percent (16/19) of patients who visited the website and then underwent surgery, found the website useful. All patients scored satisfactorily in SSQ. Even though those who visited the website tended to be more satisfied with the surgical outcomes this did not reach statistical significance. This group of patients said that would have the operation again given the option compared to 76.9 % of the group who did not visit the website before surgery (p=0.031). Despite the fact that patients who visited the website experienced more post-operative complications were equally or more satisfied with post-operative outcomes. The overall SSQ obtainable score was not different for the two subgroups, being more widespread in the group that did not visit the website. CONCLUSIONS: The introduction of a pectus patient information website has significantly improved access to specialised services. Patients are overall highly satisfied with the surgical outcomes.
Cited By :4
Cited By :4
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Tórax en Embudo/cirugía; Adolescent; Female; Male; Young Adult; Thoracic Surgical Procedures; Procedimientos Quirúrgicos Torácicos; Encuestas y Cuestionarios; Adulto Joven; Educación del Paciente como Asunto; Evaluación del Resultado de la Atención al Paciente; Internet; Funnel Chest; Information; Patient Education as Topic; Patient Outcome Assessment; Pectus website; Surveys and Questionnaires

Epidural versus PCA Pain Management after Pectus Excavatum Repair: A Multi-Institutional Prospective Randomized Trial - Sujka, Joseph A.; Dekonenko, Charlene; Millspaugh, Daniel L.; Doyle, Nichole M.; Walker, Benjamin J.; Leys, Charles M.; Ostlie, Daniel J.; Aguayo, Pablo; Fraser, Jason D.; Alemayehu, Hanna; Peter, Shawn D. St (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2020)
INTRODUCTION: Postoperative pain control remains the primary reason for inpatient stay after minimally invasive repair of pectus excavatum. In a previous study, our group reported that early pain control was better in patients managed with a thoracic epidural, while late pain control was better in patients managed with patient-controlled analgesia (PCA). After revising our epidural transition and modifying the PCA protocol, we conducted a multi-institutional prospective randomized trial to evaluate these two pain control strategies. MATERIALS AND METHODS: Patients were randomized to epidural or PCA following minimally invasive repair of pectus excavatum with standard protocols for each arm. Primary outcome was length of stay with secondary variables including mean patient pain scores, complications, and parental satisfaction. Scores were pooled for the two groups and reported as means with standard deviation. Results were compared using t-tests and one-way analysis of variance with p-value < 0.05 determining significance. RESULTS: Sixty-five patients were enrolled, 32 epidural and 33 PCA. Enrollment was stopped early when we developed an alternative strategy for controlling these patients' pain. There was no difference in length of stay in hours between the two arms; epidural 111.3 ± 18.5 versus PCA 111.4 ± 51.4, p = 0.98. Longer operative time was found in the epidural group. Nine patients in the epidural group (28%) required a PCA in addition to epidural for adequate pain control. Mean pain scores were lower on postoperative day 0 in the epidural group compared with the PCA groups, but were otherwise similar. CONCLUSION: In our prospective randomized trial, PCA is just as effective as thoracic epidural in decreasing early postoperative pain scores after minimally invasive repair of pectus excavatum.
Cited By :8
Cited By :8
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Analgesia Epidural/métodos; Adolescent; Female; Male; Estudios Prospectivos; Tempo Operativo; Tiempo de Internación/estadística & datos numéricos; Funnel Chest; Pain, Postoperative; Length of Stay; Analgesia, Patient-Controlled; Prospective Studies; Analgesia, Epidural; Operative Time

Bilateral PECS II Block is Associated with Decreased Opioid Consumption and Reduced Pain Scores for up to 24 hours After Minimally Invasive Repair of Pectus Excavatum (Nuss Procedure): A Retrospective Analysis - Sertcakacilar, Gokhan; Kose, Selcuk (Journal of Cardiothoracic and Vascular Anesthesia, 2022)
OBJECTIVE(S): Compared to the open surgical technique, the minimally invasive repair of pectus excavatum (MIRPE; Nuss procedure) is a thoracoscopic technique designed to minimize intraoperative tissue damage. It still causes severe postoperative pain due to the insertion and pressure of the retrosternal bar used to raise the sternum and stabilize the chest. This study aimed to identify associations between ultrasound-guided PECS-II block and postoperative analgesia after the Nuss procedure. DESIGN: A retrospective cohort study SETTING: Single-center, training and research hospital affiliated with a university PARTICIPANTS: From Jan 1, 2018 to Nov 15, 2021, 171 consecutive patients were identified who underwent MIRPE surgery under general anesthesia. All patients received intravenous (I) patient-controlled analgesia (PCA) with or without PECS-II blocks for postoperative analgesia. One hundred twenty-five patients who met the inclusion criteria were evaluated. INTERVENTIONS: Demand-only morphine intravenous PCA was used for postoperative pain management in the PECS and control groups. Bilateral PECS-II block with 0.25% bupivacaine was performed in to the PECS group. MEASUREMENTS AND MAIN RESULTS: The primary outcome was postoperative opioid consumption, calculated as mg/kg of IV morphine. Secondary outcomes included Numeric Rating Scale (NRS) pain scores at rest (static) and with movement (dynamic) recorded 1, 4, 8, 12, 24 h after surgery. Postoperative morphine consumption was significantly lower in the PECS group than in the control group over the first 24 hours postoperatively: 0.325 mg/kg vs. 0.425 mg/kg (p<0.001). Static and dynamic NRS values were significantly lower in the PECS group for the first 12 postoperative hours (p <0.05). CONCLUSIONS: Bilateral PECS-II block is associated with decreased pain scores for up to 12 hours, and with decreased opioid consumption for up to 24 hours, following minimally invasive repair of pectus excavatum (Nuss procedure) in adolescents. PECS-II block in this context has not been previously described.
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Humanos; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Bloqueo Nervioso/métodos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Adolescent; Analgésicos Opioides; Bloqueo Nervioso; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/etiología; Tórax en Embudo; Dimensión del Dolor/métodos; Morfina; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Analgesics, Opioid; Pain Measurement; MIRPE; Nerve Block; pectus excavatum; Morphine; numerical rating scale; Pectoral nerve block; postoperative analgesia

Correlation of Preoperative State Anxiety and Pain Six Weeks After Surgical Correction of Pectus Excavatum - Zuidema, Wietse P.; Oosterhuis, Jan Wa; van der Heide, Stefan M.; de Lange-de Klerk, Elly; van der Steeg, Alida Fw; van Heurn, Ernst Lwe (Anesthesiology and Pain Medicine, 2020)
BACKGROUND: Pain is a major concern in the early postoperative phase after correction of pectus excavatum. Most studies only focus on pain management in the first days after surgery and describe methods to alleviate the pain immediately postoperatively. The severity of postoperative pain may be influenced by anxiety. So far, few studies have looked into the relationship between anxiety and postoperative pain after pectus excavatum correction. OBJECTIVES: This study aimed to investigate the correlation between preoperative anxiety and late postoperative pain scores. METHODS: This was a prospective cohort study. Anxiety was assessed with the State and Trait Anxiety Inventory questionnaire. Visual analogue scale (VAS) for pain scores assessed the pain at rest and activity. Anxiety was measured before surgery and pain scores six weeks after surgery. A hierarchical linear regression analysis was performed to investigate the correlation between baseline anxiety and pain measurements six weeks after surgery. RESULTS: In this study, 136 patients were included. State anxiety was not associated with postoperative pain (mean of pain on activity and in rest), only with pain on activity after six weeks. Age and sex were not effect modifiers in any of the models. Relevant confounding factors, although not significant, consisted of trait, sex, minor complications, epidural duration, major complications, and the number of stabilizer plates. The explained variance of state anxiety on VAS for pain scores was minimum after 6 weeks. CONCLUSIONS: Preoperative anxiety does not appear to influence postoperative pain after PE correction.
Keywords: Pediatric; Anesthesia; Chest Wall; Fear; Postoperative Management; Thoracic Surgery

A review of anesthetic considerations and postoperative pain control after the Nuss procedure - Singhal, Neil Raj; Jerman, Jonathan D. (Seminars in Pediatric Surgery, 2018)
Cited By :11
Cited By :11
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Niño; Anestesia de Conducción/métodos; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/prevención & control; Criocirugía/métodos; Procedimientos Ortopédicos/métodos; Child; Funnel Chest; Pain, Postoperative; Cryosurgery; Orthopedic Procedures; Anesthesia, Conduction

Postoperative Pain Outcomes After Nuss Procedures: Comparison of Epidural Analgesia, Continuous Infusion of Local Anesthetic, and Preoperative Self-Hypnosis Training - Manworren, Renee C. B.; Anderson, Matthew N.; Girard, Eric D.; Ruscher, Kimberly A.; Verissimo, Ana Maria; Palac, Hannah; Weiss, Richard; Rader, Christine; Hight, Donald (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2018)
BACKGROUND/PURPOSE: The Nuss procedure to correct pectus excavatum is associated with severe postoperative pain. The purpose of this retrospective study was to compare pain management outcomes of thoracic epidural analgesia and continuous infusion of local anesthetic (CILA) with and without preoperative self-hypnosis training (SHT) after Nuss procedure (4 treatment groups). METHODS: Between February 2010 and December 2013, 24 of 53 adolescents who underwent Nuss procedure received SHT. Of these, 16 received thoracic epidural analgesia and 8 received CILA postoperatively. Of the 29 patients who did not receive SHT, 19 received thoracic epidural analgesia and 10 received CILA. All patients received intravenous patient-controlled opioid analgesia and intravenous nonsteroidal anti-inflammatory drugs (IVNSAIDs) and then were transitioned to oral opioids and NSAIDs. Postoperative mean and maximum pain scores, opioid (morphine equivalents) use and side effects, and hospital length of stay (LOS) were compared between groups. RESULTS: Patients who received SHT reported lower mean (P = .0047) and maximum (P = .0028) pain scores and used less morphine equivalents/hour over time (P = .046) compared to patients who did not receive SHT. Patients who received thoracic epidural analgesia reported lower mean (P = .0092) and maximum (P = .0083) postoperative pain scores and used more morphine equivalents/hour (P = .01) compared to those who received CILA. In addition, patients who received SHT and CILA had shorter LOS (P = .0013) than patients who received thoracic epidural analgesia without SHT. CONCLUSIONS: SHT before pectus excavatum repair by Nuss procedure results in less postoperative pain and requires less morphine equivalents over time for postoperative pain management. Opioid-sparing CILA, when paired with SHT, results in shorter LOS.
Cited By :7
Cited By :7
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Manejo del Dolor/métodos; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Analgesia Epidural/métodos; Adolescent; Female; Male; Young Adult; Dimensión del Dolor/métodos; Adulto Joven; Analgésicos Opioides/administración & dosificación; Analgésicos Opioides/efectos adversos; Tiempo de Internación/estadística & datos numéricos; Procedimientos Ortopédicos/efectos adversos; Procedimientos Ortopédicos/métodos; Anestésicos Locales/administración & dosificación; Anestesia Local/métodos; Automanejo/métodos; Cuidados Preoperatorios/métodos; Hipnosis/métodos; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Analgesics, Opioid; Length of Stay; Orthopedic Procedures; Analgesia, Patient-Controlled; Pain Management; Pain Measurement; Analgesia, Epidural; pectus excavatum; Anesthesia, Local; Anesthetics, Local; continuous infusion of local anesthetic; epidural analgesia; hypnosis; Hypnosis; pediatric surgery; postoperative pain; Preoperative Care; Self-Management; thoracic

Thoracoscopic cryoanalgesia: A new strategy for postoperative pain control in minimally invasive pectus excavatum repair - Cadaval Gallardo, C.; Martínez, J.; Bellía-Munzon, G.; Nazar, M.; Sanjurjo, D.; Toselli, L.; Martínez-Ferro, M. (Cirugia Pediatrica: Organo Oficial De La Sociedad Espanola De Cirugia Pediatrica, 2020)
OBJECTIVE: Recent publications report early discharge and low opioid requirements after minimally invasive pectus excavatum repair treated with bilateral intercostal nerve cryoablation. Our aim is to report our initial experience with this technique. MATERIAL AND METHODS: Retrospective analysis of medical records of patients undergoing bilateral thoracoscopic cryoanalgesia during minimally invasive pectus excavatum repair within our institution from September 2018 to March 2019. TECHNIQUE: A cryoprobe was applied at -70 ºC for 2 minutes each from the 3rd to the 7th intercostal nerves bilaterally under thoracoscopic control. Postoperative pain was assessed using a visual analogue scale (VAS). RESULTS: Twenty-one patients were included. Ninety percent were male, the mean age being 15.2 ± 4.29 years, and the mean weight being 53.6 ± 15.33 kg. The average Haller index was 5.1 ± 2.97, and the mean repair index was 37.6 ± 13.77%. The mean number of implants introduced was 2.55 ± 0.74. The mean duration of cryoanalgesia was 39.9 ± 21.1. No patients received epidural anesthesia. Mean postoperative stay was 1.64 ± 0.73 days. Seventy-one percent of the patients required 1 dose of opioids at the most for postoperative pain control. According to the VAS, the average pain score on postoperative days 1, 3, 7, and 21 was 2.55, 2.01, 0.5, and 0.06, respectively. CONCLUSIONS: Bilateral thoracoscopic cryoanalgesia during minimally invasive pectus excavatum repair leads to early discharge and good postoperative pain control in all cases. Cryoanalgesia has become our treatment of choice for pain control in the thoracoscopic repair of pectus excavatum.
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Nervios Intercostales; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Toracoscopía/métodos; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Young Adult; Criocirugía/métodos; Dolor Postoperatorio/cirugía; Tiempo de Internación; Adulto Joven; Analgésicos Opioides/administración & dosificación; Dimensión del Dolor; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Length of Stay; Pain Measurement; Cryoanalgesia; Thoracoscopy; Minimally invasive pectus excavatum repair; Intercostal nerve; Nerve cryoablation; Postoperative pain

Postoperative pain and psychological outcomes following minimally invasive pectus excavatum repair: A report from the Society for Pediatric Anesthesia Improvement Network - Uhl, Kristen M.; Wilder, Robert T.; Fernandez, Allison; Huang, Henry; Muhly, Wallis T.; Zurakowski, David; Cravero, Joseph P. (Paediatric Anaesthesia, 2020)
BACKGROUND: Minimally invasive repair of pectus excavatum (MIRPE) is associated with less tissue trauma; however, it may result in increased postoperative pain. Pain experience is a known risk factor for the development of posttraumatic stress symptoms, though there are little data on its relationship with long-term psychological outcomes following major surgery in pediatric patients. AIMS: In this study, we examined the relationship between immediate postoperative pain and psychological outcomes at 2 weeks and three months after discharge in a cohort of pediatric patients who underwent MIRPE. We sought to determine whether immediate postoperative pain levels were associated with ongoing distress related to aspects of surgery at both time points. We were also interested in how psychological symptoms related to persistent pain concerns. METHODS: Data on patients undergoing MIRPE across 14 institutions were collected as part of the Society for Pediatric Anesthesia Improvement Network (SPAIN). Patients were contacted at 2 weeks and three months following discharge to track pain levels and assess psychological distress using a self-report questionnaire. Patients were grouped into cohorts based on self-report of distress related to aspects of surgery, nonsurgical distress, or absence of distress. RESULTS: Analysis revealed that a higher proportion of children reporting ongoing distress related to surgery at both 2 weeks and 3 months experienced higher immediate postoperative pain levels. A subset of patients with complete data sets for 2 weeks and 3 months (N = 76) was further examined. Among the 47 patients who endorsed surgical distress at 2 weeks, 25 (53.2%) continued to endorse surgical distress at 3 months. Additionally, report of surgical distress at 3 months was associated with longer-term postoperative pain. CONCLUSIONS: Our data suggest that, in patients undergoing MIRPE, the presence of distress at 2 weeks and 3 months may be associated with higher immediate postoperative pain levels.
Cited By :5
Cited By :5
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Humanos; Niño; Tórax en Embudo/cirugía; surgery; Tórax en Embudo; Dolor Postoperatorio; Procedimientos Quirúrgicos Mínimamente Invasivos; Anestesia; Anestesia/efectos adversos; Child; Funnel Chest; Pain, Postoperative; Minimally Invasive Surgical Procedures; Anesthesia; distress; outcomes; pediatric

Elastomeric Pain Pumps as an Adjunct for Postoperative Pain Control After Minimally Invasive Repair of Pectus Excavatum - Parrado, Raphael H.; Thornburg, Danielle; Kang, Paul; McMahon, Lisa E. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2021)
Introduction: Pectus excavatum is a common congenital anomaly in the pediatric population. During the postoperative period, pain control is one of the top priorities. As a result, multiple techniques for pain control have been developed, including thoracic epidural analgesia, multimodal analgesia (MM), and elastomeric pain pump (EPP) placement. The purpose of this study was to evaluate the effectiveness of pain control using EPP as an adjunct to MM after the minimally invasive repair of pectus excavatum (MIRPE). Methods: We identified all pediatric patients undergoing MIRPE from June 2017 to July 2018. MM was employed in all patients; some patients additionally received subpleural EPP as adjuncts to postoperative analgesia. We reviewed pain scores, length of stay, opioid use, and complications. Results: During the study period, a total of 62 patients were included. The study cohort was divided into 15 patients undergoing MM alone versus 47 patients undergoing subpleural EPP placement plus MM (EPP + MM). Median pain scores were lower in the EPP + MM group (2.9 versus 4.2, P < .05). There was a significant reduction of total inpatient opioid use in the EPP + MM group (357.6 mg versus 466.9 mg, P = .03). There was no difference in median length of stay or complications. We found no significant difference between subpleural versus subcutaneous placement of the infusion catheters. Conclusion: The use of subpleural EPP as an adjunct to MM is an effective way to reduce pain and opioid use after MIRPE without increased risk of complications. Type of Study: Retrospective study with comparison group.
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Dolor Postoperatorio/tratamiento farmacológico; Manejo del Dolor/métodos; Tórax en Embudo/cirugía; Adolescent; Female; Male; Analgésicos Opioides/uso terapéutico; Tiempo de Internación; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Dimensión del Dolor; Analgésicos/administración & dosificación; Bombas de Infusión; Manejo del Dolor/instrumentación; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Length of Stay; Pain Management; Pain Measurement; postoperative analgesia; elastomeric pain pumps; Infusion Pumps; minimally invasive repair of pectus excavatum; multimodal analgesia

Infectious complications of intercostal nerve cryoablation mediated by perioperative hypothermia during pediatric Nuss procedure - Bundrant, Nikkida T.; Sayrs, Lois W.; Ostlie, Daniel; Lee, Justin; Egan, Craig; Molitor, Mark; Notrica, David; Padilla, Benjamin (Journal of Pediatric Surgery, 2022)
BACKGROUND: Intercostal nerve cryoablation (cryoanalgesia) is increasingly used for pain control in minimally invasive repair of pectus excavatum (MIRPE) by Nuss procedure. Cryoanalgesia may lower core body temperature and increase the risk of postoperative infectious complications. We investigated cryoanalgesia effects on infectious complications following MIRPE. METHOD: We performed a retrospective review of patients undergoing MIRPE at our institution. Patients treated via multimodal analgesia with cryoanalgesia (Cryo) were compared to patients treated via multimodal analgesia +/- elastomeric pain pumps (Non-cryo). Core body and intraoperative minimum/maximum temperatures were recorded. Primary outcomes were wound infection and pneumonia; secondary outcome was length of stay (LOS). Fisher's Exact and Mann-Whitney U tests compared proportions and medians respectively, p-value ≤ 0.05 being significant. RESULTS: 80 patients were included, 35(43.7%) Cryo and 45(56.3%) Non-cryo. There were no significant differences in median [IQR] for age(15[13.3,16.0];p =0.86), number of bars inserted (2[1,2];p = 0.57), or operative time(123.5[98.3, 148.8]; p = 0.11) between the two groups. We found no significant differences in median [IQR] minimum temperature (35.4°C [35.0,35.8];p = 0.76), median change in intraoperative temperature (-0.13°C [-0.44,0.00];p = 0.94) or median recovery temperature (-1.10°C [-1.56,-0.65]; p = 0.59) between Cryo and Non-cryo. PACU temperature was significantly lower in the Cryo group, 36.4°C [36.2,36.6] p = 0.04. There were no postoperative wound infections in either group and no significant difference in incidence of postoperative pneumonia (8.57% versus 2.22%,p =  0.31) or median[IQR] for LOS (4[3,4];p = 0.57), between Cryo and Non-cryo patients. CONCLUSION: Although cryoanalgesia for MIRPE resulted in lower core body temperature, there appears to be no significant difference between Cryo and Non-Cryo patients for LOS or infectious complications.
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Estudios Retrospectivos; Humanos; Niño; Tórax en Embudo/cirugía; Adolescent; Tórax en Embudo; Criocirugía; Criocirugía/métodos; Nervios Intercostales/cirugía; Criocirugía/efectos adversos; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Hipotermia; Hipotermia/complicaciones; Hipotermia/prevención & control; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally invasive repair; Minimally Invasive Surgical Procedures; Pectus excavatum; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Cryoanalgesia; Thoracoscopy; Nuss; Hypothermia; Postoperative infectious complications

Intercostal Nerve Cryoablation in Minimally Invasive Repair of Pectus Excavatum: Effect on Pulmonary Function - Lai, Krista; Lee, Justin; Notrica, David M.; Egan, J. Craig; McMahon, Lisa E.; Molitor, Mark S.; Bae, Jae-O.; Ostlie, Daniel J.; Padilla, Benjamin E. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2022)
Introduction: Cryoablation of intercostal nerves is performed for pain control after minimally invasive repair of pectus excavatum (MIRPE). Cryoablation affects both sensory and motor neurons, resulting in temporary anesthesia to the chest wall and loss of intercostal motor function. The study objective is to determine the effect of cryoablation on incentive spirometry (IS) volumes, as a measure of pulmonary function, after MIRPE. Materials and Methods: A single-institution retrospective review of pediatric patients undergoing MIRPE was performed. All patients received a multimodal regimen (MMR) of analgesics postoperatively. Three groups were compared-cryoablation (CRYO), elastomeric pain pump (EPP), and MMR alone. The primary outcomes were postoperative IS volumes and IS volumes as a ratio of preoperative forced vital capacity (FVC). Secondary outcomes included pain scores, opioid use, length of stay (LOS), and infectious complications. Results: MIRPE was performed in 115 patients: 50 CRYO, 50 EPP, and 15 MMR alone. Groups were similar for demographics and pectus excavatum severity. Postoperative spirometry measurements were similar across groups: IS (CRYO 750 mL [500,961] versus EPP 750 mL [590,1019] versus MMR 696 mL [500,1037], P = .77); IS/FVC (CRYO 0.19 [0.14,0.26] versus EPP 0.20 [0.16,0.26] versus MMR 0.16 [0.15,0.24], P = .69). Although pain scores were also similar across groups, CRYO patients used less opioid (P < .05) and had shorter LOS (P < .05). Postoperative pneumonia was rare and similar across groups (P = 1.00). Conclusion: Intercostal nerve cryoablation during MIRPE does not adversely affect postoperative IS volumes or increase pneumonia rate, despite the temporary loss of motor innervation to intercostal muscles. Cryoablation provides effective pain control with less opioid use.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; MIRPE; Nuss; cryoablation; incentive spirometry; pectus; pulmonary function

Postoperative opioid analgesic use after Nuss versus Ravitch pectus excavatum repair - Papic, Jonathan C.; Finnell, S. Maria E.; Howenstein, Abby M.; Breckler, Francine; Leys, Charles M. (Journal of Pediatric Surgery, 2014)
BACKGROUND/PURPOSE: Anticipated postoperative pain may affect procedure choice in patients with pectus excavatum. This study aims to compare postoperative pain in patients undergoing Nuss and Ravitch procedures. METHODS: A 5year retrospective review was performed. Data on age, gender, Haller index, procedure, pain scores, pain medications, and length of hospital stay were collected. Total inpatient opioid administration was converted to morphine equivalent daily dose per kilogram (MEDD/kg) and compared between procedures. RESULTS: One hundred eighty-one patients underwent 125 (69%) Nuss and 56 (31%) Ravitch procedures. Ravitch patients were older (15.7 yo vs 14.6 yo, p=0.004) and had a higher Haller index (5.21 vs 4.10, p=<0.001). Nuss patients had higher average daily pain scores, received 25% more opioids (MEDD/kg 0.66 vs. 0.49, p=<0.001), and received twice as much IV diazepam/kg. In the multivariate analysis, higher MEDD/kg correlated with both the Nuss procedure and older age in the Nuss group. Opioid administration did not correlate with Haller index or Nuss bar fixation technique. Increased NSAID administration did not correlate with lower use of opioids. CONCLUSION: The Nuss procedure is associated with greater postoperative pain compared to the Ravitch procedure. Opioid use is higher in older patients undergoing the Nuss procedure, but is not associated with severity of deformity.
Cited By :45
Cited By :45
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Young Adult; Dolor Postoperatorio/diagnóstico; Adulto Joven; Analgésicos Opioides/administración & dosificación; Dimensión del Dolor; Estudios de Seguimiento; Tiempo de Internación/tendencias; Toracoplastia/métodos; Morfina/administración & dosificación; Factores de Tiempo; Inyecciones Intravenosas; Relación Dosis-Respuesta a Droga; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Length of Stay; Pain Measurement; Thoracoplasty; Pain; Morphine; Dose-Response Relationship, Drug; Follow-Up Studies; Injections, Intravenous; Morphine equivalent daily dose; Opioid; Ravitch procedure; Time Factors

Bilateral Ultrasound-Guided Erector Spinae Plane Block for Pectus Excavatum Surgery: A Retrospective Propensity-Score Study - Fiorelli, Silvia; Menna, Cecilia; Andreetti, Claudio; Peritore, Valentina; Rocco, Monica; De Blasi, Roberto Alberto; Rendina, Erino Angelo; Massullo, Domenico; Ibrahim, Mohsen (Journal of Cardiothoracic and Vascular Anesthesia, 2022)
OBJECTIVE: Pectus excavatum (PE) repair is burdened by severe postoperative pain. This retrospective study aimed to determine whether the analgesic effect of ultrasound-guided erector spinae plane block (ESPB) plus standard intravenous analgesia (SIVA) might be superior to SIVA alone in pain control after PE surgical repair via Ravitch or Nuss technique. DESIGN: A retrospective cohort study. SETTING: At a university hospital. PARTICIPANTS: All participants were scheduled for surgical repair of PE. INTERVENTIONS: From January 2017 to December 2019, all patients who received ESPB plus SIVA or SIVA alone were investigated retrospectively. A 2:1 propensity-score matching analysis considering preoperative variables was used to compare analgesia efficacy in 2 groups. All patients received a 24-hour continuous infusion of tramadol, 0.1 mg/kg/h, and ketorolac, 0.05 mg/kg/h, via elastomeric pump, and morphine, 2 mg, intravenously as a rescue drug. The ESPB group received preoperative bilateral ESPB block. Postoperative pain, reported using a numerical rating scale at 1, 12, 24, and 48 hours after surgery; the number of required rescue doses; total postoperative morphine milligram equivalents consumption; and the incidence of postoperative nausea and vomit were analyzed. MEASUREMENT AND MAIN RESULTS: A total of 105 patients were identified for analysis. Propensity-score matching resulted in 38 patients in the SIVA group and 19 patients in the ESPB group. Postoperative pain, the number of rescue doses, and postoperative nausea and vomit incidences were lower in the ESPB group (p < 0.005). CONCLUSIONS: Erector spinae plane block may be an effective option for pain management after surgical repair of PE as part of a multimodal approach. This study showed good perioperative analgesia, opioid sparing, and reduced opioid-related adverse effects.
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Bloqueo Nervioso/métodos; Tórax en Embudo/cirugía; Analgésicos Opioides; Bloqueo Nervioso; Derivados de la Morfina/uso terapéutico; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Náusea y Vómito Posoperatorios/cirugía; Tórax en Embudo; Ultrasonografía Intervencional; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Analgesics, Opioid; Nerve Block; Ultrasonography, Interventional; Ravitch procedure; erector spinae plane block; Morphine Derivatives; pectus excavatum surgery; Postoperative Nausea and Vomiting; regional anesthesia; thoracic anesthesia

Pain Management in Pectus Excavatum Surgery: A Comparison of Subcutaneous Catheters Versus Epidurals in a Pediatric Population - Thaker, Shefali; McKenna, Elise; Rader, Christine; Misra, Meghna V. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2019)
BACKGROUND: Pectus excavatum is a common chest wall anomaly. Achieving optimal pain control is a priority for adolescents undergoing surgical correction of this condition. Options for pain control include the use of subcutaneous catheters (On-Q® pumps) and epidurals. The objective of this study is to demonstrate the feasibility of using subcutaneous catheters for pain control and to compare them with the use of epidurals during surgical correction of pectus excavatum. MATERIALS AND METHODS: We identified patients who underwent pectus excavatum repair at our institution between January 2010 and August 2016. Patients were divided into two cohorts (epidural or On-Q pump). Patient charts were reviewed for length of stay, pain scores, pain medications, and complications. RESULTS: A total of 124 patients were included. Forty percent of patients used an epidural (n = 50), and 60% had the On-Q pump (n = 74). The average patient age was 15.6 years. The average Haller index was 4.3. The On-Q pump population had a significant decrease in postoperative length of stay (mean [M] = 4.86, standard deviation [SD] = 0.85) compared with the epidural population (M = 5.60, SD = 0.97); P ≤ .001. There was a significant difference observed in pain scores for patients on the epidural (M = 2.91, SD = 1.13) and On-Q pump (M = 3.81, SD = 1.19; P ≤ .001). There was n = 1 wound infection in each group. CONCLUSION: The use of bilateral subcutaneous infusion catheters is a safe and effective method for pain control in patients undergoing surgical correction of pectus excavatum. Even though the degree of pain control is not necessarily superior to epidurals, in this study, the catheters were associated with a shorter postoperative length of stay in this patient population and did not increase the incidence of complications.
Cited By :5
Cited By :5
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Dolor Postoperatorio/tratamiento farmacológico; Manejo del Dolor/métodos; Tórax en Embudo/cirugía; Analgesia Epidural; Adolescent; Female; Male; Tiempo de Internación; Analgesia Epidural/efectos adversos; Dimensión del Dolor; Analgésicos/administración & dosificación; Bombas de Infusión; Catéteres/efectos adversos; Infusiones Subcutáneas/efectos adversos; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Length of Stay; Pain Management; Pain Measurement; Analgesia, Epidural; epidural; pectus excavatum; Infusion Pumps; Catheters; Infusions, Subcutaneous; length of stay; On-Q Pump; pain management

Implementation and acceptance rates of a specially designed vacuometer for the vacuum bell treatment of pectus excavatum - Toselli, Luzia; Vallee, Maxroxia; Elmo, Gaston; Martinez, Jorge; Sanjurjo, Daniela; Nazar, Maximiliano; Bellia-Munzon, Gaston (Journal of Pediatric Surgery, 2021)
BACKGROUND / PURPOSE: To report the implementation of a specially designed vacuometer for the ambulatory measurement of the exact negative pressure self-applied by the patient when using the vacuum bell for the treatment of pectus excavatum and to analyze patient satisfaction with the device, by conducting a survey. METHODS: Between October 2018 and June 2020, all patients with pectus excavatum who received a vacuum bell at our Pectus Clinic were provided with a specially designed pectus vacuometer for their personal use. We described the vacuometer, the fundamentals of its development, and the utilization protocol. A survey was conducted evaluating comfort, clarity of instructions, usefulness, simplicity of connection, and likeability. The level of satisfaction was assessed using a Likert scale ranging from 1 (very negative experience) to 5 (very positive experience). The occurrence of skin lesions provoked by the application of the vacuum bell was registered. RESULTS: From 72 submitted surveys, 54 patients answered. Patient demographics comprised 44 (81.5%) males and a mean age of 12.6 ± 6.0 years. The mean initial external pectus depth was 2.0 ± 0.7 cm and the mean duration of treatment was 13.2 ± 8.6 months. No skin lesions were detected while using the vacuum bell and the vacuometer. The mean general satisfaction score was 4.4 ± 0.7 and 83.3% of the respondents did not have any inconvenience with the vacuometer. A patient who considered himself cured was the only dropout during the study. CONCLUSIONS: In this study, we described the feasibility and fundamentals of the application of a specifically designed vacuometer for ambulatory use as an adjunct to the treatment of pectus excavatum with a vacuum bell, and demonstrated a high satisfaction level with the device. In addition, the vacuometer might help avoid skin lesions secondary to the vacuum bell and foster adhesion to treatment. TYPE OF STUDY: Treatment study. LEVEL OF EVIDENCE: IV.
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Humanos; Masculino; Niño; Adolescent; Male; Tórax en Embudo; Pared Torácica; Encuestas y Cuestionarios; Satisfacción del Paciente; Vacio; Child; Funnel Chest; Patient Satisfaction; Thoracic Wall; Surveys and Questionnaires; Funnel chest; Measurement; Negative pressure; Patient reported outcomes; Vacuum

[Research progress on postoperative analgesia for pectus excavatum in pediatric patients after Nuss procedure] - Zhou, Chen; Jin, Haiyan; Li, Jianhua; Hu, Zhiyong (Zhejiang Da Xue Xue Bao. Yi Xue Ban = Journal of Zhejiang University. Medical Sciences, 2013)
Pectus excavatum is the common congenital chest wall deformity in children, and Nuss procedure is the conventional surgical treatment for this disease. Nuss procedure is superior to Ravitch correction for it is less harmful in terms of the surgical technique. However, Nuss procedure is associated with severe postoperative pain, thus adequate postoperative analgesia is important. In this review, factors that influence the postoperative pain after Nuss procedure, the pain managements, the related complications and the side effects of drugs are discussed.
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Dolor Postoperatorio/terapia; Humanos; Niño; Tórax en Embudo/cirugía; Dolor Postoperatorio/etiología; Preescolar; Analgesia/métodos; Analgesia; Child; Funnel Chest; Pain, Postoperative; Child, Preschool

Limited cryoablation reduces hospital stay and opioid consumption compared to thoracic epidural analgesia after minimally invasive repair of pectus excavatum - Song, Seung Hwan; Moon, Duk Hwan; Shim, Yon Hee; Jung, Hyunjoo; Lee, Sungsoo (Medicine, 2022)
pain following minimally invasive repair of pectus excavatum (MIRPE) is a critical concern that leads to a prolonged hospital stay and high doses of opiates administered to the patients. This study aimed to evaluate the efficacy of intraoperative cryoanalgesia (cryoablation of the intercostal nerves) during MIRPE. We retrospectively analyzed the data of 64 patients who underwent MIRPE and received cryoanalgesia or epidural analgesia between January 2019 and January 2021. The oral morphine milligram equivalent (MME) was used to calculate the dosage of opioid agents. The median age was 15 years (range, 4-33 years). The median postoperative hospital stay was 4 days (range, 2-6 days), with a median oral MME consumption of 45 mg (ranging from 0 to 1360 mg). Cryoanalgesia was performed in 38 patients, and epidural analgesia was administered to the remaining 26 patients. The cryoanalgesia group had a significantly lesser pain score, shorter postoperative hospital stay and lower oral MME consumption than the epidural analgesia group (5 vs 2; P < .001, 3 days vs 5 days; P < .001, 19 mg vs 634 mg; P < .001). Cryoanalgesia appears to reduce postoperative hospital stay and opioid consumption compared with epidural analgesia. The outcomes of this study indicate that cryoanalgesia might be a safe and effective method for pain control following MIRPE.
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Humanos; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Analgesia Epidural/métodos; Adolescent; Tórax en Embudo; Analgésicos Opioides/uso terapéutico; Criocirugía; Criocirugía/métodos; Dolor Postoperatorio/cirugía; Tiempo de Internación; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Length of Stay; Analgesia, Epidural

Pectus excavatum: Benefit of randomization - Dalton, Brian G. A.; Gonzalez, Katherine W.; Millspaugh, Daniel L.; Desai, Amita A.; Sharp, Susan W.; St Peter, Shawn D. (Journal of Pediatric Surgery, 2015)
BACKGROUND: Minimally invasive bar repair for pectus patients produces substantial pain which dictates the post-operative hospital course. We have data from 2 randomized trials comparing epidural catheter placement to patient controlled analgesia. The purpose of this study was to compare the outcomes of patients who were enrolled in the trials to those that did not participate in the trials. METHODS: A retrospective chart review was performed on patients not enrolled in the trials to compare to the prospective datasets from October 2006 to June 2014. Perioperative outcomes were examined. RESULTS: There were 135 patients in a study protocol (IS) and 195 patients that were not enrolled in a study (OS). Comparing the entire IS and OS groups, length of stay was less in the IS group, as was time to regular diet. Average pain scores, operative time and complication rates were not significantly different between the groups. Of the IS patients a significantly lower number of patients had epidural failure, requiring substitution of a PCA for pain control. CONCLUSIONS: There are benefits derived from participating in our randomized trials comparing epidural to patient controlled analgesia after bar placement for pectus excavatum regardless of which arm is utilized.
Cited By :3
Cited By :3
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Manejo del Dolor; Masculino; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Tiempo de Internación; Estudios Prospectivos; Analgesia Controlada por el Paciente; Tempo Operativo; Anestesia Epidural; Hidromorfona/administración & dosificación; Anestésicos/administración & dosificación; Fentanilo/administración & dosificación; Midazolam/administración & dosificación; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Length of Stay; Analgesia, Patient-Controlled; Pain Management; Prospective Studies; Epidural; Operative Time; Anesthesia, Epidural; Anesthetics; Benefit; Fentanyl; Hydromorphone; Midazolam; Patient controlled analgesia; Pectus Excavatum; Randomization

The incidence of neuropathic pain after intercostal cryoablation during the Nuss procedure - Zobel, Michael J.; Ewbank, Clifton; Mora, Roberta; Idowu, Olajire; Kim, Sunghoon; Padilla, Benjamin E. (Pediatric Surgery International, 2020)
PURPOSE: Intercostal nerve cryoblation during the Nuss procedure for pectus excavatum decreases pain, opiate requirement, and hospital length of stay (LOS) compared to thoracic epidural analgesia. However, long-term complications of cryoablation, including neuropathic pain development, are not well studied. METHODS: We conducted a multi-institutional retrospective review of patients following intercostal nerve cryoablation during Nuss bar insertion (11/2015-7/2018). Patients completed the Leeds Assessment of Neuropathic Symptoms and Signs, a validated questionnaire for detecting neuropathic symptoms. Primary outcome was neuropathic pain development. Secondary outcomes included duration of chest numbness and LOS. T test was performed; p < 0.05 is significant. RESULTS: 43 patients underwent intercostal cryoablation during the Nuss procedure. Ages at repair ranged 11-47 years (median 16). Patients were grouped by age: ≤ 21 years (30 patients) or older (13 patients). Mean LOS was shorter for the younger group, 2.0 versus 3.9 days (p = 0.03). No patients in the younger group, and three in the older, experienced neuropathic pain. Mean time to numbness resolution was shorter for the younger group, 3.4 versus 10.8 months (p = 0.003). CONCLUSION: In pediatric patients, intercostal cryoablation provides effective analgesia following the Nuss procedure with minimal risk of post-operative neuropathic pain. Adult patients are at greater risk of experiencing neuropathic pain and prolonged numbness.
Cited By :22
Cited By :22
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Estudios Retrospectivos; Femenino; Humanos; Manejo del Dolor; Masculino; Niño; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Adulto; Dolor Postoperatorio/epidemiología; Adolescent; Adult; Female; Male; Young Adult; Dolor Postoperatorio/etiología; Analgésicos Opioides/uso terapéutico; Criocirugía/efectos adversos; Adulto Joven; Estados Unidos/epidemiología; Incidencia; Neuralgia/epidemiología; Neuralgia/etiología; Neuralgia/terapia; Persona de Mediana Edad; Child; Funnel Chest; Neuralgia; Pain, Postoperative; Retrospective Studies; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Thoracoscopic; Pain Management; Analgesia, Epidural; Incidence; Middle Aged; Neuropathic pain; United States

Nuss procedure for pectus excavatum in adults: long-term results in a prospective observational study - Hoksch, Beatrix; Kocher, Gregor; Vollmar, Philippe; Praz, Fabien; Schmid, Ralph Alexander (European Journal of Cardio-Thoracic Surgery: Official Journal of the European Association for Cardio-Thoracic Surgery, 2016)
OBJECTIVES: Since the end of the 1990s, the management of pectus excavatum has undergone major changes. The Nuss procedure (pectus bar) has been the method of choice for patients with pectus excavatum at Bern University Hospital for over a decade. The current study will describe our experiences, with a particular focus on long-term results in adults. METHODS: The prospective observational study began in autumn 2002. The Haller index was used to quantify pectus excavatum severity. Pulmonary function tests and cardiac examinations were performed preoperatively, and a standardized management for surgical techniques and for the pre- and postoperative treatments including long-term follow-up at 3, 12 and 36 months after surgery was developed. Quality of life and satisfaction with the cosmetic result after the Nuss procedure were evaluated. RESULTS: Better or much better quality of life after the Nuss procedure was observed: n = 108 (88.4%) at 3 months, n = 97 (89.0%) at 12 months and n = 87 (92.5%) at 36 months. Pain intensity decreased in the follow-up [pain score visual analogue scale (VAS) at 3 months: median 1 (0-7), 12 months: median 1 (0-4), 36 months: median 0.8 (0-5)]. After long-term observation, over 90% of patients described their quality of life after the operation as being better or much better. Satisfaction with the cosmetic results of the operation was also very high, with >90% of patients being satisfied. Only a very small group of patients suffered from pain in the long-term follow-up. Complications were rare (14.7%) and could be treated in most cases without reoperation. CONCLUSION: Our results demonstrate that the Nuss procedure is safe and can be performed with excellent results in adults, both in the short term and in the long term. The improved quality of life and patients' satisfaction with cosmetic results remained high in the long-term follow-up, 10 years after the surgical procedure.
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Female; Male; Young Adult; Calidad de Vida; Estudios Prospectivos; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Adulto Joven; Persona de Mediana Edad; Estudios de Seguimiento; Cuidados Preoperatorios/métodos; Capacidad Vital/fisiología; Cirugía Torácica Asistida por Video/efectos adversos; Cirugía Torácica Asistida por Video/instrumentación; Cirugía Torácica Asistida por Video/métodos; Cirugía Torácica Asistida por Video/rehabilitación; Dispositivos de Fijación Ortopédica; Estética; Falla de Prótesis; Procedimientos Quirúrgicos Mínimamente Invasivos/instrumentación; Procedimientos Quirúrgicos Mínimamente Invasivos/rehabilitación; Radiografía; Recurrencia; Tórax en Embudo/fisiopatología; Tórax en Embudo/rehabilitación; Volumen Espiratorio Forzado/fisiología; Funnel Chest; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Prospective Studies; MIRPE; Preoperative Care; Follow-Up Studies; Middle Aged; Esthetics; Forced Expiratory Volume; Orthopedic Fixation Devices; Pectus Bar; Prosthesis Failure; Quality of Life; Radiography; Recurrence; Thoracic Surgery, Video-Assisted; Vital Capacity

Scoring of Deformed Costal Cartilages Reduces Postoperative Pain after Nuss Procedure for Pectus Excavatum - Nagasao, Tomohisa; Hamamoto, Yusuke; Tamai, Motoki; Kogure, Tetsukuni; Jiang, Hua; Takano, Naoki; Tanaka, Yoshio (The Thoracic and Cardiovascular Surgeon, 2016)
OBJECTIVE: The present study aims to elucidate whether or not scoring deformed cartilages reduces postoperative pain after the Nuss procedure for pectus excavatum patients. METHODS: A total of 46 pectus excavatum patients for whom the Nuss procedure was conducted were included in the study. The patients were categorized into two groups, depending on whether or not the supplementary maneuver of scoring deformed cartilages was performed in addition to the Nuss procedure. Patients for whom deformed costal cartilages were scored were categorized as the Scoring Group (n = 24); those who received no such scoring were categorized as the Non-Scoring Group (n = 22). After evaluating the maximum stresses occurring on the thoraces by means of dynamic simulation using finite element analyses, intergroup comparison of the maximum von-Mises stress values was performed. Furthermore, after quantifying postoperative pain as the frequency with which patients injected anesthetics through an epidural pain-control system within 2 postoperative days, the degree of pain was compared between the two groups. RESULTS: The maximum stresses occurring on the thorax were significantly greater for the Non-Scoring Group than for the Scoring Group; injection frequency was also greater for the Non-Scoring Group (average 4.9 times for 2 days) than for the Scoring Group (average 2.5 times for 2 days). CONCLUSION: High stresses occur due to the performance of the Nuss procedure, causing postoperative pain. The stresses can be reduced by performing supplementary scoring on deformed cartilages. Accordingly, postoperative pain is reduced.
Cited By :6
Cited By :6
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Tórax en Embudo/diagnóstico; Adulto; Adolescent; Adult; Female; Male; Young Adult; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Analgesia Controlada por el Paciente; Adulto Joven; Esternón/cirugía; Dimensión del Dolor; Procedimientos Ortopédicos/efectos adversos; Procedimientos Ortopédicos/métodos; Tórax en Embudo/fisiopatología; Análisis de Elementos Finitos; Cartílago Costal/anomalías; Cartílago Costal/cirugía; Cartílago Costal/diagnóstico por imagen; Cartílago Costal/fisiopatología; Esternón/anomalías; Esternón/diagnóstico por imagen; Esternón/fisiopatología; Estrés Mecánico; Factores de Tiempo; Fenómenos Biomecánicos; Módulo de Elasticidad; Simulación por Computador; Tomografía Computarizada por Rayos X; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Orthopedic Procedures; Analgesia, Patient-Controlled; Pain Measurement; Time Factors; Biomechanical Phenomena; Computer Simulation; Costal Cartilage; Elastic Modulus; Finite Element Analysis; Sternum; Stress, Mechanical; Tomography, X-Ray Computed

Liposomal Bupivacaine Injection in Nuss Procedure Allows Narcotic Avoidance and Improved Outcomes - Jeziorczak, Paul M.; Frenette, Riley S.; Aprahamian, Charles J. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2021)
Background: The Nuss procedure has provided a minimally invasive surgical solution for pectus excavatum with excellent long-term outcomes. However, opioid avoidance, cost reduction, and length of stay (LOS) still offer room for improvement. The focus of this study is to identify the impact of Bupivacaine liposome injectable suspension (Exparel) on outcomes. Methods: A retrospective review at a Pediatric specialty hospital from October 1, 2014 to December 31, 2019 was performed. All patients underwent a Nuss procedure (n = 19) for pectus excavatum. The cohort comprised a control group that did not use liposomal Bupivacaine (Standard, n = 9) and an interventional group that received liposomal Bupivacaine (n = 10). Nonparametric Wilcoxon rank-sum tests and chi-squared or Fisher's exact tests were used to assess significance (P < .05). Results: Overall, the entire population was 68.4% male and had an average age of 15 years. There was a significant difference between the Standard and Liposomal Bupivacaine groups for total cost ($60,746 versus $13,289), total Morphine Milligram Equivalents (MME) (282 versus 76.8 MME) and Epidural Catheter usage (100% versus 0%). There was also a significant difference between groups for LOS (5.00 days versus 3.00 days) and Foley catheter usage (100% versus 20%). Conclusions: There is a significant impact of liposomal Bupivacaine usage on epidural catheter avoidance and opioid administration correlating with a significantly decreased total cost and decreased LOS. While more study is necessary, liposomal Bupivacaine for Nuss procedure offers improvement of postoperative patient outcomes and drastic cost savings.
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Adolescent; Female; Male; Analgésicos Opioides; Tiempo de Internación; Dolor Postoperatorio; Anestésicos Locales; Bupivacaína; Liposomas; Narcóticos; Child; Pain, Postoperative; Retrospective Studies; Nuss procedure; Analgesics, Opioid; Length of Stay; Narcotics; Bupivacaine; Anesthetics, Local; cost reduction; liposomal bupivacaine; Liposomes; opioid avoidance

Prediction of persistent post-operative pain: Pain-specific psychological variables compared with acute post-operative pain and general psychological variables - Horn-Hofmann, C.; Scheel, J.; Dimova, V.; Parthum, A.; Carbon, R.; Griessinger, N.; Sittl, R.; Lautenbacher, S. (European Journal of Pain (London, England), 2018)
BACKGROUND: Psychological variables and acute post-operative pain are of proven relevance for the prediction of persistent post-operative pain. We aimed at investigating whether pain-specific psychological variables like pain catastrophizing add to the predictive power of acute pain and more general psychological variables like depression. METHODS: In all, 104 young male patients undergoing thoracic surgery for pectus excavatum correction were studied on the pre-operative day (T0) and 1 week (T1) and 3 months (T2) after surgery. They provided self-report ratings (pain-related: Pain Catastrophizing Scale, Pain Anxiety Symptoms Scale = PASS, Pain Vigilance and Awareness Questionnaire = PVAQ; general psychological: Screening for Somatoform Symptoms, State-Anxiety Inventory-X1, Center for Epidemiologic Studies Depression Scale = CES-D). Additional predictors (T1) as well as criterion variables (T2) were pain intensity (Numerical Rating Scale) and pain disability (Pain Disability Index). RESULTS: Three months after surgery, 25% of the patients still reported clinically relevant pain (pain intensity ≥3) and over 50% still reported pain-related disability. Acute post-operative pain as well as general psychological variables did not allow for a significant prediction of persistent post-operative pain; in contrast, pain-related psychological variables did. The best single predictors were PASS for pain intensity and PVAQ for pain disability. CONCLUSIONS: Pain-related psychological variables derived from the fear-avoidance model contributed significantly to the prediction of persistent post-operative pain. The best possible compilation of these measures requires further research. More general psychological variables may become relevant predictors later in the medical history. SIGNIFICANCE: Our results suggest that pain-specific psychological variables such as pain anxiety and pain hypervigilance add significantly to the prediction of persistent post-operative pain and might even outperform established predictors such as acute pain and general psychological variables. Clinicians might benefit from the development of time-economic screening tools based on these variables.
Cited By :16
Cited By :16
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Humanos; Masculino; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Male; Young Adult; Thoracic Surgical Procedures; Dolor Postoperatorio/diagnóstico; Dimensión del Dolor/métodos; Encuestas y Cuestionarios; Adulto Joven; Factores de Riesgo; Dolor Postoperatorio/psicología; Ansiedad/psicología; Catastrofización/psicología; Concienciación; Depresión/psicología; Miedo/psicología; Personas con Discapacidad; Procedimientos Quirúrgicos Torácicos/psicología; Funnel Chest; Pain, Postoperative; Pain Measurement; Surveys and Questionnaires; Fear; Anxiety; Awareness; Catastrophization; Depression; Disabled Persons; Risk Factors

Intercostal cryoablation during Nuss procedure: A large volume single surgeon's experience and outcomes - Sun, Raphael C.; Mehl, Steven C.; Anbarasu, Centura R.; Portuondo, Jorge I.; Espinoza, Andres F.; Whitlock, Richard; Mazziotti, Mark V. (Journal of Pediatric Surgery, 2021)
BACKGROUND: Recent studies have shown intercostal cryoablation(IC) during the Nuss procedure decreases hospital length of stay(LOS) and opioid administration. However, few studies have also evaluated the risk of postoperative complications related to IC. METHODS: We performed a single center retrospective analysis of all patients who underwent Nuss procedure by one surgeon from 2/2016 to 2/2020, comparing intraoperative IC to other pain management modalities(non-IC). Primary outcomes were postoperative complications, hospital LOS, and opioid administration. Multivariate analysis was performed with outcomes reported as regression coefficients(RC) or odds ratios(OR) with 95% confidence interval. RESULTS: IC was associated with decreased hospital LOS (RC -1.91[-2.29 to -1.54], less hospital opioid administration (RC -4.28[-5.13 to -3.43]), and less discharge opioid administration (RC -3.82[-5.23 to -2.41]). With respect to postoperative complications, IC decreased the odds of urinary retention (OR 0.16[0.06 to 0.44]); however, increased the odds of slipped bars requiring reoperation (OR 36.65[5.04-266.39]). CONCLUSIONS: Our single surgeon experience controls for surgeon variability and demonstrates intraoperative IC for the Nuss procedure is an effective pain management modality that decreases hospital LOS and opioid use during hospitalization and at discharge; however, it is associated with increased odds of slipped bars requiring reoperation. LEVEL OF EVIDENCE: III.
Cited By :11
Cited By :11
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Tórax en Embudo/cirugía; Dolor Postoperatorio/epidemiología; Dolor Postoperatorio/etiología; Tórax en Embudo; Criocirugía; Dolor Postoperatorio/cirugía; Cirujanos; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Cryosurgery; Intercostal cryoablation; Nuss; Opioid; Abbreviations; Forced expiratory volume (FEV); Forced vital capacity (FVC); Haller index (HI); intercostal cryoablation (IC); interquartile ranges (IQR); length of stay (LOS); multiple polyester (p-dioxanone) sutures (PDS); odds ratio (OR); oral morphine equivalents (OME/kg); patient-controlled analgesia (PCA); peripheral nerve block (PNB); regression coefficient (RC); Surgeons; thoracic epidural (TE)

Postoperative pain control modalities for pectus excavatum repair: A prospective observational study of cryoablation compared to results of a randomized trial of epidural vs patient-controlled analgesia - Dekonenko, Charlene; Dorman, Robert M.; Duran, Yara; Juang, David; Aguayo, Pablo; Fraser, Jason D.; Oyetunji, Tolulope A.; Snyder, Charles L.; Holcomb, George W.; Millspaugh, Daniel L.; St Peter, Shawn D. (Journal of Pediatric Surgery, 2020)
BACKGROUND: Pain following bar placement for pectus excavatum is the dominant factor post-operatively and determines length of stay (LOS). We recently adopted intercostal cryoablation as our preferred method of pain control following minimally invasive pectus excavatum repair. We compared the outcomes of cryoablation to results of a recently concluded trial of epidural (EPI) and patient-controlled analgesia (PCA) protocols. METHODS: We conducted a prospective observational study of patients undergoing bar placement for pectus excavatum using intercostal cryoablation. Results are reported and compared with those of a randomized trial comparing EPI with PCA. Comparisons of medians were performed using Kruskal-Wallis H tests with alpha 0.05. RESULTS: Thirty-five patients were treated with cryoablation compared to 32 epidural and 33 PCA patients from the trial. Cryoablation was associated with longer operating time (101 min, versus 58 and 57 min for epidural and PCA groups, p < 0.01), resulted in less time to pain control with oral medication (21 h, versus 72 and 67 h, p < 0.01), and decreased LOS (1 day, versus 4.3 and 4.2 days, p < 0.01). CONCLUSION: Intercostal cryoablation during minimally invasive pectus excavatum repair reduces LOS and perioperative opioid consumption compared with both EPI and PCA. LEVEL OF EVIDENCE: II.
Cited By :30
Cited By :30
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Dolor Postoperatorio/terapia; Humanos; Tórax en Embudo/cirugía; Analgesia Epidural; Estudios Prospectivos; Criocirugía/efectos adversos; Analgesia Controlada por el Paciente; Tiempo de Internación/estadística & datos numéricos; Funnel Chest; Pain, Postoperative; Cryosurgery; Length of Stay; Analgesia, Patient-Controlled; Prospective Studies; Analgesia, Epidural; Cryoanalgesia; Minimally invasive pectus excavatum repair; Cryoablation

Patient-Controlled Intravenous Analgesia with or without Ultrasound-Guided Bilateral Intercostal Nerve Blocks in Children Undergoing the Nuss Procedure: A Randomized, Double-Blinded, Controlled Trial - Ma, Bingjie; Sun, Yuan; Hao, Can; Liu, Xiaoming; Shen, Sai'e (Pain Research & Management, 2022)
BACKGROUND: Two analgesic strategies have been described for pain treatment after the pectus excavatum surgery: the patient-controlled intravenous analgesia (PCIA) and ultrasound-guided intercostal nerve block. In this prospective, randomized and double-blinded trial and the short and long-term outcomes were compared in patients after surgery. METHODS: The children were randomized to either the intercostal or control group. Ultrasound-guided intercostal nerve block was with 0.25% ropivacaine and 5 mg dexamethasone in the intercostal group, while the control group was with 0.9% normal saline. The block was performed in the intercostal space corresponding to the lowest depression of the sternum and repeated bilaterally in the spaces above and below. Postoperatively, the children in the two-groups received PCIA with fentanyl for 48 hours. The primary outcome was a pain score on the postoperative day 1, as measured by the Visual Analogue Scale (VAS). RESULTS: Sixty children undergoing the Nuss procedure were enrolled in the trial. The mean differences in VAS scores between the two groups were 3.2 in the PACU (p < 0.001), 1.7 on postoperative day 1 (p < 0.001) and 0.7 on postoperative day 2 (p=0.015). The opioid consumption was significantly lower in the intercostal group during the postoperative 48 hours (p < 0.05). The anxiety and QOL scores in the intercostal group were significantly improved on some points of time (p < 0.05). The incidence of adverse events was markedly lower in the intercostal group during the postoperative 48 hours (p < 0.05). CONCLUSIONS: Our results suggest ultrasound-guided intercostal nerve block with PCIA may be more effective than PCIA alone in children who underwent the Nuss procedure.
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Humanos; Nervios Intercostales; Niño; Bloqueo Nervioso/métodos; Dolor Postoperatorio/tratamiento farmacológico; Analgesia Controlada por el Paciente/métodos; Bloqueo Nervioso; Dolor Postoperatorio/etiología; Calidad de Vida; Estudios Prospectivos; Nervios Intercostales/diagnóstico por imagen; Ultrasonografía Intervencional/métodos; Child; Pain, Postoperative; Intercostal Nerves; Analgesia, Patient-Controlled; Prospective Studies; Nerve Block; Ultrasonography, Interventional; Quality of Life

[Pediatric postoperative quality analysis : Pain and postoperative nausea and vomiting] - Balga, I.; Konrad, C.; Meissner, W. (Der Anaesthesist, 2013)
BACKGROUND: For the evaluation of postoperative pain therapy, nausea and vomiting (PONV), the Children's Hospital in Lucerne acts as a member of the postoperative quality improvement project QUIPSi for children. Initial results and the potential for evaluation of the postoperative pain therapy and PONV are presented here. The central questions are whether the postoperative therapy concept is sufficient and if QUIPSi serves as an ideal tool for postoperative quality improvement? METHODS: Over a period of 1.5 years a total of 460 children aged between 4 to 17 years evaluated their postoperative pain, requirements for more analgesic medicine and the incidence of PONV according to a standardized questionnaire on the first postoperative day. The administration of analgesic medicine was recorded until finishing the questionnaire. RESULTS: In this study 5 pediatric outpatient operation groups (hernia repair n = 36, bone surgery n = 23, metal removal surgery n = 31, circumcision n = 65 and soft tissue surgery n = 49) and 9 pediatric inpatient operation groups (appendectomy n = 21, bone surgery n = 78, metal removal surgery n = 24, orchidopexy n = 31, combined operation (orchidopexy + hernia repair or circumcision) n = 14, otoplasty n = 9, tonsillectomy n = 41 and pectus excavatum surgery n = 6 and soft tissue surgery n=28) could be classified. All operation groups except the inpatient and outpatient soft tissue surgery groups received regional or infiltration anesthesia. Analgesic medicine was prescribed with the maximum permitted daily dose per kg body weight (paracetamol 100 mg/kgBW, metamizole 80 mg/kgBW, diclofenac 3 mg/kgBW and ibuprofen 40 mg/kgBW; in reserve tramadol 8 mg/kgBW and nalbuphine 2.4 mg/kgBW). The following operation groups complained of persistent pain (scale according to Hicks 0-10) and/or required more pain medicine (%): pediatric outpatients circumcision 5.1/19 %, pediatric inpatients appendectomy 6.5/43 %, tonsillectomy 6.4/32 %, pectus excavatum surgery 7.7/33 %, orchidopexy 4.2/19.4 %, otoplasty 3.1/22.2 %. The reason for the elevated postoperative pain was mainly insufficient administered pain medicine despite the prescription of the maximum daily dose per kg body weight or maybe due to a late administration. Circumcision/appendectomy/tonsillectomy/pectus excavatum surgery/orchidopexy/otoplasty (% of max. daily dose): paracetamol 5/58/99/36/57/37 %, metamizole 0,4/18/8/54/4/4 %, diclofenac 44/45/3/97/51/68 % or ibuprofen 42/1/0/0/0/0 %, tramadol 0,4/0/0/0/0/0 %, nalbuphine 0,4/1/16/0/2/0 %). As the standard inhalative general anesthesia and PONV prophylaxis with tropisetron (body weight: < 20 kg 1 mg, > 20 kg: 2 mg intravenous bolus) was performed. Dexamethasone (0.15-0.5 mg/kgBW, maximum allowed dose 8 mg intravenous bolus) was administered as a back-up drug for PONV. The nausea incidence was higher in the inpatient group (14-50 %) than in the outpatient group (10-29 %). The incidence of vomiting was higher in the inpatient (0-37 %) than in the outpatient group (3-17 %). CONCLUSIONS: The quality analysis showed that especially children with the requirement for more pain medicine and a high PONV incidence (inpatient group) need further improvement in postoperative care. Because of small numbers in some operation groups this qualitative evaluation of the postoperative pain and PONV management only gives an approximate overview. The results of QUIPSi uncovered gaps in the postoperative pain management which will help improve the quality in the postoperative setting. The QUIPSi approach should be integrated as a daily tool into all pediatric surgical departments.
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Humanos; Niño; Analgesia Epidural; Adolescent; Dimensión del Dolor/métodos; Preescolar; Encuestas y Cuestionarios; Analgésicos/uso terapéutico; Analgesia; Atención Ambulatoria; Benchmarking; Cuidados Posoperatorios/normas; Garantía de la Calidad de Atención de Salud; Manejo del Dolor/normas; Náusea y Vómito Posoperatorios/terapia; Pediatría/normas; Child; Pain, Postoperative; Analgesics; Pain Management; Pain Measurement; Analgesia, Epidural; Surveys and Questionnaires; Postoperative Nausea and Vomiting; Child, Preschool; Ambulatory Care; Pediatrics; Postoperative Care; Quality Assurance, Health Care

A review of anesthetic techniques and outcomes following minimally invasive repair of pectus excavatum (Nuss procedure) - Frawley, Geoff; Frawley, Jacinta; Crameri, Joe (Paediatric Anaesthesia, 2016)
BACKGROUND: Pectus excavatum (PE) is the most common congenital chest wall deformity, occurring in 1 : 1000 children with a male to female ratio of 4 : 1. Several procedures have been described to manage this deformity, including cartilage resection with sternal osteotomy (the Ravitch procedure) and a minimally invasive repair technique (the Nuss procedure). While initially described as a nonthoracoscopic technique, the current surgical approach of the Royal Childrens Hospital involves thoracoscopic assistance. Postoperative pain is significant in patients undergoing the pectus repair and multiple analgesic regimens have been advocated with continuous thoracic epidural infusions and opioid infusions the most common. Some authors have advocated patient-controlled analgesia (PCA), paravertebral nerve blocks (PVNB), and wound infusion catheters as alternatives. AIMS: The primary aim of this study was to assess our experience with postoperative pain and analgesia requirements associated with the minimally invasive repair of pectus excavatum in children. METHODS: This is a retrospective cohort study with a contemporaneous comparison group examining patients treated between January 2005 and December 2015 for minimally invasive repair of pectus excavatum by the Nuss procedure. RESULTS: Two hundred and seventeen patients [mean age 14.9 (sd 1.9) years] with pectus excavatum treated at the Royal Childrens Hospital between 2005 and 2015 were identified. All patients were managed with thoracic epidural analgesia and intravenous morphine infusions. The epidural was effective in the postanesthesia care unit in 97.3% (failure to place an epidural rate was 4 (1.9%); no block on awakening 0.9%). A further 4 (1.8%) were removed within 24 h. The mean morphine equivalent dose in the first 24 h was 0.8 mg·kg-1 ·day-1 . PCA was continued for a mean of 3.8 days and the total mean morphine equivalent dose was 2.2 mg·kg-1 ·day-1 . Minor complications occurred in 67 (30.9%) with postoperative nausea and vomiting in 36 patients (16.6%) and urinary retention requiring an indwelling catheter in 40 patients (18.4%). CONCLUSION: An epidural-based analgesic regime is associated with low pain scores and few acute complications. The continuation of morphine analgesia after the first postoperative day is common but associated with an increased incidence of urinary retention and nausea and vomiting.
Cited By :28
Cited By :28
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Adolescent; Female; Male; Bloqueo Nervioso; Estudios de Cohortes; Analgesia/métodos; Anestesia/métodos; Vías de Administración de Medicamentos; Analgesia; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesia, Patient-Controlled; Nerve Block; Cohort Studies; Anesthesia; anesthesia; Drug Administration Routes; funnel chest; pediatrics; thoracic surgery; thoracoscopy

Cryoanalgesia in Patients Undergoing Nuss Repair of Pectus Excavatum: Technique Modification and Early Results - Morikawa, Nicole; Laferriere, Nicole; Koo, Sylvia; Johnson, Sidney; Woo, Russell; Puapong, Devin (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2018)
PURPOSE: The Nuss procedure for surgical correction of pectus excavatum often causes severe postoperative pain. Cryoanalgesia of intercostal nerves is an alternative modality for pain control. We describe our modification of the cryoICE™ probe that allows for nerve ablation through the ipsilateral chest along with early results utilizing this technique. METHODS: To allow for ipsilateral nerve ablation, a 20-French chest tube was cut and secured to the cryoICE probe, thus providing insulation for the malleable end of the probe. A 3-year retrospective review of patients undergoing Nuss repair at our institution was performed. Patients who received cryoanalgesia (cryo, n = 6) were compared with a historical control cohort who did not receive cryoanalgesia (nocryo, n = 13) during Nuss repair. Hospital length of stay, postoperative narcotic requirement (PNR), and highest postoperative pain score were collected. RESULTS: Both cohorts were similar regarding age, BMI, and pectus index. The cryo group had a significantly less PNR (6.4 versus 17.9 doses, P = .05) and was discharged on average >1 day earlier than nocryo patients (3.7 versus 2.2 days, P = .01). No complications occurred in either group. CONCLUSIONS: Our technique modification simplifies previously described approaches to intercostal nerve cryoablation. Patients undergoing this adjunct benefit with less PNR and a faster discharge time.
Cited By :15
Cited By :15
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Crioanestesia/instrumentación; Crioanestesia/métodos; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/prevención & control; Criocirugía/métodos; Nervios Intercostales/cirugía; Estudios de Seguimiento; Procedimientos Ortopédicos; Criocirugía/instrumentación; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Nuss procedure; Cryosurgery; Intercostal Nerves; Orthopedic Procedures; pectus excavatum; Follow-Up Studies; pain management; cryoanalgesia; Cryoanesthesia

[Intercostal nerve cryoablation in correction of pectus excavatum in adults] - Pechetov, A. A.; Lednev, A. N.; Makov, M. A.; Chlan, T. N. (Khirurgiia, 2021)
OBJECTIVE: To evaluate an effectiveness of cryoanalgesia in older patients with pectus excavatum and to determine feasibility of further research. MATERIAL AND METHODS: We have developed an original technique of intercostal nerve cryoablation for correction of pectus excavatum in adults. The results of intercostal nerve cryoablation during correction of pectus excavatum in 10 older patients were analyzed. RESULTS: Postoperative outcomes were followed-up over a period of 4 - 12 months. There were no perioperative surgical complications. In 1 case, moderate pain syndrome persisted for 3 months after surgery (mean VAS score 2±1.3). In 9 months, mean VAS score was 0.6±0.6 in a month after surgery. CONCLUSION: Intercostal nerve cryoablation in correction of pectus excavatum in adults may be an alternative to the current methods of regional analgesia. Further research is requried to achieve objective information.
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Tórax en Embudo/cirugía; Tórax en Embudo/diagnóstico; Adulto; Adult; Tórax en Embudo; Criocirugía; Nervios Intercostales/cirugía; Criocirugía/efectos adversos; Dolor Postoperatorio; Anciano; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Cryosurgery; Intercostal Nerves; pectus excavatum; cryoanalgesia; Aged; intercostal nerve cryoablation

Comparison of erector spinae plane and paravertebral nerve blocks for postoperative analgesia in children after the Nuss procedure: study protocol for a randomized controlled non-inferiority clinical trial - Xu, Min; Zhang, Guangchao; Gong, Jingxuan; Yang, Jing (Trials, 2022)
BACKGROUND: Thoracic paravertebral block (TPVB) is a widely advocated regional technique for alleviating postoperative pain in children undergoing elective pectus excavatum repair. However, this technique is associated with some undesirable adverse events. Recently, the erector spinae plane block (ESPB) has been introduced as a practical alternative to the TPVB in thoracic surgery. This interfascial regional anesthesia technique interrupts pain sensation by injecting local anesthetics between the muscular layers of the thoracic wall. Several case series described it as an effective pain management technique following pectus excavatum repair. Therefore, this trial is designed to test the hypothesis that ESPB is non-inferior to TPVB in postoperative pain control after pectus excavatum repair. METHODS: This is a prospective randomized double-blind non-inferiority trial. A total of 40 patients aged 4 to 18 years undergoing Nuss surgery will be randomly assigned to receive pain treatment with either ESPB or TPVB. All patients will receive additional systemic multimodal analgesia with an intravenous patient-controlled analgesia pump and acetaminophen. The primary outcome is the pain intensity at rest, 24 h postoperatively. Secondary outcomes include accumulated morphine-equivalent consumption, postoperative pain scores, emergence agitation incidence, time of the first mobilization, time to first rescue analgesia, complications related to pain treatment, and morphine-related adverse events. DISCUSSION: This will the first randomized controlled trial to compare ESPB with TPVB for analgesia after pectus excavatum repair. This trial aims to provide important clinical evidence to elaborate on the analgesic mechanism of ESPB in children. TRIAL REGISTRATION: ClinicalTrials.gov NCT05034601 . This trial was prospectively registered.
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Humanos; Niño; Adolescent; Thoracic Surgical Procedures; Bloqueo Nervioso; Dolor Postoperatorio/prevención & control; Estudios Prospectivos; Analgesia Controlada por el Paciente; Ensayos Clínicos Controlados Aleatorios como Asunto; Preescolar; Procedimientos Quirúrgicos Torácicos; Child; Pain, Postoperative; Pectus excavatum; Analgesia, Patient-Controlled; Prospective Studies; Pain management; Erector spinae plane block; Nerve Block; Child, Preschool; Randomized controlled trial; Randomized Controlled Trials as Topic; Thoracic paravertebral block

Effects of dezocine on PAED scale and Ramsay sedation scores in patients undergoing NUSS procedure - Xia, Yingjing; Sun, Yingying; Liu, Junxia (American Journal of Translational Research, 2021)
OBJECTIVE: To investigate the effects of dezocine on pediatric anesthesia emergence delirium (PAED) and Ramsay sedation scores in patients undergoing Nuss procedures (minimally invasive surgery for repairing pectus excavatum). METHODS: Altogether, 100 patients with pectus excavatum who underwent Nuss procedures in our hospital were selected and randomly divided into group A (n=50) and group B (n=50). General anesthesia was carried out for each patient, with an anaesthetic of sufentanil for group A, and dezocine plus sufentanil for group B. The visual analogue scale (VAS) score and Ramsay sedation score were recorded at extubation (T0), 10 min after extubation (T1), 20 min after extubation (T2), 30 min after extubation (T3) and 60 min after extubation (T4) for assessment of pain intensity and sedative effect; PAED scale score was applied to observe the emergence delirium at awakening, 15 min after awakening and 30 min after awakening. Quality of recovery-15 (QoR-15) scale score was used to evaluate the quality of early rehabilitation 1 d after operation and 2 d after operation. The occurrence of adverse reactions was recorded. RESULTS: The VAS scores at T0, T1, T2, T3 and T4 in group B were lower than those in group A, and there was statistical significance between group A and group B (P<0.001). VAS scores at T1, T2 and T3 were lower than those recorded at T0 in both groups (P<0.01), while no significant difference was noted at other time points (P>0.05). Ramsay sedation scores were increased at T0, T1, T2, T3 and T4 in group B in comparison to that in group A (all P<0.001), while the scores recorded at T4 in group A and T3 and T4 in group B were increased compared with those recorded at T0 (all P<0.01), and there was no significant difference at other time points (all P>0.05). Compared with group A, PAED scores in group B were downregulated at each time point after wakening up (all P<0.01), while QoR-15 scores in group B were increased at 1 d and 2 d after surgery (all P<0.05); there was no significant difference in adverse reactions between the two groups (all P>0.05). CONCLUSION: Sufentanil combined with dezocine is efficacious in general analgesia and sedation, which can reduce emergence agitation, improves the quality of rehabilitation and is relatively safe for patients undergoing minimally invasive repairing of pectus excavatum.
Keywords: Nuss procedure; dezocine; emergence agitation; sedation; sufentanil

Intercostal nerve cryoablation versus thoracic epidural for postoperative analgesia following pectus excavatum repair: a systematic review and meta-analysis - Daemen, Jean H. T.; de Loos, Erik R.; Vissers, Yvonne L. J.; Bakens, Maikel J. A. M.; Maessen, Jos G.; Hulsewé, Karel W. E. (Interactive Cardiovascular and Thoracic Surgery, 2020)
OBJECTIVES: Minimally invasive pectus excavatum repair via the Nuss procedure is associated with significant postoperative pain that is considered as the dominant factor affecting the duration of hospitalization. Postoperative pain after the Nuss procedures is commonly controlled by thoracic epidural analgesia. Recently, intercostal nerve cryoablation has been proposed as an alternative method with long-acting pain control and shortened hospitalization. The subsequent objective was to systematically review the outcomes of intercostal nerve cryoablation in comparison to thoracic epidural after the Nuss procedure. METHODS: Six scientific databases were searched. Data concerning the length of hospital stay, operative time and postoperative opioid usage were extracted. If possible, data were submitted to meta-analysis using the mean of differences, random-effects model with inverse variance method and I2 test for heterogeneity. RESULTS: Four observational and 1 randomized study were included, enrolling a total of 196 patients. Meta-analyses demonstrated a significantly shortened length of hospital stay [mean difference -2.91 days; 95% confidence interval (CI) -3.68 to -2.15; P < 0.001] and increased operative time (mean difference 40.91 min; 95% CI 14.42-67.40; P < 0.001) for cryoablation. Both analyses demonstrated significant heterogeneity (both I2 = 91%; P < 0.001). Qualitative analysis demonstrated the amount of postoperative opioid usage to be significantly lower for cryoablation in 3 out of 4 reporting studies. CONCLUSIONS: Intercostal nerve cryoablation during the Nuss procedure may be an attractive alternative to thoracic epidural analgesia, resulting in shortened hospitalization. However, given the low quality and heterogeneity of studies, more randomized controlled trials are needed.
Cited By :4
Cited By :4
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Dolor Postoperatorio/prevención & control; Criocirugía/métodos; Tiempo de Internación; Nervios Intercostales/cirugía; Tempo Operativo; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Pectus excavatum; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Analgesia, Epidural; Operative Time; Hospitalization; Thoracic epidural analgesia

Ultrasound-Guided Serratus Anterior Plane Block for Pain Management Following Minimally Invasive Repair of Pectus Excavatum - Tore Altun, Gulbin; Arslantas, Mustafa Kemal; Corman Dincer, Pelin; Aykac, Zeynep Zuhal (Journal of Cardiothoracic and Vascular Anesthesia, 2019)
OBJECTIVE: The Nuss procedure is a preferred technique for minimally invasive repair of pectus excavatum (MIRPE), but it is associated with significant postoperative pain. We assessed the efficacy and safety of an ultrasound-guided bilateral serratus anterior plane block (SAPB) for relieving acute pain from MIRPE. DESIGN: A retrospective cohort study. SETTING: This study was conducted at the Marmara University Pendik Training and Research Hospital, Turkey. PARTICIPANTS: All participants were scheduled for MIRPE. INTERVENTIONS: This study was conducted from November 2017 to May 2018. Postoperative pain control was achieved with bilateral SAPB done after induction of anesthesia and IV PCA in 50 patient (SABP group) and with only IV PCA in 45 patients (Control group). SAPB was achieved, targeting the interfascial plane between the serratus anterior and latissimus dorsi muscles, with a single injection of 30 mL (20 mL if patient weighed < 40 kg) of 0.25% bupivacaine and 0.5% lidocaine into each side. Pain scores were recorded for 24 h. MEASUREMENT AND MAIN RESULTS: Patients in the Control group had a higher demand (mean difference, 61; 95% confidence interval [CI] 30.5-136; P < 0.0001) and delivery dose (mean difference, 25; 95% CI 15-41.5 P = 0.001) during the first postoperative 24 h. SAPB did not affect the median (interquartile range) length of hospital stay: 5 (5-7) days vs. 5 (4-6) days, (P =0.085). CONCLUSIONS: Bilateral single-injection SAPB in patients undergoing MIRPE decreases pain and opioid consumption during the early postoperative period.
Cited By :11
Cited By :11
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Bloqueo Nervioso/métodos; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Female; Male; Young Adult; Dolor Postoperatorio/etiología; Ultrasonografía Intervencional/métodos; Dimensión del Dolor/métodos; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Tórax en Embudo/diagnóstico por imagen; Adulto Joven; Dolor Postoperatorio/diagnóstico por imagen; Estudios de Cohortes; Músculo Esquelético/diagnóstico por imagen; Músculo Esquelético/inervación; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Pain Measurement; Pain management; Nerve Block; Ultrasonography, Interventional; Cohort Studies; analgesia; Muscle, Skeletal; Serratus anterior plane block

Comparing outcomes with thoracic epidural and intercostal nerve cryoablation after Nuss procedure - Harbaugh, Calista M.; Johnson, Kevin N.; Kein, Courtney E.; Jarboe, Marcus D.; Hirschl, Ronald B.; Geiger, James D.; Gadepalli, Samir K. (The Journal of Surgical Research, 2018)
BACKGROUND: This study aimed to evaluate postoperative outcomes after minimally invasive repair of pectus excavatum (Nuss procedure) using video-assisted intercostal nerve cryoablation (INC) compared to thoracic epidural (TE). MATERIALS AND METHODS: We performed a single center retrospective review of pediatric patients who underwent Nuss procedure with INC (n = 19) or TE (n = 13) from April 2015 to August 2017. Preoperative, intraoperative, and postoperative characteristics were collected. The primary outcome was length of stay (LOS) and secondary outcomes were intravenous and oral opioid use, pain scores, and complications. Opioids were converted to oral morphine milligram equivalents per kilogram (oral morphine equivalent [OME]/kg). Mann-Whitney U test was used for continuous and chi-squared analysis for categorical variables. RESULTS: There were no significant differences in patient characteristics, except Haller Index (INC: median [interquartile range] 4.3 [3.6-4.9]; TE: 3.2 [2.8-4.0]; P = 0.03). LOS was shorter with INC (INC: 3 [3-4] days; TE: 6 [5-7] days; P < 0.001). Opioid use was higher intraoperatively (INC: 1.08 [0.87-1.37] OME/kg; TE: 0.46 [0.37-0.67] OME/kg; P = 0.002) and unchanged postoperatively (INC: 1.78 [1.26-3.77] OME/kg; TE: 1.82 [1.05-3.37] OME/kg; P = 0.80), and prescription doses were lower at discharge in INC (INC: 30 [30-40] doses; TE: 42 [40-60] doses; P = 0.005). There was no significant difference in postoperative complications (INC: 42.1%; TE: 53.9%; P = 0.51). CONCLUSIONS: INC during Nuss procedure reduced LOS, shifting postoperative opioid use earlier during admission. This may reflect the need for improved early pain control until INC takes effect. Prospective evaluation after INC is needed to characterize long-term pain medication requirements.
Cited By :28
Cited By :28
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/prevención & control; Nervios Intercostales/cirugía; Analgésicos Opioides/administración & dosificación; Procedimientos Quirúrgicos Mínimamente Invasivos; Complicaciones Posoperatorias/epidemiología; Criocirugía/estadística & datos numéricos; Analgesia Epidural/estadística & datos numéricos; Cirugía Asistida por Video; Michigan/epidemiología; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Postoperative Complications; Pain management; Analgesia, Epidural; Epidural; Cryoablation; Michigan; Pectus; Pediatric surgery; Video-Assisted Surgery

Intraoperative cryoanalgesia for managing pain after the Nuss procedure - Graves, Claire; Idowu, Olajire; Lee, Sang; Padilla, Benjamin; Kim, Sunghoon (Journal of Pediatric Surgery, 2017)
BACKGROUND: Cryoanalgesia prevents pain by freezing the affected peripheral nerve. We report the use of intraoperative cryoanalgesia during the Nuss procedure for pectus excavatum and describe our initial experience, modifications of technique, and lessons learned. MATERIALS AND METHODS: We retrospectively reviewed the medical records of patients who received cryoanalgesia during the Nuss procedure between June 1, 2015, and April 30, 2016, at our institutions and analyzed modifications in surgical technique during this early adoption period. RESULTS: Eight male and two female patients underwent the Nuss procedure with cryoanalgesia. The mean postoperative length of stay (LOS) was 2days (range 1-3). Average inpatient pain scores were 3.4, 3.2, and 4.6 on postoperative days 1-3, respectively (N=10, 7, and 2). At a 1-week postoperative visit, mean pain score was 1.1 (N=6). Compared to the preceding 15 Nuss patients at our institution, who were treated with a thoracic epidural, postoperative LOS was significantly shorter with cryoanalgesia (2.0±0.82 vs. 6.3±1.3days, P<0.001). We modified our technique for patient habitus and adopted single-lung ventilation for improved visualization. CONCLUSIONS: Cryoanalgesia may be the ideal pain management strategy for Nuss patients because it is effective and long lasting. Intraoperative application is easily integrated into the Nuss procedure. STUDY TYPE: Treatment study: case series; Evidence level IV.
Cited By :39
Cited By :39
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Nervios Intercostales; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Female; Male; Young Adult; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/prevención & control; Adulto Joven; Crioterapia/métodos; Estudios de Seguimiento; Procedimientos Ortopédicos; Analgesia/métodos; Cuidados Intraoperatorios/métodos; Toracoscopía; Analgesia; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Nuss procedure; Pectus excavatum; Intercostal Nerves; Orthopedic Procedures; Cryoanalgesia; Thoracoscopy; Follow-Up Studies; Cryoprobe; Cryotherapy; Epidural analgesia; Intraoperative Care

Epidural analgesia versus intravenous analgesia after minimally invasive repair of pectus excavatum in pediatric patients: a systematic review and meta-analysis - Heo, Min Hee; Kim, Ji Yeon; Kim, Jung Hyeon; Kim, Kyung Woo; Lee, Sang Il; Kim, Kyung-Tae; Park, Jang Su; Choe, Won Joo; Kim, Jun Hyun (Korean Journal of Anesthesiology, 2021)
BACKGROUND: Postoperative pain control after the minimally invasive repair of pectus excavatum (MIRPE) is essential, but there is a controversy about a better analgesic method between epidural and intravenous (IV) analgesia. This systematic review and meta-analysis aimed to compare the effect of epidural versus IV analgesia following MIRPE. METHODS: We searched PubMed, MEDLINE, EMBASE, Cochrane Central Register, and ClinicalTrials.gov for randomized controlled trials (RCTs) dated up to 31st May 2021. The primary outcome was the area under the curve (AUC) of the weighted mean visual analog scale (VAS) after MIRPE. The secondary outcomes were postoperative nausea, operation time, total operating room time, and postoperative length of hospital stay. RESULTS: Four RCTs involving 243 patients were finally included in this meta-analysis. The AUC of the weighted mean VAS was 343.62 in the epidural group and 375.24 in the IV group. The epidural group showed lower VAS than the IV group at 12 to 48 h after the surgery. Postoperative nausea, operation time and length of hospital stay was not different between two groups. The epidural group had a significantly longer total operating room time due to epidural catheter insertion time. CONCLUSIONS: Epidural analgesia after the MIRPE had a better analgesic effect than IV analgesia. However, IV analgesia may also be a viable option, and physicians should wisely choose analgesic modalities after MIRPE.
Cited By :4
Cited By :4
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Humanos; Manejo del Dolor; Niño; Tórax en Embudo/cirugía; Analgesia Epidural; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Tórax en Embudo; Analgesia Epidural/efectos adversos; Tórax en Embudo/diagnóstico por imagen; Child; Funnel Chest; Pain, Postoperative; Pain Management; Analgesia, Epidural; Postoperative pain; Funnel chest; Epidural analgesia; Intravenous administration; Minimally invasive surgical procedures; Statistics; Systematic review

Postoperative pain management in pediatric patients undergoing minimally invasive repair of pectus excavatum: the role of intercostal block - Lukosiene, Laura; Rugyte, Danguole Ceslava; Macas, Andrius; Kalibatiene, Lina; Malcius, Dalius; Barauskas, Vidmantas (Journal of Pediatric Surgery, 2013)
PURPOSE: There are no published data regarding value of intercostal block following pectus excavatum repair. Our aim was to evaluate the efficacy of intercostal block in children following minimally invasive repair of pectus excavatum (MIRPE). METHODS: Forty-five patients given patient-controlled analgesia (PCA) with morphine postoperatively were studied. Twenty-six patients were given bilateral intercostal blocks after induction of anesthesia (PCA-IB group), and nineteen patients were retrospective controls without regional blockade (PCA group). All patients were followed up 24 h postoperatively. RESULTS: A loading dose of morphine (0,1±0,49 mg/kg) before starting PCA was used in seventeen patients in PCA group vs. no patient in PCA-IB group. Cumulative used morphine doses were lower up to 12 h after surgery in PCA-IB group (0,29±0,08 μg/kg) than in the PCA group (0,46±0,18 μg/kg), p<0,01. There were no differences in pain scores, oxygen saturation values, sedation scores, and the incidence of pulmonary adverse events between the two groups. There was a tendency towards less morphine-related adverse effects in PCA-IB group compared to PCA group (p<0,05). No complications related to the intercostal blocks were observed. CONCLUSION: Bilateral intercostal blocks following MIRPE are safe and easy to perform and can diminish postoperative opioid requirement. Double-blind randomized study is required to confirm the potential to diminish opioid related side effects.
Cited By :33
Cited By :33
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Niño; Bloqueo Nervioso/métodos; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/prevención & control; Analgésicos Opioides/uso terapéutico; Estudios Prospectivos; Analgesia Controlada por el Paciente; Dimensión del Dolor; Esquema de Medicación; Procedimientos Quirúrgicos Mínimamente Invasivos; Bupivacaína/uso terapéutico; Estudios de Seguimiento; Procedimientos Ortopédicos; Procedimientos Ortopédicos/métodos; Cuidados Posoperatorios/métodos; Modelos Lineales; Anestésicos Locales/uso terapéutico; Epinefrina/uso terapéutico; Morfina/uso terapéutico; Quimioterapia Combinada; Simpatomiméticos/uso terapéutico; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesics, Opioid; Orthopedic Procedures; Analgesia, Patient-Controlled; Prospective Studies; Pain Measurement; Nerve Block; Bupivacaine; Morphine; Anesthetics, Local; Postoperative pain; Follow-Up Studies; Postoperative Care; Children; Drug Administration Schedule; Drug Therapy, Combination; Epinephrine; Intercostal block; Linear Models; Sympathomimetics

Which Is More Effective for Minimally Invasive Pectus Repair: Epidural or Paravertebral Block? - Aydin, Gulcin; Sahin, Ahmet Tugrul; Gencay, Isin; Akcabay, Zeynep Nur; Gunal, Nesimi; Dural, Koray; Ozpolat, Berkant; Buyukkocak, Unase (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2020)
Objective: The aim of this study was to compare the effectiveness of epidural block (EDB) and paravertebral block (PVB) for minimally invasive pectus repair with the conventional method in terms of pain control during and after pectus operations, patient comfort, and length of stay in hospital. Materials and Methods: A retrospective review was made of patients who underwent minimally invasive pectus repair. The patients were allocated into three groups as follows: PVB group (Pre-emptive ultrasound-guided bilateral thoracic single injection PVB, n = 15); EDB group (Pre-emptive landmark-guided single injection thoracic EDB, n = 8); and Control group (Neither PVB nor EPB, n = 9). The intraoperative analgesic requirement was recorded, and a visual analog scale (VAS) for pain evaluation and the Postoperative Patient Satisfaction Scale were applied to all patients. Results: The intraoperative analgesic requirement, VAS scores, postoperative satisfaction level, and time to first requirement for postoperative analgesia were different between the control and PVB groups (P < .001) and between the control and EDB groups (P < .001), but not different between the PVB and EDB groups. Although the length of stay in hospital was shorter in the PVB and EDB groups compared to the control group, the difference was not statistically significant (P = .422). Conclusion: Epidural and bilateral paravertebral blockades performed in conjunction with general anesthesia decrease the intraoperative and postoperative need for analgesics, and might be beneficial for pain management and contribute to a shorter length of hospital stay for patients undergoing minimally invasive pectus repair operations. Both blockades also significantly improved the patient satisfaction.
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Bloqueo Nervioso/métodos; Pectus Carinatum/cirugía; Tórax en Embudo/cirugía; Adolescent; Female; Male; Young Adult; Bloqueo Nervioso; Dolor Postoperatorio/prevención & control; Tiempo de Internación; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Satisfacción del Paciente; Adulto Joven; Dimensión del Dolor; Analgésicos/uso terapéutico; Anestesia Epidural; Anestesia General; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Minimally Invasive Surgical Procedures; Length of Stay; Pain Measurement; Patient Satisfaction; Nerve Block; Anesthesia, Epidural; Anesthesia, General; epidural block; minimally invasive pectus repair; paravertebral block; Pectus Carinatum; ultrasonography

Use of cryoanalgesia for pain management for the modified ravitch procedure in children - Pilkington, Mercedes; Harbaugh, Calista M.; Hirschl, Ronald B.; Geiger, James D.; Gadepalli, Samir K. (Journal of Pediatric Surgery, 2020)
BACKGROUND: Intercostal cryoablation(IC) for pain management in children undergoing Nuss Procedure has been previously described. We evaluated postoperative outcomes following Modified Ravitch procedure for pectus disorders comparing IC to thoracic epidural(TE). MATERIALS AND METHODS: Single-center retrospective review of pediatric patients (age < 21) undergoing Modified Ravitch procedure (January 2015-March 2019) with either IC(9), or TE(20) analgesia. Primary outcome was length of stay (LOS) and secondary outcomes were inpatient opioid use (in oral morphine equivalents per kilogram; OME/kg), pain scores on each postoperative day (POD), discharge prescriptions, and complications. Pairwise comparisons made with Mann-Whitney U test or Fisher Exact test as appropriate. Two-tailed p values <0.05 were considered significant. RESULTS: Patient characteristics were similar. LOS was shorter with IC compared to TE (4 days versus 6; p < 0.006). Postoperative opioid use was not significantly different (IC: 1.5 OME/kg versus TE: 1.1; p = 0.10). There was improved pain control on POD 2 in patients who underwent IC (median pain score 3 versus 4; p < 0.0004). There was no difference in discharge prescription (IC: 3.3 OME/kg; TE: 4.8; p = 0.19) or complication rate (IC: 55.6%, TE:50%; p = 1.0). CONCLUSIONS: IC during the Modified Ravitch reduced LOS compared to TE with improved pain control starting on POD 2, with similar narcotic utilization and complication rates. LEVEL OF EVIDENCE: Treatment Study, Level III (Retrospective comparative study).
Cited By :7
Cited By :7
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Estudios Retrospectivos; Humanos; Niño; Manejo del Dolor/métodos; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Young Adult; Adulto Joven; Tiempo de Internación/estadística & datos numéricos; Crioterapia; Procedimientos Ortopédicos/efectos adversos; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Length of Stay; Orthopedic Procedures; Pain Management; Cryoanalgesia; Pain; Pediatric; Pectus; Cryotherapy; Ravitch; Thoracic

Progressive reduction of hospital length of stay following minimally invasive repair of pectus excavatum: A retrospective comparison of three analgesia modalities, the role of addressing patient anxiety, and reframing patient expectations - Schlatter, Marc G.; Nguyen, Long V.; Tecos, Maria; Kalbfell, Elle L.; Gonzalez-Vega, Omar; Vlahu, Tedi (Journal of Pediatric Surgery, 2019)
PURPOSE: Management of postoperative pain is a significant challenge following the Nuss procedure. Epidurals, PCAs, and newer analgesia modalities have been used elsewhere without demonstrating consistent improvement in the reported length of hospital stays (LOS). We reviewed a large single surgeon experience identifying three different methods of analgesia used over time to highlight marked improvement in patient LOS. METHODS: IRB approval was obtained and patient clinical information was retrospectively reviewed from 2001 to 2017. The primary outcome variable was length of hospital stay. An expanded preoperative consultation reviews the issue of pain, the negative impact of anxiety on recovery, and our current success of shortened hospital stays with our patients. RESULTS: One hundred and seventy-three patients representing three different analgesia approaches had a LOS of 4.4 days (epidural); 2.2 days (PCA/intercostal nerve block); and 1.6 days (scheduled oral pain meds/intercostal nerve blocks). The current LOS for patients is 1.0 day. Patients successfully stop using narcotics by the end of the first week postoperatively. CONCLUSIONS: Intraoperative intercostal nerve blocks, scheduled postoperative pain medications, and enhanced preoperative consultation aimed to educate patients about anxiety and reframe patient pain expectations have collectively decreased LOS, and reduced postoperative narcotic usage. TYPE OF STUDY: Clinical research LEVEL OF EVIDENCE: Level III.
Cited By :16
Cited By :16
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Manejo del Dolor/métodos; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Female; Male; Young Adult; Adulto Joven; Dimensión del Dolor; Tiempo de Internación/estadística & datos numéricos; Analgesia/métodos; Ansiedad/tratamiento farmacológico; Narcóticos/uso terapéutico; Toracoscopía/efectos adversos; Toracoscopía/psicología; Analgesia; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Length of Stay; Pain Management; Pain Measurement; Thoracoscopy; Nuss repair; Narcotics; Anxiety; Minimally-invasive

Impact of Epidural Failures on the Results of a Prospective, Randomized Trial - Desai, Amita; Alemayehu, Hanna; Weesner, Kathryn A.; St Peter, Shawn D. (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2016)
INTRODUCTION: We conducted a prospective randomized trial to evaluate the merits of two established postoperative pain management strategies: thoracic epidural (EPI) versus patient-controlled analgesia (PCA) with intravenous narcotics after minimally invasive repair of pectus excavatum. Pain scores favored the EPI group for the first two postoperative days only. Critics of the trial suggest that if the epidural failure rate was not so high, results may have favored the EPI group. Therefore, we performed a subset analysis of the EPI group to evaluate the impact of these failures. METHODS: Patients for whom epidural catheter could not be placed or whose catheters were removed early owing to dysfunction were compared with those with well-functioning catheters. Those with well-functioning catheters were also compared with the PCA group. A two-tailed independent Student t-test and a two-tailed Fisher exact test were used where appropriate. RESULTS: Of 55 patients in the EPI group, 12 patients (21.8%) had failed placement or required early removal. Comparing those with failed placements with the rest of the group, there was no difference in daily visual analogue scale pain scores or measures of hospital course. Likewise, comparing those with well-functioning catheters only to those in the PCA group, the results of the trial are replicated in terms of pain scores, hospital course, and length of stay. CONCLUSION: In patients with failed epidural therapy, there is no significant difference in postoperative hospital course. Comparing those with well-functioning catheters to those in the PCA group, trial results are replicated-that is, no significant difference in length of stay, time to regular diet, or time to transition to oral medications. Therefore, failure rate in the EPI group did not influence the results of the trial.
Cited By :3
Cited By :3
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Humanos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Periodo Posoperatorio; Adolescent; Dolor Postoperatorio/prevención & control; Estudios Prospectivos; Analgesia Controlada por el Paciente; Dimensión del Dolor; Tempo Operativo; Anestesia Epidural; Estudios de Seguimiento; Catéteres; Insuficiencia del Tratamiento; Funnel Chest; Pain, Postoperative; Analgesia, Patient-Controlled; Prospective Studies; Pain Measurement; Postoperative Period; Operative Time; Follow-Up Studies; Catheters; Anesthesia, Epidural; Treatment Failure

Cryoablation is associated with shorter length of stay and reduced opioid use in pectus excavatum repair - Rettig, R. Luke; Rudikoff, Andrew G.; Lo, Hoi Yee Annie; Shaul, Donald B.; Banzali, Franklin M.; Conte, Antonio Hernandez; Sydorak, Roman M. (Pediatric Surgery International, 2021)
PURPOSE: The use of intercostal nerve cryoablation (INC) is becoming increasingly common in patients undergoing pectus excavatum (PE) repair. This study sought to evaluate the use of INC compared to traditional use of thoracic epidural (TE). METHODS: A retrospective review of 79 patients undergoing PE repair with either INC or TE from May 2009 to December 2019 was conducted. The operations were performed by four surgeons who worked together at four different hospitals and have the same standardized practice. The primary outcome measure was hospital length of stay (LOS). Secondary variables included surgical time, total operating room time, operating room time cost, total hospital cost, inpatient opioid use, long-term opioid use after discharge, and postoperative complications. RESULTS: LOS decreased to 2.5 days in the INC group compared to 5 days in the TE group (p < 0.0001). Surgical time was increased in the INC group, but there was no difference in total OR time. The INC group experienced significantly lower hospital costs. Total hospital opioid administration was significantly lower in INC group, and there was a significant decrease in long-term opioid use in the INC group. CONCLUSIONS: INC is a newer modality that decreases LOS, controls pain, and results in overall cost savings. We recommend that INC be included in the current practice for postoperative pain control in PE patients undergoing Nuss procedure.
Cited By :9
Cited By :9
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Female; Male; Young Adult; Criocirugía/métodos; Nervios Intercostales/cirugía; Adulto Joven; Analgésicos Opioides/administración & dosificación; Complicaciones Posoperatorias; Tempo Operativo; Tiempo de Internación/estadística & datos numéricos; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Pectus excavatum repair; Postoperative Complications; Operative Time; Enhanced recovery after surgery; Thoracic epidural

Guided relaxation-based virtual reality versus distraction-based virtual reality or passive control for postoperative pain management in children and adolescents undergoing Nuss repair of pectus excavatum: protocol for a prospective, randomised, controlled trial (FOREVR Peds trial) - Olbrecht, Vanessa A.; Williams, Sara E.; O'Conor, Keith T.; Boehmer, Chloe O.; Marchant, Gilbert W.; Glynn, Susan M.; Geisler, Kristie J.; Ding, Lili; Yang, Gang; King, Christopher D. (BMJ open, 2020)
INTRODUCTION: Virtual reality (VR) offers an innovative method to deliver non-pharmacological pain management. Distraction-based VR (VR-D) using immersive games to redirect attention has shown short-term pain reductions in various settings. To create lasting pain reduction, VR-based strategies must go beyond distraction. Guided relaxation-based VR (VR-GR) integrates pain-relieving mind-body based guided relaxation with VR, a novel therapy delivery mechanism. The primary aim of this study is to assess the impact of daily VR-GR, VR-D and 360 video (passive control) on pain intensity. We will also assess the impact of these interventions on pain unpleasantness, anxiety and opioid and benzodiazepine consumption. The secondary aim of this study will assess the impact of psychological factors (anxiety sensitivity and pain catastrophising) on pain following VR. METHODS AND ANALYSIS: This is a single centre, prospective, randomised, clinical trial. Ninety children/adolescents, aged 8-18 years, presenting for Nuss repair of pectus excavatum will be randomised to 1 of 3 study arms (VR-GR, VR-D and 360 video). Patients will use the Starlight Xperience (Google Daydream) VR suite for 10 min. Patients randomised to VR-GR (n=30) will engage in guided relaxation/mindfulness with the Aurora application. Patients randomised to VR-D (n=30) will play 1 of 3 distraction-based games, and those randomised to the 360 video (n=30) will watch the Aurora application without audio instructions or sound. Primary outcome is pain intensity. Secondary outcomes include pain unpleasantness, anxiety and opioid and benzodiazepine consumption. ETHICS AND DISSEMINATION: This study follows Standard Protocol Items: Recommendations for Interventional Trials guidelines. The protocol was approved by the Cincinnati Children's Hospital Medical Center's institutional review board. Patient recruitment began in July 2020. Written informed consent will be obtained for all participants. All information acquired will be disseminated via scientific meetings and published in peer-reviewed journals. TRIAL REGISTRATION NUMBER: NCT04351776.
Keywords: Humans; Adolescente; Humanos; Niño; Tórax en Embudo/cirugía; Adolescent; Tórax en Embudo; Estudios Prospectivos; Ensayos Clínicos Controlados Aleatorios como Asunto; Dolor Postoperatorio; Guías de Práctica Clínica como Asunto; Realidad Virtual; Reproducibilidad de los Resultados; Child; Funnel Chest; Pain, Postoperative; Prospective Studies; pain management; Randomized Controlled Trials as Topic; clinical trials; complementary medicine; paediatric anaesthesia; paediatric thoracic surgery; Practice Guidelines as Topic; Reproducibility of Results; Virtual Reality

Quantifying postoperative sleep loss associated with increased pain in children undergoing a modified Nuss operation - Many, Benjamin T.; Rizeq, Yazan K.; Kwon, Soyang; Vacek, Jonathan C.; Goldstein, Seth D.; Hunter, Catherine J.; Ghomrawi, Hassan; Abdullah, Fizan (Journal of Pediatric Surgery, 2020)
PURPOSE: The presence of pain may interrupt sleep and impede normal postoperative recovery; however, no prior studies have quantified sleep loss due to pain in children undergoing inpatient surgery. Wearable accelerometers objectively measure sleep patterns in children. We aimed to quantify sleep loss associated with patient reported pain scores after a Modified Nuss operation. METHODS: Ten patients undergoing Modified Nuss operations were recruited during their inpatient stay. Children wore an Actigraph GT3X-BT accelerometer postoperatively during their hospital stay. Hourly sleep minutes were recorded using the Actigraph between 10 pm and 6 am. Patient reported pain scores were abstracted from patient charts. Mixed linear regression models, adjusting for within-subject random effects, were estimated to quantify the association between hourly sleep minutes and patient reported pain scores. RESULTS: Patients were 30% female, with an average age of 15.7 years (range 13-22). The majority (70%) of patients were white non-Hispanic. All patients received a patient controlled analgesic pump. Average postoperative length of stay was 4.8 days (range 4.0-6.0; SD = 0.8). A total of 240 sleep hours and associated pain scores were analyzed. Patients slept on average 48 min per hour. Mixed model analysis predicted that a 1-point increase in pain score was associated with 2.5 min per hour less sleep time. CONCLUSION: Increases in patient-reported pain scores are associated with sleep loss after a Modified Nuss operation. Objectively quantifying sleep loss associated with postoperative pain using accelerometer data may help clinicians better understand their patient's level of pain control. Our findings provide the basis for future studies aimed at more accurately titrating pain medication to optimize sleep and speed up recovery. LEVEL OF EVIDENCE: Case Series Without Comparison Group, Level IV.
Cited By :7
Cited By :7
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Female; Male; Young Adult; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio; Adulto Joven; Analgésicos/uso terapéutico; Actigrafía; Dolor Postoperatorio/complicaciones; Procedimientos Quirúrgicos Reconstructivos/efectos adversos; Sueño/fisiología; Trastornos del Sueño-Vigilia; Trastornos del Sueño-Vigilia/diagnóstico; Trastornos del Sueño-Vigilia/etiología; Funnel Chest; Pain, Postoperative; Treatment Outcome; Analgesics; Pectus excavatum; Pain; Pediatric surgery; Children; Accelerometers; Actigraphy; Plastic Surgery Procedures; Sleep; Sleep Wake Disorders; Wearable telemetry

Thoracic epidural-based Enhanced Recovery After Surgery (ERAS) pathway for Nuss repair of pectus excavatum shortened length of stay and decreased rescue intravenous opiate use - Cramm, Shannon L.; Luckhurst, Casey; Galls, Alexandra; Pietrantonio, Nicole; Doody, Daniel P.; Ryan, Daniel P.; Masiakos, Peter T. (Pediatric Surgery International, 2021)
BACKGROUND: PCA- and block-based enhanced recovery after surgery (ERAS) pathways have been shown to decrease hospital length of stay (HLOS) and opiate use following Nuss Repair for Pectus Excavatum (NRPE). No thoracic epidural-based ERAS pathway has demonstrated similar benefits. METHODS: In this pre-post single-center study, data were retrospectively collected for patients ≤ 21 years undergoing NRPE from May 2015 to August 2019. Univariate and multivariate methods were used to evaluate whether implementation of a thoracic epidural-based ERAS in April 2017 was associated with HLOS, opiate use, or pain scores. RESULTS: There were 110 patients: 35 pre- and 75 post-ERAS. HLOS decreased from median 4.8 (1.1) to 3.3 (0.6) days with ERAS (p < 0.001). Use of rescue intravenous opiates decreased from 35.3% pre- to 9.3% with ERAS (p = 0.013). When adjusted for baseline characteristics, ERAS was associated with a 1.3 ± 0.2 day decrease in HLOS and 0.188 times the odds of rescue intravenous opiate use (p = 0.011). CONCLUSIONS: Pain scores, ED visits, and readmissions did not change with ERAS (p > 0.05). Implementation of a thoracic epidural-based ERAS following NRPE was associated with decreased HLOS and need for any rescue intravenous opiates without a change in pain scores, ED visits, or readmission.
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Tórax en Embudo; Tiempo de Internación; Alcaloides Opiáceos; Recuperación Mejorada Después de la Cirugía; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Length of Stay; Length of stay; Thoracic epidural; Enhanced Recovery After Surgery; ERAS; Opiate Alkaloids

Next day discharge after the Nuss procedure using intercostal nerve cryoablation, intercostal nerve blocks, and a perioperative ERAS pain protocol - DiFiore, John W.; Robertson, Jason O.; Chhabada, Surendrasingh; DeRoss, Anthony L.; Hossain, Mir S.; Rincon-Cruz, Lorena; Sung, Wai (Journal of Pediatric Surgery, 2022)
BACKGROUND: The Nuss procedure for pectus excavatum has historically been associated with significant postoperative pain, which has been the major factor contributing to hospital length of stay (LOS). METHODS: A single-institution, prospective study of 40 consecutive patients undergoing Nuss bar placement for pectus excavatum between November 2019 and January 2021 was conducted to assess the effectiveness of a multimodality pain management protocol. All patients received T3-T8 intercostal nerve cryoablation (INC), T3-T8 bupivacaine intercostal nerve blocks, Exparel at the skin incisions, and management with a perioperative analgesia regimen that minimized narcotic usage. The primary outcome was LOS. Secondary outcomes included opioid use, pain scores, and time to sensory recovery. RESULTS: 37/40 patients (92.5%) were discharged home on postoperative day (POD) 1, and 3/40 (7.5%) were discharged on POD 2 (mean LOS = 1.1 days). The median average postoperative pain score was 2/10. After eliminating IVPCA from our protocol, total oral morphine equivalent (OME) decreased by 73% (55.5 mg to 15 mg) with no change in pain scores or discharge timing. CONCLUSIONS: INC combined with bupivacaine intercostal nerve blocks and a pre- and post-hospital analgesia protocol facilitated discharge one day after the Nuss procedure, achieved excellent pain control, and eliminated the need for intravenous opioids.
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Nervios Intercostales; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Analgésicos Opioides; Tórax en Embudo; Criocirugía; Dolor Postoperatorio/cirugía; Tiempo de Internación; Estudios Prospectivos; Alta del Paciente; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Enhanced recovery after surgery (ERAS); Patient Discharge; Prospective Studies; Analgesia, Epidural; Intercostal nerve blocks; Nuss bar procedure

Customized silicone implant for the correction of acquired and congenital chest wall deformities: A valuable option with pectus excavatum - Soccorso, Giampiero; Parikh, Dakshesh H.; Worrollo, Steve (Journal of Pediatric Surgery, 2015)
BACKGROUND: Surgical remodeling and correction of congenital and acquired chest wall deformities (CWD) is undertaken many times for cosmesis. Although reportedly minimally invasive, commonly used Nuss procedure for correction of pectus excavatum (PE) is not without complications. Nuss procedure is also not suitable for complex deformities and Poland syndrome cases. Insertion of custom-made silicone implants for the reconstruction of defects has been adopted from adult plastic reconstructive surgery as primary repair of CWD or rescue procedure for recurrence of PE after recurrence or residual deformity. METHODS: We present our experience with CWD reconstruction in children with customized silicone prosthesis made from a surgically implantable liquid silicone rubber (NuSil MED-4805, Ca). RESULTS: Since 2006 we treated 26 patients with CWD: six were children (age <17years, median 14.6) with PE. Implants were custom made for each patient's chest. The implants were inserted under general anesthesia. Postoperatively all patients were fully satisfied with the cosmetic result and subjective patient satisfaction remained excellent at follow-up in all the children. Only one child developed postoperative complications (seroma). CONCLUSIONS: Customized silicone implant for PE in the pediatric age is an alternative therapeutic method, as primary or rescue treatment, with equally good cosmetic outcome, fewer significant complications, less postoperative pain and a faster recovery.
Cited By :6
Cited By :6
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Niño; Tórax en Embudo/cirugía; Periodo Posoperatorio; Adulto; Adolescent; Adult; Female; Male; Dolor Postoperatorio/etiología; Satisfacción del Paciente; Complicaciones Posoperatorias/etiología; Procedimientos Quirúrgicos Reconstructivos/métodos; Síndrome de Poland/cirugía; Recurrencia; Contraindicaciones; Diseño de Prótesis; Elastómeros de Silicona; Implantación de Prótesis; Pared Torácica/anomalías; Pared Torácica/cirugía; Prótesis e Implantes; Child; Funnel Chest; Pain, Postoperative; Pectus excavatum; Postoperative Complications; Patient Satisfaction; Postoperative Period; Thoracic Wall; Recurrence; Children; Plastic Surgery Procedures; Chest wall deformity; Contraindications; Poland Syndrome; Prostheses and Implants; Prosthesis Design; Prosthesis Implantation; Silicone Elastomers; Silicone implant

Successful use of an enhanced recovery after surgery (ERAS) pathway to improve outcomes following the Nuss procedure for pectus excavatum - Wharton, Kristin; Chun, Young; Hunsberger, Joann; Jelin, Eric; Garcia, Alejandro; Stewart, Dylan (Journal of Pediatric Surgery, 2020)
PURPOSE: Pectus excavatum is a common chest wall deformity amenable to surgical correction, most commonly by a technique known as the Nuss Procedure. The surgery is associated with significant postoperative pain and lengthy hospital stays. We hypothesized that a standardized enhanced recovery after surgery (ERAS) pathway would result in significantly reduced length of stay (LOS) and reduced levels of postoperative pain without an increase in readmissions or emergency department (ED) visits. METHODS: We instituted a pectus excavatum ERAS program at a high-volume academic center. Our ERAS protocol standardized perioperative exercise and pharmacologic regimens, pre- and post-operative education, and early return to activity. We conducted a retrospective review of all patients undergoing the Nuss procedure from 2015 to 2018. ERAS was implemented at the mid-point of the study period, and pre- and post-protocol patients were compared in our analysis. The primary outcome measure was LOS. The secondary outcomes included pain scores, incidence of urinary retention, and readmissions or ED visits. RESULTS: One hundred nine patients were included in this study (51 patients pre-ERAS and 58 post-ERAS). The average length of hospitalization prior to implementation of ERAS was 3.49 and after the implementation 2.90 (p = 0.0007). The implementation of ERAS showed a trend of decreasing readmissions and emergency department visits, but this did not reach statistical significance. There was a statistically significant decrease in both requirement for urinary catheter placement and pain scores on postoperative day 0. CONCLUSIONS: Implementation of ERAS for the Nuss procedure leads to a significant reduction in LOS, early pain scores, and urinary catheter usage, without an increase in post-operative ED visits and hospital readmissions. An ERAS protocol should be utilized in this patient population. TYPE OF STUDY: Retrospective comparative study. TYPE OF EVIDENCE: Level III.
Cited By :17
Cited By :17
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Tórax en Embudo/cirugía; Periodo Posoperatorio; Adolescent; Female; Infant, Newborn; Male; Young Adult; Tiempo de Internación; Preescolar; Recuperación Mejorada Después de la Cirugía; Adulto Joven; Analgésicos/uso terapéutico; Gabapentina/uso terapéutico; Lactante; Procedimientos Quirúrgicos Reconstructivos; Readmisión del Paciente; Recién Nacido; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Nuss procedure; Pectus excavatum; Length of Stay; Enhanced recovery after surgery (ERAS); Postoperative Period; Length of stay; Child, Preschool; Plastic Surgery Procedures; Enhanced Recovery After Surgery; Gabapentin; Infant; Patient Readmission

A comparison of paravertebral nerve block catheters and thoracic epidural catheters for postoperative analgesia following the Nuss procedure for pectus excavatum repair - Hall Burton, Denise M.; Boretsky, Karen R. (Paediatric Anaesthesia, 2014)
INTRODUCTION: Thoracic epidurals (TE) have been advocated as a superior method for controlling postoperative pain after repair of pectus excavatum with a Nuss procedure. However, three recent reports of permanent neurologic injury after the Nuss procedure with concurrent TE analgesia have raised concerns about the safety of this combination. Paravertebral nerve blocks (PVNB) are used successfully for analgesia of the chest, but no studies are available comparing TE and PVNB catheters for postoperative analgesia in this patient population. This study was conducted to compare the efficacy of PVNB catheters with TE catheters for postoperative analgesia in pediatric patients undergoing the Nuss procedure. METHODS: We retrospectively reviewed the medical records of 20 adolescent males undergoing a thoracoscopic Nuss procedure with either bilateral PVNB catheters (n = 10) or TE catheter (n = 10) and compared postoperative opiate consumption and pain scores. RESULTS: There were no statistically significant differences between the groups with respect to demographics, opiate consumption measured in morphine equivalents, and pain scores. DISCUSSION: In this small series, bilateral PVNB catheters resulted in equivalent opioid consumption and pain scores when compared to TE for postoperative pain management in pediatric patients undergoing the Nuss procedure. Large prospective studies are needed to further compare the efficacy, incidence of side effects, and complications of TE and PVNB catheters for postoperative analgesia in this pediatric population.
Cited By :73
Cited By :73
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Humanos; Masculino; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Bloqueo Nervioso/métodos; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Analgesia Epidural/instrumentación; Analgesia Epidural/métodos; Adolescent; Male; Dimensión del Dolor/métodos; Analgésicos Opioides/administración & dosificación; Bloqueo Nervioso/instrumentación; Catéteres; Morfina/administración & dosificación; Estudios de Casos y Controles; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Pain Measurement; Analgesia, Epidural; Nerve Block; Morphine; Catheters; pediatrics; acute pain; anesthesia conduction; anesthesia, epidural; anesthesiology; bone diseases, developmental; Case-Control Studies; nerve block; pain, postoperative

Epidural versus Patient-Controlled Analgesia after Pediatric Thoracotomy for Malignancy: A Preliminary Review - Gonzalez, Katherine W.; Dalton, Brian G.; Millspaugh, Daniel L.; Thomas, Priscilla G.; St Peter, Shawn David (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2016)
Introduction The use of thoracic epidural is standard in adult thoracotomy patients facilitating earlier mobilization, deep breathing, and minimizing narcotic effects. However, a recent randomized trial in pediatric patients who undergo repair of pectus excavatum suggests patient-controlled analgesia (PCA) produces a less costly, minimally invasive postoperative course compared with epidural. Given that thoracotomy is typically less painful than pectus bar placement, we compared the outcomes of epidural to PCA for pain management after pediatric thoracotomy. Methods A retrospective review of 17 oncologic thoracotomies was performed at a children's hospital from 2004 to 2013. Data points included operative details, epidural or PCA use, urinary catheterization, days to regular diet, days to oral pain regimen, postoperative pain scores, length of stay, and anesthesia charges. Patients were excluded if they did not have epidural or PCA following thoracotomy. Results Six thoracotomies were managed with an epidural and 11 with a PCA. Three epidural patients were opiate naïve compared with two with a PCA. The most common indication for thoracotomy was metastatic osteosarcoma (n = 13). When comparing epidural to PCA, there was no significant difference in days to removal of Foley catheter, regular diet, oral pain control, length of stay, or total operating room time. Postoperative pain scores were also comparable. The mean anesthesia charges were significantly higher in patients with an epidural than with a PCA. Conclusion Epidural catheter and PCA provided comparable pain relief and objective recovery course in children who underwent thoracotomy for oncologic disease; however, epidural catheter placement was associated with increased anesthesia charges, suggesting that PCA is a noninvasive, cost-effective alternative.
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Analgesia Controlada por el Paciente/métodos; Adolescent; Female; Male; Dolor Postoperatorio/prevención & control; Tiempo de Internación; Dimensión del Dolor; Tempo Operativo; Cuidados Posoperatorios/métodos; Analgesia Controlada por el Paciente/economía; Analgesia Controlada por el Paciente/efectos adversos; Anestesia Epidural/economía; Anestesia Epidural/efectos adversos; Anestesia Epidural/métodos; Blastoma Pulmonar/cirugía; Osteosarcoma/cirugía; Sarcoma de Ewing/cirugía; Toracotomía; Child; Pain, Postoperative; Retrospective Studies; Length of Stay; Analgesia, Patient-Controlled; Pain Measurement; Operative Time; Anesthesia, Epidural; Postoperative Care; Osteosarcoma; Pulmonary Blastoma; Sarcoma, Ewing; Thoracotomy

Pain management following the Nuss procedure: a survey of practice and review - Muhly, W. T.; Maxwell, L. G.; Cravero, J. P. (Acta Anaesthesiologica Scandinavica, 2014)
BACKGROUND: Pectus excavatum is the most common congenital chest wall deformity. The Nuss procedure is frequently used for surgical correction and this technique has been associated with severe and prolonged post-operative pain. At the present time, the optimal analgesic strategy for managing patients following this procedure has not been determined. METHODS: A web-based survey was sent to representatives from 108 primarily pediatric hospitals in North America, Europe, Asia and Australia. One individual per institution was contacted to complete the survey on behalf of their department. RESULTS: Survey response rate was 54% and 55 institutions reported using the Nuss procedure for correction of pectus excavatum. Annual case volume is less than or equal to 25 cases in 57% of institutions, and the most common age of patients is 14 to 17 years old. A clinical protocol for patient post-operative pain management is used in 45% of institutions. Thoracic epidural is utilized as a primary analgesic modality by 91% of institutions. Concomitant use of intravenous patient-controlled analgesia is reported by 27% of institutions. Nine respondents (16%) reported that they had recently stopped performing epidurals because of surgeon preference. Referral of one or more patients annually for chronic pain management was reported in 22% of surveys. CONCLUSIONS: Post-operative pain management following the Nuss procedure is variable and poorly characterized. Clinical trials or large observational registries comparing the safety and efficacy of primary modalities and long-term outcomes are needed to enable evidence-based decision-making for the management of these patients.
Cited By :28
Cited By :28
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Europe; Humans; Adolescente; Humanos; Niño; Manejo del Dolor/métodos; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Analgesia Epidural/métodos; Adolescent; Dolor Postoperatorio/prevención & control; Analgesia/métodos; Analgesia Epidural/estadística & datos numéricos; América del Norte; Analgesia Controlada por el Paciente/estadística & datos numéricos; Analgesia/estadística & datos numéricos; Asia; Australia; Encuestas de Atención de la Salud/estadística & datos numéricos; Encuestas de Atención de la Salud/métodos; Europa (Continente); Manejo del Dolor/estadística & datos numéricos; Pautas de la Práctica en Medicina/estadística & datos numéricos; Analgesia; Child; Funnel Chest; Pain, Postoperative; Analgesia, Patient-Controlled; Pain Management; Analgesia, Epidural; Health Care Surveys; North America; Practice Patterns, Physicians'

Perioperative anesthetic and surgical complications of the Nuss procedure - Umuroglu, Tumay; Bostancı, Korkut; Thomas, David Terence; Yuksel, Mustafa; Gogus, F. Yilmaz (Journal of Cardiothoracic and Vascular Anesthesia, 2013)
OBJECTIVE: The Nuss procedure is a chest wall remodeling surgery performed in patients with pectus excavatum. This study was performed to analyze perioperative surgical and anesthetic complications with the Nuss procedures. DESIGN: A retrospective analysis. SETTING: An academic hospital. PARTICIPANTS: Two hundred fourteen patients (children, adolescents, and adults) undergoing the Nuss procedure over 6 years. INTERVENTIONS: Patient age and sex, premorbid diseases, indications for surgery, patient position during the procedure, the length of surgery, time to hospital discharge, postoperative analgesia method, and the presence of perioperative complications were recorded. MEASUREMENTS: No mortality was observed. The overall complication rate was 18.7%, but the overall event rate was 42.6% (91 events in 40 patients). Intraoperative hypotension, tachycardia, and hypercapnia were the most common complications (4.7%), followed by postoperative ileus (3.2%), pneumothorax (right, left, or bilateral; 4.2%), lung parenchymal laceration (2.3%), and postoperative nausea and vomiting (2.3%). Two patients had an ulnar nerve palsy and 1 patient had a brachial nerve palsy as a result of surgical position. CONCLUSION: Although the Nuss procedure is reported to be minimally invasive, some serious complications concerning both surgery and anesthesia should not be overlooked.
Cited By :14
Cited By :14
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Female; Male; Young Adult; Thoracic Surgical Procedures; Tiempo de Internación; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Analgesia Controlada por el Paciente; Adulto Joven; Procedimientos Quirúrgicos Torácicos/efectos adversos; Procedimientos Quirúrgicos Torácicos/métodos; Atención Perioperativa; Complicaciones Posoperatorias/epidemiología; Anestesia General/métodos; Anestesia General/efectos adversos; Capacidad Vital; Complicaciones Intraoperatorias/epidemiología; Complicaciones Posoperatorias/terapia; Medicación Preanestésica; Posición Supina/fisiología; Pruebas de Función Respiratoria; Volumen Espiratorio Forzado; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Length of Stay; Analgesia, Patient-Controlled; Postoperative Complications; Forced Expiratory Volume; Vital Capacity; Anesthesia, General; Intraoperative Complications; Perioperative Care; Preanesthetic Medication; Respiratory Function Tests; Supine Position

A retrospective comparison of thoracic epidural infusion and multimodal analgesia protocol for pain management following the minimally invasive repair of pectus excavatum - Man, Janice Y.; Gurnaney, Harshad G.; Dubow, Scott R.; DiMaggio, Theresa J.; Kroeplin, Gina R.; Adzick, N. Scott; Muhly, Wallis T. (Paediatric Anaesthesia, 2017)
BACKGROUND: Pain management following minimally invasive repair of pectus excavatum is variable. We recently adopted a comprehensive multimodal analgesic protocol that standardizes perioperative analgesic management. We hypothesized that patients managed with this protocol would use more opioids postoperatively, have similar pain control, and shorter length of stay compared to patients managed with thoracic epidural infusion. AIMS: We retrospectively compared opioid consumption, pain scores, and length of stay between a cohort of patients managed with our multimodal analgesic protocol and a cohort managed with a thoracic epidural infusion. METHODS: This retrospective cohort comparison includes patients, 8 to 21 years of age, managed with either thoracic epidural infusion (n = 21) or multimodal analgesic protocol (n = 29) following minimally invasive repair of pectus excavatum from January 1, 2011 through September 15, 2015. The primary outcome, total daily opioid consumption in morphine equivalents, is presented as an average by postoperative day. Secondary outcomes included median daily pain score and length of stay. RESULTS: Patients were similar in age, weight, sex, and physical status. Patients managed with thoracic epidural infusion received less opioid (morphine equivalents-mg/kg) intraoperatively compared to multimodal analgesic protocol (difference of mean [95% confidence interval] 0.22 [0.16-0.28] P ≤ .01) but required more total opioid through postoperative day 3 (difference of mean [95% confidence interval] 1.2 [0.26-2.14] P = .01). We did not observe a difference in pain scores. Median length of stay was 1 day less in patients managed with multimodal analgesic protocol (difference of median [95% confidence interval] 1 [0.3-1.7] P = .003). CONCLUSION: Implementation of a standardized comprehensive multimodal analgesic protocol following minimally invasive repair of pectus excavatum resulted in equivalent analgesia with a modest reduction in length of stay when compared to thoracic epidural. We did not observe an opioid sparing effect in our thoracic epidural which may reflect technique variability.
Cited By :17
Cited By :17
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Dolor Postoperatorio/tratamiento farmacológico; Manejo del Dolor/métodos; Resultado del Tratamiento; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Adolescent; Female; Male; Dolor Postoperatorio/prevención & control; Analgésicos Opioides/uso terapéutico; Tiempo de Internación; Analgesia Controlada por el Paciente; Analgésicos Opioides/administración & dosificación; Estudios de Cohortes; Analgésicos no Narcóticos/uso terapéutico; Dimensión del Dolor/efectos de los fármacos; Vértebras Torácicas; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Length of Stay; Analgesia, Patient-Controlled; Pain Management; Pain Measurement; Analgesia, Epidural; Analgesics, Non-Narcotic; Cohort Studies; acute pain; adolescent; child; opioids; quality improvement; Thoracic Vertebrae

Complications after Ravitch versus Nuss repair of pectus excavatum: A Society of Thoracic Surgeons (STS) General Thoracic Surgery Database analysis - Jawitz, Oliver K.; Raman, Vignesh; Thibault, Dylan; Yerokun, Babatunde; Zwischenberger, Brittany A.; Kosinski, Andrzej S.; Allen, Mark S.; Harpole, David H. (Surgery, 2021)
BACKGROUND: There are conflicting reports in the literature comparing outcomes after open Ravitch and minimally invasive Nuss procedures for pectus excavatum repair, and there is relatively little data available comparing the outcomes of these procedures performed by thoracic surgeons. METHODS: The 2010 to 2018 Society of Thoracic Surgeons General Thoracic Surgery Database was queried for patients age 12 or greater undergoing open or minimally invasive repair of pectus excavatum. Patients were stratified by operative approach. Multivariable logistic regression was performed with a composite outcome of 30-day complications. RESULTS: A total of 1,767 patients met inclusion criteria, including 1,017 and 750 patients who underwent minimally invasive pectus repair and open repair, respectively. Open repair patients were more likely to be American Society of Anesthesiologists (ASA) class III or greater (24% vs 14%; P < .001), have a history of prior cardiothoracic surgery (26% vs 14%; P < .001), and require longer operations (median 268 vs 185 minutes; P < .001). Open repair patients were more likely to require greater than 6 days of hospitalization (18% vs 7%; P < .001), undergo transfusion (7% vs 2%; P < .001), and be readmitted (8% vs 5%; P = .004). After adjustment, open repair was not associated with an increased risk of a composite of postoperative complications (odds ratio 0.99, 95% confidence interval 0.67-1.46). This finding persisted after propensity score matching (odds ratio 1.11, 95% confidence interval 0.74-1.67). CONCLUSION: Pectus excavatum repair procedure type was not associated with the risk of postoperative complications after adjustment. Further investigation is necessary to determine the impact of pectus excavatum repair type on recurrence and patient reported outcomes, including satisfaction, quality of life, and pain control.
Cited By :3
Cited By :3
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Femenino; Humanos; Masculino; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Tórax en Embudo/cirugía; Adulto; Adult; Female; Male; Young Adult; Thoracic Surgical Procedures; Calidad de Vida; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Satisfacción del Paciente; Adulto Joven; Esternón/cirugía; Factores de Riesgo; Procedimientos Quirúrgicos Torácicos/efectos adversos; Procedimientos Quirúrgicos Torácicos/métodos; Puntaje de Propensión; Funnel Chest; Retrospective Studies; Minimally Invasive Surgical Procedures; Patient Satisfaction; Quality of Life; Sternum; Risk Factors; Propensity Score

Ultrasound-Guided Percutaneous Cryoanalgesia for Pectus Excavatum: When Should It be Applied? - Velayos, María; Alonso, Mercedes; Estefanía, Karla; Jesus Muñoz, Antonio; Torres, Raquel; Hernández, Francisco; Reinoso, Francisco; Torre, Carlos De la (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2023)
INTRODUCTION: The addition of ultrasound-guided percutaneous cryoanalgesia (PCr) for pain management after pectus excavatum (PE) surgery offers a new and advantageous approach. Our aim is to describe our experience with PCr applied on the same day, 24 hours, and 48 hours prior to PE surgery. MATERIAL AND METHODS: Prospective pilot study in patients undergoing ultrasound-guided PCr (2019-2022) was divided into three groups: PCr on the same day of surgery (PCrSD), PCr 24 hours before (PCr24), and PCr 48 hours before (PCr48). We describe the application of technique and data obtained by comparing the three groups. RESULTS: We present 42 patients (25 PCrSD, 11 PCr24, 6 PCr48). PCr24 had a shorter procedure duration than PCrSD (65.8 vs. 91.2 minute; p = 0.048). Related to analgesia, PCr24 and PCr48 showed lower opioid consumption than PCrSD in PCA volume (48.5 and 49.6 vs. 75.1 mL; p = 0.015) and PCA time (23.3 and 23.8 vs. 34.3 hours; p = 0.01). Degree of pain (VAS scale) on the day of surgery and on the second postoperative day was lower in PCr24 and PCr48 than in PCrSD (4 and 2 vs. 5; p = 0.012; 0 and 1 vs. 2; p = 0.01, respectively) as well as shorter hospital stay (3 and 3.5 vs. 5 days; p = 0.021). In addition, PCr24 showed lower opioid consumption and hospital stay than PCr48 (p > 0.05). The greatest savings in hospital costs were obtained in the PCr24 group. CONCLUSION: PCr48 and PCr24 prior to PE surgery offers lower opioid consumption, less pain and shorter hospital stay than PCrSD. PCr24 is comparable to PCr48, but seems to show advantages and simpler logistics for the patient and the hospital.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Prospective Studies; Ultrasonography, Interventional; Pilot Projects

Intercostal nerve cryoablation versus thoracic epidural catheters for postoperative analgesia following pectus excavatum repair: Preliminary outcomes in twenty-six cryoablation patients - Keller, Benjamin A.; Kabagambe, Sandra K.; Becker, James C.; Chen, Y. Julia; Goodman, Laura F.; Clark-Wronski, Julianna M.; Furukawa, Kenneth; Stark, Rebecca A.; Rahm, Amy L.; Hirose, Shinjiro; Raff, Gary W. (Journal of Pediatric Surgery, 2016)
BACKGROUND: Multimodal pain management strategies are used for analgesia following pectus excavatum repair. However, the optimal regimen has not been identified. We describe our early experience with intercostal cryoablation for pain management in children undergoing the Nuss procedure and compare early cryoablation outcomes to our prior outcomes using thoracic epidural analgesia. METHODS: A multi-institutional, retrospective review of fifty-two patients undergoing Nuss bar placement with either intercostal cryoablation (n=26) or thoracic epidural analgesia (n=26) from March 2013 to January 2016 was conducted. The primary outcome was hospital length of stay. Secondary outcomes included telemetry unit monitoring time, total intravenous narcotic use, duration of intravenous narcotic use, and postoperative complications. RESULTS: Patients who underwent intercostal cryoablation had a significant reduction in the mean hospital length of stay, time in a monitored telemetry bed, total use of intravenous narcotics, and the duration of intravenous narcotic administration when compared to thoracic epidural patients. Cryoablation patients had a slightly higher rate of postoperative complications. CONCLUSION: Intercostal cryoablation is a promising technique for postoperative pain management in children undergoing repair of pectus excavatum. This therapy results in reduced time to hospital discharge, decreased intravenous narcotic utilization, and has eliminated epidurals from our practice. LEVEL OF EVIDENCE: Retrospective study - level III.
Cited By :58
Cited By :58
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Adolescent; Female; Male; Criocirugía/métodos; Dolor Postoperatorio/cirugía; Nervios Intercostales/cirugía; Analgésicos Opioides/administración & dosificación; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Pain management; Analgesia, Epidural; Cryoablation; Epidural analgesia

Opioid use and length of stay following minimally invasive pectus excavatum repair in 436 patients - Benefits of an enhanced recovery pathway - Holmes, David M.; Polites, Stephanie F.; Roskos, Penny L.; Moir, Christopher R. (Journal of Pediatric Surgery, 2019)
PURPOSE: The purpose of this study was to determine outcomes of an enhanced recovery pathway (ERP) for minimally invasive repair of pectus excavatum (MIRPE) at a high volume center, hypothesizing it is associated with decreased opioid requirement and shorter hospital stay. METHODS: Patients were categorized into pre-ERP (1998-2006), transition (2007-2011), and ERP (2012-2017) cohorts. Data were abstracted from medical records. Univariate and multivariable analyses compared opioid utilization, length of stay (LOS), and complications between cohorts. Opioids were converted to morphine daily dose per kilogram (MEDD/kg). RESULTS: Of 436 patients, 186 were ERP, 104 were transition, and 146 were pre-ERP. ERP was associated with decreased hospital opioid utilization (mean MEDD/kg 0.5 ± 0.2 vs 0.7 ± 0.4 vs 0.7 ± 0.8 p < .001) and shorter median LOS (3 vs 4 vs 5 days, p < .001) despite equivalent pain scores at discharge (2.7 ± 0.1 vs 2.8 ± 0.2 vs 2.9 ± 0.3, p = .73). Most ERP patients (76%) had LOS ≤3 days. Differences in LOS between ERP, transition, and pre-ERP persisted on multivariable analysis after adjusting for confounding factors. Post-operative complications were rare and not different between groups (p > .05). CONCLUSIONS: Implementation of our ERP was associated with decreased opioid requirement and shorter hospital stay. ERPs are a valuable tool in pediatric surgery given the current emphasis on optimizing opioid and resource utilization. LEVELS OF EVIDENCE: Level III (Retrospective comparative study).
Cited By :12
Cited By :12
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Adulto; Dolor Postoperatorio/epidemiología; Adolescent; Adult; Female; Male; Young Adult; Analgésicos Opioides/uso terapéutico; Adulto Joven; Estados Unidos/epidemiología; Incidencia; Alta del Paciente/tendencias; Laparoscopía/métodos; Recuperación de la Función/efectos de los fármacos; Tiempo de Internación/tendencias; Toracoplastia/métodos; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally invasive repair; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesics, Opioid; Length of Stay; Patient Discharge; Thoracoplasty; Length of stay; Incidence; United States; Enhanced recovery protocol; Laparoscopy; Opioid utilization; Recovery of Function

Intercostal nerve cryoablation is associated with lower hospital cost during minimally invasive Nuss procedure for pectus excavatum - Aiken, Taylor J.; Stahl, Christopher C.; Lemaster, Deborah; Casias, Timothy W.; Walker, Benjamin J.; Nichol, Peter F.; Leys, Charles M.; Abbott, Daniel E.; Brinkman, Adam S. (Journal of Pediatric Surgery, 2021)
Minimally invasive repair of pectus excavatum (Nuss procedure) is associated with significant pain, and efforts to control pain impact resource utilization. Bilateral thoracic intercostal nerve cryoablation has been proposed as a novel technique to improve post-operative pain control, though the impact on hospital cost is unknown. METHODS: We conducted a retrospective study of patients undergoing a Nuss procedure from 2016 to 2019. Patients who received cryoablation were compared to those that received traditional pain control (patient-controlled analgesia or epidural). Outcome variables included postoperative opioid usage (milligram morphine equivalents, MME), length of stay (LOS), and hospital cost. RESULTS: Thirty-five of 73 patients studied (48%) received intercostal nerve cryoablation. LOS (1.0 vs 4.0 days, p < 0.01) and total hospital cost ($21,924 versus $23,694, p = 0.04) were decreased in the cryoablation cohort, despite longer operative time (152 vs 74 min, p < 0.01). Cryoablation was associated with decreased opioid usage (15.0 versus 148.6 MME, p < 0.01) during the 24 h following surgery and this persisted over the entire postoperative period, including discharge opioid prescription (112.5 vs 300.0 MME, p < 0.01). CONCLUSION: Bilateral intercostal nerve cryoablation is associated with decreased postoperative opioid usage and decreased resource utilization in pediatric patients undergoing a minimally invasive Nuss procedure for pectus excavatum. LEVEL OF EVIDENCE: Retrospective comparative study, level III.
Cited By :11
Cited By :11
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Nervios Intercostales; Niño; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Dolor Postoperatorio/etiología; Tórax en Embudo; Criocirugía; Dolor Postoperatorio/cirugía; Costos de Hospital; Procedimientos Quirúrgicos Mínimamente Invasivos; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Pectus excavatum; Cryosurgery; Intercostal Nerves; Pediatric; Cryoablation; Hospital cost; Hospital Costs; Minimally invasive Nuss procedure; Post-op pain

Long-term patient perception of pain control experience after participating in a trial between patient-controlled analgesia and epidural after pectus excavatum repair with bar placement - Gasior, Alessandra C.; Weesner, Kathryn A.; Knott, E. Marty; Poola, Ashwini; St Peter, Shawn D. (The Journal of Surgical Research, 2013)
BACKGROUND: Pain control is the dominant management issue after bar placement for pectus excavatum. We previously conducted a prospective, randomized trial comparing patient-controlled analgesia (PCA) to thoracic epidural (EPI) documenting similar objective outcomes. Our impression is that the subjective cognitive experience differs between the groups, which impacts trial results interpretation. Therefore, we conducted a survey to ascertain patient recollection and impression of their experience. METHODS: By telephone questionnaire, yes/no questions included early course recall, anxiety, if they would choose the same arm, do the operation again, or recommend it to friends. Qualitative questions included description, location, and time of peak pain. The graded question addressed severity of pain (1-5). RESULTS: We contacted 27 EPI and 38 PCA patients with a median follow-up of 3.2 y. The majority (~/= 85%) of both groups remembered the first 2 d. Mean pain severity was 3.0 in both groups (3 = bad, but tolerable). Description, location, and time of peak pain responses did not differ. Anxiety was reported by 30% of EPI group and 18% of PCA group (P = 0.37). Approximately 15% of both groups still think about the pain. No differences were seen in nausea, emesis, constipation, itching, or sleepiness. Most patients would choose the same group (87% PCA, 81% EPI, P = 0.73), have the operation again (87% PCA, 74% EPI, P = 0.21), and recommend the operation to friends (100% PCA, 96% EPI, P = 0.42). CONCLUSIONS: Long-term recall after repair of pectus excavatum with bar placement does not substantially differ between those managed with an epidural or PCA.
Cited By :12
Cited By :12
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Analgésicos Opioides/uso terapéutico; Estudios Prospectivos; Analgesia Controlada por el Paciente; Satisfacción del Paciente; Estudios de Seguimiento; Procedimientos Ortopédicos; Dolor Postoperatorio/psicología; Entrevistas como Asunto; Oxicodona/uso terapéutico; Tiempo; Umbral del Dolor/psicología; Funnel Chest; Pain, Postoperative; Analgesics, Opioid; Orthopedic Procedures; Analgesia, Patient-Controlled; Prospective Studies; Patient Satisfaction; Analgesia, Epidural; Pain control; Epidural; Pediatric; Follow-Up Studies; Interviews as Topic; Oxycodone; Pain Threshold; PCA; Pectus bar; Time

The Use of Cryoanalgesia in Minimally Invasive Repair of Pectus Excavatum: Lessons Learned - Parrado, Raphael; Lee, Justin; McMahon, Lisa E.; Clay, Conner; Powell, Jordan; Kang, Paul; Notrica, David M.; Ostlie, Daniel J.; Bae, Jae-O. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2019)
Introduction: Cryoanalgesia has been applied to minimally invasive repair of pectus excavatum (MIRPE). After implementation of cryoanalgesia at our institution, we had several cases of delayed postoperative pneumothorax. The purpose of this study was to critically evaluate the complications and efficacy of cryoanalgesia in MIRPE. Materials and Methods: We performed a single institution retrospective review of pediatric patients undergoing MIRPE from June 2017 to July 2018. Multimodal (MM) analgesia was used in all patients. In addition, most patients received either cryoanalgesia or elastomeric pain pumps (EPPs) as adjuncts to postoperative analgesia. Primary outcome was clinically significant late pneumothorax. Secondary outcomes included length of stay, pain scores, opiate use, and bar displacement requiring reoperation. Results: A total of 101 patients undergoing MIRPE were included: 45 had cryoanalgesia + MM, 45 EPP + MM, and 11 MM alone. Postoperative tube thoracostomy was placed in 5 patients with cryoanalgesia (4 pneumothorax; 1 effusion), 1 patient with EPP (1 pneumothorax), and none in MM alone (P = .25). Pain scores at discharge were similar in all groups. Cryoanalgesia patients received less overall inpatient opioids than other groups (P < .05). No patient required reoperation for bar displacement. Conclusion: Cryoanalgesia is an effective therapy for pain control in MIRPE. Because thermal injury can occur on the lung and chest wall with cryoanalgesia, we implemented techniques to limit and prevent this injury. Cryoanalgesia offers a safe alternative for postoperative analgesia with significant reduction in inpatient opioid requirement. Larger prospective studies are required to assess the long-term impact and complications of cryoanalgesia.
Cited By :11
Cited By :11
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/diagnóstico; Analgésicos Opioides/uso terapéutico; Procedimientos Quirúrgicos Mínimamente Invasivos; Complicaciones Posoperatorias/epidemiología; Complicaciones Posoperatorias/etiología; Complicaciones Posoperatorias/prevención & control; Crioterapia/efectos adversos; Crioterapia/métodos; Estudios de Seguimiento; Neumotórax/epidemiología; Neumotórax/etiología; Neumotórax/prevención & control; Procedimientos Ortopédicos; Terapia Combinada; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Orthopedic Procedures; Postoperative Complications; postoperative analgesia; minimally invasive repair of pectus excavatum; Follow-Up Studies; cryoanalgesia; Cryotherapy; Combined Modality Therapy; Pneumothorax

Interventions with Music in PECTus excavatum treatment (IMPECT trial): a study protocol for a randomised controlled trial investigating the clinical effects of perioperative music interventions - Billar, Ryan J.; Kühlmann, A. Y. Rosalie; Schnater, J. Marco; Vlot, John; Tomas, Jeremy J. P.; Zijp, Gerda W.; Rad, Mandana; de Beer, Sjoerd A.; Stevens, Markus F.; Poley, Marten J.; van Rosmalen, Joost; Jeekel, Johannes F.; et al. (BMJ open, 2020)
INTRODUCTION: Pectus excavatum repair is associated with substantial postoperative pain, despite the use of epidural analgesia and other analgesic regimens. Perioperative recorded music interventions have been shown to alleviate pain and anxiety in adults, but evidence for children and adolescents is still lacking. This study protocol describes a randomised controlled trial that evaluates the effects of recorded music interventions on postoperative pain relief in children and adolescents after pectus excavatum repair. METHODS: A multicentre randomised controlled trial was set up comparing the effects of perioperative recorded music interventions in addition to standard care with those of standard care only in patients undergoing a Nuss procedure for pectus excavatum repair. One hundred and seventy subjects (12-18 years of age) will be included in three centres in the Netherlands. Patient inclusion has started in November 2018, and is ongoing. The primary outcome is self-reported perceived pain measured on the visual analogue scale. Secondary outcomes are anxiety level, analgesics consumption, vital parameters such as heart rate, blood pressure and respiratory rate, length of hospital stay, postoperative complications, quality of life and cost-effectiveness. ETHICS AND DISSEMINATION: This study is being conducted in accordance with the Declaration of Helsinki. The Medical Ethics Review Board of Erasmus University Medical Centre Rotterdam, The Netherlands, has approved this protocol. Results will be disseminated via peer-reviewed scientific journals and conference presentations. TRIAL REGISTRATION NUMBER: NL6863.
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Humanos; Niño; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Analgésicos Opioides; Dolor Postoperatorio/prevención & control; Tórax en Embudo; Calidad de Vida; Ensayos Clínicos Controlados Aleatorios como Asunto; Estudios Multicéntricos como Asunto; Música; Musicoterapia; Países Bajos; Child; Funnel Chest; Pain, Postoperative; Analgesics, Opioid; pain management; Quality of Life; Randomized Controlled Trials as Topic; paediatric anaesthesia; paediatric thoracic surgery; Multicenter Studies as Topic; Music; Music Therapy; Netherlands

Cryoablation is associated with shorter length-of-stay and reduced opioid use after the Ravitch procedure - Rettig, R. Luke; Yang, Claire J.; Ashfaq, Adeel; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: The use of intercostal nerve cryoablation (INC) is becoming increasingly common in patients undergoing pectus repair. This study sought to evaluate the use of INC compared to traditional use of thoracic epidural (TE) in patients undergoing the modified Ravitch procedure. METHODS: A retrospective review of 37 patients undergoing the modified Ravitch repair with either INC or TE from March 2009 to July 2021 was conducted. The operations were performed by four surgeons who worked together at four different hospitals and have the same standardized practice. The primary outcome measure was hospital length of stay (LOS). Secondary variables included surgical time, total operating room time, operating room time cost, total hospital cost, inpatient opioid use, long term opioid use after discharge, and post-operative complications. RESULTS: LOS decreased to 2.8 days in the INC group compared to 6 days in the TE group (p<0.0001). Surgical time and total OR time was increased in the INC group. The INC group experienced significantly lower hospital costs (p<0.01). Total hospital opioid administration was significantly lower in INC group, and there was a significant decrease in long term opioid use in the INC group (p<0.0001). CONCLUSIONS: INC is a newer modality that decreases LOS, controls pain, and results in overall cost savings for patients undergoing the modified Ravitch procedure. We recommend that INC be included in the current practice for postoperative pain control in pectus disorder patients undergoing the modified Ravitch procedure.
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Tórax en Embudo; Analgésicos Opioides/uso terapéutico; Criocirugía; Criocirugía/métodos; Dolor Postoperatorio/cirugía; Tiempo de Internación; Nervios Intercostales/cirugía; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Thoracic epidural; Modified Ravitch procedure

A comparison of parecoxib and thoracic epidural analgesia for postoperative analgesia following Nuss procedure - Yang, Wendy; Ming, Yung-Ching; Kau, Yi-Chuan; Liao, Chia-Chih; Tsai, Shih-Chang; Wong, Kit-Man; Wong, Shu-Yam; Lai, Jin-Yao (Journal of Pediatric Surgery, 2015)
BACKGROUND: The purpose of this study was to compare the results of thoracic epidural analgesia (TEA) and parecoxib in controlling postoperative pain after the Nuss procedure. METHODS: Between August 2005 and July 2014, 120 adolescents and adults underwent Nuss procedures and received either TEA or parecoxib for postoperative pain control. Demographic data, preoperative preparation times, visual analog scale (VAS) pain scores from postoperative day 1 to day 5, medical costs of pain control, days to Foley catheter removal, days to being able to sit up, days to being able to walk, days of hospital stay, nausea/vomiting scores, and complications related to pain control were compared. RESULTS: A total of 106 patients received TEA, and 14 received parecoxib. No between-group differences in demographics were observed. Patients in the parecoxib group had shorter preparation times (p<0.001), lower VAS pain scores from postoperative day 2 to day 5 (day 2, p=0.006; day 3, p=0.006; day 4, p<0.001; day 5, p<0.001), shorter hospital stays (p<0.001), lower pain control costs (p<0.001), and lower nausea/vomiting scores (p=0.046). CONCLUSIONS: For adolescents and adults undergoing the Nuss procedure, parecoxib affords better pain control efficacy, a shorter hospital stay, lower medical pain control costs, and fewer side effects compared with TEA.
Cited By :3
Cited By :3
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Adulto; Adolescent; Adult; Female; Male; Young Adult; Dolor Postoperatorio/diagnóstico; Tiempo de Internación; Adulto Joven; Dimensión del Dolor; Esquema de Medicación; Procedimientos Ortopédicos; Inhibidores de la Ciclooxigenasa 2/uso terapéutico; Inyecciones Intravenosas; Isoxazoles/uso terapéutico; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Nuss procedure; Pectus excavatum; Length of Stay; Orthopedic Procedures; Pain Measurement; Analgesia, Epidural; Pain control; Injections, Intravenous; Thoracic epidural analgesia; Drug Administration Schedule; Cyclooxygenase 2 Inhibitors; Isoxazoles; Parecoxib

Are Foley catheters needed after minimally invasive repair of pectus excavatum? - Friske, Tyler C.; Sola, Richard; Yu, Yangyang R.; Jamal, Abdur R.; Rosenfeld, Eric; Zhu, Huirong; Mazziotti, Mark V.; St Peter, Shawn D.; Shah, Sohail R. (Surgery, 2018)
BACKGROUND: High narcotic requirements after minimally invasive repair of pectus excavatum (MIRPE) can increase the risk of urinary retention. Placement of intraoperative Foley catheters to minimize this risk is variable. This study determines the rate of urinary retention in this population to guide future practice. MATERIALS AND METHODS: We reviewed retrospectively all patients who underwent MIRPE from January 2012 to July 2016 at 2 academic children's hospitals. Data collected included demographics, BMI, severity of the pectus defect, postoperative pain management, and the incidence of urinary retention and urinary tract infection (UTI). RESULTS: Of 360 total patients who underwent MIRPE, 218 had an intraoperative Foley catheter. Patients with epidural pain control were more likely to receive a Foley catheter. The urinary retention rate was 34% for patients without an intraoperative Foley, and 1% in patients after removal of an intraoperatively placed Foley. Urinary retention was greater with an epidural compared with patient-controlled anesthesia (55% vs 26%, P = .002) in the no intraoperative Foley group. No urinary tract infections were identified. Epidural pain control was the only risk factor on multivariate analysis for retention in patients without an intraoperatively Foley catheter. CONCLUSION: Intraoperative Foley catheters obviate urinary retention without increasing the risk of urinary tract infection after MIRPE. These results will allow surgeons to better counsel patients regarding Foley placement.
Cited By :3
Cited By :3
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/prevención & control; Factores de Riesgo; Complicaciones Posoperatorias; Procedimientos Quirúrgicos Mínimamente Invasivos; Incidencia; Complicaciones Posoperatorias/epidemiología; Complicaciones Posoperatorias/prevención & control; Procedimientos Ortopédicos; Cateterismo Urinario; Cuidados Intraoperatorios/métodos; Infecciones Urinarias/epidemiología; Infecciones Urinarias/etiología; Infecciones Urinarias/prevención & control; Retención Urinaria/epidemiología; Retención Urinaria/etiología; Retención Urinaria/prevención & control; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Orthopedic Procedures; Postoperative Complications; Incidence; Risk Factors; Intraoperative Care; Urinary Catheterization; Urinary Retention; Urinary Tract Infections

Intercostal Nerve Cryoablation is Associated with Reduced Opioid Use in Pediatric Oncology Patients - Chen, Stephanie Y.; Mack, Shale J.; Stein, James E.; Kelley-Quon, Lorraine I.; Kim, Eugene S. (The Journal of Surgical Research, 2023)
INTRODUCTION: Intercostal nerve cryoablation reduces postoperative pain in adults undergoing thoracotomy and children undergoing pectus excavatum repair. We hypothesize that cryoablation is associated with decreased post-thoracotomy pain and opioid use in pediatric oncology patients. METHODS: A single-center retrospective cohort study was performed for oncology patients who underwent thoracotomy from January 1, 2017 to May 31, 2021. Outcomes included postoperative opioid use measured in morphine milligram equivalents per kilogram (MME/kg), pain scores (scale 0-10), and opioid prescription at discharge. Univariable analysis compared patients who received cryoablation to patients who did not receive cryoablation. Multivariable regression analysis controlling for age and prior thoracotomy evaluated associations between cryoablation and postoperative pain. RESULTS: Overall, 32 patients (19 males:13 females) underwent thoracotomy with 16 who underwent >1 thoracotomy resulting in 53 thoracotomies included for analysis. Cryoablation was used in 14 of 53 (26.4%) thoracotomies. Throughout the postoperative hospitalization, patients receiving cryoablation during thoracotomy consumed less opioids compared to patients who did not receive cryoablation (median 0.38 MME/kg, interquartile range [IQR] 0.20-1.15 versus median 1.47 MME/kg, IQR 0.71-4.02, P < 0.01). Maximum pain scores were lower in cryoablation patients (median 6, IQR 5-8) than noncryoablation patients (median 8, IQR 6-10), with a significant difference observed on postoperative day 4 (P = 0.01). Cryoablation patients were also less frequently prescribed opioids at discharge (21.4% versus 58.97%, P = 0.02). Multivariable regression demonstrated that cryoablation was associated with 2.59 MME/kg less opioid use (95% confidence interval -4.56 to -0.63) and decreased likelihood of opioid prescription at discharge (adjusted odds ratio 0.14, 95% confidence interval 0.03-0.67). CONCLUSIONS: Cryoablation is significantly associated with decreased post-thoracotomy pain and opioid use in pediatric cancer patients and should be considered in postoperative pain regimens.
Keywords: Humans; Adult; Female; Male; Child; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Morphine; Postoperative pain; Opioid; Cryoablation; Pediatric surgery; Thoracotomy; Opioid-Related Disorders; Pediatric oncology

Comparison of Ultrasonography-guided Bilateral Intercostal Nerve Blocks and Conventional Patient-controlled Intravenous Analgesia for Pain Control After the Nuss Procedure in Children: A Prospective Randomized Study - Luo, Mengqiang; Liu, Xiaoming; Ning, Li; Sun, Yuan; Cai, Ying; Shen, Sai'e (The Clinical Journal of Pain, 2017)
OBJECTIVES: Patients experience severe pain after pectus excavatum (PE) surgery. The aim of this prospective, randomized study was to compare analgesic effects of ultrasonography-guided bilateral intercostal nerve blocks (UG-ICNBs) with those of conventional patient-controlled intravenous analgesia (PCIA) on acute pain after the Nuss procedure for PE repair in children. METHODS: A prospective randomized study was performed in children with PE who were scheduled for the Nuss procedure. Participants were randomly assigned to receive either UG-ICNBs or PCIA for postoperative analgesia. Faces Pain Scale-Revised scores, opioid consumption, analgesia-associated side effects (respiratory depression, pruritus, nausea, vomiting) during the first 24 hours, and lengths of stay in the postanesthesia care unit (PACU) and hospital were recorded after the surgery. RESULTS: Sixty-two children undergoing the Nuss procedure were enrolled in the trial. Faces Pain Scale-Revised scores were significantly decreased in the UG-ICNBs group compared with the PCIA group for up to 6 hours after surgery. The opioid doses required in the PACU and during the first 24 hours after surgery were significantly greater in the PCIA group compared with the UG-ICNBs group. Accordingly, patients in the UG-ICNBs group showed a lower incidence of analgesia-associated side effects and faster PACU discharge compared with the PCIA group. CONCLUSIONS: Our study suggests that UG-ICNBs might be more effective than PCIA for postoperative analgesia in children who undergo the Nuss procedure for PE.
Cited By :19
Cited By :19
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Femenino; Humanos; Manejo del Dolor; Masculino; Nervios Intercostales; Niño; Bloqueo Nervioso/métodos; Resultado del Tratamiento; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Adolescent; Female; Male; Estudios Prospectivos; Preescolar; Dimensión del Dolor; Estudios de Seguimiento; Dolor Postoperatorio/diagnóstico por imagen; Analgesia/métodos; Administración Intravenosa; Método Doble Ciego; Ultrasonografía; Analgesia; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Intercostal Nerves; Analgesia, Patient-Controlled; Pain Management; Prospective Studies; Pain Measurement; Nerve Block; Follow-Up Studies; Child, Preschool; Administration, Intravenous; Double-Blind Method; Ultrasonography

A Novel Perioperative Multidose Methadone-Based Multimodal Analgesic Strategy in Children Achieved Safe and Low Analgesic Blood Methadone Levels Enabling Opioid-Sparing Sustained Analgesia With Minimal Adverse Effects - Sadhasivam, Senthilkumar; Aruldhas, Blessed W.; Packiasabapathy, Senthil; Overholser, Brian R.; Zhang, Pengyue; Zang, Yong; Renschler, Janelle S.; Fitzgerald, Ryan E.; Quinney, Sara K. (Anesthesia and Analgesia, 2021)
BACKGROUND: Intraoperative methadone, a long-acting opioid, is increasingly used for postoperative analgesia, although the optimal methadone dosing strategy in children is still unknown. The use of a single large dose of intraoperative methadone is controversial due to inconsistent reductions in total opioid use in children and adverse effects. We recently demonstrated that small, repeated doses of methadone intraoperatively and postoperatively provided sustained analgesia and reduced opioid use without respiratory depression. The aim of this study was to characterize pharmacokinetics, efficacy, and safety of a multiple small-dose methadone strategy. METHODS: Adolescents undergoing posterior spinal fusion (PSF) for idiopathic scoliosis or pectus excavatum (PE) repair received methadone intraoperatively (0.1 mg/kg, maximum 5 mg) and postoperatively every 12 hours for 3-5 doses in a multimodal analgesic protocol. Blood samples were collected up to 72 hours postoperatively and analyzed for R-methadone and S-methadone, 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidene (EDDP) metabolites, and alpha-1 acid glycoprotein (AAG), the primary methadone-binding protein. Peak and trough concentrations of enantiomers, total methadone, and AAG levels were correlated with clinical outcomes including pain scores, postoperative nausea and vomiting (PONV), respiratory depression, and QT interval prolongation. RESULTS: The study population included 38 children (10.8-17.9 years): 25 PSF and 13 PE patients. Median total methadone peak plasma concentration was 24.7 (interquartile range [IQR], 19.2-40.8) ng/mL and the median trough was 4.09 (IQR, 2.74-6.4) ng/mL. AAG concentration almost doubled at 48 hours after surgery (median = 193.9, IQR = 86.3-279.5 µg/mL) from intraoperative levels (median = 87.4, IQR = 70.6-115.8 µg/mL; P < .001), and change of AAG from intraoperative period to 48 hours postoperatively correlated with R-EDDP (P < .001) levels, S-EDDP (P < .001) levels, and pain scores (P = .008). Median opioid usage was minimal, 0.66 (IQR, 0.59-0.75) mg/kg morphine equivalents/d. No respiratory depression (95% Wilson binomial confidence, 0-0.09) or clinically significant QT prolongation (median = 9, IQR = -10 to 28 milliseconds) occurred. PONV occurred in 12 patients and was correlated with morphine equivalent dose (P = .005). CONCLUSIONS: Novel multiple small perioperative methadone doses resulted in safe and lower blood methadone levels, <100 ng/mL, a threshold previously associated with respiratory depression. This methadone dosing in a multimodal regimen resulted in lower blood methadone analgesia concentrations than the historically described minimum analgesic concentrations of methadone from an era before multimodal postoperative analgesia without postoperative respiratory depression and prolonged corrected QT (QTc). Larger studies are needed to further study the safety and efficacy of this methadone dosing strategy.
Cited By :5
Cited By :5
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Estudios Prospectivos; Factores de Riesgo; Analgésicos Opioides/administración & dosificación; Analgésicos Opioides/efectos adversos; Analgésicos Opioides/farmacocinética; Analgésicos Opioides/sangre; Atención Perioperativa; Dimensión del Dolor; Dimensión del Dolor/efectos adversos; Escoliosis/cirugía; Esquema de Medicación; Factores de Edad; Fusión Vertebral/efectos adversos; Indiana; Medición de Riesgo; Metadona/administración & dosificación; Metadona/efectos adversos; Metadona/farmacocinética; Metadona/sangre; Monitoreo de Drogas; Náusea y Vómito Posoperatorios/inducido químicamente; Valor Predictivo de las Pruebas; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Analgesics, Opioid; Prospective Studies; Pain Measurement; Postoperative Nausea and Vomiting; Risk Factors; Drug Administration Schedule; Perioperative Care; Age Factors; Drug Monitoring; Methadone; Predictive Value of Tests; Risk Assessment; Scoliosis; Spinal Fusion

Paravertebral regional blocks decrease length of stay following surgery for pectus excavatum in children - Loftus, Patrick D.; Elder, Craig T.; Russell, Katie W.; Spanos, Stephen P.; Barnhart, Douglas C.; Scaife, Eric R.; Skarda, David E.; Rollins, Michael D.; Meyers, Rebecka L. (Journal of Pediatric Surgery, 2016)
PURPOSE: Management of postoperative pain following repair of pectus excavatum has traditionally included thoracic epidural analgesia, narcotics, and benzodiazepines. We hypothesized that the use of intercostal or paravertebral regional blocks could result in decreased inpatient length of stay (LOS). METHODS: We conducted a retrospective cohort study of 137 patients (118 Nuss and 19 Ravitch - Nuss and Ravitch patients were analyzed separately) who underwent surgical repair of pectus excavatum with pain management via epidural, intercostal, or paravertebral analgesia from January 2009-December 2012. Measured outcomes included LOS, pain scores, benzodiazepine/narcotic requirements, emesis, professional fees, hospital cost, and total cost. RESULTS: In the Nuss patients, LOS was significantly reduced in the paravertebral group (p<0.005) and the intercostal group (p<0.005) compared to the epidural group, but was paradoxically countered by a nonsignificant increase in total cost (p=0.09). While benzodiazepine doses/day was not increased in the paravertebral group (p=0.08), an increase was seen in narcotic use (p<0.005). Despite increased narcotic use, no differences were seen in emesis between epidural and paravertebral use. Compared to epidural, pain scores were higher for both intercostal and paravertebral on day one (p<0.005), but equivalent for paravertebral on day three (p=0.62). The Ravitch group was too small for detailed independent statistical analysis but followed the same overall trend seen in the Nuss patients. CONCLUSION: Our use of paravertebral continuous infusion pain catheters for pectus excavatum repair was an effective alternative to epidural analgesia resulting in shorter LOS but not a decrease in overall cost.
Cited By :34
Cited By :34
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Niño; Bloqueo Nervioso/métodos; Tórax en Embudo/cirugía; Analgesia Epidural; Dolor Postoperatorio/prevención & control; Tiempo de Internación; Analgésicos Opioides/administración & dosificación; Analgésicos/administración & dosificación; Catéteres; Analgesia Epidural/economía; Benzodiazepinas/administración & dosificación; Bloqueo Nervioso/economía; Infusiones Intravenosas; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Pectus excavatum; Analgesics, Opioid; Length of Stay; Pain management; Analgesia, Epidural; Length of stay; Nerve Block; Epidural; Catheters; Benzodiazepines; Infusions, Intravenous; Intercostal; Paravertebral

Continuous chest wall ropivacaine infusion for analgesia in children undergoing Nuss procedure: a comparison with thoracic epidural - Choudhry, Dinesh K.; Brenn, B. Randall; Sacks, Karen; Reichard, Kirk (Paediatric Anaesthesia, 2016)
BACKGROUND: Pain following Nuss procedure is severe and its management is challenging. Many different pain treatment modalities are currently being used, but none of them have been found to be ideal. AIM: In this retrospective review, we compare our current multimodal approach, which involves continuous ropivacaine infusion through chest wall catheters (CWC), intravenous patient-controlled analgesia (IV-PCA), and adjunctive medications (gabapentin and clonidine), with the technique that we used in the past, the thoracic epidural catheter (TEC). METHODS: Following IRB approval, we performed a retrospective analysis of data on 32 patients who underwent the Nuss procedure at our institution. All children were divided into two groups: TEC group: 0.2% ropivacaine and hydromorphone 10 mcg·ml(-1) epidural infusion (n = 15) and CWC group (with IV-PCA and adjuncts [gabapentin + clonidine]): 0.2% ropivacaine infusion and hydromorphone PCA, oral gabapentin, and transdermal clonidine patch (n = 17). RESULTS: Both the groups were demographically similar. Average numeric pain scores were higher in the CWC group only on the day of surgery (mean ± sd: 3.79 ± 1.58 vs 2.68 ± 1.30; 95% CI: -2.16 to -0.05). Pain scores on postoperative day 1 (mean ± sd: 3.40 ± 1.59 vs 3.35 ± 1.32; 95% CI: -1.11 to 1.01), day 2 (mean± sd: 3.39 ± 1.79 vs 2.99 ± 1.06; 95% CI: -1.50 to 0.70), and on the day of discharge (DOD) (mean± sd: 3.25 ± 1.84 vs 3.99 ± 1.28; 95% CI: -0.42 to 1.89) were comparable between the groups. The CWC group needed fewer changes in the therapeutic regimen to maintain acceptable pain relief, had lower incidence of nausea and vomiting, had shorter anesthesia time, total OR time, and hospital length of stay. CONCLUSION: TEC provided better analgesia following the Nuss procedure only on the day of surgery. On the subsequent days until discharge, pain scores were comparable. However, CWC offered other advantages: it was less labor intensive and had fewer side effects, shorter OR time, and shorter hospital stay.
Cited By :25
Cited By :25
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Adolescent; Female; Male; Analgésicos Opioides/administración & dosificación; Analgésicos/administración & dosificación; Anestesia Epidural; Terapia Combinada; Anestésicos Locales/administración & dosificación; Ácido gamma-Aminobutírico/administración & dosificación; Ácidos Ciclohexanocarboxílicos/administración & dosificación; Amidas/administración & dosificación; Aminas/administración & dosificación; Clonidina/administración & dosificación; Gabapentina; Infusiones Parenterales; Morfina/administración & dosificación; Pared Torácica/efectos de los fármacos; Ropivacaína; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Analgesics, Opioid; Analgesia, Patient-Controlled; Thoracic Wall; Morphine; Anesthetics, Local; pediatric; pain management; Anesthesia, Epidural; Gabapentin; Combined Modality Therapy; Amides; Amines; Clonidine; Cyclohexanecarboxylic Acids; gamma-Aminobutyric Acid; Infusions, Parenteral; multimodal approach; pectus repair; Ropivacaine

Extended pain relief achieved by analgesic-eluting biodegradable nanofibers in the Nuss procedure: in vitro and in vivo studies - Liu, Kuo-Sheng; Chen, Wei-Hsun; Lee, Cheng-Hung; Su, Yong-Fong; Liu, Shih-Jung (International Journal of Nanomedicine, 2018)
BACKGROUND: The most common complaint after the Nuss procedure is severe postoperative chest pain. The aim of this study was to evaluate the effectiveness of analgesic-eluting biodegradable nanofibers in pain relief after the Nuss procedure. MATERIALS AND METHODS: Poly(d,l)-lactide-co-glycolide, lidocaine, and ketorolac were dissolved in 1,1,1,3,3,3-hexafluoro-2-propanol. This solution was electrospun into a nanofibrous membrane. The elution method and high-performance chromatography were used to characterize the in vitro drug release. Stainless steel bars with and without coating of the analgesic-eluting nanofibrous membrane were implanted underneath the sternums of New Zealand white rabbits. The in vivo characteristics were further investigated. RESULTS: The in vitro study showed that the biodegradable nanofibers released high doses of lidocaine and ketorolac within 10 days. The in vivo study demonstrated high local and systemic concentrations of lidocaine and ketorolac. The serum creatinine level was unaffected. Animals that received implants of the analgesic-eluting nanofiber-coated stainless steel bar exhibited significantly greater food and water ingestion and physical activity than the control group did, indicating effective pain relief. CONCLUSION: The proposed analgesic-eluting biodegradable nanofibers contribute to the achievement of extended pain relief after the Nuss procedure, without obvious adverse effects, in an animal model.
Cited By :5
Cited By :5
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Animals; Humans; Humanos; Dolor Postoperatorio/tratamiento farmacológico; Thoracic Surgical Procedures; Dolor Postoperatorio/etiología; Procedimientos Quirúrgicos Torácicos/efectos adversos; Analgésicos/uso terapéutico; Acero Inoxidable/química; Animales; Conducta Animal; Conejos; Copolímero de Ácido Poliláctico-Ácido Poliglicólico/química; Espectroscopía Infrarroja por Transformada de Fourier; Ketorolaco/uso terapéutico; Liberación de Fármacos; Lidocaína/uso terapéutico; Materiales Biocompatibles/química; Membranas Artificiales; Nanofibras/química; Nanofibras/ultraestructura; Pain, Postoperative; Analgesics; Nuss procedure; pectus excavatum; analgesic-eluting; Behavior, Animal; Biocompatible Materials; biodegradable; Drug Liberation; Ketorolac; Lidocaine; Membranes, Artificial; nanofibers; Nanofibers; Polylactic Acid-Polyglycolic Acid Copolymer; Rabbits; Spectroscopy, Fourier Transform Infrared; Stainless Steel

[Psychological prophylaxis training for coping with postoperative pain. Long-term effects] - Scheel, J.; Parthum, A.; Dimova, V.; Horn-Hofmann, C.; Meinfelder, F.; Carbon, R.; Grießinger, N.; Sittl, R.; Lautenbacher, S. (Schmerz (Berlin, Germany), 2014)
INTRODUCTION: The present study was performed to investigate the effect of multidimensional psychological prophylaxis training focusing on coping with cognitive-emotional pain on recovery within the first 12 months after surgery. The training included the following three components: (1) education about pain, analgesia and psychological aspects of coping with pain, (2) training for coping with pain and (3) body-centered relaxation. MATERIAL AND METHODS: In the study 48 young male patients (surgical correction of a chest malformation) were assessed 1 day before surgery, at discharge and 3, 6 and 12 months postoperatively concerning postoperative pain intensity and pain disability as well as pain anxiety, pain catastrophizing and pain hypervigilance. Additionally, 24 of these patients received training on cognitive-emotional coping with pain 1 day before surgery and 1-3 days after surgery (each session 1 h). RESULTS: The proportion of patients with clinically relevant improvement was significantly higher in the training group compared to the control group. This was the case for acute pain intensity (approximately 1 week after surgery), pain disability 3 months later and pain anxiety 12 months after surgery. CONCLUSION: The resurgence of pain anxiety after 12 months could only be found in the control group and could be due to the upcoming surgical removal of the transsternal metal implant. The prophylaxis training can therefore be seen as a protective factor for long-term management of surgery-related consequences and future pain experiences.
Keywords: Humans; Adolescente; Humanos; Masculino; Manejo del Dolor/métodos; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Male; Young Adult; Dolor Postoperatorio/prevención & control; Adulto Joven; Estudios de Seguimiento; Dolor Postoperatorio/psicología; Tórax en Embudo/psicología; Ansiedad/psicología; Catastrofización/psicología; Adaptación Psicológica; Ansiedad/prevención & control; Catastrofización/prevención & control; Dimensión del Dolor/psicología; Educación del Paciente como Asunto/métodos; Nivel de Alerta; Terapia Cognitivo-Conductual/métodos; Terapia Combinada/métodos; Terapia Combinada/psicología; Terapia por Relajación; Funnel Chest; Pain, Postoperative; Pain Management; Pain Measurement; Patient Education as Topic; Follow-Up Studies; Anxiety; Catastrophization; Combined Modality Therapy; Adaptation, Psychological; Arousal; Cognitive Behavioral Therapy; Relaxation Therapy

Standardization of clinical care pathway leads to sustained decreased length of stay following Nuss pectus repair: A multidisciplinary quality improvement initiative - Gurria, Juan P.; Simpson, Blair; Tuncel-Kara, Setenay; Bates, Christina; McKenna, Emily; Rogers, Tracy; Kraemer, Aimee; Platt, Michael; Mecoli, Marc; Garcia, Victor F.; Brown, Rebeccah L. (Journal of Pediatric Surgery, 2020)
BACKGROUND AND PURPOSE: Postoperatively, standardized clinical care pathways (SCCPs) help patients reach necessary milestones for discharge. The objective of this study was to achieve 90% compliance with a pectus specific SCCP within 9 months of implementation. We hypothesized that adherence to a pectus SCCP following the Nuss procedure would decrease postsurgical length of stay (LOS). METHODS: A multidisciplinary team implemented the pectus SCCP, including goals for mobility, lung recruitment, pain control, intake, and output. The full protocol included 42 components, tracked using chart reviews and a patient-directed checklist. The primary process measure was compliance with the pectus SCCP. The primary outcome measure was LOS; secondary outcomes were patient charges, patient satisfaction, and hospital readmission. RESULTS: Total study patients were n = 509: 159 patients pre-intervention, 350 patients post-intervention (80 implementation group; 270 sustain group). SCCP compliance data were collected on 164 patients post-intervention - 80 implementation, 84 sustain. LOS, ED visits, and hospital readmissions were recorded for all 509 patients. Mean LOS decreased from 4.5 days to 3.4 days, with >90% adherence to the pectus SCCP postintervention. There were no readmissions owing to pain despite earlier termination of epidural analgesia. Total patient charges decreased by 30% and patient satisfaction was high. CONCLUSION: Using quality improvement methodology with strict adherence to a pectus SCCP, we had significant reduction in LOS and patient charge without compromising effective postoperative pain management or patient satisfaction. TYPE OF STUDY: Clinical research; quality improvement. LEVEL OF EVIDENCE: V.
Cited By :6
Cited By :6
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Estudios Retrospectivos; Humanos; Tórax en Embudo/cirugía; Tórax en Embudo; Tiempo de Internación; Dolor Postoperatorio; Mejoramiento de la Calidad; Protocolos Clínicos/normas; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Length of Stay; Quality improvement; Length of stay; Clinical Protocols; Patient charge; Postoperative care; Quality Improvement; Standardized clinical care pathway

Complex regional pain syndrome following the Nuss procedure for severe pectus excavatum - Chen, Yi-Ling; Chen, Liang-Cheng; Chen, Jen-Chih; Cheng, Yeung-Leung (Annals of Thoracic and Cardiovascular Surgery: Official Journal of the Association of Thoracic and Cardiovascular Surgeons of Asia, 2014)
Complex regional pain syndrome (CRPS) is not an uncommon complication after surgery, but has never been reported after the Nuss procedure for repairing pectus excavatum. A 22-year-old man with pectus excavatum had type I CRPS that developed 2 weeks after the Nuss procedure. He complained of persistent pain, hyperalgesia, weakness, edema, and color and temperature changes on right upper extremity. Following intensive rehabilitation, the degree of pain, weakness and edema were ameliorated. He recovered 6 months after surgery and the pectus bars were removed uneventfully 3 years after the repair.
Cited By :3
Cited By :3
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Humanos; Masculino; Resultado del Tratamiento; Tórax en Embudo/cirugía; Tórax en Embudo/diagnóstico; Male; Young Adult; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/etiología; Adulto Joven; Dimensión del Dolor; Procedimientos Ortopédicos/efectos adversos; Índice de Severidad de la Enfermedad; Factores de Tiempo; Tomografía Computarizada por Rayos X; Distrofia Simpática Refleja/diagnóstico; Distrofia Simpática Refleja/etiología; Distrofia Simpática Refleja/rehabilitación; Dolor Postoperatorio/rehabilitación; Inducción de Remisión; Procedimientos Ortopédicos/rehabilitación; Funnel Chest; Pain, Postoperative; Treatment Outcome; Orthopedic Procedures; Pain Measurement; Time Factors; Tomography, X-Ray Computed; Reflex Sympathetic Dystrophy; Remission Induction; Severity of Illness Index

Paravertebral block for analgesia after pediatric thoracic surgery - Berde, Charles B.; Boretsky, Karen R.; Cravero, Joseph P. (Regional Anesthesia and Pain Medicine, 2014)
Cited By :3
Cited By :3
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Dolor Postoperatorio/terapia; Femenino; Humanos; Masculino; Bloqueo Nervioso/métodos; Tórax en Embudo/cirugía; Female; Male; Ultrasonografía Intervencional/métodos; Funnel Chest; Pain, Postoperative; Nerve Block; Ultrasonography, Interventional

Implementation Science Fundamentals: Pediatric Surgery Enhanced Recovery After Surgery Protocol for Pectus Repair - Thompson, Allison R.; Glick, Hannah; Rubalcava, Nathan S.; Vernamonti, Jack P.; Speck, K. Elizabeth (The Journal of Surgical Research, 2023)
INTRODUCTION: Surgical repair of pectus excavatum and carinatum in children has historically been associated with severe postoperative pain and prolonged hospitalization. Enhanced Recovery After Surgery (ERAS) is a multidisciplinary, multimodal approach designed to fast-track surgical care. However, obstacles to implementation have led to very few within pediatric surgery. The aim of this study is to outline the process of development and implementation of an ERAS protocol for pectus surgical repair using fundamental principles of implementation science. METHODS: A multidisciplinary team of providers worked collaboratively to develop an ERAS protocol for surgical repair of pectus excavatum and carinatum and methods for identifying eligible patients. The surgical champion collaborated with all end users to review and revise the ERAS protocol, assessing all foreseeable barriers and facilitators prior to implementation. RESULTS: Our entire pediatric surgery team, nurses at every stage (clinic/preoperative/recovery/floor), physical therapy, and information technology contributed to the creation and implementation of an ERAS protocol with seven phases of care. The finalized version was implemented by end users focusing on four main areas: pain control, ambulation, diet, and education. Barriers and facilitators were continually addressed with an iterative process to improve the success of implementation. CONCLUSIONS: This is one of the first studies in children which details the step-by-step process of developing and implementing an ERAS protocol for pectus excavatum and carinatum. The process of development and implementation of an ERAS protocol as outlined in this manuscript can serve as a model for future ERAS protocols in pediatric surgery.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Length of Stay; Pectus; Pediatric surgery; Children; Enhanced recovery after surgery; Enhanced Recovery After Surgery; Implementation science; Implementation Science; Practice-Based Learning and Improvement; Specialties, Surgical

Freeze the pain away: The role of cryoanalgesia during a Nuss procedure - Sancheti, Manu (The Journal of Thoracic and Cardiovascular Surgery, 2016)
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Humanos; Masculino; Tórax en Embudo/cirugía; Male; Dolor Postoperatorio/prevención & control; Nervios Intercostales/cirugía; Procedimientos Ortopédicos/efectos adversos; Crioterapia/métodos; Analgesia/métodos; Toracoscopía; Analgesia; Funnel Chest; Pain, Postoperative; Intercostal Nerves; Orthopedic Procedures; Thoracoscopy; Cryotherapy

Subcutaneous local anesthetic infusion could eliminate use of epidural analgesia after the Nuss procedure - Kabagambe, Sandra K.; Goodman, Laura F.; Chen, Y. Julia; Keller, Benjamin A.; Becker, James C.; Raff, Gary W.; Stark, Rebecca A.; Stephenson, Jacob T.; Rahm, Amy; Farmer, Diana L.; Hirose, Shinjiro (Pain Management, 2018)
AIM: To compare outcomes of continuous subcutaneous infusion of local anesthetic and epidural analgesia following the Nuss procedure. PATIENTS & METHODS: A retrospective chart review compared patients managed with subcutaneous local anesthetic infusion (n = 12) versus thoracic epidural (n = 19) following the Nuss procedure from March 2013 to June 2015. RESULTS: There was no difference in hospital length of stay or days on intravenous narcotics. Epidural catheter placement prolonged operating room time (146.58 ± 28.30 vs 121.42 ± 21.98 min, p = 0.01). Average pain scores were slightly higher in the subcutaneous infusion group (3.72 ± 1.62 vs 2.35 ± 0.95, p = 0.02), but of negligible clinical significance. CONCLUSION: Continuous subcutaneous infusion of local anesthetic could eliminate the need for thoracic epidural for pain management after the Nuss procedure.
Cited By :4
Cited By :4
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Niño; Manejo del Dolor/métodos; Resultado del Tratamiento; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Adolescent; Female; Male; Dolor Postoperatorio/prevención & control; Anestésicos Locales/administración & dosificación; Anestesia Local/métodos; Cuidados Posoperatorios/métodos; Evaluación de Resultado en la Atención de Salud; Infusiones Subcutáneas; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Nuss procedure; Pain Management; Analgesia, Epidural; epidural; pectus excavatum; Anesthesia, Local; Anesthetics, Local; regional anesthesia; Infusions, Subcutaneous; pain management; Postoperative Care; Outcome Assessment, Health Care; subcutaneous infusion

Effectiveness of one minute per level intercostal nerve cryoablation for postoperative analgesia after surgical correction of pectus excavatum - Zeineddin, Suhail; Goldstein, Seth D.; Linton, Samuel; DeBoer, Christopher; Alayleh, Amin; Ortiz, Irma; Sands, Laurie; Kujawa, Suzanne; Suresh, Santhanam; Ghomrawi, Hassan; Abdullah, Fizan (Journal of Pediatric Surgery, 2023)
PURPOSE: Intraoperative intercostal nerve cryoablation has emerged as a promising modality for postoperative analgesia following Surgical Correction of Pectus Excavatum (SCOPE). Most centers use two-minute cryoablation per level, although data from histologic and adult studies suggest the effectiveness of one-minute freezes. We aimed to describe our center's experience with one minute per level cryoablation. METHODS: A retrospective single institution review of patients undergoing SCOPE was performed to compare patients pre- and post-intercostal nerve cryoablation implementation. Cryoablation was performed as one minute for each of the thoracic intercostal nerves T3-T7. Multivariable regression analyses were conducted to compare the outcomes and cost between pre- and post-implementation groups. RESULTS: During the study period, 198 patients underwent SCOPE with one Nuss bar, receiving either intraoperative intercostal nerve cryoablation (Cryo, n = 100) or preoperative thoracic paravertebral catheters (NoCryo, n = 98). Surgical time was on average 9 min longer for the Cryo group (p<0.01). Median length of stay for the Cryo group was 3 days shorter compared to the NoCryo group (p<0.01). The Cryo group had a 19-fold and 5.6-fold reduction in average inpatient and total postoperative opioid usage, respectively (p<0.01). Total hospital costs were significantly lower in the Cryo group (p<0.01). Overall complication rate was not statistically significant different between the two groups. CONCLUSIONS: Intraoperative one minute per level cryoablation is a potent approach to postoperative analgesia for SCOPE patients that led to a shorter hospital length of stay, lower hospital costs, and decreased opioid use compared to conventional analgesia at our institution. Pediatric surgeons performing correction of chest wall deformities should consider offering this technique.
Keywords: Humans; Adult; Analgesia; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Cryoanalgesia; Thoracic Wall; Intercostal cryoablation; Nuss bar; Thoracoscopy; SCOPE

Multimodal anesthesia with the addition of methadone is superior to epidural analgesia: A retrospective comparison of intraoperative anesthetic techniques and pain management for 124 pediatric patients undergoing the Nuss procedure - Singhal, Neil R.; Jones, John; Semenova, Janet; Williamson, Amber; McCollum, Katelyn; Tong, Dennis; Jerman, Jonathan; Notrica, David M.; Nguyen, Hayden (Journal of Pediatric Surgery, 2016)
BACKGROUND: The Nuss procedure corrects pectus excavatum by forceful displacement of the sternum with metal bars. Optimal pain management remains a challenge. Mutimodal anesthesia alleviates pain through blockade of multiple nociceptive and inflammatory pain receptors. METHODS: A retrospective chart review of anesthetic and postoperative mangement of 125 children undergoing the Nuss procedure was conducted. Anesthetic mangement strategies were analyzed in four groups: opioid during general anesthesia (GA), epidural with general anesthesia (Epidural), multimodal anesthesia (MM), and multimodal anesthesia with methadone (MM+M). Data collection included total opioid use (as equivalent milligrams of morphine (Mmg)), pain scores, length of stay (LOS), and adverse effects. RESULTS: Total opioid use varied by group (median, IQR (in Mg)): Epidural 213 [149, 293], GA 179 [134, 298], MM (150 [123, 281]), and MM+M (106 [87, 149]), as did severe pain (in minutes): Epidural (208 [73, 323]), GA (115 [7, 255]), MM (54 [0, 210]), and MM+M (49 [0, 151]). LOS was shortest for the MM+M group (MM+M=3.8+1.0days; MM=4.5+1.3days; GA=4.9+1.4days, Epidural=5.5+2.3days). CONCLUSION: Multimodal anesthesia is associated with less postoperative pain and shorter LOS compared to epidural or traditional anesthetic techniques for the Nuss procedure. Multimodal anesthesia with a single intraoperative dose of methadone was associated with lowest total opioid use, time with uncontrolled pain, and shortest LOS.
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Dolor Postoperatorio/tratamiento farmacológico; Manejo del Dolor/métodos; Tórax en Embudo/cirugía; Adolescent; Female; Male; Tiempo de Internación; Analgésicos Opioides/administración & dosificación; Dimensión del Dolor; Anestesia General; Anestesia Epidural/métodos; Anestésicos/administración & dosificación; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Length of Stay; Pain Management; Pain Measurement; Pain management; Anesthesia, Epidural; Anesthetics; Anesthesia, General; Methadone; Multimodal anesthesia

Introduction of a novel ultrasound-guided extrathoracic sub-paraspinal block for control of perioperative pain in Nuss procedure patients - Bryskin, Robert B.; Robie, Daniel K.; Mansfield, Frederick M.; Freid, Eugene B.; Sukumvanich, Siam (Journal of Pediatric Surgery, 2017)
BACKGROUND: A safe and effective method of multilevel thoracic pain control remains an elusive goal in patients undergoing the Nuss procedure. The aim of our study was to develop a nonopioid centered approach using a novel regional technique as part of a quality improvement initiative. METHODS: The proposed ultrasound-guided technique positions multi-perforated soaker catheter deep to the paraspinal muscles from T2 to T11. The project was conducted in two phases. First, a cadaveric dissection was performed to establish the pathway of spread of local anesthetic in vivo. Second, a pilot double blind randomized control project was conducted to evaluate effectiveness of the technique in ten patients and to derive parameters necessary for the definitive future study. Outcomes were evaluated based on the narcotic requirement, pain scores and functional measures. RESULTS: Placement of the catheters in two cadavers demonstrated reliable positioning in the subparaspinal tissue plane, and multilevel dye spread along the intercostal nerve path. In addition, a potential route of spread toward the paravertebral space along the canal accommodating dorsal ramus of the thoracic nerve was demonstrated. The pilot trial demonstrated a trend in decreased cumulative hydromorphone requirement in comparison to the control group at both 24h (0.19±0.09mg/kg vs. 0.13±0.08mg/kg p=0.72) and 48h (0.37±0.2mg/kg vs. 0.3±0.12mg/kg p=0.37). Functional performance ability was higher in the treatment group on both POD#1 (6.7±1.8 vs. 4.8±1 p=0.0495) and POD#2 (8.9±0.8 vs. 6.5±1.2 p=0.04). Pain scores were similar among the two groups (p=0.96). CONCLUSIONS: We describe a new technique to treat multilevel thoracic pain following the Nuss procedure that is reproducible, safe, allows diminished opioid use and enhances functional recovery.
Cited By :14
Cited By :14
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Nervios Intercostales; Bloqueo Nervioso/métodos; Manejo del Dolor/métodos; Tórax en Embudo/cirugía; Adolescent; Female; Male; Thorax; Dolor Postoperatorio/prevención & control; Ultrasonografía Intervencional/métodos; Dimensión del Dolor/métodos; Analgésicos Opioides/administración & dosificación; Método Doble Ciego; Cadáver; Catéteres; Hidromorfona/administración & dosificación; Músculos Intercostales/anatomía & histología; Músculos Intercostales/diagnóstico por imagen; Proyectos Piloto; Tórax/anatomía & histología; Funnel Chest; Pain, Postoperative; Pectus excavatum; Analgesics, Opioid; Intercostal Nerves; Pain Management; Pain Measurement; Nerve Block; Ultrasonography, Interventional; Pain; Anesthesia; Postoperative pain; Catheters; Hydromorphone; Pilot Projects; Double-Blind Method; Cadaver; Chest pain; Intercostal Muscles; Nerve block; Recovery period

A prospective randomized observer-blinded study to assess postoperative analgesia provided by an ultrasound-guided bilateral thoracic paravertebral block for children undergoing the Nuss procedure - Qi, Jiashan; Du, Bin; Gurnaney, Harshad; Lu, Peilin; Zuo, Yunxia (Regional Anesthesia and Pain Medicine, 2014)
BACKGROUND AND OBJECTIVES: This prospective, randomized, single-blinded study evaluates the effectiveness of the ultrasound-guided bilateral thoracic paravertebral (BTPV) block for providing postoperative pain control in children undergoing the Nuss procedure. METHODS: Thirty American Society of Anesthesiologists I-II children with pectus excavatum, scheduled for the Nuss procedure, were enrolled at West China Hospital of Sichuan University. The patients were randomly allocated into the BTPV block group or the control group. In the BTPV group, 0.25% ropivacaine 0.5 mL/kg with 1:200,000 epinephrine was injected under ultrasound guidance on each side at the level of the fifth thoracic vertebra. Postoperative pain was evaluated in both groups for the first 48 hours. Total opioid administered and cumulative attempts on the patient/parent-controlled intravenous analgesia (PCA) pump were recorded. Postoperative negative behavioral changes in the children were evaluated on postoperative days 1, 7, and 30, respectively, using the posthospital behavior questionnaire. RESULTS: The pain scores were significantly reduced in the postanesthesia care unit and for the first 48 hours postoperatively in the BTPV group compared to the control group (P < 0.01). The sufentanil use in the postanesthesia care unit was significantly greater in the control group [mean (SD), 0.2 (0) mcg/kg] compared to the BTPV group [mean (SD), 0.05 (0.06) mcg/kg] (P < 0.01). The postoperative sufentanil use was significantly higher in the control group during the first 24 hours (P < 0.01). Numbers of attempts on the PCA pump were significantly greater in the control group (P < 0.01). The posthospital behavior questionnaire score was lower in the BTPV group on day 1, day 7, and 1 month, respectively (P < 0.01). CONCLUSIONS: Ultrasound-guided BTPV block provides improved postoperative analgesia for children undergoing the Nuss procedure as compared with intravenous PCA and decreases the incidence of postoperative behavioral disturbance.
Cited By :36
Cited By :36
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Femenino; Humanos; Masculino; Niño; Bloqueo Nervioso/métodos; Tórax en Embudo/cirugía; Adolescent; Female; Male; Estudios Prospectivos; Ultrasonografía Intervencional/métodos; Preescolar; Frecuencia Cardíaca; Método Simple Ciego; Presión Sanguínea; Child; Funnel Chest; Pain, Postoperative; Prospective Studies; Nerve Block; Ultrasonography, Interventional; Child, Preschool; Blood Pressure; Heart Rate; Single-Blind Method

Single shot intercostal block for pain management in pediatric patients undergoing the Nuss procedure: a double-blind, randomized, controlled study - Lukosiene, Laura; Macas, Andrius; Trepenaitis, Darius; Kalibatiene, Lina; Malcius, Dalius; Barauskas, Vidmantas (Journal of Pediatric Surgery, 2014)
PURPOSE: The aim of this study was to investigate the efficacy of a single shot intercostal block for pain control in pediatric patients undergoing the Nuss procedure. METHODS: A double-blind, randomized, controlled study was performed. Thirty patients received a single shot bilateral intercostal block with levobupivacaine (L group) and 30 patients with 0.9 % saline (S group). Standardized baseline analgesia was applied for all patients. Morphine consumption, pain scores, respiratory depression, nausea and vomiting, and urinary retention were recorded every 3h for 48h after surgery. RESULTS: The loading dose of morphine was lower (p<0.00001) in the L group. There were significantly lower morphine doses up to 6h after surgery and VAS scores up to 3h after surgery in the L group (p<0.001 and p=0.0003, respectively). The incidence of nausea and vomiting was lower in the L group (<0.00001). The incidence of urinary retention was lower in the L group (p=0.019). CONCLUSIONS: A single shot IB is an effective additional treatment for pediatric patients undergoing the Nuss procedure and results in the reduced consumption of morphine, less postoperative pain, and fewer opioid-related adverse effects.
Cited By :21
Cited By :21
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Femenino; Humanos; Masculino; Nervios Intercostales; Bloqueo Nervioso/métodos; Dolor Postoperatorio/tratamiento farmacológico; Manejo del Dolor/métodos; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/diagnóstico; Anestésicos Locales; Dimensión del Dolor; Procedimientos Ortopédicos/métodos; Cuidados Preoperatorios/métodos; Bupivacaína/administración & dosificación; Bupivacaína/análogos & derivados; Levobupivacaína; Método Doble Ciego; Inyecciones; Funnel Chest; Pain, Postoperative; Treatment Outcome; Nuss procedure; Intercostal Nerves; Orthopedic Procedures; Pain Management; Pain Measurement; Nerve Block; Bupivacaine; Pediatric; Morphine; Anesthetics, Local; Preoperative Care; Postoperative pain; Intercostal block; Double-Blind Method; Injections; Levobupivacaine

Bilateral ultrasound-guided erector spinae plane block for postoperative pain management in surgical repair of pectus excavatum via Ravitch technique - Fiorelli, Silvia; Leopizzi, Giulio; Saltelli, Giorgia; Andreetti, Claudio; Fiorelli, Alfonso; Peritore, Valentina; Rocco, Monica; Massullo, Domenico (Journal of Clinical Anesthesia, 2019)
Keywords: Humans; Adolescente; Humanos; Masculino; Bloqueo Nervioso/métodos; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Male; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Ultrasonografía Intervencional; Dimensión del Dolor; Procedimientos Ortopédicos/efectos adversos; Procedimientos Ortopédicos/métodos; Anestesia Intravenosa/métodos; Músculos Paraespinales/diagnóstico por imagen; Músculos Paraespinales/inervación; Funnel Chest; Pain, Postoperative; Treatment Outcome; Orthopedic Procedures; Pain Measurement; Erector spinae plane block; Nerve Block; Ultrasonography, Interventional; Ravitch procedure; Anesthesia, Intravenous; Paraspinal Muscles; Pectus excavatum surgery; Regional anesthesia; Thoracic anesthesia

Use of transthoracic cryoanalgesia during the Nuss procedure - Kim, Sunghoon; Idowu, Olajire; Palmer, Barnard; Lee, Sang H. (The Journal of Thoracic and Cardiovascular Surgery, 2016)
Cited By :29
Cited By :29
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Adolescente; Humanos; Masculino; Resultado del Tratamiento; Tórax en Embudo/cirugía; Tórax en Embudo/diagnóstico; Adolescent; Male; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Nervios Intercostales/cirugía; Procedimientos Ortopédicos/efectos adversos; Crioterapia/métodos; Analgesia/métodos; Toracoscopía; Analgesia/instrumentación; Crioterapia/instrumentación; Diseño de Equipo; Dolor Postoperatorio/fisiopatología; Frío; Nervios Intercostales/fisiopatología; Toracoscopía/instrumentación; Toracoscopios; Analgesia; Funnel Chest; Pain, Postoperative; Treatment Outcome; Intercostal Nerves; Orthopedic Procedures; Thoracoscopy; Cryotherapy; Cold Temperature; Equipment Design; Thoracoscopes

Bilateral Pecto-intercostal fascial plane nerve block with liposomal bupivacaine after modified Ravitch pectus excavatum repair: A case report - Migirov, Allan; Oweidat, Adeeb; Soliman, Loran Mounir; Ali Sakr Esa, Wael (Journal of Clinical Anesthesia, 2021)
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Humanos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Bloqueo Nervioso; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Tórax en Embudo; Anestesia de Conducción; Bupivacaína/efectos adversos; Funnel Chest; Pain, Postoperative; Anesthesia, Conduction; Nerve Block; Bupivacaine; Anterior intercostal nerve; Case report; Modified Ravich pectus excavatum repair; Open pectus excavatum repair; Pecto-intercostal plane nerve block

Bilateral erector spinae plane block using a programmed intermittent bolus technique for pain management after Nuss procedure - Yoshizaki, Mai; Murata, Hiroaki; Ogami-Takamura, Keiko; Hara, Tetsuya (Journal of Clinical Anesthesia, 2019)
Cited By :5
Cited By :5
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humans; Humanos; Masculino; Niño; Bloqueo Nervioso/métodos; Tórax en Embudo/cirugía; Male; Dolor Postoperatorio/prevención & control; Anestésicos Locales/administración & dosificación; Child; Funnel Chest; Pain, Postoperative; Nuss procedure; Pectus excavatum; Erector spinae plane block; Nerve Block; Anesthetics, Local; Programmed intermittent bolus

Case Report of Cryo Nerve Block in a Patient Undergoing Full Sternotomy: A Novel Approach to Pain Control in Cardiac Surgery - Caparrelli, David J. (A&A Practice, 2023)
We present the case of a 65-year-old man undergoing open-heart surgery through a full sternotomy with the use of bilateral intercostal cryo nerve block (cryoNB) as adjunctive therapy for postoperative analgesia. CryoNB has been previously demonstrated as safe and effective for pain control in thoracotomy procedures as well as bilaterally in adolescent patients with pectus excavatum undergoing Nuss procedure. Herein, we describe for the first time, the cryoNB procedure for postoperative pain management in a patient undergoing full sternotomy.
Keywords: Humans; Adolescent; Male; Pain, Postoperative; Pain Management; Nerve Block; Aged; Cardiac Surgical Procedures; Sternotomy

Patient-reported outcomes of laryngeal mask anesthesia in thoracoscopic pulmonary wedge resection: A randomized controlled study - Xu, K.; Zhang, Y.; Cui, Y.; Tian, F. (Thoracic Cancer, 2022)
Export Date: 8 December 2022
Export Date: 8 December 2022

Low-dose ketamine infusions reduce opioid use in pediatric and young adult oncology patients - Anghelescu, D.L.; Ryan, S.; Wu, D.; Morgan, K.J.; Patni, T.; Li, Y. (Pediatric Blood and Cancer, 2022)
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022

Key Components, Current Practice and Clinical Outcomes of ERAS Programs in Patients Undergoing Orthopedic Surgery: A Systematic Review - Salamanna, F.; Contartese, D.; Brogini, S.; Visani, A.; Martikos, K.; Griffoni, C.; Ricci, A.; Gasbarrini, A.; Fini, M. (Journal of Clinical Medicine, 2022)
Export Date: 8 December 2022
Export Date: 8 December 2022

Translation, cultural adaptation and linguistic validation of the pectus excavatum evaluation questionnaire - Janssen, N.; Daemen, J.H.T.; van Polen, E.J.; Jansen, Y.J.L.; Hulsewé, K.W.E.; Vissers, Y.L.J.; de Loos, E.R. (Journal of Thoracic Disease, 2022)
Export Date: 8 December 2022
Export Date: 8 December 2022

Health-related quality of life after Nuss procedure for pectus excavatum: A cross-sectional study - Norlander, L.; Sundqvist, A.-S.; Anderzén-Carlsson, A.; Dreifaldt, M.; Andreasson, J.; Vidlund, M. (Interactive Cardiovascular and Thoracic Surgery, 2022)
Export Date: 8 December 2022
Export Date: 8 December 2022

The psychometric properties of the Turkish version of the pectus carinatum body image quality of life questionnaire - Alaca, N.; Çağrı Aslan, D.; Alaca, İ.; Yüksel, M. (Pediatric Surgery International, 2022)
Export Date: 8 December 2022
Export Date: 8 December 2022

Opioid Requirements After Intercostal Cryoanalgesia in Thoracic Surgery - O'Connor, L.A.; Dua, A.; Orhurhu, V.; Hoepp, L.M.; Quinn, C.C. (Journal of Surgical Research, 2022)
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022

Intraoperative electroneurography-guided intercostal nerve cryoablation for pain control after thoracoabdominal aneurysm open surgical repair - Mascia, D.; Kahlberg, A.; Tinaglia, S.; Pena, A.; Morgad De Freitas, D.; Del Carro, U.; Bosco, L.; Monaco, F.; de Luca, M.; Chiesa, R.; Melissano, G. (International Angiology, 2022)
Export Date: 8 December 2022
Export Date: 8 December 2022

Prevalence and Predictors of Chronic Postsurgical Pain After Video-Assisted Thoracoscopic Surgery: A Systematic Review and Meta-analysis - Chen, W.-C.; Bai, Y.-Y.; Zhang, L.-H.; Liu, Y.-B.; Liu, C.-Y.; Liang, J.-W.; He, H.-F. (Pain and Therapy, 2022)
Export Date: 8 December 2022
Export Date: 8 December 2022

Multimodal continuous ambulatory erector spinae catheter pain protocol for early recovery following Nuss procedure: A retrospective cohort study - Abbasian, N.; Clay, S.J.; Batra, M.; Walter, C.M.; Olbrecht, V.A.; Mecoli, M.; Lee, C.S.; Nair, M.; Huq, A.; Simpson, B.E.; Brown, R.L.; Garcia, V.F.; et al. (Regional Anesthesia and Pain Medicine, 2022)
Export Date: 8 December 2022
Export Date: 8 December 2022

Pediatric Pain Screening Tool: A Simple 9-Item Questionnaire Predicts Functional and Chronic Postsurgical Pain Outcomes After Major Musculoskeletal Surgeries - Narayanasamy, S.; Yang, F.; Ding, L.; Geisler, K.; Glynn, S.; Ganesh, A.; Sathyamoorthy, M.; Garcia, V.; Sturm, P.; Chidambaran, V. (Journal of Pain, 2022)
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022

Translation and psychometric evaluation of the Swedish versions of the Nuss Questionnaire modified for Adults and the Single Step Questionnaire - Norlander, L.; Karlsson, J.; Anderzén-Carlsson, A.; Vidlund, M.; Dreifaldt, M.; Andreasson, J.; Sundqvist, A.-S. (Journal of Patient-Reported Outcomes, 2021)
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022

Thoracic paravertebral nerve catheter reduces postoperative opioid use for vertebral body tethering patients - Mathew, S.; Milbrandt, T.A.; Potter, D.D.; Larson, A.N. (Spine Deformity, 2021)
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022

Pediatric surgeon opioid prescribing behavior: A survey of the American Pediatric Surgery Association membership - Hunsberger, J.B.; Monitto, C.L.; Hsu, A.; Yenokyan, G.; Jelin, E. (Journal of Pediatric Surgery, 2021)
Cited By :6
Cited By :6
Export Date: 8 December 2022
Export Date: 8 December 2022

Reducing Unnecessary Chest X-Ray Films After Thoracic Surgery: A Quality Improvement Initiative - Porter, E.D.; Kelly, J.L.; Fay, K.A.; Hasson, R.M.; Millington, T.M.; Finley, D.J.; Phillips, J.D. (Annals of Thoracic Surgery, 2021)
Cited By :5
Cited By :5
Export Date: 8 December 2022
Export Date: 8 December 2022

Opioid stewardship in pediatric surgery: Approaching zero - Calderon, T.; Hedges, E.; Livingston, M.H.; Gitzelmann, C.; Pegoli, W.; Wakeman, D. (Journal of Pediatric Surgery, 2021)
Cited By :4
Cited By :4
Export Date: 8 December 2022
Export Date: 8 December 2022

Guidelines for Opioid Prescribing in Children and Adolescents after Surgery: An Expert Panel Opinion - Kelley-Quon, L.I.; Kirkpatrick, M.G.; Ricca, R.L.; Baird, R.; Harbaugh, C.M.; Brady, A.; Garrett, P.; Wills, H.; Argo, J.; Diefenbach, K.A.; Henry, M.C.W.; Sola, J.E.; et al. (JAMA Surgery, 2021)
Cited By :43
Cited By :43
Export Date: 8 December 2022
Export Date: 8 December 2022

Use of cryoanalgesia as a postoperative pain management for open pectus carinatum repair - Gologorsky, R.; Ewbank, C.; Idowu, O.; Kim, S. (Pediatric Surgery International, 2021)
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022

Opioid use in children's surgery: Awareness, current state, and advocacy - Bass, K.D.; Heiss, K.F.; Kelley-Quon, L.I.; Raval, M.V. (Journal of Pediatric Surgery, 2020)
Cited By :7
Cited By :7
Export Date: 8 December 2022
Export Date: 8 December 2022

Comparison of regional analgesia techniques for pleurodesis pain in pediatric patients - Xie, J.; Mooney, D.P.; Cravero, J. (Paediatric Anaesthesia, 2020)
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022

First national survey on opioids prescribing practices of Canadian pediatric surgeons - Zani-Ruttenstock, E.; Sozer, A.; O'Neill Trudeau, M.; Fecteau, A. (Journal of Pediatric Surgery, 2020)
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022

Analgesic Effectiveness of Perioperative Ultrasound-Guided Serratus Anterior Plane Block Combined with General Anesthesia in Patients Undergoing Video-Assisted Thoracoscopic Surgery: A Systematic Review and Meta-analysis - Zhang, X.; Zhang, C.; Zhou, X.; Chen, W.; Li, J.; Wang, H.; Liu, J. (Pain Medicine (United States), 2020)
Cited By :10
Cited By :10
Export Date: 8 December 2022
Export Date: 8 December 2022

Perioperative gabapentin in pediatric thoracic surgery patients-randomized, placebo-controlled, phase 4 trial - Tomaszek, L.; Fenikowski, D.; Maciejewski, P.; Komotajtys, H.; Gawron, D. (Pain Medicine (United States), 2020)
Cited By :10
Cited By :10
Export Date: 8 December 2022
Export Date: 8 December 2022

Case report: Thoracic operculum syndrome. Pain relief in pediatric patients - Pila, P.Q.; Aguilar, A.P. (Revista Chilena de Anestesia, 2020)
Export Date: 8 December 2022
Export Date: 8 December 2022

Features of Marfan syndrome not listed in the Ghent nosology–the dark side of the disease - von Kodolitsch, Y.; Demolder, A.; Girdauskas, E.; Kaemmerer, H.; Kornhuber, K.; Muino Mosquera, L.; Morris, S.; Neptune, E.; Pyeritz, R.; Rand-Hendriksen, S.; Rahman, A.; Riise, N.; et al. (Expert Review of Cardiovascular Therapy, 2019)
Cited By :29
Cited By :29
Export Date: 8 December 2022
Export Date: 8 December 2022

Comparative efficacy of continuous infusion of bupivacaine/fentanyl and ropivacaine/fentanyl for paediatric pain control after the ravitch procedure and thoracotomy. A prospective randomized study - Tomaszek, L.; Fenikowski, D.; Gawron, D.; Komotajtys, H. (Biomedical Papers, 2019)
Cited By :5
Cited By :5
Export Date: 8 December 2022
Export Date: 8 December 2022

Peripheral nerve blocks for postoperative analgesia: From traditional unencapsulated local anesthetic to liposomes, cryoneurolysis and peripheral nerve stimulation - Gabriel, R.A.; Ilfeld, B.M. (Best Practice and Research: Clinical Anaesthesiology, 2019)
Cited By :6
Cited By :6
Export Date: 8 December 2022
Export Date: 8 December 2022

Ropivacaine/Fentanyl vs. Bupivacaine/Fentanyl for Pain Control in Children after Thoracic Surgery: A Randomized Study - Tomaszek, L.; Fenikowski, D.; Komotajtys, H.; Gawron, D. (Pain Management Nursing, 2019)
Cited By :10
Cited By :10
Export Date: 8 December 2022
Export Date: 8 December 2022

Pediatric thoracic anesthesia: Airway management for lung isolation and postoperative analgesia - Piccioni, F.; Templeton, T.W.; Morris, B.; Valenza, F. (Pediatric Medicine, 2019)
Cited By :3
Cited By :3
Export Date: 8 December 2022
Export Date: 8 December 2022

Pediatric postoperative opioid prescribing and the opioid crisis - Harbaugh, C.M.; Gadepalli, S.K. (Current Opinion in Pediatrics, 2019)
Cited By :28
Cited By :28
Export Date: 8 December 2022
Export Date: 8 December 2022

Percutaneous peripheral nerve stimulation and other alternatives for perineural catheters for postoperative analgesia - Gabriel, R.A.; Ilfeld, B.M. (Best Practice and Research: Clinical Anaesthesiology, 2019)
Cited By :5
Cited By :5
Export Date: 8 December 2022
Export Date: 8 December 2022

Changes in chest wall motion with removal of Nuss bar in repaired pectus excavatum - a cohort study - Oswald, N.; Jalal, Z.; Kadiri, S.; Naidu, B. (Journal of Cardiothoracic Surgery, 2019)
Cited By :3
Cited By :3
Export Date: 8 December 2022
Export Date: 8 December 2022

Withholding urinary catheters in children receiving patient-controlled analgesia for appendicitis - Sobrino, J.A.; Axt, J.; Sujka, J.A.; Benedict, L.A.; Wedel, L.; Millspaugh, D.; St. Peter, S.D. (Journal of Surgical Research, 2019)
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022

Pain and sensory disturbances following surgical repair of pectus carinatum - Knudsen, M.V.; Pilegaard, H.K.; Grosen, K. (Journal of Pediatric Surgery, 2018)
Export Date: 8 December 2022
Export Date: 8 December 2022

Regional anesthetic techniques for the pediatric patient - Nossaman, V.E.; Nossaman, B.D. (Essentials of Regional Anesthesia: Second Edition, 2018)
Cited By :1
Cited By :1
Export Date: 8 December 2022
Export Date: 8 December 2022

Endogenous Opiates and Behavior: 2015 - Bodnar, R.J. (Peptides, 2017)
Cited By :40
Cited By :40
Export Date: 8 December 2022
Export Date: 8 December 2022

A 20-year review of pectus surgery: An analysis of factors predictive of recurrence and outcomes - Tikka, T.; Kalkat, M.S.; Bishay, E.; Steyn, R.S.; Rajesh, P.B.; Naidu, B. (Interactive Cardiovascular and Thoracic Surgery, 2016)
Cited By :20
Cited By :20
Export Date: 8 December 2022
Export Date: 8 December 2022

Day surgery regional anesthesia in children: Safety and improving outcomes, do they make a difference? - Deer, J.D.; Sawardekar, A.; Suresh, S. (Current Opinion in Anaesthesiology, 2016)
Cited By :8
Cited By :8
Export Date: 8 December 2022
Export Date: 8 December 2022

Patch Testing for Evaluation of Hypersensitivity to Implanted Metal Devices: A Perspective from the American Contact Dermatitis Society - Schalock, P.C.; Crawford, G.; Nedorost, S.; Scheinman, P.L.; Atwater, A.R.; Mowad, C.; Brod, B.; Ehrlich, A.; Watsky, K.L.; Sasseville, D.; Silvestri, D.; Worobec, S.M.; et al. (Dermatitis, 2016)
Cited By :46
Cited By :46
Export Date: 8 December 2022
Export Date: 8 December 2022

Postoperative pain control with paravertebral catheters after pediatric total pancreatectomy and islet autotransplantation: A retrospective cohort study - Hutchins, J.; Castro, C.; Wang, Q.; Chinnakotla, S. (Paediatric Anaesthesia, 2016)
Cited By :11
Cited By :11
Export Date: 8 December 2022
Export Date: 8 December 2022

Continuous chloroprocaine infusion for thoracic and caudal epidurals as a postoperative analgesia modality in neonates, infants, and children - Veneziano, G.; Iliev, P.; Tripi, J.; Martin, D.; Aldrink, J.; Bhalla, T.; Tobias, J. (Paediatric Anaesthesia, 2016)
Cited By :20
Cited By :20
Export Date: 8 December 2022
Export Date: 8 December 2022

Update on paravertebral blocks - Wardhan, R. (Current Opinion in Anaesthesiology, 2015)
Cited By :12
Cited By :12
Export Date: 8 December 2022
Export Date: 8 December 2022

Clinical evaluation of quality of life: A survey among members of European Society of Thoracic Surgeons (ESTS) - Pompili, C.; Novoa, N.; Balduyck, B. (Interactive Cardiovascular and Thoracic Surgery, 2015)
Cited By :21
Cited By :21
Export Date: 8 December 2022
Export Date: 8 December 2022

Surgical correction of pectus carinatum improves perceived body image, mental health and self-esteem - Knudsen, M.V.; Grosen, K.; Pilegaard, H.K.; Laustsen, S. (Journal of Pediatric Surgery, 2015)
Cited By :26
Cited By :26
Export Date: 8 December 2022
Export Date: 8 December 2022

An exceptional indication for bilateral thoracic paravertebral block performance in a pediatric patient - Salviz, E.A.; Akman, N.; Sivrikoz, N.; Demir, K.; Aydin, A.; Tuǧrul, K.M. (Agri, 2015)
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022

A prospective study concerning the relationship between metal allergy and post-operative pain following total hip and knee arthroplasty - Zeng, Y.; Feng, W.; Li, J.; Lu, L.; Ma, C.; Zeng, J.; Li, F.; Qi, X.; Fan, Y. (International Orthopaedics, 2014)
Cited By :20
Cited By :20
Export Date: 8 December 2022
Export Date: 8 December 2022

Surgical interventions for treating pectus excavatum - de Oliveira Carvalho, P.E.; da Silva, M.V.M.; Rodrigues, O.R.; Cataneo, A.J.M. (Cochrane Database of Systematic Reviews, 2014)
Cited By :22
Cited By :22
Export Date: 8 December 2022
Export Date: 8 December 2022

Pediatric acute and surgical pain management: Recent advances and future perspectives - Chidambaran, V.; Sadhasivam, S. (International Anesthesiology Clinics, 2012)
Cited By :15
Cited By :15
Export Date: 8 December 2022
Export Date: 8 December 2022

Pediatric hypnosis: Pre-, peri-, and post-anesthesia - Kuttner, L. (Paediatric Anaesthesia, 2012)
Cited By :37
Cited By :37
Export Date: 8 December 2022
Export Date: 8 December 2022

Pain Management in the Pediatric Surgical Patient - Sohn, V.Y.; Zenger, D.; Steele, S.R. (Surgical Clinics of North America, 2012)
Cited By :9
Cited By :9
Export Date: 8 December 2022
Export Date: 8 December 2022

Beneficial effects of adding ketamine to intravenous patient-controlled analgesia with fentanyl after the nuss procedure in pediatric patients - Cha, M.H.; Eom, J.H.; Lee, Y.S.; Kim, W.Y.; Park, Y.C.; Min, S.H.; Kim, J.H. (Yonsei Medical Journal, 2012)
Cited By :21
Cited By :21
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Fentanilo/uso terapéutico; Analgésicos/uso terapéutico; Ketamina/uso terapéutico; Método Doble Ciego; Inyecciones Intravenosas

Thirty years' experience of open-repair surgery for pectus excavatum: Development of a metal-free procedure - Masaoka, A.; Kondo, S.; Sasaki, S.; Hara, F.; Mizuno, T.; Yamakawa, Y.; Kobayashi, T.; Fujii, Y. (European Journal of Cardio-thoracic Surgery, 2012)
Cited By :7
Cited By :7
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adulto; Dolor Postoperatorio/prevención & control; Preescolar; Adulto Joven; Esternón/cirugía; Complicaciones Posoperatorias; Tiempo de Internación/estadística & datos numéricos; Índice de Severidad de la Enfermedad; Osteotomía/métodos; Prótesis e Implantes; Cartílago/cirugía; Costillas/cirugía; Metales; Pérdida de Sangre Quirúrgica; Periodo Intraoperatorio; Reoperación/estadística & datos numéricos

Lumbar epidural analgesia in pain management of Nuss procedures: Paediatric case - Birbicer, H.; Doruk, N.; Uguz, Y.; Altun, T. (Annals of Cardiac Anaesthesia, 2012)
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humanos; Masculino; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Dolor Postoperatorio/prevención & control; Preescolar

Epidural vs patient-controlled analgesia for postoperative pain after pectus excavatum repair: A prospective, randomized trial - St. Peter, S.D.; Weesner, K.A.; Weissend, E.E.; Sharp, S.W.; Valusek, P.A.; Sharp, R.J.; Snyder, C.L.; Holcomb III, G.W.; Ostlie, D.J. (Journal of Pediatric Surgery, 2012)
Cited By :66
Cited By :66
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Humanos; Tórax en Embudo/cirugía; Analgesia Epidural; Dolor Postoperatorio/prevención & control; Estudios Prospectivos; Analgesia Controlada por el Paciente

Indications and technique of nuss procedure for pectus excavatum - Nuss, D.; Kelly, R.E. (Thoracic Surgery Clinics, 2010)
Cited By :66
Cited By :66
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humanos; Tórax en Embudo/cirugía; Tórax en Embudo/diagnóstico; Dolor Postoperatorio/prevención & control; Complicaciones Posoperatorias/epidemiología; Procedimientos Ortopédicos/métodos; Toracoscopía; Tórax en Embudo/fisiopatología; Prótesis e Implantes; Capacidad Vital; Pruebas de Función Respiratoria; Reoperación/estadística & datos numéricos; Cuidados Preoperatorios; Imagen Corporal; Implantación de Prótesis/métodos; Remoción de Dispositivos; Selección de Paciente; Tolerancia al Ejercicio

Initial surgical and pain management outcomes after Nuss procedure - Densmore, J.C.; Peterson, D.B.; Stahovic, L.L.; Czarnecki, M.L.; Hainsworth, K.R.; Davies, H.W.; Cassidy, L.D.; Weisman, S.J.; Oldham, K.T. (Journal of Pediatric Surgery, 2010)
Cited By :41
Cited By :41
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Dolor Postoperatorio/etiología; Procedimientos Quirúrgicos Torácicos/efectos adversos

Age-related change of postoperative pain location after Nuss procedure for pectus excavatum - Nagasao, T.; Miyamoto, J.; Ichihara, K.; Jiang, H.; Jin, H.; Tamaki, T. (European Journal of Cardio-thoracic Surgery, 2010)
Cited By :22
Cited By :22
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Tórax en Embudo/cirugía; Adulto; Dolor Postoperatorio/etiología; Dimensión del Dolor/métodos; Adulto Joven; Factores de Edad; Dolor Postoperatorio/fisiopatología; Análisis de Elementos Finitos; Estrés Mecánico; Tórax/fisiopatología; Dolor Postoperatorio/patología; Tórax/patología

Editorial comment. Postoperative pain location following the Nuss procedure - what is the evidence and does it make a difference? - Pilegaard, H.K.; Grosen, K. (European Journal of Cardio-thoracic Surgery, 2010)
Cited By :5
Cited By :5
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humanos; Niño; Tórax en Embudo/cirugía; Adulto; Dolor Postoperatorio/etiología; Factores de Edad; Analgesia/métodos; Dolor Postoperatorio/fisiopatología; Análisis de Elementos Finitos; Estrés Mecánico; Tórax/fisiopatología

Systemic postoperative pain management following minimally invasive pectus excavatum repair in children and adolescents: A retrospective comparison of intravenous patient-controlled analgesia and continuous infusion with morphine - Rugyte, D.C.; Kilda, A.; Karbonskiene, A.; Barauskas, V. (Pediatric Surgery International, 2010)
Cited By :6
Cited By :6
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Adulto Joven; Analgésicos Opioides/administración & dosificación; Dimensión del Dolor; Morfina/administración & dosificación; Infusiones Intravenosas; Anestesia Intravenosa; Antiinflamatorios no Esteroideos/uso terapéutico

Comparison of the Nuss and the Ravitch procedure for pectus excavatum repair: a meta-analysis - Nasr, A.; Fecteau, A.; Wales, P.W. (Journal of Pediatric Surgery, 2010)
Cited By :94
Cited By :94
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humanos; Resultado del Tratamiento; Tórax en Embudo/cirugía; Dolor Postoperatorio/prevención & control; Procedimientos Quirúrgicos Torácicos/efectos adversos; Procedimientos Quirúrgicos Torácicos/métodos; Recién Nacido; Factores de Tiempo; Procedimientos Quirúrgicos Torácicos/rehabilitación

Postoperative consumption of opioid analgesics following correction of pectus excavatum is influenced by pectus severity: a single-centre study of 236 patients undergoing minimally invasive correction of pectus excavatum - Grosen, K.; Pfeiffer-Jensen, M.; Pilegaard, H.K. (European Journal of Cardio-thoracic Surgery, 2010)
Cited By :22
Cited By :22
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Adulto; Dolor Postoperatorio/etiología; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Adulto Joven; Analgésicos Opioides/administración & dosificación; Esquema de Medicación; Factores de Edad; Complicaciones Posoperatorias; Procedimientos Quirúrgicos Reconstructivos/efectos adversos; Persona de Mediana Edad; Procedimientos Quirúrgicos Reconstructivos/métodos; Métodos Epidemiológicos; Tórax en Embudo/patología

Usefulness of a short-term register for health technology assessment where the evidence base is poor - Patrick, H.; Gallaugher, S.; Czoski-Murray, C.; Wheeler, R.; Chattle, M.; Marlow, M.; Lyratzopoulos, G.; Campbell, B. (International Journal of Technology Assessment in Health Care, 2010)
Cited By :12
Cited By :12
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Humanos; Resultado del Tratamiento; Tórax en Embudo/cirugía; Evaluación de la Tecnología Biomédica/estadística & datos numéricos; Evaluación de la Tecnología Biomédica/organización & administración; Proyectos de Investigación; Reino Unido; Sistema de Registros/estadística & datos numéricos; Sistemas de Información/estadística & datos numéricos; Sistemas de Información/organización & administración

Intravenous versus epidural analgesia after surgical repair of pectus excavatum - Soliman, I.E.; Apuya, J.S.; Fertal, K.M.; Simpson, P.M.; Tobias, J.D. (American Journal of Therapeutics, 2009)
Cited By :27
Cited By :27
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Analgesia Epidural/métodos; Dolor Postoperatorio/prevención & control; Analgesia Epidural/efectos adversos; Adulto Joven; Analgésicos Opioides/administración & dosificación; Analgésicos Opioides/efectos adversos; Dimensión del Dolor; Analgesia Controlada por el Paciente/efectos adversos; Factores de Tiempo; Infusiones Intravenosas

Development of a new patient-reported outcome measure for breast surgery: The BREAST-Q - Pusic, A.L.; Klassen, A.F.; Scott, A.M.; Klok, J.A.; Cordeiro, P.G.; Cano, S.J. (Plastic and Reconstructive Surgery, 2009)
Cited By :981
Cited By :981
Export Date: 8 December 2022
Export Date: 8 December 2022

The effectiveness of hypnosis for reducing procedure-related pain in children and adolescents: A comprehensive methodological review - Accardi, M.C.; Milling, L.S. (Journal of Behavioral Medicine, 2009)
Cited By :64
Cited By :64
Export Date: 8 December 2022
Export Date: 8 December 2022

Operative innovation to the "Nuss" procedure for pectus excavatum: operative and functional effects - Al-Assiri, A.; Kravarusic, D.; Wong, V.; Dicken, B.; Milbrandt, K.; Sigalet, D.L. (Journal of Pediatric Surgery, 2009)
Cited By :22
Cited By :22
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Estudios Prospectivos; Adulto Joven; Tiempo de Internación/estadística & datos numéricos; Procedimientos Quirúrgicos Mínimamente Invasivos; Toracoscopía; Estética; Prótesis e Implantes; Pruebas de Función Respiratoria; Cartílago/cirugía; Pérdida de Sangre Quirúrgica; Tolerancia al Ejercicio; Pruebas de Función Cardíaca; Toracotomía/métodos

Stress distribution on the thorax after the Nuss procedure for pectus excavatum results in different patterns between adult and child patients - Nagasao, T.; Miyamoto, J.; Tamaki, T.; Ichihara, K.; Jiang, H.; Taguchi, T.; Yozu, R.; Nakajima, T. (Journal of Thoracic and Cardiovascular Surgery, 2007)
Cited By :48
Cited By :48
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Femenino; Humanos; Masculino; Niño; Tórax en Embudo/cirugía; Adulto; Dolor Postoperatorio/etiología; Preescolar; Procedimientos Quirúrgicos Torácicos; Procedimientos Quirúrgicos Torácicos/efectos adversos; Dispositivos de Fijación Ortopédica; Tórax en Embudo/fisiopatología; Estrés Mecánico; Tomografía Computarizada por Rayos X; Tórax/fisiopatología; Imagenología Tridimensional; Modelos Biológicos; Procedimientos Quirúrgicos Torácicos/instrumentación

Superior postoperative pain relief with thoracic epidural analgesia versus intravenous patient-controlled analgesia after minimally invasive pectus excavatum repair - Weber, T.; Mätzl, J.; Rokitansky, A.; Klimscha, W.; Neumann, K.; Deusch, E. (Journal of Thoracic and Cardiovascular Surgery, 2007)
Cited By :81
Cited By :81
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Analgesia Epidural; Adulto; Dolor Postoperatorio/prevención & control; Estudios Prospectivos; Analgesia Controlada por el Paciente; Analgésicos Opioides/administración & dosificación; Dimensión del Dolor; Procedimientos Quirúrgicos Mínimamente Invasivos; Morfina/administración & dosificación; Análisis de Varianza; Antiinflamatorios no Esteroideos/administración & dosificación; Diclofenaco/administración & dosificación; Modelos Logísticos

Prospective Multicenter Study of Surgical Correction of Pectus Excavatum: Design, Perioperative Complications, Pain, and Baseline Pulmonary Function Facilitated by Internet-Based Data Collection - Kelly Jr., R.E.; Shamberger, R.C.; Mellins, R.B.; Mitchell, K.K.; Lawson, M.L.; Oldham, K.; Azizkhan, R.G.; Hebra, A.V.; Nuss, D.; Goretsky, M.J.; Sharp, R.J.; Holcomb III, G.W.; et al. (Journal of the American College of Surgeons, 2007)
Cited By :165
Cited By :165
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Tórax en Embudo/cirugía; Adulto; Dolor Postoperatorio/epidemiología; Estudios Prospectivos; Preescolar; Procedimientos Ortopédicos/efectos adversos; Complicaciones Posoperatorias/epidemiología; Procedimientos Ortopédicos/métodos; Tórax en Embudo/fisiopatología; Internet; Pruebas de Función Respiratoria

Self and Parental Assessment After Minimally Invasive Repair of Pectus Excavatum: Lasting Satisfaction After Bar Removal - Metzelder, M.L.; Kuebler, J.F.; Leonhardt, J.; Ure, B.M.; Petersen, C. (Annals of Thoracic Surgery, 2007)
Cited By :51
Cited By :51
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adulto; Calidad de Vida; Dolor Postoperatorio; Satisfacción del Paciente; Factores de Edad; Procedimientos Quirúrgicos Mínimamente Invasivos; Estudios de Seguimiento; Tórax en Embudo/psicología; Remoción de Dispositivos; Autoevaluación (Psicología); Factores Sexuales; Padres/psicología

Postoperative analgesia with intravenous fentanyl PCA vs epidural block after thoracoscopic pectus excavatum repair in children - Butkovic, D.; Kralik, S.; Matolic, M.; Kralik, M.; Toljan, S.; Radesic, L. (British Journal of Anaesthesia, 2007)
Cited By :62
Cited By :62
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Analgesia Epidural/métodos; Dolor Postoperatorio/prevención & control; Dimensión del Dolor/métodos; Analgesia Epidural/efectos adversos; Analgésicos Opioides/administración & dosificación; Analgésicos Opioides/efectos adversos; Cuidados Posoperatorios/métodos; Toracoscopía; Analgesia Controlada por el Paciente/efectos adversos; Fentanilo/administración & dosificación; Respiración/efectos de los fármacos; Dióxido de Carbono/sangre; Fentanilo/efectos adversos; Frecuencia Cardíaca/efectos de los fármacos; Oxígeno/sangre; Presión Parcial; Presión Sanguínea/efectos de los fármacos

Perioperative hypnosis reduces hospitalization in patients undergoing the Nuss procedure for pectus excavatum - Lobe, T.E. (Journal of Laparoendoscopic and Advanced Surgical Techniques, 2006)
Cited By :13
Cited By :13
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Tiempo de Internación; Toracoscopía/efectos adversos; Narcóticos/administración & dosificación; Hipnosis Anestésica

Anesthetic management for the minimally invasive Nuss procedure in 21 patients with pectus excavatum - Futagawa, K.; Suwa, I.; Okuda, T.; Kamamoto, H.; Sugiura, J.; Kajikawa, R.; Koga, Y. (Journal of Anesthesia, 2006)
Cited By :41
Cited By :41
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Preescolar; Anestesia/métodos; Complicaciones Posoperatorias/terapia

Lumbar epidural morphine for postoperative analgesia in children undergoing Nuss procedure - Kariya, N.; Inoue, Y.; Minami, W.; Ikeda, Y.; Nishi, S.; Nishikawa, K.; Asada, A. (Japanese Journal of Anesthesiology, 2005)
Cited By :4
Cited By :4
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Dolor Postoperatorio/terapia; Humanos; Niño; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Preescolar; Morfina/administración & dosificación; Región Lumbosacra

Continuous thoracic epidural analgesia with 0.2% ropivacaine for pectus excavatum repair in children [2] - Barros, F. (Paediatric Anaesthesia, 2004)
Cited By :7
Cited By :7
Export Date: 8 December 2022
Export Date: 8 December 2022

Reducing trauma by minimally invasive surgery from the viewpoint of pediatric surgery - Waag, K.-L.; Hosie, S. (Chirurg, 2003)
Cited By :2
Cited By :2
Export Date: 8 December 2022
Export Date: 8 December 2022

Early experience with the Nuss minimally invasive correction of pectus excavatum in adults - Coln, D.; Gunning, T.; Ramsay, M.; Swygert, T.; Vera, R. (World Journal of Surgery, 2002)
Cited By :84
Cited By :84
Export Date: 8 December 2022
Export Date: 8 December 2022
Keywords: Femenino; Humanos; Masculino; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Tórax en Embudo/cirugía; Adulto; Dolor Postoperatorio; Persona de Mediana Edad

Crioanalgesia toracoscópica: nueva estrategia para el control del dolor postoperatorio en cirugía del pectus excavatum - Cadaval Gallardo, C; Martínez, J; Bellía-Munzon, G; Nazar, M; Sanjurjo, D; Toselli, L; Martínez-Ferro, M (Cir. pediátr, 2020)
Introducción: Publicaciones recientes reportaron el alta temprana y bajos requerimientos de opioides para el control del dolor postope-ratorio en la reparación mínimamente invasiva del pectus excavatumtras crioablación bilateral de nervios intercostales. Nuestro objetivo es describir nuestra experiencia inicial con esta técnica. Material y métodos: Análisis retrospectivo de historias clínicas de pacientes sometidos a crioanalgesia toracoscópica bilateral durante la reparación mínimamente invasiva del pectus excavatum en nuestra institución desde septiembre de 2018 a marzo de 2019. Técnica: Se aplicó una criosonda a -70°C bajo visión toracoscópica durante 2 minutos del 3º al 7º espacio intercostal, de manera bilateral. El dolor postoperatorio fue evaluado con una Escala Visual Analógica. Resultados: Se incluyeron 21 pacientes, de los cuales el 90% era de sexo masculino con una edad media de 15,2 ± 4,29 años y un peso de 53,6 ± 15,33 kg. El índice de Haller promedio fue de 5,1 ± 2,97 y el índice de corrección de 37,6 ± 13,77%. El número promedio de implantes fue de 2,55 ± 0,74. La duración media de la crioanalgesia fue de 39,9 ± 21,1 minutos. Ninguno recibió anestesia peridural. El tiempo de internación postquirúrgico fue de 1,64 ± 0,73. La necesidad de rescate con opiáceos fue menor a 1 dosis en el 71,3%. La puntuación de dolor en los días postoperatorios 1, 3, 7 y 21 fue, en promedio, de 2,55; 2,01; 0,5 y 0,06, respectivamente. Conclusiones: El empleo de la crioanalgesia toracoscópica bilateral permitió el alta hospitalaria temprana y buen control del dolor postoperatorio en todos los casos, convirtiéndose en el método analgésico de elección en nuestra práctica clínica
Keywords: Adolescente; Cirugía Torácica/métodos; Crioanestesia/instrumentación; Crioanestesia/métodos; Crioanestesia/tendencias; Dolor Postoperatorio/terapia; Estudios Retrospectivos; Femenino; Humanos; Manejo del Dolor; Masculino; Nervios Intercostales; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Toracoscopía/métodos

Bloqueo bilateral del plano del músculo erector de la columna espinal para cirugía de pectus excavatum y pectus carinatum en 2 pacientes pediátricos - Nardiello, MA; Herlitz, M (Rev. esp. anestesiol. reanim, 2018)
Recientemente han surgido numerosas publicaciones sobre la aplicación del bloqueo del plano del músculo erector de la columna espinal en población adulta. Existen escasos reportes del uso de este bloqueo en cirugía pediátrica. Nuestro objetivo es reportar 2 casos de adolescentes, uno con diagnóstico de pectus excavatum y otro de pectus carinatum, sometidos a cirugía reconstructiva esternal a los que se realizó bloqueo del plano del músculo erector de la columna espinal bilateral en inyección única como técnica analgésica. El bloqueo se realizó antes de la cirugía con los pacientes sometidos a anestesia general en posición de decúbito lateral, guiado por ecografía utilizando 20ml de bupivacaína al 0,25% por lado. Luego de la cirugía fueron extubados y trasladados a la Unidad de Cuidados Intensivos. Durante su hospitalización los valores de la escala visual análoga fueron menores de 4 y no fue requerido el uso de opioides de larga duración durante el intraoperatorio ni el postoperatorio de los pacientes. El bloqueo del plano del músculo erector de la columna espinal bilateral en inyección única fue efectivo como técnica analgésica para el intra y el postoperatorio en cirugía de pectus excavatum y pectus carinatum en población adolescente
Keywords: Adolescente; Humanos; Masculino; Anestesia de Conducción/métodos; Bloqueo Nervioso/métodos; Dolor Postoperatorio/tratamiento farmacológico; Manejo del Dolor/métodos; Pectus Carinatum/cirugía; Resultado del Tratamiento; Tórax en Embudo/cirugía

Analgesia epidural torácica frente a analgesia con fentanilo controlada por el paciente en niños operados de pectus excavatum con la técnica de Nuss - Reinoso-Barbero, F; Fernández, A; Durán, P; Castro, L. E; Campo, G; Melo, M. M (Rev. esp. anestesiol. reanim, 2010)
OBJETIVOS: Tanto la analgesia epidural torácica comola analgesia intravenosa con fentanilo controlada por elpaciente se han demostrado eficaces en los pacientespediátricos operados de pectus excavatum con la técnicade Nuss. En el presente estudio se analizan la eficacia yseguridad de ambas técnicas.MÉTODOS: Se analizaron retrospectivamente pacientespediátricos operados con la técnica de Nuss de pectusexcavatum entre octubre de 1997 y febrero de 2009. Seevaluaron peso, edad, sexo e índice de Haller. El dolor sevaloró cada 8 horas del 0 al 10 con la escala analógicavisual (EVA) o con la escala observacional LLANTO.Igualmente se registró la duración del tratamiento analgésicoen días. Finalmente se recogió la incidencia decomplicaciones del catéter o efectos secundarios del tratamientocomo náuseas, vómitos y depresión respiratoria.RESULTADOS: El estudio incluyó 31 pacientes distribuidosen 2 grupos: grupo EPI (n = 22) y grupo PCA(n = 9). No se observaron diferencias estadísticamentesignificativas entre ambos grupos en las variables demográficasestudiadas, en la incidencia de complicaciones oefectos secundarios, ni en las puntuaciones medias dedolor entre ambos grupos (grupo EPI 1,8 ± 3,8 frente agrupo PCA 2,1 ± 3,4; p = 0,775), pero sí en la duraciónen días de la necesidad de tratamiento analgésico (grupoEPI 2,9 ± 1,1 frente a grupo PCA 5,9 ± 1,4; p = 0,001).CONCLUSIONES: La analgesia epidural torácica tieneun perfil de eficacia y seguridad similar al de la analgesiaintravenosa con fentanilo controlada por el paciente,aunque permite acortar de un modo muy importante eltiempo de duración de la analgesia postoperatoria(AU)
Keywords: Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adyuvantes Anestésicos/uso terapéutico; Analgesia Controlada por el Paciente/instrumentación; Analgesia Controlada por el Paciente/métodos; Analgesia Epidural; Analgesia Epidural/instrumentación; Analgesia Epidural/métodos; Clínicas de Dolor; Evaluación de Eficacia-Efectividad de Intervenciones; Fentanilo/uso terapéutico; Periodo Posoperatorio; Tórax en Embudo/diagnóstico

Corrección del pectus excavatum por cirugía toracoscópica con la técnica de nuss - Ayarra Jarne, J; Congregado, M; Arroyo Tristán, A; Jiménez Tristán, A; Jiménez Merchán, R; Girón Arjona, J. C; Arenas Linares, C; Loscertales, J (Neumosur (Sevilla), 2005)
FUNDAMENTO: El pectus excavatum (PE) constituye ladeformación congénita más frecuente de la pared torácica, conimportantes consecuencias psicológicas y estéticas, además de funcionales.Hasta ahora la técnica más utilizada era la de Ravitch,consistente en la realización de condrectomías subpericóndricasbilaterales de los cartílagos afectos y osteotomías esternales transversalesy posterior estabilización.OBJETIVOS: Presentar nuestra experiencia en el tratamientoquirúrgico del pectus excavatum, siguiendo la técnica de correcciónmínimamente invasiva descrita por Nuss.MATERIALYMÉTODOS: A todos los pacientes se les realizóTAC de tórax con índices de Haller superiores a 3,25. Bajo anestesiageneral y mediante videotoracoscopia se colocó una barra estabilizadorasubesternal, realizando el abordaje mediante dos incisioneslaterales. Los extremos de la barra se fijaron medianteestabilizadores.RESULTADOS: Se trataron 11 pacientes (9 varones, 2 mujeres,rango de edad 10-31 años). El motivo de la intervención fue lacorrección estética. No se presentaron complicaciones intra ni postoperatoriasimportantes y no hubo ninguna muerte. El tiempooperatorio medio fue 58,6 min, el inicio de la deambulación mediafue 4,3 días y la estancia hospitalaria postoperatoria fue 7,2 días(tiempos menores que con la técnica de Ravitch). La complicaciónmás frecuente fue el dolor postoperatorio, bien controlado conanalgesia. Un paciente presentó intolerancia a la barra, siendonecesaria extraerla al año. En el 91% de nuestros casos se obtuvieronunos excelentes resultados estéticos.CONCLUSIONES: Consideramos que la técnica de Nussmínimamente invasiva debe de ser el procedimiento de elecciónpara corregir el pectus excavatum
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Toracoscopía/métodos; Tórax en Embudo/cirugía; Adulto; Dolor Postoperatorio/epidemiología

Modified Ravitch Procedure for Left Poland Syndrome Combined With Pectus Excavatum. - Cortés-Julián, Gildardo; Bushra-Nuritu, Hussein B; Buenfil-Fuentes, Renata; Merino Rajme, José A (Ann Thorac Surg, 2017)
Poland Syndrome is a rare disease with an incidence of 1 in 30,000. This disease is characterized by agenesis of the pectoralis major, hypoplasia of mammarian tissue and the nipple complex, and limb abnormalities. The severe form of this disease can be associated with rib and sternal malformations like pectus excavatum. A 19-year-old man with severe Poland syndrome with cardiac extrasystoles and restrictive ventilation as shown by a spirometry test is presented. A total sternal reconstruction with partial osteotomies and bilateral resection of cartilage was performed. The sternum was stabilized with underlying titanium bars and clips. The cosmetic result was satisfactory.
Keywords: Humanos; Masculino; Resultado del Tratamiento; Tórax en Embudo/cirugía; Calidad de Vida; Tórax en Embudo/complicaciones; Tórax en Embudo/diagnóstico por imagen; Adulto Joven; Esternón/cirugía; Dimensión del Dolor; Estudios de Seguimiento; Enfermedades Raras; Fijadores Internos; Índice de Severidad de la Enfermedad; Músculos Pectorales/anomalías; Músculos Pectorales/cirugía; Osteotomía/métodos; Posicionamiento del Paciente; Procedimientos Quirúrgicos Reconstructivos/instrumentación; Procedimientos Quirúrgicos Reconstructivos/métodos; Síndrome de Poland/cirugía; Síndrome de Poland/complicaciones; Síndrome de Poland/diagnóstico por imagen; Tomografía Computarizada por Rayos X/métodos

Clinical experiences of ultrasound-guided lateral thoracolumbar Interfascial plane (TLIP) block. - Ueshima, Hironobu; Otake, Hiroshi (J Clin Anesth, 2017)
Keywords: Femenino; Humanos; Masculino; Bloqueo Nervioso/métodos; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Ultrasonografía Intervencional/métodos; Anciano; Anestésicos Locales/administración & dosificación; Analgesia/métodos; Músculos Paraespinales/diagnóstico por imagen; Músculos Paraespinales/inervación; Anestesia General/métodos; Bloqueo Nervioso/instrumentación; Bupivacaína/administración & dosificación; Bupivacaína/análogos & derivados; Laminoplastia/efectos adversos; Levobupivacaína; Nervios Torácicos/efectos de los fármacos; Plexo Lumbosacro/efectos de los fármacos; Ultrasonografía Intervencional/instrumentación; Vértebras Lumbares

Situational but Not Dispositional Pain Catastrophizing Correlates With Early Postoperative Pain in Pain-Free Patients Before Surgery. - Grosen, Kasper; Drewes, Asbjørn Mohr; Pilegaard, Hans Kristian; Pfeiffer-Jensen, Mogens; Brock, Birgitte; Vase, Lene (J Pain, 2016)
UNLABELLED: Pain catastrophizing may be assessed as a dispositional measure using a previous painful experience as a reference or as a situational measure using an actual ongoing pain as a reference. The latter has shown more robust correlations with pain-related outcomes; the relative influence of dispositional and situational pain catastrophizing remains unknown in relation to populations with no pain before surgery. Forty-two consecutive patients who underwent corrective surgery for funnel chest were asked to complete the Pain Catastrophizing Scale with reference to 1) a previous painful experience (dispositional pain catastrophizing), 2) experimental pain during a 2-minute cold pressor test (situational experimental pain catastrophizing), and 3) clinical pain 3 days after surgery (situational clinical pain catastrophizing) to investigate whether these measures predicted immediate pain intensity and unpleasantness in the early postoperative period. Thirty-four patients were available for analyses. Dispositional pain catastrophizing was unrelated to situational experimental and situational clinical pain catastrophizing and to postoperative pain and unpleasantness (P > .05). In contrast, the 2 situation-specific pain catastrophizing measures were strongly associated (ρ = .59, P = .0002). In analyses adjusted for preoperative anxiety, depression, and cold pressor pain sensitivity, situational experimental and situational clinical pain catastrophizing correlated with postoperative movement-evoked pain (ß = 1.36, P = .01 and ß = 1.24, P = .02, respectively) and unpleasantness (ß = 1.32, P = .01 and ß = 1.36, P = .01, respectively). PERSPECTIVE: Pain catastrophizing should be captured in relation to specific painful events in otherwise healthy patients. Future studies might benefit from assessing situational pain catastrophizing to identify patients at risk for increased postoperative pain to optimize stratified pain treatment.
Keywords: Femenino; Humanos; Manejo del Dolor; Masculino; Encuestas y Cuestionarios; Dimensión del Dolor; Estudios de Seguimiento; Dolor Postoperatorio/psicología; Catastrofización/psicología; Ansiedad/etiología; Catastrofización/complicaciones; Depresión/etiología; Escalas de Valoración Psiquiátrica; Estadística como Asunto; Modelos Lineales; Periodo Preoperatorio; Umbral del Dolor/fisiología

Pupillometry: a non-invasive technique for pain assessment in paediatric patients. - Connelly, Mark A; Brown, Jacob T; Kearns, Gregory L; Anderson, Rawni A; St Peter, Shawn D; Neville, Kathleen A (Arch Dis Child, 2014)
OBJECTIVE: Pupillometry has been used to assess pain intensity and response to analgesic medications in adults. The aim of this observational study was to explore proof of concept for the use of this technique in paediatric patients. Changes in pupil parameters before and after opioid exposure also were evaluated. DESIGN AND SETTING: This was a single-centre, prospective study conducted at an academic paediatric medical centre. PATIENTS: Children 9-17âyears of age undergoing elective surgical correction of pectus excavatum were enrolled into a protocol approved by the human ethical committee (institutional review board). INTERVENTIONS: Pupil size and reactivity were measured using a handheld pupillometer. Pain was assessed using age-appropriate, validated pain self-report scales. RESULTS: Thirty patients were enrolled. Each point change on a 10âcm visual analogue pain intensity scale was associated with a statistically significant mean change of 0.11âmm/s in maximum pupil constriction velocity, and of approximately 0.4% in pupil diameter. As expected, there was an association between total opioid dose (expressed as morphine equivalents) and pupil diameter. Age, sex and baseline anxiety scores did not correlate significantly with pupillary response. CONCLUSIONS: The association of maximum pupillary constriction velocity and diameter with pain scores illustrates the potential for using pupillometry as a non-invasive method to objectively quantitate pain response/intensity in children. The technique holds promise as a pharmacodynamic 'tool' to assess opioid response in paediatric patients.
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Analgésicos Opioides/uso terapéutico; Estudios Prospectivos; Dimensión del Dolor/métodos; Dolor/fisiopatología; Dolor/tratamiento farmacológico; Pupila/efectos de los fármacos; Reflejo Pupilar/fisiología; Técnicas de Diagnóstico Oftalmológico/instrumentación

Conditioned pain modulation and situational pain catastrophizing as preoperative predictors of pain following chest wall surgery: a prospective observational cohort study. - Grosen, Kasper; Vase, Lene; Pilegaard, Hans K; Pfeiffer-Jensen, Mogens; Drewes, Asbjørn M (PLoS One, 2014)
BACKGROUND: Variability in patients' postoperative pain experience and response to treatment challenges effective pain management. Variability in pain reflects individual differences in inhibitory pain modulation and psychological sensitivity, which in turn may be clinically relevant for the disposition to acquire pain. The aim of this study was to investigate the effects of conditioned pain modulation and situational pain catastrophizing on postoperative pain and pain persistency. METHODS: Preoperatively, 42 healthy males undergoing funnel chest surgery completed the Spielberger's State-Trait Anxiety Inventory and Beck's Depression Inventory before undergoing a sequential conditioned pain modulation paradigm. Subsequently, the Pain Catastrophizing Scale was introduced and patients were instructed to reference the conditioning pain while answering. Ratings of movement-evoked pain and consumption of morphine equivalents were obtained during postoperative days 2-5. Pain was reevaluated at six months postoperatively. RESULTS: Patients reporting persistent pain at six months follow-up (nâ=â15) were not significantly different from pain-free patients (nâ=â16) concerning preoperative conditioned pain modulation response (Zâ=â1.0, Pâ=â0.3) or level of catastrophizing (Zâ=â0.4, Pâ=â1.0). In the acute postoperative phase, situational pain catastrophizing predicted movement-evoked pain, independently of anxiety and depression (ßâ=â1.0, Pâ=â0.007) whereas conditioned pain modulation predicted morphine consumption (ßâ=â-0.005, Pâ=â0.001). CONCLUSIONS: Preoperative conditioned pain modulation and situational pain catastrophizing were not associated with the development of persistent postoperative pain following funnel chest repair. Secondary outcome analyses indicated that conditioned pain modulation predicted morphine consumption and situational pain catastrophizing predicted movement-evoked pain intensity in the acute postoperative phase. These findings may have important implications for developing strategies to treat or prevent acute postoperative pain in selected patients. Pain may be predicted and the malfunctioning pain inhibition mechanism as tested with CPM may be treated with suitable drugs augmenting descending inhibition.
Keywords: Adolescente; Femenino; Humanos; Masculino; Manejo del Dolor/métodos; Estudios Prospectivos; Adulto Joven; Dolor Postoperatorio/psicología; Periodo Preoperatorio; Pared Torácica/cirugía; Análisis de Regresión; Catastrofización; Cognición; Manejo del Dolor/psicología; Riesgo

Case report: neurological complications associated with epidural analgesia in children: a report of 4 cases of ambiguous etiologies. - Meyer, Mark J; Krane, Elliot J; Goldschneider, Kenneth R; Klein, Norma J (Anesth Analg, 2012)
The safety and utility of pediatric epidural analgesia is well established, but the risk of permanent neurological injury is unknown and largely must be extrapolated from adult literature. In this article we present a series of 4 cases of longterm or permanent neurologic complications associated with epidural analgesia. Possible mechanisms of injury and implications for practice are discussed.
Keywords: Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Complicaciones Posoperatorias/cirugía; Analgesia Epidural/efectos adversos; Lactante; Bupivacaína/uso terapéutico; Anestesia General; Complicaciones Posoperatorias/etiología; Anestésicos Locales/administración & dosificación; Bupivacaína/administración & dosificación; Anestésicos Locales/uso terapéutico; Anomalías Urogenitales/cirugía; Colitis Ulcerosa/cirugía; Columna Vertebral/patología; Complicaciones Posoperatorias/tratamiento farmacológico; Compresión de la Médula Espinal/complicaciones; Dexametasona/uso terapéutico; Enfermedades del Sistema Nervioso/cirugía; Enfermedades del Sistema Nervioso/etiología; Enfermedades del Sistema Nervioso/tratamiento farmacológico; Imagen por Resonancia Magnética; Laminectomía; Parálisis/inducido químicamente; Recuperación de la Función; Síndromes de Dolor Regional Complejo/complicaciones; Síndromes de Dolor Regional Complejo/terapia

Epidural and opioid analgesia following the Nuss procedure. - Walaszczyk, Malgorzata; Knapik, Piotr; Misiolek, Hanna; Korlacki, Wojciech (Med Sci Monit, 2011)
BACKGROUND: Parents have the right to decide on behalf of their children and deny consent to regional anaesthesia. The investigators decided to investigate quality of postoperative analgesia in adolescents undergoing epidural and opioid analgesia following the Nuss procedure. material/methods: The study subjects were 61 adolescents aged 11-18 years who underwent pectus excavatum repair with the Nuss procedure. Patients were divided into epidural (n=41) and opioid (n=20) groups, depending on their parents' consent to epidural catheter insertion. Intraoperatively, 0.5% epidural ropivacaine with fentanyl or intermittent intravenous injections of fentanyl were used. Postoperative analgesia was achieved with either epidural infusion of 0.1% ropivacaine with fentanyl, or subcutaneous morphine via an intraoperatively inserted "butterfly" cannula. Additionally, both groups received metamizol and paracetamol. Primary outcome variables were postoperative pain scores (Numeric Rating Scale and Prince Henry Hospital Pain Score). Secondary outcome variables included hemodynamic parameters, additional analgesia and side effects. RESULTS: Heart rate and blood pressure values in the postoperative period were significantly higher in the opioid group. Pain scores requiring intervention were noted almost exclusively in the opioid group. CONCLUSIONS: Denial of parental consent to epidural analgesia following the Nuss procedure results in significantly worse control of postoperative pain. Our data may be useful when discussing with parents the available anaesthetic techniques for exceptionally painful procedures.
Keywords: Adolescente; Femenino; Humanos; Masculino; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Tórax en Embudo/cirugía; Analgesia Epidural; Dolor Postoperatorio/prevención & control; Analgésicos Opioides/uso terapéutico; Dimensión del Dolor/métodos; Morfina; Ropivacaína; Frecuencia Cardíaca; Presión Sanguínea; Amidas; Análisis de Varianza; Consentimiento Paterno; Dipirona; Estadísticas no Paramétricas; Fentanilo

Attentional and emotional mechanisms related to pain as predictors of chronic postoperative pain: a comparison with other psychological and physiological predictors. - Lautenbacher, Stefan; Huber, Claudia; Schöfer, Dorothea; Kunz, Miriam; Parthum, Andreas; Weber, Peter G; Roman, Carbon; Griessinger, Norbert; Sittl, Reinhard (Pain, 2010)
The present prospective longitudinal study on chronic postoperative pain was conducted to assess the predictive power of attentional and emotional variables specifically assumed to augment pain, such as pain hypervigilance, pain-related anxiety, pain catastrophizing and attentional biases to pain. Their relevance was determined in comparison with other psychological and physiological predictors (depression, anxiety, somatization, cortisol reactivity, pain sensitivity). In 84 young male patients the predictor variables were assessed one day before surgery (correction of chest malformation). Postoperative outcome (subjective pain intensity and pain-related disability) was assessed three (N=84) and six months (N=78) after surgery. Patients were classified into good and poor outcome groups. Patients with high pain intensity three (25%) or six months (14%) after surgery, differed significantly from those low in pain with regard to their preoperative performance in the dot-probe task (high attentional bias towards positive words). A sizeable portion (54%) of patients still felt disabled due to pain after three months and a few patients after six months (13%). These patients were those with high preoperative ratings in the Pain Vigilance and Awareness Questionnaire. The few subjectively disabled patients after six months could be identified in addition by low pressure pain and high cold pain thresholds before surgery. An attentional bias towards positive stimuli prior to surgery may indicate a maladaptive coping style, which avoids necessary confrontation with pain and predisposes patients to chronic postoperative pain. Lasting subjectively felt pain-related disability occurs predominantly in patients with high levels of pain hypervigilance before surgery.
Keywords: Adolescente; Humanos; Masculino; Tórax en Embudo/cirugía; Adulto; Estudios Prospectivos; Encuestas y Cuestionarios; Dimensión del Dolor; Valor Predictivo de las Pruebas; Dolor Postoperatorio/psicología; Ansiedad/psicología; Catastrofización/psicología; Depresión/psicología; Adaptación Psicológica; Umbral del Dolor/psicología; Atención; Emociones; Enfermedad Crónica/psicología

[Characteristics of postoperative period in children with funnel chest deformity after thoracoplasty]. - Mishina, T P; Isalabdulaeva, P A; Magomedov, A D; Makhachev, S M (Anesteziol Reanimatol, 2010)
The efficiency of postoperative analgesia using the epidural infusion of bupivacaine (0.2 mg/kg/hr) in 42 children and with opioid analgesics (1 mg per year of life) was studied in 17 children after Paltia thoracoplasty for funnel chest deformity. Analysis of hemodynamic and external respiratory parameters and visual pain scores demonstrated the high postoperative efficiency of analgesia using the epidural infusion of bupivacaine. By causing respiratory depression, opioid analgesics did not deteriorate alveolar ventilation during active postoperative management.
Keywords: Adolescente; Humanos; Niño; Tórax en Embudo/cirugía; Analgesia Epidural/instrumentación; Analgesia Epidural/métodos; Periodo Posoperatorio; Dolor Postoperatorio/prevención & control; Analgésicos Opioides/uso terapéutico; Bupivacaína/efectos adversos; Analgésicos Opioides/administración & dosificación; Analgésicos Opioides/efectos adversos; Dimensión del Dolor; Bupivacaína/uso terapéutico; Toracoplastia/métodos; Anestésicos Locales/administración & dosificación; Dolor Postoperatorio/psicología; Bupivacaína/administración & dosificación; Anestésicos Locales/uso terapéutico; Anestésicos Locales/efectos adversos; Bombas de Infusión Implantables; Hemodinámica/efectos de los fármacos; Respiración/efectos de los fármacos

Double-bar application decreases postoperative pain after the Nuss procedure. - Nagaso, Tomohisa; Miyamoto, Junpei; Kokaji, Kiyokazu; Yozu, Ryohei; Jiang, Hua; Jin, HongMei; Tamaki, Tamotsu (J Thorac Cardiovasc Surg, 2010)
OBJECTIVE: This biomechanical study aims to elucidate whether additional bar application increases postoperative pain after the Nuss procedure for pectus excavatum. METHODS: Clinical evaluation: The intensity of postoperative pain was compared between patients for whom a single-bar was used (single-bar group: n = 14) and those for whom double bars (double-bar group: n = 10) were used to correct the thoracic deformity. The evaluation was performed by referring to the frequency with which local anesthetics were self-injected in a patient-controlled anesthetic system and how many days were needed for the patients to resume ambulation. Theoretical evaluation: An original simulation system for the Nuss procedure was developed by producing 3-dimensional finite element analysis models from computed tomographic data of patients with pectus excavatum. With this system, single-bar and double-bar placement was simulated separately for the thorax models of the double-bar group. The stresses occurring on the thoraces were then compared between the two situations. RESULTS: Clinical evaluation: Self-injection of local anesthetic was more frequent for the single-bar group than for the double-bar group; single-bar patients restarted ambulation later than the double-bar group. Theoretical evaluation: Stresses on the thoraces were smaller when double bars were applied than when a single bar was applied. CONCLUSIONS: Performing double-bar placement decreases postoperative pain. Therefore, surgeons should not hesitate to perform double-bar correction in patients in whom the deformity extends to multiple intercostal spaces, requiring correction of the thorax shape at multiple sites.
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Analgesia Controlada por el Paciente/métodos; Adulto; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Tórax en Embudo/diagnóstico por imagen; Adulto Joven; Dimensión del Dolor; Procedimientos Ortopédicos/efectos adversos; Anestésicos Locales/administración & dosificación; Análisis de Elementos Finitos; Estrés Mecánico; Factores de Tiempo; Fenómenos Biomecánicos; Simulación por Computador; Tomografía Computarizada por Rayos X; Recuperación de la Función; Autoadministración; Caminata; Equipo Ortopédico; Modelos Anatómicos; Procedimientos Ortopédicos/instrumentación

Three new datasets supporting use of the Numerical Rating Scale (NRS-11) for children's self-reports of pain intensity. - von Baeyer, Carl L; Spagrud, Lara J; McCormick, Julia C; Choo, Eugene; Neville, Kathleen; Connelly, Mark A (Pain, 2009)
Despite wide usage of the Numerical Rating Scale (NRS) for self-report of pain intensity in clinical practice with children and adolescents, validation data are lacking. We present here three datasets from studies in which the NRS was used together with another self-report scale. Study A compared post-operative pain ratings on the NRS with scores on the Faces Pain Scale-Revised (FPS-R) in 69 children age 7-17 years who had undergone a variety of surgical procedures. Study B compared post-operative pain ratings on the NRS with scores on the Visual Analogue Scale (VAS) in 29 children age 9-17 years who had undergone pectus excavatum repair. Study C compared ratings of remembered immunization pain in 236 children who comprised an NRS group and a sex- and age-matched VAS group. Correlations of the NRS with the FPS-R and VAS were r=0.87 and 0.89 in Studies A and B, respectively. In Study C, the distributions of scores on the NRS and VAS were very similar except that scores closest to the no pain anchor were more likely to be selected on the VAS than the NRS. The NRS can be considered functionally equivalent to the VAS and FPS-R except for very mild pain (<1/10). We conclude that use of the NRS is tentatively supported for clinical practice with children of 8years and older, and we recommend further research on the lower age limit and on standardized age-appropriate anchors and instructions for this scale.
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/diagnóstico; Dimensión del Dolor/métodos; Factores de Edad; Valor Predictivo de las Pruebas; Dolor Postoperatorio/psicología; Índice de Severidad de la Enfermedad; Umbral del Dolor/fisiología; Autoevaluación (Psicología); Evaluación de la Discapacidad; Sensibilidad y Especificidad

Morphine added to local anaesthetic improves epidural analgesia in minimally invasive Nuss operation for pectus excavatum. - Yapici, D; Atici, S; Alic, M; Ayan, E; Koksel, O (Br J Anaesth, 2008)
Keywords: Adolescente; Humanos; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Adulto; Dolor Postoperatorio/prevención & control; Morfina; Anestésicos Locales; Analgésicos Opioides/administración & dosificación; Procedimientos Quirúrgicos Mínimamente Invasivos

Intravenous ketoprofen as an adjunct to patient-controlled analgesia morphine in adolescents with thoracic surgery: a placebo controlled double-blinded study. - Rugyte, Danguole; Kokki, Hannu (Eur J Pain, 2007)
BACKGROUND: Surgery to correct pectus deformities entail substantial destruction of the thoracic skeleton and thus may cause significant postoperative pain. AIMS: To evaluate the efficacy of intravenous ketoprofen, a NSAID, as an adjunct to PCA morphine in pain treatment in children having pectus surgery. METHODS: Thirty-one children aged 10-15 years completed the study according to protocol. Children (n=14) in the ketoprofen-group received ketoprofen 1mg/kg i.v. at the skin closure, and at 8 and 16 h after surgery, while children (n=17) in the placebo-group received normal saline, respectively. For rescue analgesia the patient had an access to PCA-morphine. The children expressed their pain by a coloured VAS. RESULTS: Mean cumulative 24h morphine dose used was less in the ketoprofen-group (mean+/-SD: 490+/-240 microg/kg) than in the placebo-group (670+/-200 microg/kg) (mean difference 180 microg/kg, 95% CI for diff: 15-340 microg/kg, P=0.03). The area under the pain intensity-time-curve was lower in the ketorpofen-group (49+/-26 score hour) than in the placebo-group (68+/-24 score hour) (mean difference 21 score hour, 95% CI for diff: 3-40 score hour, P=0.026). There was no difference between the two groups in adverse events, 4/14 in the ketoprofen group and 8/17 in the placebo-group developed oxygen desaturation, and one patient in the ketoprofen-group developed bleeding at 5h after surgery. CONCLUSIONS: Intravenous ketoprofen in adjunct to PCA morphine provided a significant opioid sparing effect and improved analgesia in children having chest wall correction surgery.
Keywords: Adolescente; Humanos; Niño; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Dolor Postoperatorio/prevención & control; Procedimientos Quirúrgicos Torácicos/efectos adversos; Factores de Edad; Dimensión del Dolor/efectos de los fármacos; Método Doble Ciego; Morfina/administración & dosificación; Inyecciones Intravenosas; Relación Dosis-Respuesta a Droga; Autoadministración; Antiinflamatorios no Esteroideos/administración & dosificación; Cetoprofeno/administración & dosificación; Efecto Placebo; Narcóticos/administración & dosificación; Placebos; Sinergismo Farmacológico

A comparison of epidural bupivacaine-fentanyl and bupivacaine-clonidine in children undergoing the Nuss procedure. - Cucchiaro, Giovanni; Adzick, Scott N; Rose, John B; Maxwell, Lynne; Watcha, Mehernoor (Anesth Analg, 2006)
The administration of epidural opioids, though effective for producing analgesia, has severe side effects in most patients. It is unknown whether clonidine can effectively replace opioids and cause fewer side effects. We compared, in this randomized trial, the incidence of vomiting and pruritus as well as the analgesic profile of three different combinations of bupivacaine, fentanyl, and clonidine administered epidurally in patients undergoing the Nuss procedure: bupivacaine + fentanyl, bupivacaine + clonidine, bupivacaine + fentanyl + clonidine. The incidence of side effects was significantly less in the bupivacaine + clonidine group (33%) compared with the bupivacaine + fentanyl (92%) and bupivacaine + fentanyl + clonidine (73%) groups (P = 0.004). Quality of postoperative analgesia was similar in the three groups. No significant complications were observed. In conclusion, clonidine is an effective and safe alternative to epidural opioids.
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Adulto; Bupivacaína/efectos adversos; Dimensión del Dolor; Bupivacaína/administración & dosificación; Método Doble Ciego; Clonidina/administración & dosificación; Fentanilo/administración & dosificación; Fentanilo/efectos adversos; Clonidina/efectos adversos

Open repair of pectus excavatum and carinatum deformities with minimal cartilage resection. - Fonkalsrud, Eric W; Mendoza, Julianne (Am J Surg, 2006)
BACKGROUND: Numerous modifications of the Ravitch open repair of pectus excavatum (PE) and carinatum (PC) have been used by surgeons with inconsistent results. METHODS: During a 3-year period, 275 consecutive patients underwent open repair of PE and PC using a new less invasive technique. A small chip of costal cartilage was resected medially and laterally from each deformed cartilage, allowing it to barely touch the sternum and rib (laterally) after the sternum had been elevated or depressed, and twisted to the desired position. A support strut used for all patients was routinely removed within 6 months. RESULTS: With mean follow-up of 17 months, all but 5 patients regarded the results as very good or excellent. There were no major complications or deaths. CONCLUSION: Open repair using minimal cartilage resection is effective for all variations of PE and PC in patients of all ages, causes only mild pain, and produces good physiologic and cosmetic results.
Keywords: Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adulto; Preescolar; Dolor Postoperatorio; Anciano; Esternón/cirugía; Medición de Riesgo; Persona de Mediana Edad; Estudios de Seguimiento; Estudios de Cohortes; Estética; Esternón/anomalías; Cartílago/cirugía; Toracotomía/métodos

What postoperative outcomes matter to pediatric patients? - Cucchiaro, Giovanni; Farrar, John T; Guite, Jessica W; Li, Yuelin (Anesth Analg, 2006)
Children are often excluded from making decisions related to their medical treatment, and parents' proxy reports are often used. This approach fails to consider that parents and children may differ in their perception of the child's health. In this study, we assessed children's decision-making processes related to postoperative pain management. Forty-five children who underwent an anterior cruciate ligament repair or Nuss procedure for pectus excavatum repair were studied. A standard gamble technique was used to assess children's perceptions of the utility of a hypothetical treatment that would provide them with perfect pain control, with respect to different rates of risk for vomiting during the postoperative period. The maximum risk of vomiting that the overall study population was willing to accept to decrease the pain level to zero was 32% +/- 24%. Girls were willing to take a significantly higher risk (41% +/- 24%) compared to boys (25% +/- 22%) (P = 0.02). Children who actually experienced vomiting before they were questioned were willing to take a higher risk (46% +/- 26%) compared to those who did not (23% +/- 17%) (P = 0.035). Children can express opinions about preferred postoperative outcomes and provide useful input about their care. Girls, more than boys, seem to perceive vomiting as less important than improved pain control in the postoperative period.
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Periodo Posoperatorio; Dolor Postoperatorio/epidemiología; Dolor Postoperatorio/prevención & control; Dolor Postoperatorio/psicología; Analgesia Controlada por el Paciente/estadística & datos numéricos; Estadísticas no Paramétricas; Analgesia Controlada por el Paciente/psicología; Análisis Multivariante; Distribución de Chi-Cuadrado; Toma de Decisiones

[Continuous epidural ropivacaine analgesia in adolescents]. - Geodakian, O S; Tsypin, L E (Anesteziol Reanimatol, 2006)
The paper deals with the efficiency of postoperative analgesia after thoracoplasty in 43 adolescents with the funnel chest. Within the first 64-72 postoperative hours, the patients received a continuous epidural infusion of 0.2% ropivacaine solution at a rate of 0.3 ml/kg/hr. Analyses of hemodynamic parameters and the pain scale demonstrated the efficiency of this postoperative analgesia in 74.4% of the adolescents.
Keywords: Adolescente; Humanos; Niño; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Analgesia Epidural/métodos; Dimensión del Dolor; Esquema de Medicación; Bombas de Infusión; Anestésicos Locales/administración & dosificación; Amidas/administración & dosificación; Ropivacaína; Factores de Tiempo; Anestésicos Locales/uso terapéutico; Amidas/uso terapéutico; Toracoplastia

Nuss procedure improves the quality of life in young male adults with pectus excavatum deformity. - Krasopoulos, George; Dusmet, Michael; Ladas, George; Goldstraw, Peter (Eur J Cardiothorac Surg, 2006)
OBJECTIVE: The Nuss procedure is a minimally invasive pectus repair. This study represents an attempt towards exploring the changes in quality of life and overall satisfaction in young male adults who underwent a Nuss procedure. METHODS: We have included 20 male patients with a median age of 18 years (range: 14-37 years). We have used two specific questionnaires: the two-step Nuss evaluation Questionnaire modified for Adults (NQ-mA) and a new Single Step Questionnaire (SSQ). The data was analysed using Wilcoxon signed rank test to determine statistical significance of differences, with a <0.05 level of significance. Spearman's correlation coefficient was used to assess the correlation between the answers. RESULTS: The primary indication for surgery was cosmetic. Both questionnaires were adequate to measure disease-specific quality-of-life changes after surgery and were able to confirm the positive impact of surgery on both the physical and the physiological well-being of young adults. Statistical analysis of the scoring of the individual questions and the total score of individual patients revealed a statistically significant improvement (p<0.05) following surgery. The SSQ had a highly significant correlation to the NQ-mA questionnaire (correlation coefficient=0.682, p=0.001). Overall, the SSQ revealed a statistically significant improvement (p=0.001) in self-esteem and a high level of satisfaction following the Nuss procedure. Only two patients fell into a low satisfaction group. CONCLUSION: The Nuss procedure has already been shown to have a positive impact on both the physical and psychosocial well-being of children who are suffering from pectus excavatum deformity. We have shown a similar positive impact in young male adults, in the short term.
Keywords: Adolescente; Estudios Retrospectivos; Humanos; Masculino; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adulto; Calidad de Vida; Encuestas y Cuestionarios; Satisfacción del Paciente; Dimensión del Dolor; Complicaciones Posoperatorias; Tórax en Embudo/psicología; Cirugía Torácica Asistida por Video/instrumentación; Cirugía Torácica Asistida por Video/métodos; Procedimientos Quirúrgicos Mínimamente Invasivos/instrumentación

A case report of anesthetic management of the minimally invasive Nuss operation for pectus excavatum. - Ichizawa, Manami; Morimura, Eri; Tsuchiya, Naohisa; Hanafusa, Tetsuji; Shinomura, Tetsutaro (J Anesth, 2005)
We describe the anesthetic management of a patient with pectus excavatum, receiving the minimally invasive Nuss operation, which corrects chest wall deformity by insertion of a convex steel bar (pectus bar). An 8-year-old female patient was scheduled for the Nuss operation. The manipulation of the bar in the thorax was guided by thoracic endoscopy. Anesthesia was maintained with a combination of general and epidural anesthesia. The intraarterial catheter and epidural catheter were inserted after the induction of general anesthesia. During the manipulation of the pectus bar in the anterior mediastinum, a sudden decrease in arterial pressure might occur due to the compression of the heart. Therefore, the intraarterial line was essential for continuous monitoring of arterial pressure. The pectus bar causes severe postoperative pain, and the patient was required to remain at bed rest for several days. Continuous epidural infusion of ropivacaine and morphine eliminated the postoperative pain and enabled the patient to maintain bed rest. For the anesthetic managements of patients undergoing the Nuss operation, close monitoring of arterial pressure intraoperatively and postoperative analgesia are important.
Keywords: Femenino; Humanos; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Toracoscopía/métodos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Anestesia; Anestesia Epidural; Anestesia General; Hemodinámica; Monitoreo Intraoperatorio

Continuous thoracic epidural analgesia with 0.2% ropivacaine for pectus excavatum repair in children. - Barros, Fernanda (Paediatr Anaesth, 2004)
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Fentanilo/uso terapéutico; Dolor Postoperatorio/prevención & control; Estudios Prospectivos; Analgesia Epidural/efectos adversos; Anestesia General; Anestésicos Locales/administración & dosificación; Amidas/administración & dosificación; Ropivacaína; Factores de Tiempo; Infusiones Intravenosas; Anestésicos Locales/uso terapéutico; Anestésicos Locales/efectos adversos; Amidas/uso terapéutico; Amidas/efectos adversos; Anestésicos Intravenosos/uso terapéutico

Reduced hospitalization cost for patients with pectus excavatum treated using minimally invasive surgery. - Inge, T H; Owings, E; Blewett, C J; Baldwin, C E; Cain, W S; Hardin, W; Georgeson, K E (Surg Endosc, 2003)
BACKGROUND: Currently, few data exist regarding the relative costs associated with open and minimally invasive pectus excavatum repair. The aim of this study was to compare the surgical and hospitalization costs for these two surgical techniques and to identify factors responsible for cost differences. METHODS: A retrospective review of hospital charts, patient and parent questionnaires, and hospital accounting records was performed for 68 patients who underwent surgical correction of pectus excavatum between June 1996 and December 1999. RESULTS: In this series, 25 patients underwent open repair, whereas 43 patients underwent minimally invasive repair of pectus excavatum (MIRPE). The patient ages ranged from 4 to 19 years. The average ages for open repair (12 years) and MIRPE (11 years) did not differ significantly. As compared with open repair, MIRPE was associated with a 27% lower overall cost of hospitalization ( p < 0.05). The operating room costs were 12% higher for the patients who underwent MIRPE ( p < 0.05). The mean operative time for open repair was 3 h 15 min, whereas MIRPE required 1 h 10 min ( p < 0.001). The hospital stay for open repair averaged 4.4 days, as compared with 2.4 days for MIRPE ( p < 0.001). In contrast to other published series, the postoperative analgesia after MIRPE in this series consisted of narcotics, ketorolac, and methocarbamol. No patient received epidural analgesia, regardless of the repair technique selected. The postoperative complication rate was 4% in the open group and 14% in the MIRPE group. Most of the patients treated with either open or MIRPE reported postoperative oral narcotic usage for 2 weeks or less and returned to routine activities within 3 weeks. The patients and parents alike reported good to excellent overall outcomes in 85% or more of the open repair cases and 90% or more of the MIRPE cases. CONCLUSIONS: These data demonstrate for the first time that the use of an alternate pain management strategy including, narcotics, NSAIDs, and methocarbamol, but without epidural catheters, results in reduced hospital length of stay and decreased overall hospitalization costs for MIRPE, as compared with open pectus repair. This cost benefit was achieved without compromising pain management or patient satisfaction with surgical care.
Keywords: Adolescente; Estudios Retrospectivos; Humanos; Niño; Toracoscopía/métodos; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Preescolar; Tiempo de Internación/estadística & datos numéricos; Analgésicos/administración & dosificación; Estudios de Seguimiento; Alabama; Control de Costos/métodos; Cuidados Posoperatorios; Hospitalización/economía; Osteotomía/economía; Satisfacción del Paciente/estadística & datos numéricos; Técnicas de Sutura; Tiempo de Internación/economía; Toracoscopía/economía; Tórax en Embudo/economía

[Thoracic epidural analgesia in the postoperative period of pediatric surgery for the repair of pectus excavatum and pectus carinatum]. - Cánovas Martínez, L; Domínguez García, M; Fernández Gil, N; Montes Deza, A; López Alonso, D; Castro Méndez, A (Rev Esp Anestesiol Reanim, 1998)
To assess thoracic analgesia by continuous infusion in surgery to repair pectus excavatum and carinatum in children. This prospective study enrolled 14 children aged 6 to 14 years old scheduled for surgery to correct pectus excavatum and carinatum. After induction of general anesthesia, the T8-T9 epidural space was accessed and a catheter was inserted to T3-T7 with radioscopic monitoring. A loading dose of 0.03-0.04 ml/kg per segment to be blocked (5 segments: T3-T8) of 0.125% bupivacaine and 3 micrograms/ml fentanyl was given to children under 7 years of age; a dose of 0.02-0.03 ml/kg per segment was administered to children over the age of 7 years. A continuous perfusion of 0.1-0.4 ml/kg/h was maintained, with the possibility of additional boluses of 1 ml at 20 min intervals during surgery and the first three days thereafter. An intraoperative bolus was given when the level of blockade was not reached or when mean blood pressure and heart rate increased 15% over baseline. Pain relief was assessed on a numerical scale of 0 to 5 or on a scale of facial icons, depending on the patient's age. During the postoperative period, the pediatric ICU nurse administered a bolus if pain was [symbol see text]3 or heart rate increased 75% over age-based reference values. Top-up analgesia was provided with Metamizole at a dose of 25 mg/kg. No complications attributable to the technique or to sympathetic blockade were observed. All tubes were removed in the operating room. The thoracic epidural catheter was left in place for 70.3 +/- 2.6 h. Mean initial doses of analgesia were 0.45 microgram/kg of fentanyl and 0.2 mg/kg of bupivacaine. The mean number of complementary boluses was 3 +/- 1 during surgery, 5 +/- 2 on the first postoperative day and 4 +/- 1 on the second day. No patient required top-up analgesia on the third day. Hemodynamic stability during surgery and the postoperative period was good. Analgesia was excellent (< 2) for 78.5% of the patients on the first day after surgery, for 85.7% on the second day and for all patients on the third day. We recorded one case of pruritus (7.1%), three of nausea (21.4%) that subsided when butorphanol was given epidurally (20 micrograms/kg), and two cases of light sedation. Thoracic epidural analgesia is effective for alleviating postoperative pain from corrective thoracic surgery in children. Side effects were minimal and no anesthetic complications were observed.
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Tórax en Embudo/cirugía; Analgesia Epidural; Dolor Postoperatorio/prevención & control; Estudios Prospectivos; Dimensión del Dolor; Anestésicos Locales/administración & dosificación; Bupivacaína/administración & dosificación; Fentanilo/administración & dosificación; Cuidados Posoperatorios; Adyuvantes Anestésicos/administración & dosificación

Continuous thoracic epidural infusions for postoperative analgesia after pectus deformity repair. - McBride, W J; Dicker, R; Abajian, J C; Vane, D W (J Pediatr Surg, 1996)
PURPOSE: To determine whether continuous epidural analgesia after repair of a pectus deformity is a viable and safe alternative to high-dose narcotics in children. METHODS: Data were collected prospectively for 19 children (4 to 17 years of age; 15 boys, 4 girls) who underwent pectus excavatum (14) or carinatum (5) repair between June 1, 1991 and July 1, 1994. Seventeen had a thoracic epidural catheter placed for postoperative pain control and two did not. The epidural catheter was routinely plead preoperatively by the anesthesiologist at the T3-T8 level, after induction of general anesthesia. Epidural catheters were test-dosed with local anesthesia alone or in combination with fentanyl, and afterward a continuous epidural infusion was maintained on the floor. Postoperative pain was assessed by nursing and house staff on the Wong-Baker scale, with adjustment of the dose rate or analgesic medication as appropriate. RESULTS: All patients had extubation before leaving the operating room and were sent to the general pediatrics ward after leaving the recovery room. The average duration of the epidural was 69 hours (range, 20 to 116 hours). Sixteen patients received their test epidural dose preoperatively, and one patient had his in the recovery room. Fifteen epidural initially were dosed with bupivicaine (1 to 2 mg/kg) alone or in combination with fentanyl (1 to 2 micrograms/kg). Two patients received initial doses of lidocaine (1 to 1.5 micrograms/kg). Ten of 17 patients received fentanyl (1 microgram/kg/h) with bupivicaine (0.5 to 1.0 mg/kg/h) in the epidural as their maintenance medication, and the remainder received bupivicaine alone at the same dosage rate. Eight of 17 patients required additional intermittent supplemental narcotics, with an average of two doses of intravenous morphine per day (0.1 mg/kg) over the first 3 postoperative days. In contrast, the two patients who did not have an epidural catheter for pain control required high-dose intravenous morphine (0.2 mg/kg) every 2 to 3 hours for the first 3 to 4 postoperative days. No catheter-related complications occurred. CONCLUSION: Thoracic epidural analgesia was completely successful in nine (53%) children who underwent repair of pectus deformity, and effectively reduced the intravenous narcotic demand in the other eight. Pain control was excellent, and no catheter-related complications were encountered. The data show that this method of analgesia in children is a safe and attractive alternative to intravenous narcotics, and eliminates the potential disadvantages of sedation and respiratory compromise.
Keywords: Adolescente; Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Estudios Prospectivos; Preescolar; Esternón/cirugía; Analgésicos Opioides/administración & dosificación; Dimensión del Dolor; Anestésicos Locales/administración & dosificación; Bupivacaína/administración & dosificación; Esternón/anomalías; Fentanilo/administración & dosificación; Quimioterapia Combinada; Analgésicos Opioides/farmacología; Anestésicos Locales/farmacología; Bupivacaína/farmacología; Fentanilo/farmacología; Lidocaína/administración & dosificación; Lidocaína/farmacología; Vermont

[Acupuncture in the postoperative period in patients of the orthopedic-traumatological profile]. - Pashchuk, A Iu; Zavorina, A P (Ortop Travmatol Protez, 1977)
Keywords: Adolescente; Dolor Postoperatorio/terapia; Humanos; Masculino; Niño; Tórax en Embudo/cirugía; Adulto; Persona de Mediana Edad; Enfermedades de la Columna Vertebral/cirugía; Enfermedades Óseas/cirugía; Osteocondritis/cirugía; Terapia por Acupuntura

The Role of Pericardial Window Techniques in the Management of Penetrating Cardiac Injuries in the Hemodynamically Stable Patient: Where Does It Fit in the Current Trauma Algorithm? - Selvakumar, Sruthi; Newsome, Kevin; Nguyen, Truc; McKenny, Mark; Bilski, Tracy; Elkbuli, Adel (Journal of Surgical Research, 2022)

Safety and Feasibility of Laparoscopic Transabdominal Preperitoneal Hernia Repair for Octo- and Nonagenarians. - Kohga, Atsushi; Kawabe, Akihiro; Makino, Akihiro; Yajima, Kiyoshige; Okumura, Takuya; Yamashita, Kimihiro; Isogaki, Jun; Suzuki, Kenji (Journal of Laparoendoscopic & Advanced Surgical Techniques, 2022)

Association of Intercostal Nerve Cryoablation During Nuss Procedure With Complications and Costs - Mehl, Steven C.; Sun, Raphael C.; Anbarasu, Centura R.; Portuondo, Jorge I.; Espinoza, Andres F.; Whitlock, Richard S.; Shah, Sohail R.; Nuchtern, Jed G.; Minifee, Paul K.; Rodriguez, J. Ruben; Le, Louis D.; Stafford, Shawn J.; et al. (The Annals of Thoracic Surgery)
doi: 10.1016/j.athoracsur.2022.04.022

Primary Sjögren’s syndrome and the eye - Bjordal, Oddbjørn; Norheim, Katrine Brække; Rødahl, Eyvind; Jonsson, Roland; Omdal, Roald (Survey of Ophthalmology, 2020)

Systemic Conditions Associated with Severity of Dry Eye Signs and Symptoms in the Dry Eye Assessment and Management Study - Yu, Kimberley; Bunya, Vatinee; Maguire, Maureen; Asbell, Penny; Ying, Gui-Shuang (Ophthalmology, 2021)

Correlation of clinical symptoms and signs with conjunctival gene expression in primary Sjögren syndrome dry eye patients - Liang, H.; Kessal, K.; Rabut, G.; Daull, P.; Garrigue, J.S.; Melik Parsadaniantz, S.; Docquier, M.; Baudouin, C.; Brignole-Baudouin, F. (The Ocular Surface, 2019)

Intraoperative intercostal nerve cryoablation During the Nuss procedure reduces length of stay and opioid requirement: A randomized clinical trial - Graves, Claire E.; Moyer, Jarrett; Zobel, Michael J.; Mora, Roberto; Smith, Derek; O'Day, Maura; Padilla, Benjamin E. (Journal of Pediatric Surgery, 2019)
PURPOSE: Minimally-invasive repair of pectus excavatum by the Nuss procedure is associated with significant postoperative pain, prolonged hospital stay, and high opiate requirement. We hypothesized that intercostal nerve cryoablation during the Nuss procedure reduces hospital length of stay (LOS) compared to thoracic epidural analgesia. DESIGN: This randomized clinical trial evaluated 20 consecutive patients undergoing the Nuss procedure for pectus excavatum between May 2016 and March 2018. Patients were randomized evenly via closed-envelope method to receive either cryoanalgesia or thoracic epidural analgesia. Patients and physicians were blinded to study arm until immediately preoperatively. SETTING: Single institution, UCSF-Benioff Children's Hospital. PARTICIPANTS: 20 consecutive patients were recruited from those scheduled for the Nuss procedure. Exclusion criteria were age < 13 years, chest wall anomaly other than pectus excavatum, previous repair or other thoracic surgery, and chronic use of pain medications. MAIN OUTCOMES AND MEASURES: Primary outcome was postoperative LOS. Secondary outcomes included total operative time, total/daily opioid requirement, inpatient/outpatient pain score, and complications. Primary outcome data were analyzed by the Mann-Whitney U-test for nonparametric continuous variables. Other continuous variables were analyzed by two-tailed t-test, while categorical data were compared via Chi-squared test, with alpha = 0.05 for significance. RESULTS: 20 patients were randomized to receive either cryoablation (n = 10) or thoracic epidural (n = 10). Mean operating room time was 46.5 min longer in the cryoanalgesia group (p = 0.0001). Median LOS decreased by 2 days in patients undergoing cryoablation, to 3 days from 5 days (Mann-Whitney U, p = 0.0001). Cryoablation patients required significantly less inpatient opioid analgesia with a mean decrease of 416 mg oral morphine equivalent per patient (p = 0.0001), requiring 52%-82% fewer milligrams on postoperative days 1-3 (p < 0.01 each day). There was no difference in mean pain score between the groups at any point postoperatively, up to one year, and no increased incidence of neuropathic pain in the cryoablation group. No complications were noted in the cryoablation group; among patients with epidurals, one patient experienced a symptomatic pneumothorax and another had urinary retention. CONCLUSIONS AND RELEVANCE: Intercostal nerve cryoablation during the Nuss procedure decreases hospital length of stay and opiate requirement versus thoracic epidural analgesia, while offering equivalent pain control. TYPE OF STUDY: Treatment study. LEVEL OF EVIDENCE: Level I.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Orthopedic Procedures; Thoracoscopic

Percutaneous Cryoanalgesia: A New Strategy for Pain Management in Pectus Excavatum Surgery - Velayos, María; Alonso, Mercedes; Delgado-Miguel, Carlos; Estefanía-Fernández, Karla; Muñoz-Serrano, Antonio J.; Santamaría, Manuel V. López; Reinoso-Barbero, Francisco; De La Torre, Carlos A. (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2022)
INTRODUCTION: In recent years, pain protocols for pectus excavatum (PE) have incorporated cryoanalgesia through thoracoscopic approach. Since 2019, ultrasound-guided percutaneous cryoanalgesia (PCr) has been applied at our institution, either on the same day as the Nuss procedure or 48 hours before surgery. We carried out a preliminary retrospective review of patients with PE in whom PCr prior to surgery was performed at our institution between 2019 and 2021. MATERIALS AND METHODS: Two groups were evaluated: PCr on the same day (PCrSD) and PCr 48 hours before surgery (PCr48). Despite PCr, patients were treated with "patient-controlled analgesia" (PCA) with opioids for at least 24 hours, switching to conventional intravenous analgesia and oral analgesia in the following days. Demographic, clinical-radiological variables, PCA opioid use, pain grade according to the visual analog scale (VAS), and length of stay (LOS) were compared between the groups. A total of 20 patients were included (12 with PCrSD and 8 with PCr48), without significant differences in demographics or clinical-radiological variables. The overall median time of PCr was 65 minutes (55-127), with no differences between the groups. RESULTS: PCr48 group presented with significantly lower median number of hours of continuous PCA (24 vs. 32 hours; p = 0.031), lower median number of rescue boluses (11 vs. 18; p = 0.042), lower median VAS in the early postoperative hours (2 vs. 5.5; p = 0.043), and lower median LOS (3.5 vs. 5 days). CONCLUSION: PCr performed 48 hours prior to surgery is more effective in terms of PCA requirements, VAS, and LOS when compared with cryoanalgesia on the same day.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Analgesia, Patient-Controlled; Pain Management

Epidural versus PCA Pain Management after Pectus Excavatum Repair: A Multi-Institutional Prospective Randomized Trial - Sujka, Joseph A.; Dekonenko, Charlene; Millspaugh, Daniel L.; Doyle, Nichole M.; Walker, Benjamin J.; Leys, Charles M.; Ostlie, Daniel J.; Aguayo, Pablo; Fraser, Jason D.; Alemayehu, Hanna; Peter, Shawn D. St (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2020)
INTRODUCTION: Postoperative pain control remains the primary reason for inpatient stay after minimally invasive repair of pectus excavatum. In a previous study, our group reported that early pain control was better in patients managed with a thoracic epidural, while late pain control was better in patients managed with patient-controlled analgesia (PCA). After revising our epidural transition and modifying the PCA protocol, we conducted a multi-institutional prospective randomized trial to evaluate these two pain control strategies. MATERIALS AND METHODS: Patients were randomized to epidural or PCA following minimally invasive repair of pectus excavatum with standard protocols for each arm. Primary outcome was length of stay with secondary variables including mean patient pain scores, complications, and parental satisfaction. Scores were pooled for the two groups and reported as means with standard deviation. Results were compared using t-tests and one-way analysis of variance with p-value < 0.05 determining significance. RESULTS: Sixty-five patients were enrolled, 32 epidural and 33 PCA. Enrollment was stopped early when we developed an alternative strategy for controlling these patients' pain. There was no difference in length of stay in hours between the two arms; epidural 111.3 ± 18.5 versus PCA 111.4 ± 51.4, p = 0.98. Longer operative time was found in the epidural group. Nine patients in the epidural group (28%) required a PCA in addition to epidural for adequate pain control. Mean pain scores were lower on postoperative day 0 in the epidural group compared with the PCA groups, but were otherwise similar. CONCLUSION: In our prospective randomized trial, PCA is just as effective as thoracic epidural in decreasing early postoperative pain scores after minimally invasive repair of pectus excavatum.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Length of Stay; Analgesia, Patient-Controlled; Prospective Studies; Analgesia, Epidural; Operative Time

Pectus excavatum: Benefit of randomization - Dalton, Brian G. A.; Gonzalez, Katherine W.; Millspaugh, Daniel L.; Desai, Amita A.; Sharp, Susan W.; St Peter, Shawn D. (Journal of Pediatric Surgery, 2015)
BACKGROUND: Minimally invasive bar repair for pectus patients produces substantial pain which dictates the post-operative hospital course. We have data from 2 randomized trials comparing epidural catheter placement to patient controlled analgesia. The purpose of this study was to compare the outcomes of patients who were enrolled in the trials to those that did not participate in the trials. METHODS: A retrospective chart review was performed on patients not enrolled in the trials to compare to the prospective datasets from October 2006 to June 2014. Perioperative outcomes were examined. RESULTS: There were 135 patients in a study protocol (IS) and 195 patients that were not enrolled in a study (OS). Comparing the entire IS and OS groups, length of stay was less in the IS group, as was time to regular diet. Average pain scores, operative time and complication rates were not significantly different between the groups. Of the IS patients a significantly lower number of patients had epidural failure, requiring substitution of a PCA for pain control. CONCLUSIONS: There are benefits derived from participating in our randomized trials comparing epidural to patient controlled analgesia after bar placement for pectus excavatum regardless of which arm is utilized.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Length of Stay; Analgesia, Patient-Controlled; Pain Management; Prospective Studies; Epidural; Operative Time; Anesthesia, Epidural; Anesthetics; Benefit; Fentanyl; Hydromorphone; Midazolam; Patient controlled analgesia; Pectus Excavatum; Randomization

Epidural versus Patient-Controlled Analgesia after Pediatric Thoracotomy for Malignancy: A Preliminary Review - Gonzalez, Katherine W.; Dalton, Brian G.; Millspaugh, Daniel L.; Thomas, Priscilla G.; St Peter, Shawn David (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2016)
Introduction The use of thoracic epidural is standard in adult thoracotomy patients facilitating earlier mobilization, deep breathing, and minimizing narcotic effects. However, a recent randomized trial in pediatric patients who undergo repair of pectus excavatum suggests patient-controlled analgesia (PCA) produces a less costly, minimally invasive postoperative course compared with epidural. Given that thoracotomy is typically less painful than pectus bar placement, we compared the outcomes of epidural to PCA for pain management after pediatric thoracotomy. Methods A retrospective review of 17 oncologic thoracotomies was performed at a children's hospital from 2004 to 2013. Data points included operative details, epidural or PCA use, urinary catheterization, days to regular diet, days to oral pain regimen, postoperative pain scores, length of stay, and anesthesia charges. Patients were excluded if they did not have epidural or PCA following thoracotomy. Results Six thoracotomies were managed with an epidural and 11 with a PCA. Three epidural patients were opiate naïve compared with two with a PCA. The most common indication for thoracotomy was metastatic osteosarcoma (n = 13). When comparing epidural to PCA, there was no significant difference in days to removal of Foley catheter, regular diet, oral pain control, length of stay, or total operating room time. Postoperative pain scores were also comparable. The mean anesthesia charges were significantly higher in patients with an epidural than with a PCA. Conclusion Epidural catheter and PCA provided comparable pain relief and objective recovery course in children who underwent thoracotomy for oncologic disease; however, epidural catheter placement was associated with increased anesthesia charges, suggesting that PCA is a noninvasive, cost-effective alternative.
Keywords: Humans; Adolescent; Female; Male; Child; Pain, Postoperative; Retrospective Studies; Length of Stay; Analgesia, Patient-Controlled; Pain Measurement; Operative Time; Anesthesia, Epidural; Postoperative Care; Osteosarcoma; Pulmonary Blastoma; Sarcoma, Ewing; Thoracotomy

Impact of Epidural Failures on the Results of a Prospective, Randomized Trial - Desai, Amita; Alemayehu, Hanna; Weesner, Kathryn A.; St Peter, Shawn D. (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2016)
INTRODUCTION: We conducted a prospective randomized trial to evaluate the merits of two established postoperative pain management strategies: thoracic epidural (EPI) versus patient-controlled analgesia (PCA) with intravenous narcotics after minimally invasive repair of pectus excavatum. Pain scores favored the EPI group for the first two postoperative days only. Critics of the trial suggest that if the epidural failure rate was not so high, results may have favored the EPI group. Therefore, we performed a subset analysis of the EPI group to evaluate the impact of these failures. METHODS: Patients for whom epidural catheter could not be placed or whose catheters were removed early owing to dysfunction were compared with those with well-functioning catheters. Those with well-functioning catheters were also compared with the PCA group. A two-tailed independent Student t-test and a two-tailed Fisher exact test were used where appropriate. RESULTS: Of 55 patients in the EPI group, 12 patients (21.8%) had failed placement or required early removal. Comparing those with failed placements with the rest of the group, there was no difference in daily visual analogue scale pain scores or measures of hospital course. Likewise, comparing those with well-functioning catheters only to those in the PCA group, the results of the trial are replicated in terms of pain scores, hospital course, and length of stay. CONCLUSION: In patients with failed epidural therapy, there is no significant difference in postoperative hospital course. Comparing those with well-functioning catheters to those in the PCA group, trial results are replicated-that is, no significant difference in length of stay, time to regular diet, or time to transition to oral medications. Therefore, failure rate in the EPI group did not influence the results of the trial.
Keywords: Humans; Adolescent; Funnel Chest; Pain, Postoperative; Analgesia, Patient-Controlled; Prospective Studies; Pain Measurement; Postoperative Period; Operative Time; Follow-Up Studies; Catheters; Anesthesia, Epidural; Treatment Failure

Pain management for the Nuss procedure: comparison between erector spinae plane block, thoracic epidural, and control - Santana, Lisgelia; Driggers, John; Carvalho, Norman F. (World Journal of Pediatric Surgery, 2022)
OBJECTIVE: Pectus excavatum is a congenital deformity characterized by a caved-in chest wall. Repair requires surgery. The less invasive Nuss procedure is very successful, but postoperative pain management is challenging and evolving. New pain management techniques to reduce opioid reliance include the erector spinae plane (ESP) block. We retrospectively examined opioid consumption after Nuss procedure comparing three pain management techniques: ESP block, thoracic epidural (TE), and patient-controlled analgesia (PCA). METHODS: This retrospective cohort study compared pain management outcomes of three patient groups. Seventy-eight subjects aged 10-18 years underwent Nuss procedure at our institution between January 2014 and January 2020. The primary outcome measure was opioid consumption measured in morphine milligram equivalents. Secondary measures included pain ratings and length of stay (LOS). Pain was quantified using the Numeric Pain Rating Scale. Analysis of variance was performed on all outcome measures. RESULTS: Average cumulative opioid use was significantly lower in the ESP block (67 mg) than the TE (117 mg) (p=0.0002) or the PCA group (172 mg) (p=0.0002). The ESP block and PCA groups both had a significantly shorter average LOS (3.3 and 3.7 days, respectively) than the TE group (4.7 days). ESP block performed best for reducing opioid consumption and LOS. Reduced opioid consumption is key for limiting side effects. This study supports use of ESP block as a superior choice when choosing among the three postoperative pain management options that were evaluated. CONCLUSION: ESP resulted in reduced opioid consumption postoperatively and shorter LOS than TE or PCA for patients undergoing the Nuss procedure for surgical repair of pectus excavatum.
Keywords: pediatrics; thoracic surgery; analgesia; pain

Intercostal cryoablation during Nuss procedure: A large volume single surgeon's experience and outcomes - Sun, Raphael C.; Mehl, Steven C.; Anbarasu, Centura R.; Portuondo, Jorge I.; Espinoza, Andres F.; Whitlock, Richard; Mazziotti, Mark V. (Journal of Pediatric Surgery, 2021)
BACKGROUND: Recent studies have shown intercostal cryoablation(IC) during the Nuss procedure decreases hospital length of stay(LOS) and opioid administration. However, few studies have also evaluated the risk of postoperative complications related to IC. METHODS: We performed a single center retrospective analysis of all patients who underwent Nuss procedure by one surgeon from 2/2016 to 2/2020, comparing intraoperative IC to other pain management modalities(non-IC). Primary outcomes were postoperative complications, hospital LOS, and opioid administration. Multivariate analysis was performed with outcomes reported as regression coefficients(RC) or odds ratios(OR) with 95% confidence interval. RESULTS: IC was associated with decreased hospital LOS (RC -1.91[-2.29 to -1.54], less hospital opioid administration (RC -4.28[-5.13 to -3.43]), and less discharge opioid administration (RC -3.82[-5.23 to -2.41]). With respect to postoperative complications, IC decreased the odds of urinary retention (OR 0.16[0.06 to 0.44]); however, increased the odds of slipped bars requiring reoperation (OR 36.65[5.04-266.39]). CONCLUSIONS: Our single surgeon experience controls for surgeon variability and demonstrates intraoperative IC for the Nuss procedure is an effective pain management modality that decreases hospital LOS and opioid use during hospitalization and at discharge; however, it is associated with increased odds of slipped bars requiring reoperation. LEVEL OF EVIDENCE: III.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Cryosurgery; Intercostal cryoablation; Nuss; Opioid; Abbreviations; Forced expiratory volume (FEV); Forced vital capacity (FVC); Haller index (HI); intercostal cryoablation (IC); interquartile ranges (IQR); length of stay (LOS); multiple polyester (p-dioxanone) sutures (PDS); odds ratio (OR); oral morphine equivalents (OME/kg); patient-controlled analgesia (PCA); peripheral nerve block (PNB); regression coefficient (RC); Surgeons; thoracic epidural (TE)

Cryoanalgesia is Associated With Decreased Postoperative Opioid Use in Minimally Invasive Repair of Pectus Excavatum - Arshad, Seyed A.; Ferguson, Dalya M.; Garcia, Elisa I.; Hebballi, Nutan B.; Buchanan, Allison C.; Tsao, KuoJen (The Journal of Surgical Research, 2022)
BACKGROUND: Postoperative pain control is challenging after pectus excavatum repair. We aimed to understand the impact that cryoanalgesia had on opioid utilization and outcomes of pediatric patients undergoing minimally invasive repair of pectus excavatum (MIRPE). METHODS: A single-center retrospective cohort study was conducted of all patients (< 18 y) who underwent MIRPE (2011-2019). Patients receiving cryoanalgesia were compared to those who did not. The primary outcome was total postoperative, inpatient, opioid use, measured as milligrams of oral morphine equivalents per kilogram (OME/kg). Univariate and multivariable analyses were performed. RESULTS: Of 35 patients, 20 received cryoanalgesia (57%). Baseline characteristics were similar. Patients who received cryoanalgesia had a lower opioid requirement: median 2.3 mg OME/kg (IQR 1.2-3.1), versus 4.9 mg OME/kg (IQR 2.9-5.8), P < 0.001. Accounting for receipt of cryoanalgesia, epidural, and/or patient-controlled analgesia, cryoanalgesia was associated with a 3.3 mg OME/kg reduction in opioid use (P < 0.001). Median length of stay (LOS) was shorter in cryoanalgesia patients: 3.1 d (IQR 2.3-3.4), versus 5.1 d (IQR 4.3-5.4), P < 0.001. Complications within 90 d were similar between groups. CONCLUSIONS: Cryoanalgesia is an effective adjunctive pain control modality for patients undergoing MIRPE. Use of cryoanalgesia was associated with lower postoperative opioid requirements and shorter LOS, without increased short-term complications, and should be considered for enhanced recovery after MIRPE.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryoanalgesia; Length of stay; Minimally invasive repair of pectus excavatum; Pain control

Do health beliefs affect pain perception after pectus excavatum repair? - Sujka, Joseph; St Peter, Shawn; Mueller, Claudia M. (Pediatric Surgery International, 2018)
PURPOSE: The pain experience is highly variable among patients. Psychological mindsets, in which individuals view a particular characteristic as either fixed or changeable, have been demonstrated to influence people's actions and perceptions in a variety of settings including school, sports, and interpersonal. The purpose of this study was to determine if health mindsets influence the pain scores and immediate outcomes of post-operative surgical patients. METHODS: As part of a multi-institutional, prospective, randomized clinical trial involving patients undergoing a minimally invasive pectus excavatum repair of pectus excavatum, patients were surveyed to determine whether they had a fixed or growth health mindset. Their post-operative pain was followed prospectively and scored on a Visual Analog Scale and outcomes were measured according to time to oral pain medication use. RESULTS: Fifty patients completed the Health Beliefs survey, 17 had a fixed mindset (8 epidural, 9 PCA) and 33 had a growth mindset (17 epidural, 16 PCA). Patients with a growth mindset had lower post-operative pain scores than patients with a fixed mindset although pain medication use was not different. CONCLUSION: This is the first usage of health mindsets as a means to characterize the perception of pain in the post-operative period. Mindset appears to make a difference in how patients perceive and report their pain. Interventions to improve a patient's mindset could be effective in the future to improve pain control and patient satisfaction.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesia, Patient-Controlled; Prospective Studies; Attitude to Health; Fixed; Growth; Mindset; Pain Measurement; Pain Perception; Pain scores; Patient Satisfaction; Postoperative Period; Thoracoplasty; Visual Analog Scale

Perioperative anesthetic and surgical complications of the Nuss procedure - Umuroglu, Tumay; Bostancı, Korkut; Thomas, David Terence; Yuksel, Mustafa; Gogus, F. Yilmaz (Journal of Cardiothoracic and Vascular Anesthesia, 2013)
OBJECTIVE: The Nuss procedure is a chest wall remodeling surgery performed in patients with pectus excavatum. This study was performed to analyze perioperative surgical and anesthetic complications with the Nuss procedures. DESIGN: A retrospective analysis. SETTING: An academic hospital. PARTICIPANTS: Two hundred fourteen patients (children, adolescents, and adults) undergoing the Nuss procedure over 6 years. INTERVENTIONS: Patient age and sex, premorbid diseases, indications for surgery, patient position during the procedure, the length of surgery, time to hospital discharge, postoperative analgesia method, and the presence of perioperative complications were recorded. MEASUREMENTS: No mortality was observed. The overall complication rate was 18.7%, but the overall event rate was 42.6% (91 events in 40 patients). Intraoperative hypotension, tachycardia, and hypercapnia were the most common complications (4.7%), followed by postoperative ileus (3.2%), pneumothorax (right, left, or bilateral; 4.2%), lung parenchymal laceration (2.3%), and postoperative nausea and vomiting (2.3%). Two patients had an ulnar nerve palsy and 1 patient had a brachial nerve palsy as a result of surgical position. CONCLUSION: Although the Nuss procedure is reported to be minimally invasive, some serious complications concerning both surgery and anesthesia should not be overlooked.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Thoracic Surgical Procedures; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Length of Stay; Analgesia, Patient-Controlled; Postoperative Complications; Forced Expiratory Volume; Vital Capacity; Anesthesia, General; Intraoperative Complications; Perioperative Care; Preanesthetic Medication; Respiratory Function Tests; Supine Position

Epidural analgesia versus intravenous patient-controlled analgesia following minimally invasive pectus excavatum repair: a systematic review and meta-analysis - Stroud, Andrea M.; Tulanont, Darena D.; Coates, Thomasena E.; Goodney, Philip P.; Croitoru, Daniel P. (Journal of Pediatric Surgery, 2014)
BACKGROUND/PURPOSE: The minimally invasive pectus excavatum repair (MIPER) is a painful procedure. The ideal approach to postoperative analgesia is debated. We performed a systematic review and meta-analysis to assess the efficacy and safety of epidural analgesia compared to intravenous Patient Controlled Analgesia (PCA) following MIPER. METHODS: We searched MEDLINE (1946-2012) and the Cochrane Library (inception-2012) for randomized controlled trials (RCT) and cohort studies comparing epidural analgesia to PCA for postoperative pain management in children following MIPER. We calculated weighted mean differences (WMD) for numeric pain scores and summarized secondary outcomes qualitatively. RESULTS: Of 699 studies, 3 RCTs and 3 retrospective cohorts met inclusion criteria. Compared to PCA, mean pain scores were modestly lower with epidural immediately (WMD -1.04, 95% CI -2.11 to 0.03, p=0.06), 12 hours (WMD -1.12; 95% CI -1.61 to -0.62, p<0.001), 24 hours (WMD -0.51, 95%CI -1.05 to 0.02, p=0.06), and 48 hours (WMD -0.85, 95% CI -1.62 to -0.07, p=0.03) after surgery. We found no statistically significant differences between secondary outcomes. CONCLUSIONS: Epidural analgesia may provide superior pain control but was comparable with PCA for secondary outcomes. Better designed studies are needed. Currently the analgesic technique should be based on patient preference and institutional resources.
Keywords: Humans; Analgesia; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Length of Stay; Analgesia, Patient-Controlled; Analgesia, Epidural; Pain control; Cost-Benefit Analysis; Epidural; Minimally invasive pectus excavatum repair; Nuss; Operative Time; Research Design

Bilateral PECS II Block is Associated with Decreased Opioid Consumption and Reduced Pain Scores for up to 24 hours After Minimally Invasive Repair of Pectus Excavatum (Nuss Procedure): A Retrospective Analysis - Sertcakacilar, Gokhan; Kose, Selcuk (Journal of Cardiothoracic and Vascular Anesthesia, 2022)
OBJECTIVE(S): Compared to the open surgical technique, the minimally invasive repair of pectus excavatum (MIRPE; Nuss procedure) is a thoracoscopic technique designed to minimize intraoperative tissue damage. It still causes severe postoperative pain due to the insertion and pressure of the retrosternal bar used to raise the sternum and stabilize the chest. This study aimed to identify associations between ultrasound-guided PECS-II block and postoperative analgesia after the Nuss procedure. DESIGN: A retrospective cohort study SETTING: Single-center, training and research hospital affiliated with a university PARTICIPANTS: From Jan 1, 2018 to Nov 15, 2021, 171 consecutive patients were identified who underwent MIRPE surgery under general anesthesia. All patients received intravenous (I) patient-controlled analgesia (PCA) with or without PECS-II blocks for postoperative analgesia. One hundred twenty-five patients who met the inclusion criteria were evaluated. INTERVENTIONS: Demand-only morphine intravenous PCA was used for postoperative pain management in the PECS and control groups. Bilateral PECS-II block with 0.25% bupivacaine was performed in to the PECS group. MEASUREMENTS AND MAIN RESULTS: The primary outcome was postoperative opioid consumption, calculated as mg/kg of IV morphine. Secondary outcomes included Numeric Rating Scale (NRS) pain scores at rest (static) and with movement (dynamic) recorded 1, 4, 8, 12, 24 h after surgery. Postoperative morphine consumption was significantly lower in the PECS group than in the control group over the first 24 hours postoperatively: 0.325 mg/kg vs. 0.425 mg/kg (p<0.001). Static and dynamic NRS values were significantly lower in the PECS group for the first 12 postoperative hours (p <0.05). CONCLUSIONS: Bilateral PECS-II block is associated with decreased pain scores for up to 12 hours, and with decreased opioid consumption for up to 24 hours, following minimally invasive repair of pectus excavatum (Nuss procedure) in adolescents. PECS-II block in this context has not been previously described.
Keywords: Humans; Adolescent; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Analgesics, Opioid; Pain Measurement; MIRPE; Nerve Block; pectus excavatum; Morphine; numerical rating scale; Pectoral nerve block; postoperative analgesia

Randomized trial of epidural vs. subcutaneous catheters for managing pain after modified Nuss in adults - Jaroszewski, Dawn E.; Temkit, M'hamed; Ewais, MennatAllah M.; Luckritz, Todd C.; Stearns, Joshua D.; Craner, Ryan C.; Gaitan, Brantley D.; Ramakrishna, Harish; Thunberg, Christopher A.; Weis, Ricardo A.; Myers, Kelly M.; Merritt, Marianne V.; et al. (Journal of Thoracic Disease, 2016)
BACKGROUND: Minimally invasive repair of pectus excavatum (MIRPE) is now performed in adults. Managing adult patients' pain postoperatively has been challenging due to increased chest wall rigidity and the pressure required for supporting the elevated sternum. The optimal pain management regimen has not been determined. We designed this prospective, randomized trial to compare postoperative pain management and outcomes between thoracic epidural analgesia (TEA) and bilateral subcutaneous infusion pump catheters (On-Q). METHODS: Patients undergoing MIRPE (modified Nuss) underwent random assignment to TEA or On-Q group. Both groups received intravenous, patient-controlled opioid analgesia, with concomitant delivery of local anesthetic. Primary outcomes were length of stay (LOS), opioid use, and pain scores. RESULTS: Of 85 randomly assigned patients, 68 completed the study [52 men, 76.5%; mean (range) age, 32.2 (20.0-58.0) years; Haller index, 5.9 (range, 3.0-26.7)]. The groups were equally matched for preoperative variables; however, the On-Q arm had more patients (60.3%). No significant differences were found between groups in mean daily pain scores (P=0.52), morphine-equivalent opioid usage (P=0.28), or hospital stay 3.5 vs. 3.3 days (TEA vs. On-Q; P=0.55). Thirteen patients randomized to TEA refused the epidural and withdrew from the study because they perceived greater benefit of the On-Q system. CONCLUSIONS: Postoperative pain management in adults after MIRPE can be difficult. Both continuous local anesthetic delivery by TEA and On-Q catheters with concomitant, intravenous, patient-controlled anesthesia maintained acceptable analgesia with a reasonable LOS. In our cohort, there was preference for the On-Q system for pain management.
Keywords: postoperative pain; funnel chest; Minimally invasive surgery; pectus excavatum (PE); postoperative care

Epidural analgesia versus intravenous analgesia after minimally invasive repair of pectus excavatum in pediatric patients: a systematic review and meta-analysis - Heo, Min Hee; Kim, Ji Yeon; Kim, Jung Hyeon; Kim, Kyung Woo; Lee, Sang Il; Kim, Kyung-Tae; Park, Jang Su; Choe, Won Joo; Kim, Jun Hyun (Korean Journal of Anesthesiology, 2021)
BACKGROUND: Postoperative pain control after the minimally invasive repair of pectus excavatum (MIRPE) is essential, but there is a controversy about a better analgesic method between epidural and intravenous (IV) analgesia. This systematic review and meta-analysis aimed to compare the effect of epidural versus IV analgesia following MIRPE. METHODS: We searched PubMed, MEDLINE, EMBASE, Cochrane Central Register, and ClinicalTrials.gov for randomized controlled trials (RCTs) dated up to 31st May 2021. The primary outcome was the area under the curve (AUC) of the weighted mean visual analog scale (VAS) after MIRPE. The secondary outcomes were postoperative nausea, operation time, total operating room time, and postoperative length of hospital stay. RESULTS: Four RCTs involving 243 patients were finally included in this meta-analysis. The AUC of the weighted mean VAS was 343.62 in the epidural group and 375.24 in the IV group. The epidural group showed lower VAS than the IV group at 12 to 48 h after the surgery. Postoperative nausea, operation time and length of hospital stay was not different between two groups. The epidural group had a significantly longer total operating room time due to epidural catheter insertion time. CONCLUSIONS: Epidural analgesia after the MIRPE had a better analgesic effect than IV analgesia. However, IV analgesia may also be a viable option, and physicians should wisely choose analgesic modalities after MIRPE.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Pain Management; Analgesia, Epidural; Postoperative pain; Funnel chest; Epidural analgesia; Intravenous administration; Minimally invasive surgical procedures; Statistics; Systematic review

Double-bar application decreases postoperative pain after the Nuss procedure - Nagaso, Tomohisa; Miyamoto, Junpei; Kokaji, Kiyokazu; Yozu, Ryohei; Jiang, Hua; Jin, HongMei; Tamaki, Tamotsu (The Journal of Thoracic and Cardiovascular Surgery, 2010)
OBJECTIVE: This biomechanical study aims to elucidate whether additional bar application increases postoperative pain after the Nuss procedure for pectus excavatum. METHODS: Clinical evaluation: The intensity of postoperative pain was compared between patients for whom a single-bar was used (single-bar group: n = 14) and those for whom double bars (double-bar group: n = 10) were used to correct the thoracic deformity. The evaluation was performed by referring to the frequency with which local anesthetics were self-injected in a patient-controlled anesthetic system and how many days were needed for the patients to resume ambulation. Theoretical evaluation: An original simulation system for the Nuss procedure was developed by producing 3-dimensional finite element analysis models from computed tomographic data of patients with pectus excavatum. With this system, single-bar and double-bar placement was simulated separately for the thorax models of the double-bar group. The stresses occurring on the thoraces were then compared between the two situations. RESULTS: Clinical evaluation: Self-injection of local anesthetic was more frequent for the single-bar group than for the double-bar group; single-bar patients restarted ambulation later than the double-bar group. Theoretical evaluation: Stresses on the thoraces were smaller when double bars were applied than when a single bar was applied. CONCLUSIONS: Performing double-bar placement decreases postoperative pain. Therefore, surgeons should not hesitate to perform double-bar correction in patients in whom the deformity extends to multiple intercostal spaces, requiring correction of the thorax shape at multiple sites.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Orthopedic Procedures; Analgesia, Patient-Controlled; Pain Measurement; Anesthetics, Local; Time Factors; Biomechanical Phenomena; Computer Simulation; Finite Element Analysis; Stress, Mechanical; Tomography, X-Ray Computed; Recovery of Function; Models, Anatomic; Orthopedic Equipment; Self Administration; Walking

Pectus excavatum repair: experience with standard and minimal invasive techniques - Molik, K. A.; Engum, S. A.; Rescorla, F. J.; West, K. W.; Scherer, L. R.; Grosfeld, J. L. (Journal of Pediatric Surgery, 2001)
BACKGROUND/PURPOSE: The Nuss procedure is a minimally invasive pectus repair that helps avoid cartilage resection and osteotomy. This report compares outcomes in patients undergoing a standard pectus repair to patients with the Nuss procedure. METHODS: One hundred three children (ages 5 to 20 years) with severe pectus excavatum underwent repair. Patients were evaluated for type of repair performed, associated anomalies, cardiopulmonary function, operating time, analgesia requirements, complications, length of hospital stay, hospital and operative charges, and cosmetic result. Statistical analysis was performed using the Mann-Whitney rank sum test. RESULTS: There were 68 patients (average age, 12.6 years) in the standard group and 35, (average age, 9.5 years) in the Nuss group. Associated anomalies were found in 6 standard group and 2 Nuss group patients. Average operating time in Nuss was 3.3 hours and in open procedures, 4.7 hours. Postoperative complications occurred in 13 (20%) standard repair patients and 15 (43%) after the Nuss. In the standard group, 14 patients received intrathecal and 3 received epidural analgesia, while 35 (52%) required an intravenous patient-controlled anesthetic device (PCA; average, 1.8 days). In the Nuss group, 25 patients (71%) received epidural anesthesia (average, 3 days), and 31 (89%) utilized PCA (average 3.8 days). Four (6%) standard patients and 8 Nuss patients (29%) required reoperation. Length of stay averaged 4.0 days (range 2 to 30) in the standard group and 4.8 days (range, 2 to 11) in the Nuss group. Average operating room charge was $8,325 in the standard group and $9,480 in the Nuss group. Average hospital charge was $4,137 for the standard patient and $4,044 for the Nuss group. Analgesic requirements and length of hospital stay were increased (P <.05). The complication rate and operative and hospital charges were similar between groups. CONCLUSIONS: Although the Nuss repair is associated with shorter operating time, smaller incisions, and less dissection, early results indicate few other advantages. Drawbacks of the Nuss procedure include high complication and reoperation rates and lack of efficacy in older teenagers and those with connective tissue disorders. Long-term follow-up will be necessary to determine final cosmetic and functional outcomes and define the overall risks and benefits of this procedure as compared with the standard technique.
Keywords: Humans; Adolescent; Adult; Female; Male; Child; Funnel Chest; Treatment Outcome; Minimally Invasive Surgical Procedures; Length of Stay; Postoperative Complications; Child, Preschool; Risk Factors; Plastic Surgery Procedures

Outcomes Using Cryoablation for Postoperative Pain Control in Children Following Minimally Invasive Pectus Excavatum Repair - Sujka, Joseph; Benedict, Leo Andrew; Fraser, Jason D.; Aguayo, Pablo; Millspaugh, Daniel L.; St Peter, Shawn D. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2018)
PURPOSE: Pain is the main factor that determines the postoperative course for patients undergoing pectus bar placement. Cryoablation of the intercostal nerves has been suggested to mitigate this pain. We instituted a protocol for using intercostal cryoablation and report our early results compared to our immediately previous cohort. MATERIALS AND METHODS: A retrospective study was conducted on patients undergoing minimally invasive repair for pectus excavatum between January 1, 2017, and August 21, 2017. Demographic data, anthropometrics, operative times, type and duration of patient analgesia, and postoperative length of stay were collected. Descriptive statistics were performed with all means reported ± standard deviations. Comparisons between groups were analyzed on STATA using T-tests with a P value <.05 determined as significant. RESULTS: Twenty-eight patients were treated for pectus excavatum during the study period with 9 (32%) undergoing cryoablation. Mean number of rib spaces ablated was 5 ± 0.53 with no reported intraoperative complications. Mean operative time was 30 minutes longer in the cryoablation group (P = .00). Days to only oral pain medication was shorter in the cryoablation group, (1.22 ± 0.66 day versus 2.63 ± 0.68 day, P = .00). Length of stay, in days, was shorter in the cryoablation group (1.4 ± 0.72 days versus 4.0 ± 1.0 days, P = .00). There were no reported complications from cryoablation or bar placement during the study period. Days to discontinuation of oral narcotics were less in the cryoablation group (8.2 ± 7.0 versus 18.2 ± 10.4, P = .00). CONCLUSION: Cryoablation after pectus bar placement dramatically decreases narcotic usage and postoperative length of stay.
Keywords: Humans; Adolescent; Female; Male; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Minimally Invasive Surgical Procedures; Cryosurgery; Intercostal Nerves; Length of Stay; Operative Time; Cohort Studies; cryoablation; epidural; minimally invasive; Narcotics; patient-controlled anesthesia; pectus excavatum

Scoring of Deformed Costal Cartilages Reduces Postoperative Pain after Nuss Procedure for Pectus Excavatum - Nagasao, Tomohisa; Hamamoto, Yusuke; Tamai, Motoki; Kogure, Tetsukuni; Jiang, Hua; Takano, Naoki; Tanaka, Yoshio (The Thoracic and Cardiovascular Surgeon, 2016)
OBJECTIVE: The present study aims to elucidate whether or not scoring deformed cartilages reduces postoperative pain after the Nuss procedure for pectus excavatum patients. METHODS: A total of 46 pectus excavatum patients for whom the Nuss procedure was conducted were included in the study. The patients were categorized into two groups, depending on whether or not the supplementary maneuver of scoring deformed cartilages was performed in addition to the Nuss procedure. Patients for whom deformed costal cartilages were scored were categorized as the Scoring Group (n = 24); those who received no such scoring were categorized as the Non-Scoring Group (n = 22). After evaluating the maximum stresses occurring on the thoraces by means of dynamic simulation using finite element analyses, intergroup comparison of the maximum von-Mises stress values was performed. Furthermore, after quantifying postoperative pain as the frequency with which patients injected anesthetics through an epidural pain-control system within 2 postoperative days, the degree of pain was compared between the two groups. RESULTS: The maximum stresses occurring on the thorax were significantly greater for the Non-Scoring Group than for the Scoring Group; injection frequency was also greater for the Non-Scoring Group (average 4.9 times for 2 days) than for the Scoring Group (average 2.5 times for 2 days). CONCLUSION: High stresses occur due to the performance of the Nuss procedure, causing postoperative pain. The stresses can be reduced by performing supplementary scoring on deformed cartilages. Accordingly, postoperative pain is reduced.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Orthopedic Procedures; Analgesia, Patient-Controlled; Pain Measurement; Time Factors; Biomechanical Phenomena; Computer Simulation; Costal Cartilage; Elastic Modulus; Finite Element Analysis; Sternum; Stress, Mechanical; Tomography, X-Ray Computed

Postoperative Pain Outcomes After Nuss Procedures: Comparison of Epidural Analgesia, Continuous Infusion of Local Anesthetic, and Preoperative Self-Hypnosis Training - Manworren, Renee C. B.; Anderson, Matthew N.; Girard, Eric D.; Ruscher, Kimberly A.; Verissimo, Ana Maria; Palac, Hannah; Weiss, Richard; Rader, Christine; Hight, Donald (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2018)
BACKGROUND/PURPOSE: The Nuss procedure to correct pectus excavatum is associated with severe postoperative pain. The purpose of this retrospective study was to compare pain management outcomes of thoracic epidural analgesia and continuous infusion of local anesthetic (CILA) with and without preoperative self-hypnosis training (SHT) after Nuss procedure (4 treatment groups). METHODS: Between February 2010 and December 2013, 24 of 53 adolescents who underwent Nuss procedure received SHT. Of these, 16 received thoracic epidural analgesia and 8 received CILA postoperatively. Of the 29 patients who did not receive SHT, 19 received thoracic epidural analgesia and 10 received CILA. All patients received intravenous patient-controlled opioid analgesia and intravenous nonsteroidal anti-inflammatory drugs (IVNSAIDs) and then were transitioned to oral opioids and NSAIDs. Postoperative mean and maximum pain scores, opioid (morphine equivalents) use and side effects, and hospital length of stay (LOS) were compared between groups. RESULTS: Patients who received SHT reported lower mean (P = .0047) and maximum (P = .0028) pain scores and used less morphine equivalents/hour over time (P = .046) compared to patients who did not receive SHT. Patients who received thoracic epidural analgesia reported lower mean (P = .0092) and maximum (P = .0083) postoperative pain scores and used more morphine equivalents/hour (P = .01) compared to those who received CILA. In addition, patients who received SHT and CILA had shorter LOS (P = .0013) than patients who received thoracic epidural analgesia without SHT. CONCLUSIONS: SHT before pectus excavatum repair by Nuss procedure results in less postoperative pain and requires less morphine equivalents over time for postoperative pain management. Opioid-sparing CILA, when paired with SHT, results in shorter LOS.
Keywords: Humans; Adolescent; Female; Male; Young Adult; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Analgesics, Opioid; Length of Stay; Orthopedic Procedures; Analgesia, Patient-Controlled; Pain Management; Pain Measurement; Analgesia, Epidural; pectus excavatum; Anesthesia, Local; Anesthetics, Local; continuous infusion of local anesthetic; epidural analgesia; hypnosis; Hypnosis; pediatric surgery; postoperative pain; Preoperative Care; Self-Management; thoracic

Bilateral PECS II Block is Associated with Decreased Opioid Consumption and Reduced Pain Scores for up to 24 hours After Minimally Invasive Repair of Pectus Excavatum (Nuss Procedure): A Retrospective Analysis. - Sertcakacilar, Gokhan; Kose, Selcuk (Journal of cardiothoracic and vascular anesthesia, 2022)
OBJECTIVE(S): Compared to the open surgical technique, the minimally invasive repair of pectus excavatum (MIRPE; Nuss procedure) is a thoracoscopic technique designed to minimize intraoperative tissue damage. It still causes severe postoperative pain due to the insertion and pressure of the retrosternal bar used to raise the sternum and stabilize the chest. This study aimed to identify associations between ultrasound-guided PECS-II block and postoperative analgesia after the Nuss procedure., DESIGN: A retrospective cohort study SETTING: Single-center, training and research hospital affiliated with a university PARTICIPANTS: From Jan 1, 2018 to Nov 15, 2021, 171 consecutive patients were identified who underwent MIRPE surgery under general anesthesia. All patients received intravenous (I) patient-controlled analgesia (PCA) with or without PECS-II blocks for postoperative analgesia. One hundred twenty-five patients who met the inclusion criteria were evaluated., INTERVENTIONS: Demand-only morphine intravenous PCA was used for postoperative pain management in the PECS and control groups. Bilateral PECS-II block with 0.25% bupivacaine was performed in to the PECS group., MEASUREMENTS AND MAIN RESULTS: The primary outcome was postoperative opioid consumption, calculated as mg/kg of IV morphine. Secondary outcomes included Numeric Rating Scale (NRS) pain scores at rest (static) and with movement (dynamic) recorded 1, 4, 8, 12, 24 h after surgery. Postoperative morphine consumption was significantly lower in the PECS group than in the control group over the first 24 hours postoperatively: 0.325 mg/kg vs. 0.425 mg/kg (p<0.001). Static and dynamic NRS values were significantly lower in the PECS group for the first 12 postoperative hours (p <0.05)., CONCLUSIONS: Bilateral PECS-II block is associated with decreased pain scores for up to 12 hours, and with decreased opioid consumption for up to 24 hours, following minimally invasive repair of pectus excavatum (Nuss procedure) in adolescents. PECS-II block in this context has not been previously described. Copyright © 2022 The Author(s). Published by Elsevier Inc. All rights reserved.
Keywords: Humans; Adolescent; Retrospective Studies; Analgesics, Opioid; Morphine; *Funnel Chest; *Nerve Block; Funnel Chest/su [Surgery]; Minimally Invasive Surgical Procedures/mt [Methods]; Nerve Block/mt [Methods]; Pain Measurement/mt [Methods]; Pain, Postoperative/di [Diagnosis]; Pain, Postoperative/dt [Drug Therapy]; Pain, Postoperative/et [Etiology]

Postoperative management of pediatric patients undergoing minimally invasive repair of pectus excavatum: Where are we now?. - Kirupaharan, Sawmmiya; Briatico, Daniel; Robinson, Tessa; Fitzgerald, Peter; Walton, J Mark (Journal of pediatric surgery, 2022)
PURPOSE: Minimally invasive repair of pectus excavatum (MIRPE) often leads to a painful and challenging recovery period. This study aims to describe the postoperative management of pediatric patients undergoing MIRPE and compare postoperative outcomes between patients using different routes of postoperative analgesia., METHODS: Retrospective chart review of pediatric patients who underwent MIRPE from July 2003 to September 2019 at a single pediatric tertiary care center. Data on pain management and course of hospital stay were ascertained. Descriptive statistics, Mann-Whitney U and Pearson Chi-Square tests were used to analyze data. A p-value <0.05 was considered significant., RESULTS: Of the 115 patients identified, 58 (50.4%) managed pain postoperatively using thoracic epidural and 57 (49.6%) used intravenous patient-controlled analgesia (IVPCA). The transition from the predominant use of epidural to IVPCA for MIRPE occurred between 2012 and 2013. Higher pain scores were reported by the IVPCA group at 6 h (p<0.001) and 12 h (p<0.001) postoperative. Patients using IVPCA had lower postoperative opioid consumption (p<0.001) and switched to oral opioids sooner than the epidural group (p<0.001). Fewer patients in the IVPCA group required urinary catheterization (p<0.001). Patients using IVPCA had a shorter hospital stay (4 days [IQR 4-5]) compared to the epidural group (5.5 [IQR 5-6]; p<0.001). Readmission was comparable at 3.48% in the total sample., CONCLUSION: Patients using intravenous patient-controlled analgesia reported higher pain scores however, this route of analgesia was associated with shorter hospital stay. Prospective studies designed to address moderator variables are required to confirm findings and develop standardized recovery protocols. Copyright © 2022 Elsevier Inc. All rights reserved.
Keywords: Humans; Child; Retrospective Studies; Analgesics, Opioid; Prospective Studies; *Funnel Chest; Funnel Chest/su [Surgery]; Minimally Invasive Surgical Procedures/mt [Methods]; Pain, Postoperative/dt [Drug Therapy]; Pain, Postoperative/et [Etiology]; Analgesia, Patient-Controlled/mt [Methods]; Funnel Chest/et [Etiology]

Percutaneous Cryoanalgesia: A New Strategy for Pain Management in Pectus Excavatum Surgery. - Velayos, Maria; Alonso, Mercedes; Delgado-Miguel, Carlos; Estefania-Fernandez, Karla; Munoz-Serrano, Antonio J; Santamaria, Manuel V Lopez; Reinoso-Barbero, Francisco; De La Torre, Carlos A (European journal of pediatric surgery : official journal of Austrian Association of Pediatric Surgery ... [et al] = Zeitschrift fur Kinderchirurgie, 2022)
INTRODUCTION: In recent years, pain protocols for pectus excavatum (PE) have incorporated cryoanalgesia through thoracoscopic approach. Since 2019, ultrasound-guided percutaneous cryoanalgesia (PCr) has been applied at our institution, either on the same day as the Nuss procedure or 48 hours before surgery. We carried out a preliminary retrospective review of patients with PE in whom PCr prior to surgery was performed at our institution between 2019 and 2021., MATERIALS AND METHODS: Two groups were evaluated: PCr on the same day (PCrSD) and PCr 48 hours before surgery (PCr48). Despite PCr, patients were treated with "patient-controlled analgesia" (PCA) with opioids for at least 24 hours, switching to conventional intravenous analgesia and oral analgesia in the following days. Demographic, clinical-radiological variables, PCA opioid use, pain grade according to the visual analog scale (VAS), and length of stay (LOS) were compared between the groups. A total of 20 patients were included (12 with PCrSD and 8 with PCr48), without significant differences in demographics or clinical-radiological variables. The overall median time of PCr was 65 minutes (55-127), with no differences between the groups., RESULTS: PCr48 group presented with significantly lower median number of hours of continuous PCA (24 vs. 32 hours; p = 0.031), lower median number of rescue boluses (11 vs. 18; p = 0.042), lower median VAS in the early postoperative hours (2 vs. 5.5; p = 0.043), and lower median LOS (3.5 vs. 5 days)., CONCLUSION: PCr performed 48 hours prior to surgery is more effective in terms of PCA requirements, VAS, and LOS when compared with cryoanalgesia on the same day. Copyright Thieme. All rights reserved.
Keywords: Humans; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Analgesia, Patient-Controlled; Pain Management; *Funnel Chest; Funnel Chest/su [Surgery]

Cryoanalgesia is Associated With Decreased Postoperative Opioid Use in Minimally Invasive Repair of Pectus Excavatum. - Arshad, Seyed A; Ferguson, Dalya M; Garcia, Elisa I; Hebballi, Nutan B; Buchanan, Allison C; Tsao, KuoJen (The Journal of surgical research, 2022)
BACKGROUND: Postoperative pain control is challenging after pectus excavatum repair. We aimed to understand the impact that cryoanalgesia had on opioid utilization and outcomes of pediatric patients undergoing minimally invasive repair of pectus excavatum (MIRPE)., METHODS: A single-center retrospective cohort study was conducted of all patients (< 18 y) who underwent MIRPE (2011-2019). Patients receiving cryoanalgesia were compared to those who did not. The primary outcome was total postoperative, inpatient, opioid use, measured as milligrams of oral morphine equivalents per kilogram (OME/kg). Univariate and multivariable analyses were performed., RESULTS: Of 35 patients, 20 received cryoanalgesia (57%). Baseline characteristics were similar. Patients who received cryoanalgesia had a lower opioid requirement: median 2.3 mg OME/kg (IQR 1.2-3.1), versus 4.9 mg OME/kg (IQR 2.9-5.8), P < 0.001. Accounting for receipt of cryoanalgesia, epidural, and/or patient-controlled analgesia, cryoanalgesia was associated with a 3.3 mg OME/kg reduction in opioid use (P < 0.001). Median length of stay (LOS) was shorter in cryoanalgesia patients: 3.1 d (IQR 2.3-3.4), versus 5.1 d (IQR 4.3-5.4), P < 0.001. Complications within 90 d were similar between groups., CONCLUSIONS: Cryoanalgesia is an effective adjunctive pain control modality for patients undergoing MIRPE. Use of cryoanalgesia was associated with lower postoperative opioid requirements and shorter LOS, without increased short-term complications, and should be considered for enhanced recovery after MIRPE. Copyright © 2021 Elsevier Inc. All rights reserved.
Keywords: Humans; Child; Retrospective Studies; *Funnel Chest; Funnel Chest/su [Surgery]; Pain, Postoperative/et [Etiology]; *Analgesics, Opioid; Analgesics, Opioid/tu [Therapeutic Use]; Minimally Invasive Surgical Procedures/ae [Adverse Effects]; Pain, Postoperative/pc [Prevention & Control]; Pain, Postoperative/su [Surgery]

Intercostal cryoablation during Nuss procedure: A large volume single surgeon's experience and outcomes. - Sun, Raphael C; Mehl, Steven C; Anbarasu, Centura R; Portuondo, Jorge I; Espinoza, Andres F; Whitlock, Richard; Mazziotti, Mark V (Journal of pediatric surgery, 2021)
BACKGROUND: Recent studies have shown intercostal cryoablation(IC) during the Nuss procedure decreases hospital length of stay(LOS) and opioid administration. However, few studies have also evaluated the risk of postoperative complications related to IC., METHODS: We performed a single center retrospective analysis of all patients who underwent Nuss procedure by one surgeon from 2/2016 to 2/2020, comparing intraoperative IC to other pain management modalities(non-IC). Primary outcomes were postoperative complications, hospital LOS, and opioid administration. Multivariate analysis was performed with outcomes reported as regression coefficients(RC) or odds ratios(OR) with 95% confidence interval., RESULTS: IC was associated with decreased hospital LOS (RC -1.91[-2.29 to -1.54], less hospital opioid administration (RC -4.28[-5.13 to -3.43]), and less discharge opioid administration (RC -3.82[-5.23 to -2.41]). With respect to postoperative complications, IC decreased the odds of urinary retention (OR 0.16[0.06 to 0.44]); however, increased the odds of slipped bars requiring reoperation (OR 36.65[5.04-266.39])., CONCLUSIONS: Our single surgeon experience controls for surgeon variability and demonstrates intraoperative IC for the Nuss procedure is an effective pain management modality that decreases hospital LOS and opioid use during hospitalization and at discharge; however, it is associated with increased odds of slipped bars requiring reoperation., LEVEL OF EVIDENCE: III. Copyright © 2021 Elsevier Ltd. All rights reserved.
Keywords: Humans; Retrospective Studies; *Funnel Chest; Funnel Chest/su [Surgery]; Pain, Postoperative/et [Etiology]; Pain, Postoperative/su [Surgery]; *Cryosurgery; *Surgeons; Pain, Postoperative/ep [Epidemiology]

Intercostal nerve cryoablation is associated with lower hospital cost during minimally invasive Nuss procedure for pectus excavatum. - Aiken, Taylor J; Stahl, Christopher C; Lemaster, Deborah; Casias, Timothy W; Walker, Benjamin J; Nichol, Peter F; Leys, Charles M; Abbott, Daniel E; Brinkman, Adam S (Journal of pediatric surgery, 2021)
Minimally invasive repair of pectus excavatum (Nuss procedure) is associated with significant pain, and efforts to control pain impact resource utilization. Bilateral thoracic intercostal nerve cryoablation has been proposed as a novel technique to improve post-operative pain control, though the impact on hospital cost is unknown., METHODS: We conducted a retrospective study of patients undergoing a Nuss procedure from 2016 to 2019. Patients who received cryoablation were compared to those that received traditional pain control (patient-controlled analgesia or epidural). Outcome variables included postoperative opioid usage (milligram morphine equivalents, MME), length of stay (LOS), and hospital cost., RESULTS: Thirty-five of 73 patients studied (48%) received intercostal nerve cryoablation. LOS (1.0 vs 4.0days, p<0.01) and total hospital cost ($21,924 versus $23,694, p=0.04) were decreased in the cryoablation cohort, despite longer operative time (152 vs 74min, p<0.01). Cryoablation was associated with decreased opioid usage (15.0 versus 148.6 MME, p<0.01) during the 24h following surgery and this persisted over the entire postoperative period, including discharge opioid prescription (112.5 vs 300.0 MME, p<0.01)., CONCLUSION: Bilateral intercostal nerve cryoablation is associated with decreased postoperative opioid usage and decreased resource utilization in pediatric patients undergoing a minimally invasive Nuss procedure for pectus excavatum., LEVEL OF EVIDENCE: Retrospective comparative study, level III. Copyright © 2020 Elsevier Inc. All rights reserved.
Keywords: Humans; Child; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Intercostal Nerves; Hospital Costs; *Funnel Chest; Funnel Chest/su [Surgery]; Pain, Postoperative/dt [Drug Therapy]; Pain, Postoperative/et [Etiology]; Pain, Postoperative/su [Surgery]; *Cryosurgery

Postoperative pain control modalities for pectus excavatum repair: A prospective observational study of cryoablation compared to results of a randomized trial of epidural vs patient-controlled analgesia. - Dekonenko, Charlene; Dorman, Robert M; Duran, Yara; Juang, David; Aguayo, Pablo; Fraser, Jason D; Oyetunji, Tolulope A; Snyder, Charles L; Holcomb, George W 3rd; Millspaugh, Daniel L; St Peter, Shawn D (Journal of pediatric surgery, 2020)
BACKGROUND: Pain following bar placement for pectus excavatum is the dominant factor post-operatively and determines length of stay (LOS). We recently adopted intercostal cryoablation as our preferred method of pain control following minimally invasive pectus excavatum repair. We compared the outcomes of cryoablation to results of a recently concluded trial of epidural (EPI) and patient-controlled analgesia (PCA) protocols., METHODS: We conducted a prospective observational study of patients undergoing bar placement for pectus excavatum using intercostal cryoablation. Results are reported and compared with those of a randomized trial comparing EPI with PCA. Comparisons of medians were performed using Kruskal-Wallis H tests with alpha 0.05., RESULTS: Thirty-five patients were treated with cryoablation compared to 32 epidural and 33 PCA patients from the trial. Cryoablation was associated with longer operating time (101min, versus 58 and 57min for epidural and PCA groups, p<0.01), resulted in less time to pain control with oral medication (21h, versus 72 and 67h, p<0.01), and decreased LOS (1 day, versus 4.3 and 4.2 days, p<0.01)., CONCLUSION: Intercostal cryoablation during minimally invasive pectus excavatum repair reduces LOS and perioperative opioid consumption compared with both EPI and PCA., LEVEL OF EVIDENCE: II. Copyright © 2019 Elsevier Inc. All rights reserved.
Keywords: Humans; Prospective Studies; *Analgesia, Epidural; *Analgesia, Patient-Controlled; *Cryosurgery/ae [Adverse Effects]; *Funnel Chest/su [Surgery]; *Pain, Postoperative/th [Therapy]; Length of Stay/sn [Statistics & Numerical Data]

A review of anesthetic techniques and outcomes following minimally invasive repair of pectus excavatum (Nuss procedure). - Frawley, Geoff; Frawley, Jacinta; Crameri, Joe (Paediatric anaesthesia, 2016)
BACKGROUND: Pectus excavatum (PE) is the most common congenital chest wall deformity, occurring in 1 : 1000 children with a male to female ratio of 4 : 1. Several procedures have been described to manage this deformity, including cartilage resection with sternal osteotomy (the Ravitch procedure) and a minimally invasive repair technique (the Nuss procedure). While initially described as a nonthoracoscopic technique, the current surgical approach of the Royal Childrens Hospital involves thoracoscopic assistance. Postoperative pain is significant in patients undergoing the pectus repair and multiple analgesic regimens have been advocated with continuous thoracic epidural infusions and opioid infusions the most common. Some authors have advocated patient-controlled analgesia (PCA), paravertebral nerve blocks (PVNB), and wound infusion catheters as alternatives., AIMS: The primary aim of this study was to assess our experience with postoperative pain and analgesia requirements associated with the minimally invasive repair of pectus excavatum in children., METHODS: This is a retrospective cohort study with a contemporaneous comparison group examining patients treated between January 2005 and December 2015 for minimally invasive repair of pectus excavatum by the Nuss procedure., RESULTS: Two hundred and seventeen patients [mean age 14.9 (sd 1.9) years] with pectus excavatum treated at the Royal Childrens Hospital between 2005 and 2015 were identified. All patients were managed with thoracic epidural analgesia and intravenous morphine infusions. The epidural was effective in the postanesthesia care unit in 97.3% (failure to place an epidural rate was 4 (1.9%); no block on awakening 0.9%). A further 4 (1.8%) were removed within 24 h. The mean morphine equivalent dose in the first 24 h was 0.8 mg.kg-1 .day-1 . PCA was continued for a mean of 3.8 days and the total mean morphine equivalent dose was 2.2 mg.kg-1 .day-1 . Minor complications occurred in 67 (30.9%) with postoperative nausea and vomiting in 36 patients (16.6%) and urinary retention requiring an indwelling catheter in 40 patients (18.4%)., CONCLUSION: An epidural-based analgesic regime is associated with low pain scores and few acute complications. The continuation of morphine analgesia after the first postoperative day is common but associated with an increased incidence of urinary retention and nausea and vomiting. Copyright © 2016 John Wiley & Sons Ltd.
Keywords: Humans; Adolescent; Female; Male; Retrospective Studies; Nerve Block; Cohort Studies; Drug Administration Routes; Analgesia, Patient-Controlled/mt [Methods]; *Funnel Chest/su [Surgery]; *Analgesia/mt [Methods]; *Anesthesia/mt [Methods]; *Minimally Invasive Surgical Procedures/mt [Methods]; *Pain, Postoperative/dt [Drug Therapy]

Continuous chest wall ropivacaine infusion for analgesia in children undergoing Nuss procedure: a comparison with thoracic epidural. - Choudhry, Dinesh K; Brenn, B Randall; Sacks, Karen; Reichard, Kirk (Paediatric anaesthesia, 2016)
BACKGROUND: Pain following Nuss procedure is severe and its management is challenging. Many different pain treatment modalities are currently being used, but none of them have been found to be ideal., AIM: In this retrospective review, we compare our current multimodal approach, which involves continuous ropivacaine infusion through chest wall catheters (CWC), intravenous patient-controlled analgesia (IV-PCA), and adjunctive medications (gabapentin and clonidine), with the technique that we used in the past, the thoracic epidural catheter (TEC)., METHODS: Following IRB approval, we performed a retrospective analysis of data on 32 patients who underwent the Nuss procedure at our institution. All children were divided into two groups: TEC group: 0.2% ropivacaine and hydromorphone 10 mcg.ml(-1) epidural infusion (n = 15) and CWC group (with IV-PCA and adjuncts [gabapentin + clonidine]): 0.2% ropivacaine infusion and hydromorphone PCA, oral gabapentin, and transdermal clonidine patch (n = 17)., RESULTS: Both the groups were demographically similar. Average numeric pain scores were higher in the CWC group only on the day of surgery (mean +/- sd: 3.79 +/- 1.58 vs 2.68 +/- 1.30; 95% CI: -2.16 to -0.05). Pain scores on postoperative day 1 (mean +/- sd: 3.40 +/- 1.59 vs 3.35 +/- 1.32; 95% CI: -1.11 to 1.01), day 2 (mean+/- sd: 3.39 +/- 1.79 vs 2.99 +/- 1.06; 95% CI: -1.50 to 0.70), and on the day of discharge (DOD) (mean+/- sd: 3.25 +/- 1.84 vs 3.99 +/- 1.28; 95% CI: -0.42 to 1.89) were comparable between the groups. The CWC group needed fewer changes in the therapeutic regimen to maintain acceptable pain relief, had lower incidence of nausea and vomiting, had shorter anesthesia time, total OR time, and hospital length of stay., CONCLUSION: TEC provided better analgesia following the Nuss procedure only on the day of surgery. On the subsequent days until discharge, pain scores were comparable. However, CWC offered other advantages: it was less labor intensive and had fewer side effects, shorter OR time, and shorter hospital stay. Copyright © 2016 John Wiley & Sons Ltd.
Keywords: Humans; Adolescent; Female; Male; Retrospective Studies; Gabapentin; Combined Modality Therapy; Infusions, Parenteral; Ropivacaine; Analgesia, Patient-Controlled/mt [Methods]; *Funnel Chest/su [Surgery]; *Pain, Postoperative/dt [Drug Therapy]; *Amides/ad [Administration & Dosage]; *Anesthesia, Epidural; *Anesthetics, Local/ad [Administration & Dosage]; Amines/ad [Administration & Dosage]; Analgesics, Opioid/ad [Administration & Dosage]; Analgesics/ad [Administration & Dosage]; Clonidine/ad [Administration & Dosage]; Cyclohexanecarboxylic Acids/ad [Administration & Dosage]; gamma-Aminobutyric Acid/ad [Administration & Dosage]; Morphine/ad [Administration & Dosage]; Thoracic Wall/de [Drug Effects]

[Thoracic epidural analgesia vs patient-controlled analgesia with intravenous fentanyl in children treated for pectus excavatum with the Nuss procedure]. - Reinoso-Barbero, F; Fernandez, A; Duran, P; Castro, L E; Campo, G; Melo, M M (Analgesia epidural toracica frente a analgesia con fentanilo controlada por el paciente en ninos operados de pectus excavatum con la tecnica de Nuss., 2010)
BACKGROUND AND OBJECTIVE: Thoracic epidural analgesia and patient-controlled analgesia (PCA) with intravenous fentanyl have both been shown to be effective in pediatric patients treated surgically for pectus excavatum using the Nuss procedure. We compare the efficacy and safety of these techniques., METHODS: Retrospective study of pediatric cases in which the Nuss procedure was used to treat pectus excavatum between October 1997 and February 2009. Weight, age, sex, and Haller index were analyzed. Pain was assessed every 8 hours on a visual analog scale of 0 to 10 or on a scale based on observation of distress (LLANTO scale). Daily use of analgesics was also recorded. The incidence of catheter-related complications or adverse events of treatment such as nausea, vomiting, and respiratory depression were also noted., RESULTS: We identified 31 patients in 2 groups: the epidural group (n=22) and the PCA group (n=9). Demographic characteristics, the incidences of complications or adverse events, and mean (SD) pain scores (epidural group, 1.8 [3.8]; PCA group, 2.1 [3.4]; P = .775) were statistically similar in the 2 groups. However, analgesic requirements and the duration of analgesic use in days differed significantly, at 2.9 (1.1) days in the epidural group and 5.9 (1.4) days in the PCA group (P =.001)., CONCLUSIONS: The efficacy and safety of thoracic epidural analgesia is similar to that of PCA with intravenous fentanyl, although the use of epidural analgesia is associated with a markedly shorter duration of requirement for postoperative analgesia.
Keywords: Humans; Female; Male; Child; Retrospective Studies; Infusions, Intravenous; *Analgesia, Patient-Controlled; *Funnel Chest/su [Surgery]; *Analgesics, Opioid/ad [Administration & Dosage]; *Electric Countershock; *Fentanyl/ad [Administration & Dosage]; Orthopedic Procedures/mt [Methods]

Systemic postoperative pain management following minimally invasive pectus excavatum repair in children and adolescents: a retrospective comparison of intravenous patient-controlled analgesia and continuous infusion with morphine. - Rugyte, Danguole Ceslava; Kilda, Arturas; Karbonskiene, Aurika; Barauskas, Vidmantas (Pediatric surgery international, 2010)
PURPOSE: Optimal postoperative pain management following minimally invasive surgical repair of pectus excavatum is not established. We compared efficacy and adverse effects in patients treated with patient-controlled analgesia (PCA) with those treated with continuous infusion (CI) with morphine in addition to nonsteroidal anti-inflammatory drugs., METHODS: 33 patient records were examined retrospectively: 21 given PCA and 12 CI with morphine. Main outcome variables were used doses of morphine, pain scores every 3 h and adverse effects., RESULTS: Median (range) used morphine dose was 0.58 (0.21-1.12) and 0.52 (0.34-0.84) mg/kg on the day 1 and 0.3 (0.02-0.6) and 0.33 (0.09-0.53) mg/kg on the day 2 in PCA and CI groups, respectively (p > 0.05). Pain scores were within moderate and low levels during 42 h after surgery and did not differ between the groups. Median (range) oxygen saturation was 96.5 (93-100) and 97 (94-100) in PCA and CI groups, respectively (p > 0.05). Additional oxygen therapy was required in 14.3% in PCA group and 25% in CI group (p > 0.05). The incidence of pulmonary adverse effects was rare and did not differ between the groups., CONCLUSION: Both methods of systemic analgesia in addition to non-opioid analgesics were equally effective and resulted in a low incidence of pulmonary adverse effects.
Keywords: Humans; Adolescent; Female; Male; Young Adult; Child; Retrospective Studies; Pain Measurement; Infusions, Intravenous; *Funnel Chest/su [Surgery]; *Pain, Postoperative/dt [Drug Therapy]; *Analgesics, Opioid/ad [Administration & Dosage]; *Analgesia, Patient-Controlled/mt [Methods]; *Anesthesia, Intravenous; *Morphine/ad [Administration & Dosage]; Anti-Inflammatory Agents, Non-Steroidal/tu [Therapeutic Use]

Superior postoperative pain relief with thoracic epidural analgesia versus intravenous patient-controlled analgesia after minimally invasive pectus excavatum repair. - Weber, Thomas; Matzl, Johanna; Rokitansky, Alexander; Klimscha, Walter; Neumann, Konrad; Deusch, Engelbert (The Journal of thoracic and cardiovascular surgery, 2007)
OBJECTIVE: Minimally invasive pectus excavatum repair is a common and painful surgical procedure in children and adolescents. Adequate postoperative pain therapy is important far beyond the immediate postoperative period because sensitization to painful stimuli can cause chronic pain or higher pain levels during subsequent surgical procedures. Although data in adults favor thoracic epidural anesthesia for pain control in thoracotomy, data for adolescents and children are scarce. We tested the hypothesis that pain relief with thoracic epidural analgesia was superior to that with intravenous patient-controlled analgesia after minimally invasive pectus excavatum repair in children and adolescents., METHODS: We performed a prospective randomized trial with adolescents who had undergone minimally invasive pectus excavatum repair to compare postoperative pain using two different postoperative pain therapy settings: intravenous patient-controlled analgesia (n = 20) with morphine versus continuous thoracic epidural analgesia (n = 20) with 0.2% ropivacain containing 2 microg/mL fentanyl., RESULTS: Forty patients (32 male and 8 female patients) aged 10 to 28 years were studied. The thoracic epidural analgesia group showed lower pain scores (P < .0001) and required less additional pain medication in conjunction with greater well-being postoperatively (P < .0001) compared with patients receiving patient-controlled intravenous morphine. There was no significant difference regarding the incidence of sedation (P = .38), nausea (P = .10), and pruritus (P = .72) in both groups., CONCLUSIONS: For adolescents undergoing minimally invasive pectus excavatum repair, thoracic epidural analgesia was superior to intravenous patient-controlled analgesia for postoperative analgesia, resulting in lower postoperative pain scores in conjunction with greater well-being.
Keywords: Humans; Adolescent; Adult; Female; Male; Child; Treatment Outcome; Prospective Studies; Pain Measurement; *Analgesia, Epidural; *Analgesia, Patient-Controlled; *Funnel Chest/su [Surgery]; Analgesics, Opioid/ad [Administration & Dosage]; Morphine/ad [Administration & Dosage]; *Minimally Invasive Surgical Procedures; *Pain, Postoperative/pc [Prevention & Control]; Analysis of Variance; Anti-Inflammatory Agents, Non-Steroidal/ad [Administration & Dosage]; Diclofenac/ad [Administration & Dosage]; Logistic Models

Management of pre‐, peri‐, and post‐menopausal abnormal uterine bleeding: When to perform endometrial sampling? - Efthymia Papakonstantinou; Georgios Adonakis (International Journal of Gynecology & Obstetrics, 2021)

Intercostal nerve cryoablation versus thoracic epidural for postoperative analgesia following pectus excavatum repair: a systematic review and meta-analysis - Daemen, Jean H T; De Loos, Erik R; Vissers, Yvonne L J; Bakens, Maikel J A M; Maessen, Jos G; Hulsewé, Karel W E (Interactive CardioVascular and Thoracic Surgery, 2020)
Abstract OBJECTIVES Minimally invasive pectus excavatum repair via the Nuss procedure is associated with significant postoperative pain that is considered as the dominant factor affecting the duration of hospitalization. Postoperative pain after the Nuss procedures is commonly controlled by thoracic epidural analgesia. Recently, intercostal nerve cryoablation has been proposed as an alternative method with long-acting pain control and shortened hospitalization. The subsequent objective was to systematically review the outcomes of intercostal nerve cryoablation in comparison to thoracic epidural after the Nuss procedure. METHODS Six scientific databases were searched. Data concerning the length of hospital stay, operative time and postoperative opioid usage were extracted. If possible, data were submitted to meta-analysis using the mean of differences, random-effects model with inverse variance method and I2 test for heterogeneity. RESULTS Four observational and 1 randomized study were included, enrolling a total of 196 patients. Meta-analyses demonstrated a significantly shortened length of hospital stay [mean difference −2.91 days; 95% confidence interval (CI) −3.68 to −2.15; P < 0.001] and increased operative time (mean difference 40.91 min; 95% CI 14.42–67.40; P < 0.001) for cryoablation. Both analyses demonstrated significant heterogeneity (both I2 = 91%; P < 0.001). Qualitative analysis demonstrated the amount of postoperative opioid usage to be significantly lower for cryoablation in 3 out of 4 reporting studies. CONCLUSIONS Intercostal nerve cryoablation during the Nuss procedure may be an attractive alternative to thoracic epidural analgesia, resulting in shortened hospitalization. However, given the low quality and heterogeneity of studies, more randomized controlled trials are needed.

Current Concepts in the Etiology and Pathogenesis of Pectus Excavatum in Humans—A Systematic Review - David, Vlad Laurentiu (Journal of Clinical Medicine, 2022)
Pectus excavatum (PE) is the most common deformity of the chest wall and is characterized by the posterior depression of the sternum and the lower costal cartilages. To date, the etiology of PE in humans remains enigmatic. Several etiologic hypotheses have been proposed over the past two centuries. However, most of them have been scientifically dismissed and now have only historic value. In this systematic review, we assess scientific publications of the past two centuries addressing the issue of the origin of PE in humans. We present and discuss the histologic, genetic, biomechanical, and experimental scientific achievements that contributed to the clarification of its etiology and pathogenesis. With no clear consensus over the exact mechanism, most recent studies agree that the primordial defect leading the deformation of the anterior chest wall in PE is related to the costal hyaline cartilage structure and function. Further studies on this subject must be carried out. Genetic studies seem to be the most promising way to understand the exact mechanism of PE’s origin and pathogenesis.

Same-day discharge following the Nuss repair: A comparison - Rettig, R. Luke; Rudikoff, Andrew G.; Annie Lo, Hoi Yee; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)

Limited cryoablation reduces hospital stay and opioid consumption compared to thoracic epidural analgesia after minimally invasive repair of pectus excavatum - Song, Seung Hwan; Moon, Duk Hwan; Shim, Yon Hee; Jung, Hyunjoo; Lee, Sungsoo (Medicine, 2022)

Surgical interventions for treating pectus excavatum - De Oliveira Carvalho, Paulo Eduardo; Da Silva, Marcos Vinícius Muriano; Rodrigues, Olavo Ribeiro; Cataneo, Antonio José Maria (Cochrane Database of Systematic Reviews, 2014)

Intraoperative intercostal nerve cryoablation During the Nuss procedure reduces length of stay and opioid requirement: A randomized clinical trial - Graves, Claire E.; Moyer, Jarrett; Zobel, Michael J.; Mora, Roberto; Smith, Derek; O'Day, Maura; Padilla, Benjamin E. (Journal of Pediatric Surgery, 2019)

Pectus excavatum and carinatum - Cobben, Jan M.; Oostra, Roelof-Jan; Van Dijk, Fleur S. (European Journal of Medical Genetics, 2014)

Minimally Invasive Repair of Pectus Excavatum - Hebra, André (Seminars in Thoracic and Cardiovascular Surgery, 2009)

Postoperative pain control following minimally invasive correction of pectus excavatum in pediatric patients: A systematic review - Archer, Victoria; Robinson, Tessa; Kattail, Deepa; Fitzgerald, Peter; Walton, J Mark (Journal of Pediatric Surgery, 2020)

Acute mesenteric ischemia: guidelines of the World Society of Emergency Surgery - Bala, Miklosh; Kashuk, Jeffry; Moore, Ernest E.; Kluger, Yoram; Biffl, Walter; Gomes, Carlos Augusto; Ben-Ishay, Offir; Rubinstein, Chen; Balogh, Zsolt J.; Civil, Ian; Coccolini, Federico; Leppaniemi, Ari; et al. (World Journal of Emergency Surgery, 2017)

Mesenteric Ischemia - Lawson, Robin M. (Critical Care Nursing Clinics of North America, 2018)

Mesenteric Ischemia - Lawson, Robin M. (Critical Care Nursing Clinics of North America, 2018)

Acute Mesenteric Ischemia: A Challenge for the Acute Care Surgeon - Kärkkäinen, J. M. (Scandinavian Journal of Surgery, 2021)
Acute mesenteric ischemia is considered uncommon, but it appears to be more frequent cause of acute abdomen than appendicitis or ruptured abdominal aortic aneurysm in elderly patients. Surgical treatment without revascularization is associated with high overall mortality, up to 80%. The modern treatment of acute mesenteric ischemia requires collaboration of gastrointestinal surgeons, vascular surgeons, and interventional radiologists. Early revascularization may reduce the overall mortality associated with acute mesenteric ischemia by up to 50%. Clinical suspicion and contrast-enhanced computed tomography performed at early stage are keys to improve outcomes of acute mesenteric ischemia treatment. This review summarizes what the acute care surgeon needs to know about acute mesenteric ischemia with special emphasis on slowly progressing “acute on chronic” mesenteric ischemia.

Pain Quality After Pediatric Pectus Excavatum Repair - Manworren, Renee C. B.; Di Franco, Maria Victoria; Mishra, Trishla; Kaduwela, Naomi (Pain Management Nursing: Official Journal of the American Society of Pain Management Nurses, 2022)
BACKGROUND: Neuropathic pain medications are included in multimodal postoperative analgesic strategies, but quality of perioperative pain is rarely assessed. AIMS: The purpose of this study was to describe adolescents' pain experiences after thoracoscopic pectus excavatum repair (Nuss procedure) using the Adolescent Pediatric Pain Tool. DESIGN: This prospective descriptive longitudinal study was designed to test the hypothesis that pain quality descriptors reported are consistent with neuropathic pain. METHODS: A convenience sample of 23 adolescents aged 12 to 17 years from a single urban, university affiliated, nonprofit children's hospital consented to self-report pain using the Adolescent Pediatric Pain Tool before and during hospitalization, and up to 14 months after Nuss procedure. Visual analytic techniques were used to analyze reported pain intensity, location, and affective, evaluative, sensory, and temporal qualities. RESULTS: Postoperative pain quality, intensity, number of sites, and surface area decreased over time. Word clouds illustrated that neuropathic sensory and temporal pain quality descriptors increased in frequency 2 to 6 weeks after surgery and were the predominant descriptors 2 to 4 months after surgery. Dot matrix charts illustrated an inconsistent relationship of pain quality and intensity with pain surface area. CONCLUSIONS: Pain quality should be assessed with valid, reliable, and developmentally appropriate tools. Visual analytics help illustrate pain quality at single points in time and longitudinally and may be helpful in guiding postoperative pain treatment.
Keywords: Humans; Adolescent; Child; Funnel Chest; Longitudinal Studies; Neuralgia; Pain, Postoperative; Retrospective Studies; Treatment Outcome

Intraoperative intercostal nerve cryoablation During the Nuss procedure reduces length of stay and opioid requirement: A randomized clinical trial - Graves, Claire E.; Moyer, Jarrett; Zobel, Michael J.; Mora, Roberto; Smith, Derek; O'Day, Maura; Padilla, Benjamin E. (Journal of Pediatric Surgery, 2019)
PURPOSE: Minimally-invasive repair of pectus excavatum by the Nuss procedure is associated with significant postoperative pain, prolonged hospital stay, and high opiate requirement. We hypothesized that intercostal nerve cryoablation during the Nuss procedure reduces hospital length of stay (LOS) compared to thoracic epidural analgesia. DESIGN: This randomized clinical trial evaluated 20 consecutive patients undergoing the Nuss procedure for pectus excavatum between May 2016 and March 2018. Patients were randomized evenly via closed-envelope method to receive either cryoanalgesia or thoracic epidural analgesia. Patients and physicians were blinded to study arm until immediately preoperatively. SETTING: Single institution, UCSF-Benioff Children's Hospital. PARTICIPANTS: 20 consecutive patients were recruited from those scheduled for the Nuss procedure. Exclusion criteria were age < 13 years, chest wall anomaly other than pectus excavatum, previous repair or other thoracic surgery, and chronic use of pain medications. MAIN OUTCOMES AND MEASURES: Primary outcome was postoperative LOS. Secondary outcomes included total operative time, total/daily opioid requirement, inpatient/outpatient pain score, and complications. Primary outcome data were analyzed by the Mann-Whitney U-test for nonparametric continuous variables. Other continuous variables were analyzed by two-tailed t-test, while categorical data were compared via Chi-squared test, with alpha = 0.05 for significance. RESULTS: 20 patients were randomized to receive either cryoablation (n = 10) or thoracic epidural (n = 10). Mean operating room time was 46.5 min longer in the cryoanalgesia group (p = 0.0001). Median LOS decreased by 2 days in patients undergoing cryoablation, to 3 days from 5 days (Mann-Whitney U, p = 0.0001). Cryoablation patients required significantly less inpatient opioid analgesia with a mean decrease of 416 mg oral morphine equivalent per patient (p = 0.0001), requiring 52%-82% fewer milligrams on postoperative days 1-3 (p < 0.01 each day). There was no difference in mean pain score between the groups at any point postoperatively, up to one year, and no increased incidence of neuropathic pain in the cryoablation group. No complications were noted in the cryoablation group; among patients with epidurals, one patient experienced a symptomatic pneumothorax and another had urinary retention. CONCLUSIONS AND RELEVANCE: Intercostal nerve cryoablation during the Nuss procedure decreases hospital length of stay and opiate requirement versus thoracic epidural analgesia, while offering equivalent pain control. TYPE OF STUDY: Treatment study. LEVEL OF EVIDENCE: Level I.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Orthopedic Procedures; Thoracoscopic

Postoperative pain following minimally invasive repair of pectus excavatum: A descriptive study - Ganescu, Olivia; Emil, Sherif; Saint-Martin, Christine; Guadagno, Elena; Laberge, Jean-Martin; LaRusso, Kathryn; Frigon, Chantal (Journal of Pediatric Surgery, 2022)
BACKGROUND: Minimally Invasive Repair of Pectus Excavatum (MIRPE) is associated with significant postoperative pain. The objective of our study was to characterize the severity and duration of this pain, and to investigate possible associations with pectus severity. METHODS: We conducted a retrospective cohort study of pediatric patients who underwent MIRPE from January 2014 to April 2018. Pectus excavatum (PE) severity was determined with 3 indices measured from computed tomography: Depression Index (DI), Correction Index (CI), and Haller index (HI). Mean pain scores for every 6-hour period and the presence of pain and intake of analgesics during follow-up were extracted from the medical record. RESULTS: The cohort included 57 patients with a mean age of 15.9 ± 1.3 years. All 3 severity indices were positively correlated, with a correlation coefficient of 0.8 between the DI and CI. The requirement for 2 bars was significantly associated with higher indices (95% CI:0.18-0.63, p = 0.01). Pain was managed with thoracic epidural analgesia for all but one patient. Growth linear modeling identified five different pain trajectory subgroups of patients up to post-operative day 5. None of the tested predictors (age, gender, body image, physical activity level, DI, CI, HI, difference deformity-epidural level) were significantly associated with class membership. Persistent pain at one-year follow-up was present in 18% of patients, all with severe deformity (DI≥0.8). CONCLUSION: Pain trajectory and intensity after MIRPE can be classified into discrete patterns but are not influenced by PE severity. Severe deformity seems to predict persistent pain at one year.
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Depression index; Level III; Minimally invasive repair; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Persistent post surgical pain; Post-operative pain; Retrospective Study; Severity deformity

Impact of Cryoablation on Pectus Excavatum Repair in Pediatric Patients - Clark, Rachael A.; Jacobson, Jillian C.; Singhal, Amogh; Alder, Adam C.; Chung, Dai H.; Pandya, Samir R. (Journal of the American College of Surgeons, 2022)
BACKGROUND: Minimally invasive repair of pectus excavatum (MIRPE) involves placement of a transthoracic, retrosternal support bar under thoracoscopic guidance. Despite its minimally invasive technical approach, postoperative pain is a significant morbidity that often results in increased length of stay. Multi-modal pain control strategies have been used in the past with limited success. Recently, the use of intraoperative intercostal nerve cryoablation (CA) has been added. In the present study, we aim to evaluate the effects of CA on postoperative pain control, opioid requirements, and perioperative outcomes. STUDY DESIGN: A single-center, retrospective chart review of all patients (less than 18 years old) who underwent MIRPE from 2009 to 2020 was performed. CA was started in June 2018. Data collection included demographics, preoperative characteristics, intraoperative findings, and postoperative outcomes. We hypothesized that CA would be associated with improved pain scores, lower doses of total inpatient opioid requirement, and shorter length of stay (LOS). RESULTS: One hundred sixty-one patients met inclusion criteria: 75 underwent intraoperative CA and 86 underwent MIRPE without CA (NCA group). CA significantly decreased median LOS from 4 days in NCA to 2 days; the use of CA was the only significant predictor of LOS on linear regression. CA was also associated with decreased total PCA, intravenous opioid, and oral opioid dosages. There was no difference in inpatient pain scores and a slight increase in mean procedure time. However, CA was associated with significantly decreased postoperative complications. CONCLUSIONS: The use of cryoablation during MIRPE significantly decreases LOS, perioperative opioid requirements, and postoperative complications, with a minimal increase in operative time. Cryoablation is an effective pain control modality in the surgical management of chest wall deformities in children.
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Postoperative Complications

Same day discharge for pectus excavatum-is it possible? - Rettig, R. Luke; Rudikoff, Andrew G.; Lo, Hoi Yee Annie; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: The use of intercostal nerve cryoablation (INC) has been an effective modality for treating pain in patients undergoing pectus excavatum (PE) repair. This study sought to evaluate if PE patients undergoing Nuss procedures with INC and intercostal nerve block (INB) could safely be discharged the same day of surgery. METHODS: A prospective study with IRB approval of 15 consecutive patients undergoing PE Nuss repair with INC, INB, and an enhanced recovery after surgery (ERAS) protocol was conducted. The primary outcome measure was hospital length of stay (LOS) in hours. Secondary variables included same day discharge, postoperative complications, emergency department (ED) visits, urgent care (UC) visits, opioid use, and return to the operating room (OR). RESULTS: LOS averaged 11.9 h amongst 15 patients. Ten patients (66.7%) went home on postoperative day (POD) 0, and the rest went home on POD 1. No patients stayed in the hospital due to pain. Reasons for failure to discharge included urinary retention, drowsiness, vomiting, and anxiety, but not pain. No patients were readmitted to the ED. One patient visited UC for constipation. One patient had bar migration requiring return to the OR for revision. Ten (66.7%) patients did not use opioids after discharge. CONCLUSIONS: Same day discharge is feasible and safe in PE patients undergoing Nuss procedure with INC and INB. INC with INB can adequately control pain without significant complications. Same day discharge can be safely considered for PE patients undergoing Nuss procedure with INC with INB. TYPE OF STUDY: Prognosis study LEVEL-OF-EVIDENCE RATING: Level II.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Intercostal nerve cryoablation; Enhanced recovery after surgery (ERAS); Patient Discharge; Pectus excavatum repair; Prospective Studies; Same day discharge

Percutaneous Cryoanalgesia: A New Strategy for Pain Management in Pectus Excavatum Surgery - Velayos, María; Alonso, Mercedes; Delgado-Miguel, Carlos; Estefanía-Fernández, Karla; Muñoz-Serrano, Antonio J.; Santamaría, Manuel V. López; Reinoso-Barbero, Francisco; De La Torre, Carlos A. (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2022)
INTRODUCTION: In recent years, pain protocols for pectus excavatum (PE) have incorporated cryoanalgesia through thoracoscopic approach. Since 2019, ultrasound-guided percutaneous cryoanalgesia (PCr) has been applied at our institution, either on the same day as the Nuss procedure or 48 hours before surgery. We carried out a preliminary retrospective review of patients with PE in whom PCr prior to surgery was performed at our institution between 2019 and 2021. MATERIALS AND METHODS: Two groups were evaluated: PCr on the same day (PCrSD) and PCr 48 hours before surgery (PCr48). Despite PCr, patients were treated with "patient-controlled analgesia" (PCA) with opioids for at least 24 hours, switching to conventional intravenous analgesia and oral analgesia in the following days. Demographic, clinical-radiological variables, PCA opioid use, pain grade according to the visual analog scale (VAS), and length of stay (LOS) were compared between the groups. A total of 20 patients were included (12 with PCrSD and 8 with PCr48), without significant differences in demographics or clinical-radiological variables. The overall median time of PCr was 65 minutes (55-127), with no differences between the groups. RESULTS: PCr48 group presented with significantly lower median number of hours of continuous PCA (24 vs. 32 hours; p = 0.031), lower median number of rescue boluses (11 vs. 18; p = 0.042), lower median VAS in the early postoperative hours (2 vs. 5.5; p = 0.043), and lower median LOS (3.5 vs. 5 days). CONCLUSION: PCr performed 48 hours prior to surgery is more effective in terms of PCA requirements, VAS, and LOS when compared with cryoanalgesia on the same day.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Analgesia, Patient-Controlled; Pain Management

Postoperative pain control following minimally invasive correction of pectus excavatum in pediatric patients: A systematic review - Archer, Victoria; Robinson, Tessa; Kattail, Deepa; Fitzgerald, Peter; Walton, J. Mark (Journal of Pediatric Surgery, 2020)
PURPOSE: Surgery for pectus excavatum is associated with significant postoperative pain. The aim of this study was to summarize the current literature regarding postoperative pain control for pediatric patients undergoing minimally invasive repair of pectus excavatum (MIRPE). METHODS: A systematic search of Medline, Embase, PubMed, CINAHL, Web of Science, and the Cochrane Library for randomized controlled trials (RCT) comparing methods of pain control in pediatric patients undergoing MIRPE was conducted. Studies were restricted to the English language. RESULTS: After screening 1304 references, 9 randomized control trials (RCTs) enrolling 485 patients were included. The average age was 11.9 years (±3.1). Pain scores were decreased with ropivacaine compared to bupivacaine-based epidurals. In studies comparing ketamine to opioid based patient-controlled anesthesia (PCA) pumps, the results were variable. Intercostal and paravertebral nerve blocks had decreased pain scores in 75% of the studies compared to opioid-based PCA. Opioid consumption was decreased in 50% of the trials assessing ketamine-based infusions and 75% of the studies comparing intercostal and paravertebral nerve blocks. Nausea was decreased in several of the ketamine-based infusion and intercostal and paravertebral nerve block studies. CONCLUSION: Ketamine-including infusions or paravertebral and intercostal nerve blocks may represent superior methods of postoperative pain control for MIRPE. Further work is needed to confirm results. LEVEL OF EVIDENCE: 2A [1].
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Analgesics; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesics, Opioid; Bupivacaine; Ketamine; MIRPE: minimally invasive repair of pectus excavatum; Pain; Pediatric; Postoperative

Intercostal Nerve Cryoablation in Minimally Invasive Repair of Pectus Excavatum: Effect on Pulmonary Function - Lai, Krista; Lee, Justin; Notrica, David M.; Egan, J. Craig; McMahon, Lisa E.; Molitor, Mark S.; Bae, Jae-O.; Ostlie, Daniel J.; Padilla, Benjamin E. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2022)
Introduction: Cryoablation of intercostal nerves is performed for pain control after minimally invasive repair of pectus excavatum (MIRPE). Cryoablation affects both sensory and motor neurons, resulting in temporary anesthesia to the chest wall and loss of intercostal motor function. The study objective is to determine the effect of cryoablation on incentive spirometry (IS) volumes, as a measure of pulmonary function, after MIRPE. Materials and Methods: A single-institution retrospective review of pediatric patients undergoing MIRPE was performed. All patients received a multimodal regimen (MMR) of analgesics postoperatively. Three groups were compared-cryoablation (CRYO), elastomeric pain pump (EPP), and MMR alone. The primary outcomes were postoperative IS volumes and IS volumes as a ratio of preoperative forced vital capacity (FVC). Secondary outcomes included pain scores, opioid use, length of stay (LOS), and infectious complications. Results: MIRPE was performed in 115 patients: 50 CRYO, 50 EPP, and 15 MMR alone. Groups were similar for demographics and pectus excavatum severity. Postoperative spirometry measurements were similar across groups: IS (CRYO 750 mL [500,961] versus EPP 750 mL [590,1019] versus MMR 696 mL [500,1037], P = .77); IS/FVC (CRYO 0.19 [0.14,0.26] versus EPP 0.20 [0.16,0.26] versus MMR 0.16 [0.15,0.24], P = .69). Although pain scores were also similar across groups, CRYO patients used less opioid (P < .05) and had shorter LOS (P < .05). Postoperative pneumonia was rare and similar across groups (P = 1.00). Conclusion: Intercostal nerve cryoablation during MIRPE does not adversely affect postoperative IS volumes or increase pneumonia rate, despite the temporary loss of motor innervation to intercostal muscles. Cryoablation provides effective pain control with less opioid use.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; MIRPE; Nuss; cryoablation; incentive spirometry; pectus; pulmonary function

Postoperative management of pediatric patients undergoing minimally invasive repair of pectus excavatum: Where are we now? - Kirupaharan, Sawmmiya; Briatico, Daniel; Robinson, Tessa; Fitzgerald, Peter; Walton, J. Mark (Journal of Pediatric Surgery, 2022)
PURPOSE: Minimally invasive repair of pectus excavatum (MIRPE) often leads to a painful and challenging recovery period. This study aims to describe the postoperative management of pediatric patients undergoing MIRPE and compare postoperative outcomes between patients using different routes of postoperative analgesia. METHODS: Retrospective chart review of pediatric patients who underwent MIRPE from July 2003 to September 2019 at a single pediatric tertiary care center. Data on pain management and course of hospital stay were ascertained. Descriptive statistics, Mann-Whitney U and Pearson Chi-Square tests were used to analyze data. A p-value <0.05 was considered significant. RESULTS: Of the 115 patients identified, 58 (50.4%) managed pain postoperatively using thoracic epidural and 57 (49.6%) used intravenous patient-controlled analgesia (IVPCA). The transition from the predominant use of epidural to IVPCA for MIRPE occurred between 2012 and 2013. Higher pain scores were reported by the IVPCA group at 6 h (p<0.001) and 12 h (p<0.001) postoperative. Patients using IVPCA had lower postoperative opioid consumption (p<0.001) and switched to oral opioids sooner than the epidural group (p<0.001). Fewer patients in the IVPCA group required urinary catheterization (p<0.001). Patients using IVPCA had a shorter hospital stay (4 days [IQR 4-5]) compared to the epidural group (5.5 [IQR 5-6]; p<0.001). Readmission was comparable at 3.48% in the total sample. CONCLUSION: Patients using intravenous patient-controlled analgesia reported higher pain scores however, this route of analgesia was associated with shorter hospital stay. Prospective studies designed to address moderator variables are required to confirm findings and develop standardized recovery protocols.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Analgesia, Patient-Controlled; Prospective Studies; MIRPE; Pain management; Quality improvement

Same-day discharge following the Nuss repair: A comparison - Rettig, R. Luke; Rudikoff, Andrew G.; Annie Lo, Hoi Yee; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: Intercostal Nerve Cryoablation (INC) has significantly improved pain control following the Nuss repair of pectus excavatum (PE). This study sought to evaluate patients undergoing the Nuss repair with INC compared to the Nuss repair with an ERAS protocol, INC, and intercostal nerve blocks (INB). METHODS: In June 2020, a new protocol was implemented involving surgery, anesthesia, nursing, physical therapy, and child life with the goal of safe same day discharge for patients undergoing the Nuss repair. They were compared to a control group who underwent the Nuss repair with INC alone in 2017-2019. The primary outcome measure was hospital length of stay (LOS) in hours, secondary outcomes were number of patients discharged on postoperative day (POD) 0, and returns to the emergency department (ED), urgent care (UC), and operating room (OR). RESULTS: The characteristics between the groups were the same (Table 1). The mean LOS was 11.8 h in the INB group versus 58.2 h in the INC group, p < 0.01. 10 of 15 patients in the INB group went home on POD 0 (average of 5.5 h postop), versus 0 patients in the INC only group, p < 0.01. Five patients in the INB stayed overnight. Two patients stayed owing to anxiety, one owing to urinary retention, one owing to nausea, and one owing to drowsiness. None stayed for pain control. Four patients in the INC group returned to the ED for pain control, versus 0 in the INB group, and 1 patient in the INB returned to UC for constipation. CONCLUSIONS: The majority of patients undergoing the Nuss repair of PE with a multidisciplinary regimen of pre and postoperative nursing education, precise intraoperative anesthesia care, performance of direct vision INB and INC, as well as careful surgery can go home on the day of surgery without adverse outcomes or unanticipated returns to the hospital. LEVEL-OF-EVIDENCE: Level II.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Intercostal nerve cryoablation; Enhanced recovery after surgery (ERAS); Patient Discharge; Pectus excavatum repair; Same day discharge; Anesthesia, Conduction; Intercostal nerve block

Neurolysis for analgesia following pectus repair in a national cohort - Pecoraro, Anthony R.; Hunter, Chelsea E.; Colgate, Cameron L.; Landman, Matthew P. (Journal of Pediatric Surgery, 2022)
INTRODUCTION: Pectus excavatum and pectus carinatum are the most common chest wall deformities of childhood. Surgical repair can be complicated by post-operative analgesic challenges. Thoracic epidural analgesia, patient-controlled analgesia, and multimodal pain control are among the most common strategies. We sought to define the current utilization of intraoperative thoracic neurolysis, hypothesizing that this would minimize length of stay (LOS) and post-operative narcotic use with relatively higher proportion of non-narcotic post-operative analgesia. METHODS: We performed a retrospective review of the Pediatric Health Information System (PHIS) database between 2017 and 2020. We first identified patients who underwent a pectus repair via ICD-10-PCS codes. We used ICD-10-PCS codes 01580ZZ and 01584ZZ to identify those patients who underwent concomitant thoracic neurolysis. Statistical analyses were performed using R; p value less than 0.05 was considered significant. RESULTS: We identified 2979 patients who underwent a pectus repair. 184 underwent a concomitant thoracic nerve destruction procedure (6.7%); 13 were performed in 2017 (2.01%), 76 in 2018 (10.7%), and 84 in 2019 (9.6%). LOS was shorter in those patients who underwent neurolysis (mean=2.55 vs 3.73 days, SD=1.33 vs 1.78 days, p<0.001). There were fewer post-operative ICU admissions in neurolysis patients (3/184 vs. 193/2795, p = 0.003). The cost of procedures that included a neurolysis were higher, though not significantly so (mean=$24,885.64 vs $22,200.59). CONCLUSION: Thoracic neurolysis may be a useful analgesic strategy, expediating post-operative discharge and potentially obviating the need for intensive care. Further larger-scale prospective trials should be considered to further elucidate the role of this analgesia method. LEVEL OF EVIDENCE: Level III.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Pectus excavatum; Length of Stay; Prospective Studies; Analgesia, Epidural; Analgesics, Non-Narcotic; Cryoanalgesia; Neurolysis; Thoracic Wall

Limited cryoablation reduces hospital stay and opioid consumption compared to thoracic epidural analgesia after minimally invasive repair of pectus excavatum - Song, Seung Hwan; Moon, Duk Hwan; Shim, Yon Hee; Jung, Hyunjoo; Lee, Sungsoo (Medicine, 2022)
pain following minimally invasive repair of pectus excavatum (MIRPE) is a critical concern that leads to a prolonged hospital stay and high doses of opiates administered to the patients. This study aimed to evaluate the efficacy of intraoperative cryoanalgesia (cryoablation of the intercostal nerves) during MIRPE. We retrospectively analyzed the data of 64 patients who underwent MIRPE and received cryoanalgesia or epidural analgesia between January 2019 and January 2021. The oral morphine milligram equivalent (MME) was used to calculate the dosage of opioid agents. The median age was 15 years (range, 4-33 years). The median postoperative hospital stay was 4 days (range, 2-6 days), with a median oral MME consumption of 45 mg (ranging from 0 to 1360 mg). Cryoanalgesia was performed in 38 patients, and epidural analgesia was administered to the remaining 26 patients. The cryoanalgesia group had a significantly lesser pain score, shorter postoperative hospital stay and lower oral MME consumption than the epidural analgesia group (5 vs 2; P < .001, 3 days vs 5 days; P < .001, 19 mg vs 634 mg; P < .001). Cryoanalgesia appears to reduce postoperative hospital stay and opioid consumption compared with epidural analgesia. The outcomes of this study indicate that cryoanalgesia might be a safe and effective method for pain control following MIRPE.
Keywords: Humans; Adolescent; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Length of Stay; Analgesia, Epidural

Outcomes Using Cryoablation for Postoperative Pain Control in Children Following Minimally Invasive Pectus Excavatum Repair - Sujka, Joseph; Benedict, Leo Andrew; Fraser, Jason D.; Aguayo, Pablo; Millspaugh, Daniel L.; St Peter, Shawn D. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2018)
PURPOSE: Pain is the main factor that determines the postoperative course for patients undergoing pectus bar placement. Cryoablation of the intercostal nerves has been suggested to mitigate this pain. We instituted a protocol for using intercostal cryoablation and report our early results compared to our immediately previous cohort. MATERIALS AND METHODS: A retrospective study was conducted on patients undergoing minimally invasive repair for pectus excavatum between January 1, 2017, and August 21, 2017. Demographic data, anthropometrics, operative times, type and duration of patient analgesia, and postoperative length of stay were collected. Descriptive statistics were performed with all means reported ± standard deviations. Comparisons between groups were analyzed on STATA using T-tests with a P value <.05 determined as significant. RESULTS: Twenty-eight patients were treated for pectus excavatum during the study period with 9 (32%) undergoing cryoablation. Mean number of rib spaces ablated was 5 ± 0.53 with no reported intraoperative complications. Mean operative time was 30 minutes longer in the cryoablation group (P = .00). Days to only oral pain medication was shorter in the cryoablation group, (1.22 ± 0.66 day versus 2.63 ± 0.68 day, P = .00). Length of stay, in days, was shorter in the cryoablation group (1.4 ± 0.72 days versus 4.0 ± 1.0 days, P = .00). There were no reported complications from cryoablation or bar placement during the study period. Days to discontinuation of oral narcotics were less in the cryoablation group (8.2 ± 7.0 versus 18.2 ± 10.4, P = .00). CONCLUSION: Cryoablation after pectus bar placement dramatically decreases narcotic usage and postoperative length of stay.
Keywords: Humans; Adolescent; Female; Male; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Minimally Invasive Surgical Procedures; Cryosurgery; Intercostal Nerves; Length of Stay; Operative Time; Cohort Studies; cryoablation; epidural; minimally invasive; Narcotics; patient-controlled anesthesia; pectus excavatum

Pectus patient information website has improved access to care and patient reported outcomes - Tikka, Theofano; Webb, Joanne; Agostini, Paula; Kerr, Amy; Mannion, Glenn; Steyn, Richard S.; Bishay, Ehab; Kalkat, Maninder S.; Rajesh, Pala B.; Naidu, Babu (Journal of Cardiothoracic Surgery, 2016)
BACKGROUND: Pectus is the most common congenital disorder. Awareness amongst primary care physicians and the general public is poor. NHS commissioning bodies plan to withdraw funding for this surgery because they deem a lack of sufficient evidence of benefit. The purpose of this study is to assess the effects of introducing a patient information website on referral and activity patterns and on patients reported outcomes. METHODS: We produced an innovative information website, www.pectus.co.uk , accessible to the general public, providing information about pectus deformities; management options and advice about surgery. Referral patterns and number of cases where studied before and after the introduction of the website in 2010. Patients' satisfaction post-op was assessed using the Brompton's single step questionnaire (SSQ). RESULTS: The website had considerable traffic with 2179 hits in 2012, 4983 in 2013 and 7416 in 2014. This has led to 1421 contacts and 372 email enquiries. These emails have resulted in an increased number of patients who have been assessed and go on to have surgery. We asked 59 pectus excavatum patients who were operated from 2008 to 2014 to complete the SSQ. We received 32 replies. Eighty-four percent (16/19) of patients who visited the website and then underwent surgery, found the website useful. All patients scored satisfactorily in SSQ. Even though those who visited the website tended to be more satisfied with the surgical outcomes this did not reach statistical significance. This group of patients said that would have the operation again given the option compared to 76.9 % of the group who did not visit the website before surgery (p=0.031). Despite the fact that patients who visited the website experienced more post-operative complications were equally or more satisfied with post-operative outcomes. The overall SSQ obtainable score was not different for the two subgroups, being more widespread in the group that did not visit the website. CONCLUSIONS: The introduction of a pectus patient information website has significantly improved access to specialised services. Patients are overall highly satisfied with the surgical outcomes.
Keywords: Humans; Adolescent; Female; Male; Young Adult; Thoracic Surgical Procedures; Internet; Funnel Chest; Information; Patient Education as Topic; Patient Outcome Assessment; Pectus website; Surveys and Questionnaires

Short and long term outcomes of using cryoablation for postoperative pain control in patients after pectus excavatum repair - Fraser, James A.; Briggs, Kayla B.; Svetanoff, Wendy Jo; Aguayo, Pablo; Juang, David; Fraser, Jason D.; Snyder, Charles L.; Oyetunji, Tolulope A.; St Peter, Shawn D. (Journal of Pediatric Surgery, 2022)
INTRODUCTION: We report the findings of a three-year prospective observational study elucidating long-term symptoms and complications of patients who underwent minimally invasive pectus excavatum repair with intercostal nerve cryoablation with specific attention to postoperative pain control associated with the cryoablation technique. METHODS: Surveys were administered to patients who underwent bar placement for pectus excavatum with intercostal nerve cryoablation from 2017 to 2021 regarding pain scores, pain medication usage, and limitations to activity beginning on the day of surgery, on the day of discharge, and at two-week and three-month follow-up. RESULTS: Of 110 patients, forty-eight (44%) completed the discharge survey; sharp pain and pressure on the first postoperative night were the most described pain characteristics, most frequently in the middle of the chest. On follow-up, 55% of patients reported tolerable residual pain at two weeks and 41% at three months, with 25% requiring intermittent pain medication at three months. There were three readmissions for inadequate pain control and 110 calls to the surgery clinic by three-month follow-up, most commonly for persistent pain and frequent popping sensation with movement. DISCUSSION: Although cryoablation is an excellent pain control modality, these data suggest that patients underreport functional symptoms and experience more frequent discomfort and alteration of daily living activities.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Cryosurgery; Intercostal Nerves; Intercostal cryoablation; Nuss bar; Thoracoscopy

Epidural versus PCA Pain Management after Pectus Excavatum Repair: A Multi-Institutional Prospective Randomized Trial - Sujka, Joseph A.; Dekonenko, Charlene; Millspaugh, Daniel L.; Doyle, Nichole M.; Walker, Benjamin J.; Leys, Charles M.; Ostlie, Daniel J.; Aguayo, Pablo; Fraser, Jason D.; Alemayehu, Hanna; Peter, Shawn D. St (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2020)
INTRODUCTION: Postoperative pain control remains the primary reason for inpatient stay after minimally invasive repair of pectus excavatum. In a previous study, our group reported that early pain control was better in patients managed with a thoracic epidural, while late pain control was better in patients managed with patient-controlled analgesia (PCA). After revising our epidural transition and modifying the PCA protocol, we conducted a multi-institutional prospective randomized trial to evaluate these two pain control strategies. MATERIALS AND METHODS: Patients were randomized to epidural or PCA following minimally invasive repair of pectus excavatum with standard protocols for each arm. Primary outcome was length of stay with secondary variables including mean patient pain scores, complications, and parental satisfaction. Scores were pooled for the two groups and reported as means with standard deviation. Results were compared using t-tests and one-way analysis of variance with p-value < 0.05 determining significance. RESULTS: Sixty-five patients were enrolled, 32 epidural and 33 PCA. Enrollment was stopped early when we developed an alternative strategy for controlling these patients' pain. There was no difference in length of stay in hours between the two arms; epidural 111.3 ± 18.5 versus PCA 111.4 ± 51.4, p = 0.98. Longer operative time was found in the epidural group. Nine patients in the epidural group (28%) required a PCA in addition to epidural for adequate pain control. Mean pain scores were lower on postoperative day 0 in the epidural group compared with the PCA groups, but were otherwise similar. CONCLUSION: In our prospective randomized trial, PCA is just as effective as thoracic epidural in decreasing early postoperative pain scores after minimally invasive repair of pectus excavatum.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Length of Stay; Analgesia, Patient-Controlled; Prospective Studies; Analgesia, Epidural; Operative Time

Do health beliefs affect pain perception after pectus excavatum repair? - Sujka, Joseph; St Peter, Shawn; Mueller, Claudia M. (Pediatric Surgery International, 2018)
PURPOSE: The pain experience is highly variable among patients. Psychological mindsets, in which individuals view a particular characteristic as either fixed or changeable, have been demonstrated to influence people's actions and perceptions in a variety of settings including school, sports, and interpersonal. The purpose of this study was to determine if health mindsets influence the pain scores and immediate outcomes of post-operative surgical patients. METHODS: As part of a multi-institutional, prospective, randomized clinical trial involving patients undergoing a minimally invasive pectus excavatum repair of pectus excavatum, patients were surveyed to determine whether they had a fixed or growth health mindset. Their post-operative pain was followed prospectively and scored on a Visual Analog Scale and outcomes were measured according to time to oral pain medication use. RESULTS: Fifty patients completed the Health Beliefs survey, 17 had a fixed mindset (8 epidural, 9 PCA) and 33 had a growth mindset (17 epidural, 16 PCA). Patients with a growth mindset had lower post-operative pain scores than patients with a fixed mindset although pain medication use was not different. CONCLUSION: This is the first usage of health mindsets as a means to characterize the perception of pain in the post-operative period. Mindset appears to make a difference in how patients perceive and report their pain. Interventions to improve a patient's mindset could be effective in the future to improve pain control and patient satisfaction.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesia, Patient-Controlled; Prospective Studies; Attitude to Health; Fixed; Growth; Mindset; Pain Measurement; Pain Perception; Pain scores; Patient Satisfaction; Postoperative Period; Thoracoplasty; Visual Analog Scale

Postoperative pain and psychological outcomes following minimally invasive pectus excavatum repair: A report from the Society for Pediatric Anesthesia Improvement Network - Uhl, Kristen M.; Wilder, Robert T.; Fernandez, Allison; Huang, Henry; Muhly, Wallis T.; Zurakowski, David; Cravero, Joseph P. (Paediatric Anaesthesia, 2020)
BACKGROUND: Minimally invasive repair of pectus excavatum (MIRPE) is associated with less tissue trauma; however, it may result in increased postoperative pain. Pain experience is a known risk factor for the development of posttraumatic stress symptoms, though there are little data on its relationship with long-term psychological outcomes following major surgery in pediatric patients. AIMS: In this study, we examined the relationship between immediate postoperative pain and psychological outcomes at 2 weeks and three months after discharge in a cohort of pediatric patients who underwent MIRPE. We sought to determine whether immediate postoperative pain levels were associated with ongoing distress related to aspects of surgery at both time points. We were also interested in how psychological symptoms related to persistent pain concerns. METHODS: Data on patients undergoing MIRPE across 14 institutions were collected as part of the Society for Pediatric Anesthesia Improvement Network (SPAIN). Patients were contacted at 2 weeks and three months following discharge to track pain levels and assess psychological distress using a self-report questionnaire. Patients were grouped into cohorts based on self-report of distress related to aspects of surgery, nonsurgical distress, or absence of distress. RESULTS: Analysis revealed that a higher proportion of children reporting ongoing distress related to surgery at both 2 weeks and 3 months experienced higher immediate postoperative pain levels. A subset of patients with complete data sets for 2 weeks and 3 months (N = 76) was further examined. Among the 47 patients who endorsed surgical distress at 2 weeks, 25 (53.2%) continued to endorse surgical distress at 3 months. Additionally, report of surgical distress at 3 months was associated with longer-term postoperative pain. CONCLUSIONS: Our data suggest that, in patients undergoing MIRPE, the presence of distress at 2 weeks and 3 months may be associated with higher immediate postoperative pain levels.
Keywords: Humans; surgery; Child; Funnel Chest; Pain, Postoperative; Minimally Invasive Surgical Procedures; Anesthesia; distress; outcomes; pediatric

Pain Management in Pectus Excavatum Surgery: A Comparison of Subcutaneous Catheters Versus Epidurals in a Pediatric Population - Thaker, Shefali; McKenna, Elise; Rader, Christine; Misra, Meghna V. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2019)
BACKGROUND: Pectus excavatum is a common chest wall anomaly. Achieving optimal pain control is a priority for adolescents undergoing surgical correction of this condition. Options for pain control include the use of subcutaneous catheters (On-Q® pumps) and epidurals. The objective of this study is to demonstrate the feasibility of using subcutaneous catheters for pain control and to compare them with the use of epidurals during surgical correction of pectus excavatum. MATERIALS AND METHODS: We identified patients who underwent pectus excavatum repair at our institution between January 2010 and August 2016. Patients were divided into two cohorts (epidural or On-Q pump). Patient charts were reviewed for length of stay, pain scores, pain medications, and complications. RESULTS: A total of 124 patients were included. Forty percent of patients used an epidural (n = 50), and 60% had the On-Q pump (n = 74). The average patient age was 15.6 years. The average Haller index was 4.3. The On-Q pump population had a significant decrease in postoperative length of stay (mean [M] = 4.86, standard deviation [SD] = 0.85) compared with the epidural population (M = 5.60, SD = 0.97); P ≤ .001. There was a significant difference observed in pain scores for patients on the epidural (M = 2.91, SD = 1.13) and On-Q pump (M = 3.81, SD = 1.19; P ≤ .001). There was n = 1 wound infection in each group. CONCLUSION: The use of bilateral subcutaneous infusion catheters is a safe and effective method for pain control in patients undergoing surgical correction of pectus excavatum. Even though the degree of pain control is not necessarily superior to epidurals, in this study, the catheters were associated with a shorter postoperative length of stay in this patient population and did not increase the incidence of complications.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Length of Stay; Pain Management; Pain Measurement; Analgesia, Epidural; epidural; pectus excavatum; Infusion Pumps; Catheters; Infusions, Subcutaneous; length of stay; On-Q Pump; pain management

Correlation of Preoperative State Anxiety and Pain Six Weeks After Surgical Correction of Pectus Excavatum - Zuidema, Wietse P.; Oosterhuis, Jan Wa; van der Heide, Stefan M.; de Lange-de Klerk, Elly; van der Steeg, Alida Fw; van Heurn, Ernst Lwe (Anesthesiology and Pain Medicine, 2020)
BACKGROUND: Pain is a major concern in the early postoperative phase after correction of pectus excavatum. Most studies only focus on pain management in the first days after surgery and describe methods to alleviate the pain immediately postoperatively. The severity of postoperative pain may be influenced by anxiety. So far, few studies have looked into the relationship between anxiety and postoperative pain after pectus excavatum correction. OBJECTIVES: This study aimed to investigate the correlation between preoperative anxiety and late postoperative pain scores. METHODS: This was a prospective cohort study. Anxiety was assessed with the State and Trait Anxiety Inventory questionnaire. Visual analogue scale (VAS) for pain scores assessed the pain at rest and activity. Anxiety was measured before surgery and pain scores six weeks after surgery. A hierarchical linear regression analysis was performed to investigate the correlation between baseline anxiety and pain measurements six weeks after surgery. RESULTS: In this study, 136 patients were included. State anxiety was not associated with postoperative pain (mean of pain on activity and in rest), only with pain on activity after six weeks. Age and sex were not effect modifiers in any of the models. Relevant confounding factors, although not significant, consisted of trait, sex, minor complications, epidural duration, major complications, and the number of stabilizer plates. The explained variance of state anxiety on VAS for pain scores was minimum after 6 weeks. CONCLUSIONS: Preoperative anxiety does not appear to influence postoperative pain after PE correction.
Keywords: Pediatric; Anesthesia; Chest Wall; Fear; Postoperative Management; Thoracic Surgery

Ultrasound-Guided Percutaneous Cryoanalgesia for Pectus Excavatum: When Should It be Applied? - Velayos, María; Alonso, Mercedes; Estefanía, Karla; Jesus Muñoz, Antonio; Torres, Raquel; Hernández, Francisco; Reinoso, Francisco; Torre, Carlos De la (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2023)
INTRODUCTION: The addition of ultrasound-guided percutaneous cryoanalgesia (PCr) for pain management after pectus excavatum (PE) surgery offers a new and advantageous approach. Our aim is to describe our experience with PCr applied on the same day, 24 hours, and 48 hours prior to PE surgery. MATERIAL AND METHODS: Prospective pilot study in patients undergoing ultrasound-guided PCr (2019-2022) was divided into three groups: PCr on the same day of surgery (PCrSD), PCr 24 hours before (PCr24), and PCr 48 hours before (PCr48). We describe the application of technique and data obtained by comparing the three groups. RESULTS: We present 42 patients (25 PCrSD, 11 PCr24, 6 PCr48). PCr24 had a shorter procedure duration than PCrSD (65.8 vs. 91.2 minute; p = 0.048). Related to analgesia, PCr24 and PCr48 showed lower opioid consumption than PCrSD in PCA volume (48.5 and 49.6 vs. 75.1 mL; p = 0.015) and PCA time (23.3 and 23.8 vs. 34.3 hours; p = 0.01). Degree of pain (VAS scale) on the day of surgery and on the second postoperative day was lower in PCr24 and PCr48 than in PCrSD (4 and 2 vs. 5; p = 0.012; 0 and 1 vs. 2; p = 0.01, respectively) as well as shorter hospital stay (3 and 3.5 vs. 5 days; p = 0.021). In addition, PCr24 showed lower opioid consumption and hospital stay than PCr48 (p > 0.05). The greatest savings in hospital costs were obtained in the PCr24 group. CONCLUSION: PCr48 and PCr24 prior to PE surgery offers lower opioid consumption, less pain and shorter hospital stay than PCrSD. PCr24 is comparable to PCr48, but seems to show advantages and simpler logistics for the patient and the hospital.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Prospective Studies; Ultrasonography, Interventional; Pilot Projects

Ultrasound-guided erector spinae plane block versus thoracic epidural analgesia: Postoperative pain management after Nuss repair for pectus excavatum - Bliss, David P.; Strandness, Thomas B.; Derderian, Sarkis C.; Kaizer, Alexander M.; Partrick, David A. (Journal of Pediatric Surgery, 2022)
AIM OF THE STUDY: Postoperative pain management is a significant challenge in patients undergoing Nuss repair for pectus excavatum chest wall deformity. Therapeutic anesthetic options primarily include patient-controlled intravenous analgesia, thoracic epidural analgesia (TEA), and cryoanalgesia. However, TEA is limited to inpatient use and both TEA and cryoanalgesia can result in neurologic injury. The novel technique of ultrasound-guided erector spinae plane regional analgesia has been used recently in our patients undergoing the Nuss repair and has shown impressive pain relief, but without the potential complications of other modalities. Erector spinae plane block (ESPB) postoperative pain management outcomes were studied as compared to TEA. METHODS: Thirty consecutive patients with severe pectus excavatum undergoing Nuss repair and placement of ultrasound-guided ESPB were each paired to a historical cohort control patient with TEA postoperative pain management. The cohort patient match was defined by age (± 2 years), gender, and CT pectus index (± 15%). Study variables included hospital length of stay (LOS), pain scores, and pain medication usage. RESULTS: Pain scores as measured by area under the curve per hour (Day 1: 2.72 (SD = 1.37) vs. 3.90 (SD = 1.81), P = 0.006; Day 2: 2.83 (SD = 1.32) vs. 3.97 (SD = 1.82), P = 0.007) and oral morphine equivalent (OME) pain medication usage (Day 1: 11.9 (SD = 4.9) vs 56.0 (SD = 32.2), P < 0.001; Day 2: 14.7 (SD = 7.1) vs. 38.0 (SD = 21.7), P < 0.001) were higher for the first two postoperative days in the ESPB group. However, mean hospital LOS was nearly one day shorter for ESPB patients (3.78 (SD = 0.82) vs. 2.90 (SD = 0.87), P < 0.001) who were discharged home with the catheter in place until removal, typically at 5-7 days postoperatively. CONCLUSION: Ultrasound-guided ESPB is thus a feasible, safe, and effective alternative to TEA in postoperative pain management after Nuss repair and results in decreased hospital stay. LEVEL OF EVIDENCE: III.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Analgesia, Epidural; Erector spinae plane block; Nerve Block; Nuss repair; Ultrasonography, Interventional

Thoracoscopic cryoanalgesia: A new strategy for postoperative pain control in minimally invasive pectus excavatum repair - Cadaval Gallardo, C.; Martínez, J.; Bellía-Munzon, G.; Nazar, M.; Sanjurjo, D.; Toselli, L.; Martínez-Ferro, M. (Cirugia Pediatrica: Organo Oficial De La Sociedad Espanola De Cirugia Pediatrica, 2020)
OBJECTIVE: Recent publications report early discharge and low opioid requirements after minimally invasive pectus excavatum repair treated with bilateral intercostal nerve cryoablation. Our aim is to report our initial experience with this technique. MATERIAL AND METHODS: Retrospective analysis of medical records of patients undergoing bilateral thoracoscopic cryoanalgesia during minimally invasive pectus excavatum repair within our institution from September 2018 to March 2019. TECHNIQUE: A cryoprobe was applied at -70 ºC for 2 minutes each from the 3rd to the 7th intercostal nerves bilaterally under thoracoscopic control. Postoperative pain was assessed using a visual analogue scale (VAS). RESULTS: Twenty-one patients were included. Ninety percent were male, the mean age being 15.2 ± 4.29 years, and the mean weight being 53.6 ± 15.33 kg. The average Haller index was 5.1 ± 2.97, and the mean repair index was 37.6 ± 13.77%. The mean number of implants introduced was 2.55 ± 0.74. The mean duration of cryoanalgesia was 39.9 ± 21.1. No patients received epidural anesthesia. Mean postoperative stay was 1.64 ± 0.73 days. Seventy-one percent of the patients required 1 dose of opioids at the most for postoperative pain control. According to the VAS, the average pain score on postoperative days 1, 3, 7, and 21 was 2.55, 2.01, 0.5, and 0.06, respectively. CONCLUSIONS: Bilateral thoracoscopic cryoanalgesia during minimally invasive pectus excavatum repair leads to early discharge and good postoperative pain control in all cases. Cryoanalgesia has become our treatment of choice for pain control in the thoracoscopic repair of pectus excavatum.
Keywords: Humans; Adolescent; Female; Male; Young Adult; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Length of Stay; Pain Measurement; Cryoanalgesia; Thoracoscopy; Minimally invasive pectus excavatum repair; Intercostal nerve; Nerve cryoablation; Postoperative pain

Cryoanalgesia is Associated With Decreased Postoperative Opioid Use in Minimally Invasive Repair of Pectus Excavatum - Arshad, Seyed A.; Ferguson, Dalya M.; Garcia, Elisa I.; Hebballi, Nutan B.; Buchanan, Allison C.; Tsao, KuoJen (The Journal of Surgical Research, 2022)
BACKGROUND: Postoperative pain control is challenging after pectus excavatum repair. We aimed to understand the impact that cryoanalgesia had on opioid utilization and outcomes of pediatric patients undergoing minimally invasive repair of pectus excavatum (MIRPE). METHODS: A single-center retrospective cohort study was conducted of all patients (< 18 y) who underwent MIRPE (2011-2019). Patients receiving cryoanalgesia were compared to those who did not. The primary outcome was total postoperative, inpatient, opioid use, measured as milligrams of oral morphine equivalents per kilogram (OME/kg). Univariate and multivariable analyses were performed. RESULTS: Of 35 patients, 20 received cryoanalgesia (57%). Baseline characteristics were similar. Patients who received cryoanalgesia had a lower opioid requirement: median 2.3 mg OME/kg (IQR 1.2-3.1), versus 4.9 mg OME/kg (IQR 2.9-5.8), P < 0.001. Accounting for receipt of cryoanalgesia, epidural, and/or patient-controlled analgesia, cryoanalgesia was associated with a 3.3 mg OME/kg reduction in opioid use (P < 0.001). Median length of stay (LOS) was shorter in cryoanalgesia patients: 3.1 d (IQR 2.3-3.4), versus 5.1 d (IQR 4.3-5.4), P < 0.001. Complications within 90 d were similar between groups. CONCLUSIONS: Cryoanalgesia is an effective adjunctive pain control modality for patients undergoing MIRPE. Use of cryoanalgesia was associated with lower postoperative opioid requirements and shorter LOS, without increased short-term complications, and should be considered for enhanced recovery after MIRPE.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryoanalgesia; Length of stay; Minimally invasive repair of pectus excavatum; Pain control

Postoperative pain control modalities for pectus excavatum repair: A prospective observational study of cryoablation compared to results of a randomized trial of epidural vs patient-controlled analgesia - Dekonenko, Charlene; Dorman, Robert M.; Duran, Yara; Juang, David; Aguayo, Pablo; Fraser, Jason D.; Oyetunji, Tolulope A.; Snyder, Charles L.; Holcomb, George W.; Millspaugh, Daniel L.; St Peter, Shawn D. (Journal of Pediatric Surgery, 2020)
BACKGROUND: Pain following bar placement for pectus excavatum is the dominant factor post-operatively and determines length of stay (LOS). We recently adopted intercostal cryoablation as our preferred method of pain control following minimally invasive pectus excavatum repair. We compared the outcomes of cryoablation to results of a recently concluded trial of epidural (EPI) and patient-controlled analgesia (PCA) protocols. METHODS: We conducted a prospective observational study of patients undergoing bar placement for pectus excavatum using intercostal cryoablation. Results are reported and compared with those of a randomized trial comparing EPI with PCA. Comparisons of medians were performed using Kruskal-Wallis H tests with alpha 0.05. RESULTS: Thirty-five patients were treated with cryoablation compared to 32 epidural and 33 PCA patients from the trial. Cryoablation was associated with longer operating time (101 min, versus 58 and 57 min for epidural and PCA groups, p < 0.01), resulted in less time to pain control with oral medication (21 h, versus 72 and 67 h, p < 0.01), and decreased LOS (1 day, versus 4.3 and 4.2 days, p < 0.01). CONCLUSION: Intercostal cryoablation during minimally invasive pectus excavatum repair reduces LOS and perioperative opioid consumption compared with both EPI and PCA. LEVEL OF EVIDENCE: II.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Cryosurgery; Length of Stay; Analgesia, Patient-Controlled; Prospective Studies; Analgesia, Epidural; Cryoanalgesia; Minimally invasive pectus excavatum repair; Cryoablation

The incidence of neuropathic pain after intercostal cryoablation during the Nuss procedure - Zobel, Michael J.; Ewbank, Clifton; Mora, Roberta; Idowu, Olajire; Kim, Sunghoon; Padilla, Benjamin E. (Pediatric Surgery International, 2020)
PURPOSE: Intercostal nerve cryoblation during the Nuss procedure for pectus excavatum decreases pain, opiate requirement, and hospital length of stay (LOS) compared to thoracic epidural analgesia. However, long-term complications of cryoablation, including neuropathic pain development, are not well studied. METHODS: We conducted a multi-institutional retrospective review of patients following intercostal nerve cryoablation during Nuss bar insertion (11/2015-7/2018). Patients completed the Leeds Assessment of Neuropathic Symptoms and Signs, a validated questionnaire for detecting neuropathic symptoms. Primary outcome was neuropathic pain development. Secondary outcomes included duration of chest numbness and LOS. T test was performed; p < 0.05 is significant. RESULTS: 43 patients underwent intercostal cryoablation during the Nuss procedure. Ages at repair ranged 11-47 years (median 16). Patients were grouped by age: ≤ 21 years (30 patients) or older (13 patients). Mean LOS was shorter for the younger group, 2.0 versus 3.9 days (p = 0.03). No patients in the younger group, and three in the older, experienced neuropathic pain. Mean time to numbness resolution was shorter for the younger group, 3.4 versus 10.8 months (p = 0.003). CONCLUSION: In pediatric patients, intercostal cryoablation provides effective analgesia following the Nuss procedure with minimal risk of post-operative neuropathic pain. Adult patients are at greater risk of experiencing neuropathic pain and prolonged numbness.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Child; Funnel Chest; Neuralgia; Pain, Postoperative; Retrospective Studies; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Thoracoscopic; Pain Management; Analgesia, Epidural; Incidence; Middle Aged; Neuropathic pain; United States

Comparison of erector spinae plane and paravertebral nerve blocks for postoperative analgesia in children after the Nuss procedure: study protocol for a randomized controlled non-inferiority clinical trial - Xu, Min; Zhang, Guangchao; Gong, Jingxuan; Yang, Jing (Trials, 2022)
BACKGROUND: Thoracic paravertebral block (TPVB) is a widely advocated regional technique for alleviating postoperative pain in children undergoing elective pectus excavatum repair. However, this technique is associated with some undesirable adverse events. Recently, the erector spinae plane block (ESPB) has been introduced as a practical alternative to the TPVB in thoracic surgery. This interfascial regional anesthesia technique interrupts pain sensation by injecting local anesthetics between the muscular layers of the thoracic wall. Several case series described it as an effective pain management technique following pectus excavatum repair. Therefore, this trial is designed to test the hypothesis that ESPB is non-inferior to TPVB in postoperative pain control after pectus excavatum repair. METHODS: This is a prospective randomized double-blind non-inferiority trial. A total of 40 patients aged 4 to 18 years undergoing Nuss surgery will be randomly assigned to receive pain treatment with either ESPB or TPVB. All patients will receive additional systemic multimodal analgesia with an intravenous patient-controlled analgesia pump and acetaminophen. The primary outcome is the pain intensity at rest, 24 h postoperatively. Secondary outcomes include accumulated morphine-equivalent consumption, postoperative pain scores, emergence agitation incidence, time of the first mobilization, time to first rescue analgesia, complications related to pain treatment, and morphine-related adverse events. DISCUSSION: This will the first randomized controlled trial to compare ESPB with TPVB for analgesia after pectus excavatum repair. This trial aims to provide important clinical evidence to elaborate on the analgesic mechanism of ESPB in children. TRIAL REGISTRATION: ClinicalTrials.gov NCT05034601 . This trial was prospectively registered.
Keywords: Humans; Adolescent; Thoracic Surgical Procedures; Child; Pain, Postoperative; Pectus excavatum; Analgesia, Patient-Controlled; Prospective Studies; Pain management; Erector spinae plane block; Nerve Block; Child, Preschool; Randomized controlled trial; Randomized Controlled Trials as Topic; Thoracic paravertebral block

Pain management following the Nuss procedure: a survey of practice and review - Muhly, W. T.; Maxwell, L. G.; Cravero, J. P. (Acta Anaesthesiologica Scandinavica, 2014)
BACKGROUND: Pectus excavatum is the most common congenital chest wall deformity. The Nuss procedure is frequently used for surgical correction and this technique has been associated with severe and prolonged post-operative pain. At the present time, the optimal analgesic strategy for managing patients following this procedure has not been determined. METHODS: A web-based survey was sent to representatives from 108 primarily pediatric hospitals in North America, Europe, Asia and Australia. One individual per institution was contacted to complete the survey on behalf of their department. RESULTS: Survey response rate was 54% and 55 institutions reported using the Nuss procedure for correction of pectus excavatum. Annual case volume is less than or equal to 25 cases in 57% of institutions, and the most common age of patients is 14 to 17 years old. A clinical protocol for patient post-operative pain management is used in 45% of institutions. Thoracic epidural is utilized as a primary analgesic modality by 91% of institutions. Concomitant use of intravenous patient-controlled analgesia is reported by 27% of institutions. Nine respondents (16%) reported that they had recently stopped performing epidurals because of surgeon preference. Referral of one or more patients annually for chronic pain management was reported in 22% of surveys. CONCLUSIONS: Post-operative pain management following the Nuss procedure is variable and poorly characterized. Clinical trials or large observational registries comparing the safety and efficacy of primary modalities and long-term outcomes are needed to enable evidence-based decision-making for the management of these patients.
Keywords: Europe; Humans; Adolescent; Asia; Australia; Analgesia; Child; Funnel Chest; Pain, Postoperative; Analgesia, Patient-Controlled; Pain Management; Analgesia, Epidural; Health Care Surveys; North America; Practice Patterns, Physicians'

Postoperative Pain Outcomes After Nuss Procedures: Comparison of Epidural Analgesia, Continuous Infusion of Local Anesthetic, and Preoperative Self-Hypnosis Training - Manworren, Renee C. B.; Anderson, Matthew N.; Girard, Eric D.; Ruscher, Kimberly A.; Verissimo, Ana Maria; Palac, Hannah; Weiss, Richard; Rader, Christine; Hight, Donald (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2018)
BACKGROUND/PURPOSE: The Nuss procedure to correct pectus excavatum is associated with severe postoperative pain. The purpose of this retrospective study was to compare pain management outcomes of thoracic epidural analgesia and continuous infusion of local anesthetic (CILA) with and without preoperative self-hypnosis training (SHT) after Nuss procedure (4 treatment groups). METHODS: Between February 2010 and December 2013, 24 of 53 adolescents who underwent Nuss procedure received SHT. Of these, 16 received thoracic epidural analgesia and 8 received CILA postoperatively. Of the 29 patients who did not receive SHT, 19 received thoracic epidural analgesia and 10 received CILA. All patients received intravenous patient-controlled opioid analgesia and intravenous nonsteroidal anti-inflammatory drugs (IVNSAIDs) and then were transitioned to oral opioids and NSAIDs. Postoperative mean and maximum pain scores, opioid (morphine equivalents) use and side effects, and hospital length of stay (LOS) were compared between groups. RESULTS: Patients who received SHT reported lower mean (P = .0047) and maximum (P = .0028) pain scores and used less morphine equivalents/hour over time (P = .046) compared to patients who did not receive SHT. Patients who received thoracic epidural analgesia reported lower mean (P = .0092) and maximum (P = .0083) postoperative pain scores and used more morphine equivalents/hour (P = .01) compared to those who received CILA. In addition, patients who received SHT and CILA had shorter LOS (P = .0013) than patients who received thoracic epidural analgesia without SHT. CONCLUSIONS: SHT before pectus excavatum repair by Nuss procedure results in less postoperative pain and requires less morphine equivalents over time for postoperative pain management. Opioid-sparing CILA, when paired with SHT, results in shorter LOS.
Keywords: Humans; Adolescent; Female; Male; Young Adult; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Analgesics, Opioid; Length of Stay; Orthopedic Procedures; Analgesia, Patient-Controlled; Pain Management; Pain Measurement; Analgesia, Epidural; pectus excavatum; Anesthesia, Local; Anesthetics, Local; continuous infusion of local anesthetic; epidural analgesia; hypnosis; Hypnosis; pediatric surgery; postoperative pain; Preoperative Care; Self-Management; thoracic

Bilateral PECS II Block is Associated with Decreased Opioid Consumption and Reduced Pain Scores for up to 24 hours After Minimally Invasive Repair of Pectus Excavatum (Nuss Procedure): A Retrospective Analysis - Sertcakacilar, Gokhan; Kose, Selcuk (Journal of Cardiothoracic and Vascular Anesthesia, 2022)
OBJECTIVE(S): Compared to the open surgical technique, the minimally invasive repair of pectus excavatum (MIRPE; Nuss procedure) is a thoracoscopic technique designed to minimize intraoperative tissue damage. It still causes severe postoperative pain due to the insertion and pressure of the retrosternal bar used to raise the sternum and stabilize the chest. This study aimed to identify associations between ultrasound-guided PECS-II block and postoperative analgesia after the Nuss procedure. DESIGN: A retrospective cohort study SETTING: Single-center, training and research hospital affiliated with a university PARTICIPANTS: From Jan 1, 2018 to Nov 15, 2021, 171 consecutive patients were identified who underwent MIRPE surgery under general anesthesia. All patients received intravenous (I) patient-controlled analgesia (PCA) with or without PECS-II blocks for postoperative analgesia. One hundred twenty-five patients who met the inclusion criteria were evaluated. INTERVENTIONS: Demand-only morphine intravenous PCA was used for postoperative pain management in the PECS and control groups. Bilateral PECS-II block with 0.25% bupivacaine was performed in to the PECS group. MEASUREMENTS AND MAIN RESULTS: The primary outcome was postoperative opioid consumption, calculated as mg/kg of IV morphine. Secondary outcomes included Numeric Rating Scale (NRS) pain scores at rest (static) and with movement (dynamic) recorded 1, 4, 8, 12, 24 h after surgery. Postoperative morphine consumption was significantly lower in the PECS group than in the control group over the first 24 hours postoperatively: 0.325 mg/kg vs. 0.425 mg/kg (p<0.001). Static and dynamic NRS values were significantly lower in the PECS group for the first 12 postoperative hours (p <0.05). CONCLUSIONS: Bilateral PECS-II block is associated with decreased pain scores for up to 12 hours, and with decreased opioid consumption for up to 24 hours, following minimally invasive repair of pectus excavatum (Nuss procedure) in adolescents. PECS-II block in this context has not been previously described.
Keywords: Humans; Adolescent; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Analgesics, Opioid; Pain Measurement; MIRPE; Nerve Block; pectus excavatum; Morphine; numerical rating scale; Pectoral nerve block; postoperative analgesia

Pectus excavatum: Benefit of randomization - Dalton, Brian G. A.; Gonzalez, Katherine W.; Millspaugh, Daniel L.; Desai, Amita A.; Sharp, Susan W.; St Peter, Shawn D. (Journal of Pediatric Surgery, 2015)
BACKGROUND: Minimally invasive bar repair for pectus patients produces substantial pain which dictates the post-operative hospital course. We have data from 2 randomized trials comparing epidural catheter placement to patient controlled analgesia. The purpose of this study was to compare the outcomes of patients who were enrolled in the trials to those that did not participate in the trials. METHODS: A retrospective chart review was performed on patients not enrolled in the trials to compare to the prospective datasets from October 2006 to June 2014. Perioperative outcomes were examined. RESULTS: There were 135 patients in a study protocol (IS) and 195 patients that were not enrolled in a study (OS). Comparing the entire IS and OS groups, length of stay was less in the IS group, as was time to regular diet. Average pain scores, operative time and complication rates were not significantly different between the groups. Of the IS patients a significantly lower number of patients had epidural failure, requiring substitution of a PCA for pain control. CONCLUSIONS: There are benefits derived from participating in our randomized trials comparing epidural to patient controlled analgesia after bar placement for pectus excavatum regardless of which arm is utilized.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Length of Stay; Analgesia, Patient-Controlled; Pain Management; Prospective Studies; Epidural; Operative Time; Anesthesia, Epidural; Anesthetics; Benefit; Fentanyl; Hydromorphone; Midazolam; Patient controlled analgesia; Pectus Excavatum; Randomization

Epidural analgesia versus intravenous patient-controlled analgesia following minimally invasive pectus excavatum repair: a systematic review and meta-analysis - Stroud, Andrea M.; Tulanont, Darena D.; Coates, Thomasena E.; Goodney, Philip P.; Croitoru, Daniel P. (Journal of Pediatric Surgery, 2014)
BACKGROUND/PURPOSE: The minimally invasive pectus excavatum repair (MIPER) is a painful procedure. The ideal approach to postoperative analgesia is debated. We performed a systematic review and meta-analysis to assess the efficacy and safety of epidural analgesia compared to intravenous Patient Controlled Analgesia (PCA) following MIPER. METHODS: We searched MEDLINE (1946-2012) and the Cochrane Library (inception-2012) for randomized controlled trials (RCT) and cohort studies comparing epidural analgesia to PCA for postoperative pain management in children following MIPER. We calculated weighted mean differences (WMD) for numeric pain scores and summarized secondary outcomes qualitatively. RESULTS: Of 699 studies, 3 RCTs and 3 retrospective cohorts met inclusion criteria. Compared to PCA, mean pain scores were modestly lower with epidural immediately (WMD -1.04, 95% CI -2.11 to 0.03, p=0.06), 12 hours (WMD -1.12; 95% CI -1.61 to -0.62, p<0.001), 24 hours (WMD -0.51, 95%CI -1.05 to 0.02, p=0.06), and 48 hours (WMD -0.85, 95% CI -1.62 to -0.07, p=0.03) after surgery. We found no statistically significant differences between secondary outcomes. CONCLUSIONS: Epidural analgesia may provide superior pain control but was comparable with PCA for secondary outcomes. Better designed studies are needed. Currently the analgesic technique should be based on patient preference and institutional resources.
Keywords: Humans; Analgesia; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Length of Stay; Analgesia, Patient-Controlled; Analgesia, Epidural; Pain control; Cost-Benefit Analysis; Epidural; Minimally invasive pectus excavatum repair; Nuss; Operative Time; Research Design

Postoperative opioid analgesic use after Nuss versus Ravitch pectus excavatum repair - Papic, Jonathan C.; Finnell, S. Maria E.; Howenstein, Abby M.; Breckler, Francine; Leys, Charles M. (Journal of Pediatric Surgery, 2014)
BACKGROUND/PURPOSE: Anticipated postoperative pain may affect procedure choice in patients with pectus excavatum. This study aims to compare postoperative pain in patients undergoing Nuss and Ravitch procedures. METHODS: A 5year retrospective review was performed. Data on age, gender, Haller index, procedure, pain scores, pain medications, and length of hospital stay were collected. Total inpatient opioid administration was converted to morphine equivalent daily dose per kilogram (MEDD/kg) and compared between procedures. RESULTS: One hundred eighty-one patients underwent 125 (69%) Nuss and 56 (31%) Ravitch procedures. Ravitch patients were older (15.7 yo vs 14.6 yo, p=0.004) and had a higher Haller index (5.21 vs 4.10, p=<0.001). Nuss patients had higher average daily pain scores, received 25% more opioids (MEDD/kg 0.66 vs. 0.49, p=<0.001), and received twice as much IV diazepam/kg. In the multivariate analysis, higher MEDD/kg correlated with both the Nuss procedure and older age in the Nuss group. Opioid administration did not correlate with Haller index or Nuss bar fixation technique. Increased NSAID administration did not correlate with lower use of opioids. CONCLUSION: The Nuss procedure is associated with greater postoperative pain compared to the Ravitch procedure. Opioid use is higher in older patients undergoing the Nuss procedure, but is not associated with severity of deformity.
Keywords: Humans; Adolescent; Female; Male; Young Adult; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Length of Stay; Pain Measurement; Thoracoplasty; Pain; Morphine; Dose-Response Relationship, Drug; Follow-Up Studies; Injections, Intravenous; Morphine equivalent daily dose; Opioid; Ravitch procedure; Time Factors

Ultrasound-Guided Serratus Anterior Plane Block for Pain Management Following Minimally Invasive Repair of Pectus Excavatum - Tore Altun, Gulbin; Arslantas, Mustafa Kemal; Corman Dincer, Pelin; Aykac, Zeynep Zuhal (Journal of Cardiothoracic and Vascular Anesthesia, 2019)
OBJECTIVE: The Nuss procedure is a preferred technique for minimally invasive repair of pectus excavatum (MIRPE), but it is associated with significant postoperative pain. We assessed the efficacy and safety of an ultrasound-guided bilateral serratus anterior plane block (SAPB) for relieving acute pain from MIRPE. DESIGN: A retrospective cohort study. SETTING: This study was conducted at the Marmara University Pendik Training and Research Hospital, Turkey. PARTICIPANTS: All participants were scheduled for MIRPE. INTERVENTIONS: This study was conducted from November 2017 to May 2018. Postoperative pain control was achieved with bilateral SAPB done after induction of anesthesia and IV PCA in 50 patient (SABP group) and with only IV PCA in 45 patients (Control group). SAPB was achieved, targeting the interfascial plane between the serratus anterior and latissimus dorsi muscles, with a single injection of 30 mL (20 mL if patient weighed < 40 kg) of 0.25% bupivacaine and 0.5% lidocaine into each side. Pain scores were recorded for 24 h. MEASUREMENT AND MAIN RESULTS: Patients in the Control group had a higher demand (mean difference, 61; 95% confidence interval [CI] 30.5-136; P < 0.0001) and delivery dose (mean difference, 25; 95% CI 15-41.5 P = 0.001) during the first postoperative 24 h. SAPB did not affect the median (interquartile range) length of hospital stay: 5 (5-7) days vs. 5 (4-6) days, (P =0.085). CONCLUSIONS: Bilateral single-injection SAPB in patients undergoing MIRPE decreases pain and opioid consumption during the early postoperative period.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Pain Measurement; Pain management; Nerve Block; Ultrasonography, Interventional; Cohort Studies; analgesia; Muscle, Skeletal; Serratus anterior plane block

Elastomeric Pain Pumps as an Adjunct for Postoperative Pain Control After Minimally Invasive Repair of Pectus Excavatum - Parrado, Raphael H.; Thornburg, Danielle; Kang, Paul; McMahon, Lisa E. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2021)
Introduction: Pectus excavatum is a common congenital anomaly in the pediatric population. During the postoperative period, pain control is one of the top priorities. As a result, multiple techniques for pain control have been developed, including thoracic epidural analgesia, multimodal analgesia (MM), and elastomeric pain pump (EPP) placement. The purpose of this study was to evaluate the effectiveness of pain control using EPP as an adjunct to MM after the minimally invasive repair of pectus excavatum (MIRPE). Methods: We identified all pediatric patients undergoing MIRPE from June 2017 to July 2018. MM was employed in all patients; some patients additionally received subpleural EPP as adjuncts to postoperative analgesia. We reviewed pain scores, length of stay, opioid use, and complications. Results: During the study period, a total of 62 patients were included. The study cohort was divided into 15 patients undergoing MM alone versus 47 patients undergoing subpleural EPP placement plus MM (EPP + MM). Median pain scores were lower in the EPP + MM group (2.9 versus 4.2, P < .05). There was a significant reduction of total inpatient opioid use in the EPP + MM group (357.6 mg versus 466.9 mg, P = .03). There was no difference in median length of stay or complications. We found no significant difference between subpleural versus subcutaneous placement of the infusion catheters. Conclusion: The use of subpleural EPP as an adjunct to MM is an effective way to reduce pain and opioid use after MIRPE without increased risk of complications. Type of Study: Retrospective study with comparison group.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Length of Stay; Pain Management; Pain Measurement; postoperative analgesia; elastomeric pain pumps; Infusion Pumps; minimally invasive repair of pectus excavatum; multimodal analgesia

A pilot study of multi-modal pain management for same-day discharge after minimally invasive repair of pectus excavatum (Nuss procedure) in children - Akinboro, Sophia; John, Rebecca; Reyna, Troy; Davis, Rachel; Ayoub, Christine; Sangster, Rebecca; Kim, Joseph; Nguyen, Hai; Moreno, Claudia; Guner, Yigit; Goodman, Laura; Yu, Peter T.; et al. (Pediatric Surgery International, 2023)
BACKGROUND: Despite advancements in minimally invasive repair of pectus excavatum (MIRPE), Nuss procedure, postoperative pain control remains challenging. This report covers a multimodal regimen using bilateral single-shot paravertebral block (PVB) and bilateral thoracoscopic intercostal nerve (T3-T7) cryoablation, leading to significant reduction in length of stay (LOS) and high rate of same-day discharge. METHODS: This is a comparative study of pain management protocols for patients undergoing the Nuss procedure at a single center from 2016 through 2020. All patients underwent the the same surgical technique for the treatment of pectus excavatum at a single center. Patients received bilateral PVB with continuous infusion (Group 1, n = 12), bilateral PVB with infusion and right-side cryoablation (Group 2, n = 9), or bilateral single-shot PVB and bilateral cryoablation (Group 3, n = 17). The primary outcome was LOS with focus on same-day discharge, and the secondary outcome was decreased opioid usage. RESULTS: Eleven of 17 patients in Group 3 (65%) (bilateral single-shot PVB and bilateral cryoablation) were discharged the same day as surgery. The remaining Group 3 patients were discharged the following day with no complications or interventions. Compared to Group 1 (no cryoablation), Group 3 had shorter LOS (median 4.4 days vs. 0.7 days, respectively, p < 0.001) and significantly decreased median opioid use on the day of surgery (0.92 mg/kg vs. 0.47 mg/kg, p = 0.006). CONCLUSION: Findings demonstrate the feasibility of multimodal pain management for same-day discharge after the Nuss procedure. Future multisite studies are needed to investigate the superiority of this approach to established methods. LEVEL OF EVIDENCE: III.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Pain Management; Patient Discharge; Nuss; Pain; Cryoablation; Pectus; Pilot Projects; Paravertebral block

Scoring of Deformed Costal Cartilages Reduces Postoperative Pain after Nuss Procedure for Pectus Excavatum - Nagasao, Tomohisa; Hamamoto, Yusuke; Tamai, Motoki; Kogure, Tetsukuni; Jiang, Hua; Takano, Naoki; Tanaka, Yoshio (The Thoracic and Cardiovascular Surgeon, 2016)
OBJECTIVE: The present study aims to elucidate whether or not scoring deformed cartilages reduces postoperative pain after the Nuss procedure for pectus excavatum patients. METHODS: A total of 46 pectus excavatum patients for whom the Nuss procedure was conducted were included in the study. The patients were categorized into two groups, depending on whether or not the supplementary maneuver of scoring deformed cartilages was performed in addition to the Nuss procedure. Patients for whom deformed costal cartilages were scored were categorized as the Scoring Group (n = 24); those who received no such scoring were categorized as the Non-Scoring Group (n = 22). After evaluating the maximum stresses occurring on the thoraces by means of dynamic simulation using finite element analyses, intergroup comparison of the maximum von-Mises stress values was performed. Furthermore, after quantifying postoperative pain as the frequency with which patients injected anesthetics through an epidural pain-control system within 2 postoperative days, the degree of pain was compared between the two groups. RESULTS: The maximum stresses occurring on the thorax were significantly greater for the Non-Scoring Group than for the Scoring Group; injection frequency was also greater for the Non-Scoring Group (average 4.9 times for 2 days) than for the Scoring Group (average 2.5 times for 2 days). CONCLUSION: High stresses occur due to the performance of the Nuss procedure, causing postoperative pain. The stresses can be reduced by performing supplementary scoring on deformed cartilages. Accordingly, postoperative pain is reduced.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Orthopedic Procedures; Analgesia, Patient-Controlled; Pain Measurement; Time Factors; Biomechanical Phenomena; Computer Simulation; Costal Cartilage; Elastic Modulus; Finite Element Analysis; Sternum; Stress, Mechanical; Tomography, X-Ray Computed

Nuss procedure for pectus excavatum in adults: long-term results in a prospective observational study - Hoksch, Beatrix; Kocher, Gregor; Vollmar, Philippe; Praz, Fabien; Schmid, Ralph Alexander (European Journal of Cardio-Thoracic Surgery: Official Journal of the European Association for Cardio-Thoracic Surgery, 2016)
OBJECTIVES: Since the end of the 1990s, the management of pectus excavatum has undergone major changes. The Nuss procedure (pectus bar) has been the method of choice for patients with pectus excavatum at Bern University Hospital for over a decade. The current study will describe our experiences, with a particular focus on long-term results in adults. METHODS: The prospective observational study began in autumn 2002. The Haller index was used to quantify pectus excavatum severity. Pulmonary function tests and cardiac examinations were performed preoperatively, and a standardized management for surgical techniques and for the pre- and postoperative treatments including long-term follow-up at 3, 12 and 36 months after surgery was developed. Quality of life and satisfaction with the cosmetic result after the Nuss procedure were evaluated. RESULTS: Better or much better quality of life after the Nuss procedure was observed: n = 108 (88.4%) at 3 months, n = 97 (89.0%) at 12 months and n = 87 (92.5%) at 36 months. Pain intensity decreased in the follow-up [pain score visual analogue scale (VAS) at 3 months: median 1 (0-7), 12 months: median 1 (0-4), 36 months: median 0.8 (0-5)]. After long-term observation, over 90% of patients described their quality of life after the operation as being better or much better. Satisfaction with the cosmetic results of the operation was also very high, with >90% of patients being satisfied. Only a very small group of patients suffered from pain in the long-term follow-up. Complications were rare (14.7%) and could be treated in most cases without reoperation. CONCLUSION: Our results demonstrate that the Nuss procedure is safe and can be performed with excellent results in adults, both in the short term and in the long term. The improved quality of life and patients' satisfaction with cosmetic results remained high in the long-term follow-up, 10 years after the surgical procedure.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Funnel Chest; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Prospective Studies; MIRPE; Preoperative Care; Follow-Up Studies; Middle Aged; Esthetics; Forced Expiratory Volume; Orthopedic Fixation Devices; Pectus Bar; Prosthesis Failure; Quality of Life; Radiography; Recurrence; Thoracic Surgery, Video-Assisted; Vital Capacity

[Pediatric postoperative quality analysis : Pain and postoperative nausea and vomiting] - Balga, I.; Konrad, C.; Meissner, W. (Der Anaesthesist, 2013)
BACKGROUND: For the evaluation of postoperative pain therapy, nausea and vomiting (PONV), the Children's Hospital in Lucerne acts as a member of the postoperative quality improvement project QUIPSi for children. Initial results and the potential for evaluation of the postoperative pain therapy and PONV are presented here. The central questions are whether the postoperative therapy concept is sufficient and if QUIPSi serves as an ideal tool for postoperative quality improvement? METHODS: Over a period of 1.5 years a total of 460 children aged between 4 to 17 years evaluated their postoperative pain, requirements for more analgesic medicine and the incidence of PONV according to a standardized questionnaire on the first postoperative day. The administration of analgesic medicine was recorded until finishing the questionnaire. RESULTS: In this study 5 pediatric outpatient operation groups (hernia repair n = 36, bone surgery n = 23, metal removal surgery n = 31, circumcision n = 65 and soft tissue surgery n = 49) and 9 pediatric inpatient operation groups (appendectomy n = 21, bone surgery n = 78, metal removal surgery n = 24, orchidopexy n = 31, combined operation (orchidopexy + hernia repair or circumcision) n = 14, otoplasty n = 9, tonsillectomy n = 41 and pectus excavatum surgery n = 6 and soft tissue surgery n=28) could be classified. All operation groups except the inpatient and outpatient soft tissue surgery groups received regional or infiltration anesthesia. Analgesic medicine was prescribed with the maximum permitted daily dose per kg body weight (paracetamol 100 mg/kgBW, metamizole 80 mg/kgBW, diclofenac 3 mg/kgBW and ibuprofen 40 mg/kgBW; in reserve tramadol 8 mg/kgBW and nalbuphine 2.4 mg/kgBW). The following operation groups complained of persistent pain (scale according to Hicks 0-10) and/or required more pain medicine (%): pediatric outpatients circumcision 5.1/19 %, pediatric inpatients appendectomy 6.5/43 %, tonsillectomy 6.4/32 %, pectus excavatum surgery 7.7/33 %, orchidopexy 4.2/19.4 %, otoplasty 3.1/22.2 %. The reason for the elevated postoperative pain was mainly insufficient administered pain medicine despite the prescription of the maximum daily dose per kg body weight or maybe due to a late administration. Circumcision/appendectomy/tonsillectomy/pectus excavatum surgery/orchidopexy/otoplasty (% of max. daily dose): paracetamol 5/58/99/36/57/37 %, metamizole 0,4/18/8/54/4/4 %, diclofenac 44/45/3/97/51/68 % or ibuprofen 42/1/0/0/0/0 %, tramadol 0,4/0/0/0/0/0 %, nalbuphine 0,4/1/16/0/2/0 %). As the standard inhalative general anesthesia and PONV prophylaxis with tropisetron (body weight: < 20 kg 1 mg, > 20 kg: 2 mg intravenous bolus) was performed. Dexamethasone (0.15-0.5 mg/kgBW, maximum allowed dose 8 mg intravenous bolus) was administered as a back-up drug for PONV. The nausea incidence was higher in the inpatient group (14-50 %) than in the outpatient group (10-29 %). The incidence of vomiting was higher in the inpatient (0-37 %) than in the outpatient group (3-17 %). CONCLUSIONS: The quality analysis showed that especially children with the requirement for more pain medicine and a high PONV incidence (inpatient group) need further improvement in postoperative care. Because of small numbers in some operation groups this qualitative evaluation of the postoperative pain and PONV management only gives an approximate overview. The results of QUIPSi uncovered gaps in the postoperative pain management which will help improve the quality in the postoperative setting. The QUIPSi approach should be integrated as a daily tool into all pediatric surgical departments.
Keywords: Humans; Adolescent; Analgesia; Benchmarking; Child; Pain, Postoperative; Analgesics; Pain Management; Pain Measurement; Analgesia, Epidural; Surveys and Questionnaires; Postoperative Nausea and Vomiting; Child, Preschool; Ambulatory Care; Pediatrics; Postoperative Care; Quality Assurance, Health Care

A review of anesthetic techniques and outcomes following minimally invasive repair of pectus excavatum (Nuss procedure) - Frawley, Geoff; Frawley, Jacinta; Crameri, Joe (Paediatric Anaesthesia, 2016)
BACKGROUND: Pectus excavatum (PE) is the most common congenital chest wall deformity, occurring in 1 : 1000 children with a male to female ratio of 4 : 1. Several procedures have been described to manage this deformity, including cartilage resection with sternal osteotomy (the Ravitch procedure) and a minimally invasive repair technique (the Nuss procedure). While initially described as a nonthoracoscopic technique, the current surgical approach of the Royal Childrens Hospital involves thoracoscopic assistance. Postoperative pain is significant in patients undergoing the pectus repair and multiple analgesic regimens have been advocated with continuous thoracic epidural infusions and opioid infusions the most common. Some authors have advocated patient-controlled analgesia (PCA), paravertebral nerve blocks (PVNB), and wound infusion catheters as alternatives. AIMS: The primary aim of this study was to assess our experience with postoperative pain and analgesia requirements associated with the minimally invasive repair of pectus excavatum in children. METHODS: This is a retrospective cohort study with a contemporaneous comparison group examining patients treated between January 2005 and December 2015 for minimally invasive repair of pectus excavatum by the Nuss procedure. RESULTS: Two hundred and seventeen patients [mean age 14.9 (sd 1.9) years] with pectus excavatum treated at the Royal Childrens Hospital between 2005 and 2015 were identified. All patients were managed with thoracic epidural analgesia and intravenous morphine infusions. The epidural was effective in the postanesthesia care unit in 97.3% (failure to place an epidural rate was 4 (1.9%); no block on awakening 0.9%). A further 4 (1.8%) were removed within 24 h. The mean morphine equivalent dose in the first 24 h was 0.8 mg·kg-1 ·day-1 . PCA was continued for a mean of 3.8 days and the total mean morphine equivalent dose was 2.2 mg·kg-1 ·day-1 . Minor complications occurred in 67 (30.9%) with postoperative nausea and vomiting in 36 patients (16.6%) and urinary retention requiring an indwelling catheter in 40 patients (18.4%). CONCLUSION: An epidural-based analgesic regime is associated with low pain scores and few acute complications. The continuation of morphine analgesia after the first postoperative day is common but associated with an increased incidence of urinary retention and nausea and vomiting.
Keywords: Humans; Adolescent; Female; Male; Analgesia; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesia, Patient-Controlled; Nerve Block; Cohort Studies; Anesthesia; anesthesia; Drug Administration Routes; funnel chest; pediatrics; thoracic surgery; thoracoscopy

Intercostal nerve cryoablation versus thoracic epidural for postoperative analgesia following pectus excavatum repair: a systematic review and meta-analysis - Daemen, Jean H. T.; de Loos, Erik R.; Vissers, Yvonne L. J.; Bakens, Maikel J. A. M.; Maessen, Jos G.; Hulsewé, Karel W. E. (Interactive Cardiovascular and Thoracic Surgery, 2020)
OBJECTIVES: Minimally invasive pectus excavatum repair via the Nuss procedure is associated with significant postoperative pain that is considered as the dominant factor affecting the duration of hospitalization. Postoperative pain after the Nuss procedures is commonly controlled by thoracic epidural analgesia. Recently, intercostal nerve cryoablation has been proposed as an alternative method with long-acting pain control and shortened hospitalization. The subsequent objective was to systematically review the outcomes of intercostal nerve cryoablation in comparison to thoracic epidural after the Nuss procedure. METHODS: Six scientific databases were searched. Data concerning the length of hospital stay, operative time and postoperative opioid usage were extracted. If possible, data were submitted to meta-analysis using the mean of differences, random-effects model with inverse variance method and I2 test for heterogeneity. RESULTS: Four observational and 1 randomized study were included, enrolling a total of 196 patients. Meta-analyses demonstrated a significantly shortened length of hospital stay [mean difference -2.91 days; 95% confidence interval (CI) -3.68 to -2.15; P < 0.001] and increased operative time (mean difference 40.91 min; 95% CI 14.42-67.40; P < 0.001) for cryoablation. Both analyses demonstrated significant heterogeneity (both I2 = 91%; P < 0.001). Qualitative analysis demonstrated the amount of postoperative opioid usage to be significantly lower for cryoablation in 3 out of 4 reporting studies. CONCLUSIONS: Intercostal nerve cryoablation during the Nuss procedure may be an attractive alternative to thoracic epidural analgesia, resulting in shortened hospitalization. However, given the low quality and heterogeneity of studies, more randomized controlled trials are needed.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Pectus excavatum; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Analgesia, Epidural; Operative Time; Hospitalization; Thoracic epidural analgesia

Infectious complications of intercostal nerve cryoablation mediated by perioperative hypothermia during pediatric Nuss procedure - Bundrant, Nikkida T.; Sayrs, Lois W.; Ostlie, Daniel; Lee, Justin; Egan, Craig; Molitor, Mark; Notrica, David; Padilla, Benjamin (Journal of Pediatric Surgery, 2022)
BACKGROUND: Intercostal nerve cryoablation (cryoanalgesia) is increasingly used for pain control in minimally invasive repair of pectus excavatum (MIRPE) by Nuss procedure. Cryoanalgesia may lower core body temperature and increase the risk of postoperative infectious complications. We investigated cryoanalgesia effects on infectious complications following MIRPE. METHOD: We performed a retrospective review of patients undergoing MIRPE at our institution. Patients treated via multimodal analgesia with cryoanalgesia (Cryo) were compared to patients treated via multimodal analgesia +/- elastomeric pain pumps (Non-cryo). Core body and intraoperative minimum/maximum temperatures were recorded. Primary outcomes were wound infection and pneumonia; secondary outcome was length of stay (LOS). Fisher's Exact and Mann-Whitney U tests compared proportions and medians respectively, p-value ≤ 0.05 being significant. RESULTS: 80 patients were included, 35(43.7%) Cryo and 45(56.3%) Non-cryo. There were no significant differences in median [IQR] for age(15[13.3,16.0];p =0.86), number of bars inserted (2[1,2];p = 0.57), or operative time(123.5[98.3, 148.8]; p = 0.11) between the two groups. We found no significant differences in median [IQR] minimum temperature (35.4°C [35.0,35.8];p = 0.76), median change in intraoperative temperature (-0.13°C [-0.44,0.00];p = 0.94) or median recovery temperature (-1.10°C [-1.56,-0.65]; p = 0.59) between Cryo and Non-cryo. PACU temperature was significantly lower in the Cryo group, 36.4°C [36.2,36.6] p = 0.04. There were no postoperative wound infections in either group and no significant difference in incidence of postoperative pneumonia (8.57% versus 2.22%,p =  0.31) or median[IQR] for LOS (4[3,4];p = 0.57), between Cryo and Non-cryo patients. CONCLUSION: Although cryoanalgesia for MIRPE resulted in lower core body temperature, there appears to be no significant difference between Cryo and Non-Cryo patients for LOS or infectious complications.
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally invasive repair; Minimally Invasive Surgical Procedures; Pectus excavatum; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Cryoanalgesia; Thoracoscopy; Nuss; Hypothermia; Postoperative infectious complications

A review of anesthetic considerations and postoperative pain control after the Nuss procedure - Singhal, Neil Raj; Jerman, Jonathan D. (Seminars in Pediatric Surgery, 2018)
Keywords: Humans; Adolescent; Female; Male; Child; Funnel Chest; Pain, Postoperative; Cryosurgery; Orthopedic Procedures; Anesthesia, Conduction

Implementation and acceptance rates of a specially designed vacuometer for the vacuum bell treatment of pectus excavatum - Toselli, Luzia; Vallee, Maxroxia; Elmo, Gaston; Martinez, Jorge; Sanjurjo, Daniela; Nazar, Maximiliano; Bellia-Munzon, Gaston (Journal of Pediatric Surgery, 2021)
BACKGROUND / PURPOSE: To report the implementation of a specially designed vacuometer for the ambulatory measurement of the exact negative pressure self-applied by the patient when using the vacuum bell for the treatment of pectus excavatum and to analyze patient satisfaction with the device, by conducting a survey. METHODS: Between October 2018 and June 2020, all patients with pectus excavatum who received a vacuum bell at our Pectus Clinic were provided with a specially designed pectus vacuometer for their personal use. We described the vacuometer, the fundamentals of its development, and the utilization protocol. A survey was conducted evaluating comfort, clarity of instructions, usefulness, simplicity of connection, and likeability. The level of satisfaction was assessed using a Likert scale ranging from 1 (very negative experience) to 5 (very positive experience). The occurrence of skin lesions provoked by the application of the vacuum bell was registered. RESULTS: From 72 submitted surveys, 54 patients answered. Patient demographics comprised 44 (81.5%) males and a mean age of 12.6 ± 6.0 years. The mean initial external pectus depth was 2.0 ± 0.7 cm and the mean duration of treatment was 13.2 ± 8.6 months. No skin lesions were detected while using the vacuum bell and the vacuometer. The mean general satisfaction score was 4.4 ± 0.7 and 83.3% of the respondents did not have any inconvenience with the vacuometer. A patient who considered himself cured was the only dropout during the study. CONCLUSIONS: In this study, we described the feasibility and fundamentals of the application of a specifically designed vacuometer for ambulatory use as an adjunct to the treatment of pectus excavatum with a vacuum bell, and demonstrated a high satisfaction level with the device. In addition, the vacuometer might help avoid skin lesions secondary to the vacuum bell and foster adhesion to treatment. TYPE OF STUDY: Treatment study. LEVEL OF EVIDENCE: IV.
Keywords: Humans; Adolescent; Male; Child; Funnel Chest; Patient Satisfaction; Thoracic Wall; Surveys and Questionnaires; Funnel chest; Measurement; Negative pressure; Patient reported outcomes; Vacuum

Retrospective study comparing outcomes of multimodal epidural and erector spinae catheter pain protocols after pectus surgery - Walter, Charlotte M.; Lee, Christopher S.; Moore, David L.; Abbasian, Niekoo; Clay, Smokey J.; Mecoli, Marc D.; Olbrecht, Vanessa A.; Batra, Meenu; Ding, Lili; Yang, Fang; Nair, Manu; Huq, Abraar; et al. (Journal of Pediatric Surgery, 2023)
INTRODUCTION: There are no optimal postoperative analgesia regimens for Nuss procedures. We compared the effectiveness of thoracic epidurals (EPI) and novel ambulatory erector spinae plane (ESP) catheters as part of multimodal pain protocols after Nuss surgery. METHODS: Data on demographics, comorbidities, perioperative details, length of stay (LOS), in hospital and post discharge pain/opioid use, side effects, and emergency department (ED) visits were collected retrospectively in children who underwent Nuss repair with EPI (N = 114) and ESP protocols (N = 97). Association of the group with length of stay (LOS), in hospital opioid use (intravenous morphine equivalents (MEq)/kg over postoperative day (POD) 0-2), and oral opioid use beyond POD7 was analyzed using inverse probability of treatment weighting (IPTW) with propensity scores, followed by multivariable regression. RESULTS: Groups had similar demographics. Compared to EPI, ESP had longer block time and higher rate of ketamine and dexmedetomidine use. LOS for ESP was 2 days IQR (2, 2) compared to 3 days IQR (3, 4) for EPI (p < 0.01). Compared to EPI, ESP group had higher opioid use (in MEq/kg) intraoperatively (0.32 (IQR 0.27, 0.36) vs. 0.28 (0.24, 0.32); p < 0.01) but lower opioid use on POD 0 (0.09 (IQR 0.04, 0.17) vs. 0.11 (0.08, 0.17); p = 0.03) and POD2 (0.00 (IQR 0.00, 0.00) vs. 0.04 (0.00, 0.06) ; p < 0.01). ESP group also had lower total in hospital opioid use (0.57 (IQR 0.42, 0.73) vs.0.82 (0.71, 0.91); p < 0.01), and shorter duration of post discharge opioid use (6 days (IQR 5,8) vs. 9 days (IQR 7,12) (p < 0.01). After IPTW adjustment, ESP continued to be associated with shorter LOS (difference -1.20, 95% CI: -1.38, -1.01, p < 0.01) and decreased odds for opioid use beyond POD7 (OR 0.11, 95% CI: 0.05, 0.24); p < 0.01). However, total in hospital opioid use in MEq/kg (POD0-2) was now similar between groups (difference -0.02 (95% CI: -0.09, -0.04); p = 0.50). The EPI group had higher incidence of emesis (29% v 4%, p < 0.01), while ESP had higher catheter malfunction rates (23% v 0%; p < 0.01) but both groups had comparable ED visits/readmissions. DISCUSSION/CONCLUSION: Compared to EPI, multimodal ambulatory ESP protocol decreased LOS and postoperative opioid use, with comparable ED visits/readmissions. Disadvantages included higher postoperative pain scores, longer block times and higher catheter leakage/malfunction. LEVELS OF EVIDENCE: Level III.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Patient Discharge; Pain management; Length of stay; Morphine; Catheters; Aftercare; Erector spinae catheters; Postoperative opioid use

Postoperative pain management in pediatric patients undergoing minimally invasive repair of pectus excavatum: the role of intercostal block - Lukosiene, Laura; Rugyte, Danguole Ceslava; Macas, Andrius; Kalibatiene, Lina; Malcius, Dalius; Barauskas, Vidmantas (Journal of Pediatric Surgery, 2013)
PURPOSE: There are no published data regarding value of intercostal block following pectus excavatum repair. Our aim was to evaluate the efficacy of intercostal block in children following minimally invasive repair of pectus excavatum (MIRPE). METHODS: Forty-five patients given patient-controlled analgesia (PCA) with morphine postoperatively were studied. Twenty-six patients were given bilateral intercostal blocks after induction of anesthesia (PCA-IB group), and nineteen patients were retrospective controls without regional blockade (PCA group). All patients were followed up 24 h postoperatively. RESULTS: A loading dose of morphine (0,1±0,49 mg/kg) before starting PCA was used in seventeen patients in PCA group vs. no patient in PCA-IB group. Cumulative used morphine doses were lower up to 12 h after surgery in PCA-IB group (0,29±0,08 μg/kg) than in the PCA group (0,46±0,18 μg/kg), p<0,01. There were no differences in pain scores, oxygen saturation values, sedation scores, and the incidence of pulmonary adverse events between the two groups. There was a tendency towards less morphine-related adverse effects in PCA-IB group compared to PCA group (p<0,05). No complications related to the intercostal blocks were observed. CONCLUSION: Bilateral intercostal blocks following MIRPE are safe and easy to perform and can diminish postoperative opioid requirement. Double-blind randomized study is required to confirm the potential to diminish opioid related side effects.
Keywords: Humans; Adolescent; Female; Male; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesics, Opioid; Orthopedic Procedures; Analgesia, Patient-Controlled; Prospective Studies; Pain Measurement; Nerve Block; Bupivacaine; Morphine; Anesthetics, Local; Postoperative pain; Follow-Up Studies; Postoperative Care; Children; Drug Administration Schedule; Drug Therapy, Combination; Epinephrine; Intercostal block; Linear Models; Sympathomimetics

Impact of Epidural Failures on the Results of a Prospective, Randomized Trial - Desai, Amita; Alemayehu, Hanna; Weesner, Kathryn A.; St Peter, Shawn D. (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2016)
INTRODUCTION: We conducted a prospective randomized trial to evaluate the merits of two established postoperative pain management strategies: thoracic epidural (EPI) versus patient-controlled analgesia (PCA) with intravenous narcotics after minimally invasive repair of pectus excavatum. Pain scores favored the EPI group for the first two postoperative days only. Critics of the trial suggest that if the epidural failure rate was not so high, results may have favored the EPI group. Therefore, we performed a subset analysis of the EPI group to evaluate the impact of these failures. METHODS: Patients for whom epidural catheter could not be placed or whose catheters were removed early owing to dysfunction were compared with those with well-functioning catheters. Those with well-functioning catheters were also compared with the PCA group. A two-tailed independent Student t-test and a two-tailed Fisher exact test were used where appropriate. RESULTS: Of 55 patients in the EPI group, 12 patients (21.8%) had failed placement or required early removal. Comparing those with failed placements with the rest of the group, there was no difference in daily visual analogue scale pain scores or measures of hospital course. Likewise, comparing those with well-functioning catheters only to those in the PCA group, the results of the trial are replicated in terms of pain scores, hospital course, and length of stay. CONCLUSION: In patients with failed epidural therapy, there is no significant difference in postoperative hospital course. Comparing those with well-functioning catheters to those in the PCA group, trial results are replicated-that is, no significant difference in length of stay, time to regular diet, or time to transition to oral medications. Therefore, failure rate in the EPI group did not influence the results of the trial.
Keywords: Humans; Adolescent; Funnel Chest; Pain, Postoperative; Analgesia, Patient-Controlled; Prospective Studies; Pain Measurement; Postoperative Period; Operative Time; Follow-Up Studies; Catheters; Anesthesia, Epidural; Treatment Failure

Progressive reduction of hospital length of stay following minimally invasive repair of pectus excavatum: A retrospective comparison of three analgesia modalities, the role of addressing patient anxiety, and reframing patient expectations - Schlatter, Marc G.; Nguyen, Long V.; Tecos, Maria; Kalbfell, Elle L.; Gonzalez-Vega, Omar; Vlahu, Tedi (Journal of Pediatric Surgery, 2019)
PURPOSE: Management of postoperative pain is a significant challenge following the Nuss procedure. Epidurals, PCAs, and newer analgesia modalities have been used elsewhere without demonstrating consistent improvement in the reported length of hospital stays (LOS). We reviewed a large single surgeon experience identifying three different methods of analgesia used over time to highlight marked improvement in patient LOS. METHODS: IRB approval was obtained and patient clinical information was retrospectively reviewed from 2001 to 2017. The primary outcome variable was length of hospital stay. An expanded preoperative consultation reviews the issue of pain, the negative impact of anxiety on recovery, and our current success of shortened hospital stays with our patients. RESULTS: One hundred and seventy-three patients representing three different analgesia approaches had a LOS of 4.4 days (epidural); 2.2 days (PCA/intercostal nerve block); and 1.6 days (scheduled oral pain meds/intercostal nerve blocks). The current LOS for patients is 1.0 day. Patients successfully stop using narcotics by the end of the first week postoperatively. CONCLUSIONS: Intraoperative intercostal nerve blocks, scheduled postoperative pain medications, and enhanced preoperative consultation aimed to educate patients about anxiety and reframe patient pain expectations have collectively decreased LOS, and reduced postoperative narcotic usage. TYPE OF STUDY: Clinical research LEVEL OF EVIDENCE: Level III.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Analgesia; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Length of Stay; Pain Management; Pain Measurement; Thoracoscopy; Nuss repair; Narcotics; Anxiety; Minimally-invasive

Effects of dezocine on PAED scale and Ramsay sedation scores in patients undergoing NUSS procedure - Xia, Yingjing; Sun, Yingying; Liu, Junxia (American Journal of Translational Research, 2021)
OBJECTIVE: To investigate the effects of dezocine on pediatric anesthesia emergence delirium (PAED) and Ramsay sedation scores in patients undergoing Nuss procedures (minimally invasive surgery for repairing pectus excavatum). METHODS: Altogether, 100 patients with pectus excavatum who underwent Nuss procedures in our hospital were selected and randomly divided into group A (n=50) and group B (n=50). General anesthesia was carried out for each patient, with an anaesthetic of sufentanil for group A, and dezocine plus sufentanil for group B. The visual analogue scale (VAS) score and Ramsay sedation score were recorded at extubation (T0), 10 min after extubation (T1), 20 min after extubation (T2), 30 min after extubation (T3) and 60 min after extubation (T4) for assessment of pain intensity and sedative effect; PAED scale score was applied to observe the emergence delirium at awakening, 15 min after awakening and 30 min after awakening. Quality of recovery-15 (QoR-15) scale score was used to evaluate the quality of early rehabilitation 1 d after operation and 2 d after operation. The occurrence of adverse reactions was recorded. RESULTS: The VAS scores at T0, T1, T2, T3 and T4 in group B were lower than those in group A, and there was statistical significance between group A and group B (P<0.001). VAS scores at T1, T2 and T3 were lower than those recorded at T0 in both groups (P<0.01), while no significant difference was noted at other time points (P>0.05). Ramsay sedation scores were increased at T0, T1, T2, T3 and T4 in group B in comparison to that in group A (all P<0.001), while the scores recorded at T4 in group A and T3 and T4 in group B were increased compared with those recorded at T0 (all P<0.01), and there was no significant difference at other time points (all P>0.05). Compared with group A, PAED scores in group B were downregulated at each time point after wakening up (all P<0.01), while QoR-15 scores in group B were increased at 1 d and 2 d after surgery (all P<0.05); there was no significant difference in adverse reactions between the two groups (all P>0.05). CONCLUSION: Sufentanil combined with dezocine is efficacious in general analgesia and sedation, which can reduce emergence agitation, improves the quality of rehabilitation and is relatively safe for patients undergoing minimally invasive repairing of pectus excavatum.
Keywords: Nuss procedure; dezocine; emergence agitation; sedation; sufentanil

Prediction of persistent post-operative pain: Pain-specific psychological variables compared with acute post-operative pain and general psychological variables - Horn-Hofmann, C.; Scheel, J.; Dimova, V.; Parthum, A.; Carbon, R.; Griessinger, N.; Sittl, R.; Lautenbacher, S. (European Journal of Pain (London, England), 2018)
BACKGROUND: Psychological variables and acute post-operative pain are of proven relevance for the prediction of persistent post-operative pain. We aimed at investigating whether pain-specific psychological variables like pain catastrophizing add to the predictive power of acute pain and more general psychological variables like depression. METHODS: In all, 104 young male patients undergoing thoracic surgery for pectus excavatum correction were studied on the pre-operative day (T0) and 1 week (T1) and 3 months (T2) after surgery. They provided self-report ratings (pain-related: Pain Catastrophizing Scale, Pain Anxiety Symptoms Scale = PASS, Pain Vigilance and Awareness Questionnaire = PVAQ; general psychological: Screening for Somatoform Symptoms, State-Anxiety Inventory-X1, Center for Epidemiologic Studies Depression Scale = CES-D). Additional predictors (T1) as well as criterion variables (T2) were pain intensity (Numerical Rating Scale) and pain disability (Pain Disability Index). RESULTS: Three months after surgery, 25% of the patients still reported clinically relevant pain (pain intensity ≥3) and over 50% still reported pain-related disability. Acute post-operative pain as well as general psychological variables did not allow for a significant prediction of persistent post-operative pain; in contrast, pain-related psychological variables did. The best single predictors were PASS for pain intensity and PVAQ for pain disability. CONCLUSIONS: Pain-related psychological variables derived from the fear-avoidance model contributed significantly to the prediction of persistent post-operative pain. The best possible compilation of these measures requires further research. More general psychological variables may become relevant predictors later in the medical history. SIGNIFICANCE: Our results suggest that pain-specific psychological variables such as pain anxiety and pain hypervigilance add significantly to the prediction of persistent post-operative pain and might even outperform established predictors such as acute pain and general psychological variables. Clinicians might benefit from the development of time-economic screening tools based on these variables.
Keywords: Humans; Adolescent; Adult; Male; Young Adult; Thoracic Surgical Procedures; Funnel Chest; Pain, Postoperative; Pain Measurement; Surveys and Questionnaires; Fear; Anxiety; Awareness; Catastrophization; Depression; Disabled Persons; Risk Factors

[Intercostal nerve cryoablation in correction of pectus excavatum in adults] - Pechetov, A. A.; Lednev, A. N.; Makov, M. A.; Chlan, T. N. (Khirurgiia, 2021)
OBJECTIVE: To evaluate an effectiveness of cryoanalgesia in older patients with pectus excavatum and to determine feasibility of further research. MATERIAL AND METHODS: We have developed an original technique of intercostal nerve cryoablation for correction of pectus excavatum in adults. The results of intercostal nerve cryoablation during correction of pectus excavatum in 10 older patients were analyzed. RESULTS: Postoperative outcomes were followed-up over a period of 4 - 12 months. There were no perioperative surgical complications. In 1 case, moderate pain syndrome persisted for 3 months after surgery (mean VAS score 2±1.3). In 9 months, mean VAS score was 0.6±0.6 in a month after surgery. CONCLUSION: Intercostal nerve cryoablation in correction of pectus excavatum in adults may be an alternative to the current methods of regional analgesia. Further research is requried to achieve objective information.
Keywords: Humans; Adult; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Cryosurgery; Intercostal Nerves; pectus excavatum; cryoanalgesia; Aged; intercostal nerve cryoablation

Cryoanalgesia in Patients Undergoing Nuss Repair of Pectus Excavatum: Technique Modification and Early Results - Morikawa, Nicole; Laferriere, Nicole; Koo, Sylvia; Johnson, Sidney; Woo, Russell; Puapong, Devin (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2018)
PURPOSE: The Nuss procedure for surgical correction of pectus excavatum often causes severe postoperative pain. Cryoanalgesia of intercostal nerves is an alternative modality for pain control. We describe our modification of the cryoICE™ probe that allows for nerve ablation through the ipsilateral chest along with early results utilizing this technique. METHODS: To allow for ipsilateral nerve ablation, a 20-French chest tube was cut and secured to the cryoICE probe, thus providing insulation for the malleable end of the probe. A 3-year retrospective review of patients undergoing Nuss repair at our institution was performed. Patients who received cryoanalgesia (cryo, n = 6) were compared with a historical control cohort who did not receive cryoanalgesia (nocryo, n = 13) during Nuss repair. Hospital length of stay, postoperative narcotic requirement (PNR), and highest postoperative pain score were collected. RESULTS: Both cohorts were similar regarding age, BMI, and pectus index. The cryo group had a significantly less PNR (6.4 versus 17.9 doses, P = .05) and was discharged on average >1 day earlier than nocryo patients (3.7 versus 2.2 days, P = .01). No complications occurred in either group. CONCLUSIONS: Our technique modification simplifies previously described approaches to intercostal nerve cryoablation. Patients undergoing this adjunct benefit with less PNR and a faster discharge time.
Keywords: Humans; Adolescent; Female; Male; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Nuss procedure; Cryosurgery; Intercostal Nerves; Orthopedic Procedures; pectus excavatum; Follow-Up Studies; pain management; cryoanalgesia; Cryoanesthesia

Which Is More Effective for Minimally Invasive Pectus Repair: Epidural or Paravertebral Block? - Aydin, Gulcin; Sahin, Ahmet Tugrul; Gencay, Isin; Akcabay, Zeynep Nur; Gunal, Nesimi; Dural, Koray; Ozpolat, Berkant; Buyukkocak, Unase (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2020)
Objective: The aim of this study was to compare the effectiveness of epidural block (EDB) and paravertebral block (PVB) for minimally invasive pectus repair with the conventional method in terms of pain control during and after pectus operations, patient comfort, and length of stay in hospital. Materials and Methods: A retrospective review was made of patients who underwent minimally invasive pectus repair. The patients were allocated into three groups as follows: PVB group (Pre-emptive ultrasound-guided bilateral thoracic single injection PVB, n = 15); EDB group (Pre-emptive landmark-guided single injection thoracic EDB, n = 8); and Control group (Neither PVB nor EPB, n = 9). The intraoperative analgesic requirement was recorded, and a visual analog scale (VAS) for pain evaluation and the Postoperative Patient Satisfaction Scale were applied to all patients. Results: The intraoperative analgesic requirement, VAS scores, postoperative satisfaction level, and time to first requirement for postoperative analgesia were different between the control and PVB groups (P < .001) and between the control and EDB groups (P < .001), but not different between the PVB and EDB groups. Although the length of stay in hospital was shorter in the PVB and EDB groups compared to the control group, the difference was not statistically significant (P = .422). Conclusion: Epidural and bilateral paravertebral blockades performed in conjunction with general anesthesia decrease the intraoperative and postoperative need for analgesics, and might be beneficial for pain management and contribute to a shorter length of hospital stay for patients undergoing minimally invasive pectus repair operations. Both blockades also significantly improved the patient satisfaction.
Keywords: Humans; Adolescent; Female; Male; Young Adult; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Minimally Invasive Surgical Procedures; Length of Stay; Pain Measurement; Patient Satisfaction; Nerve Block; Anesthesia, Epidural; Anesthesia, General; epidural block; minimally invasive pectus repair; paravertebral block; Pectus Carinatum; ultrasonography

Patient-Controlled Intravenous Analgesia with or without Ultrasound-Guided Bilateral Intercostal Nerve Blocks in Children Undergoing the Nuss Procedure: A Randomized, Double-Blinded, Controlled Trial - Ma, Bingjie; Sun, Yuan; Hao, Can; Liu, Xiaoming; Shen, Sai'e (Pain Research & Management, 2022)
BACKGROUND: Two analgesic strategies have been described for pain treatment after the pectus excavatum surgery: the patient-controlled intravenous analgesia (PCIA) and ultrasound-guided intercostal nerve block. In this prospective, randomized and double-blinded trial and the short and long-term outcomes were compared in patients after surgery. METHODS: The children were randomized to either the intercostal or control group. Ultrasound-guided intercostal nerve block was with 0.25% ropivacaine and 5 mg dexamethasone in the intercostal group, while the control group was with 0.9% normal saline. The block was performed in the intercostal space corresponding to the lowest depression of the sternum and repeated bilaterally in the spaces above and below. Postoperatively, the children in the two-groups received PCIA with fentanyl for 48 hours. The primary outcome was a pain score on the postoperative day 1, as measured by the Visual Analogue Scale (VAS). RESULTS: Sixty children undergoing the Nuss procedure were enrolled in the trial. The mean differences in VAS scores between the two groups were 3.2 in the PACU (p < 0.001), 1.7 on postoperative day 1 (p < 0.001) and 0.7 on postoperative day 2 (p=0.015). The opioid consumption was significantly lower in the intercostal group during the postoperative 48 hours (p < 0.05). The anxiety and QOL scores in the intercostal group were significantly improved on some points of time (p < 0.05). The incidence of adverse events was markedly lower in the intercostal group during the postoperative 48 hours (p < 0.05). CONCLUSIONS: Our results suggest ultrasound-guided intercostal nerve block with PCIA may be more effective than PCIA alone in children who underwent the Nuss procedure.
Keywords: Humans; Child; Pain, Postoperative; Intercostal Nerves; Analgesia, Patient-Controlled; Prospective Studies; Nerve Block; Ultrasonography, Interventional; Quality of Life

Guided relaxation-based virtual reality versus distraction-based virtual reality or passive control for postoperative pain management in children and adolescents undergoing Nuss repair of pectus excavatum: protocol for a prospective, randomised, controlled trial (FOREVR Peds trial) - Olbrecht, Vanessa A.; Williams, Sara E.; O'Conor, Keith T.; Boehmer, Chloe O.; Marchant, Gilbert W.; Glynn, Susan M.; Geisler, Kristie J.; Ding, Lili; Yang, Gang; King, Christopher D. (BMJ open, 2020)
INTRODUCTION: Virtual reality (VR) offers an innovative method to deliver non-pharmacological pain management. Distraction-based VR (VR-D) using immersive games to redirect attention has shown short-term pain reductions in various settings. To create lasting pain reduction, VR-based strategies must go beyond distraction. Guided relaxation-based VR (VR-GR) integrates pain-relieving mind-body based guided relaxation with VR, a novel therapy delivery mechanism. The primary aim of this study is to assess the impact of daily VR-GR, VR-D and 360 video (passive control) on pain intensity. We will also assess the impact of these interventions on pain unpleasantness, anxiety and opioid and benzodiazepine consumption. The secondary aim of this study will assess the impact of psychological factors (anxiety sensitivity and pain catastrophising) on pain following VR. METHODS AND ANALYSIS: This is a single centre, prospective, randomised, clinical trial. Ninety children/adolescents, aged 8-18 years, presenting for Nuss repair of pectus excavatum will be randomised to 1 of 3 study arms (VR-GR, VR-D and 360 video). Patients will use the Starlight Xperience (Google Daydream) VR suite for 10 min. Patients randomised to VR-GR (n=30) will engage in guided relaxation/mindfulness with the Aurora application. Patients randomised to VR-D (n=30) will play 1 of 3 distraction-based games, and those randomised to the 360 video (n=30) will watch the Aurora application without audio instructions or sound. Primary outcome is pain intensity. Secondary outcomes include pain unpleasantness, anxiety and opioid and benzodiazepine consumption. ETHICS AND DISSEMINATION: This study follows Standard Protocol Items: Recommendations for Interventional Trials guidelines. The protocol was approved by the Cincinnati Children's Hospital Medical Center's institutional review board. Patient recruitment began in July 2020. Written informed consent will be obtained for all participants. All information acquired will be disseminated via scientific meetings and published in peer-reviewed journals. TRIAL REGISTRATION NUMBER: NCT04351776.
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Prospective Studies; pain management; Randomized Controlled Trials as Topic; clinical trials; complementary medicine; paediatric anaesthesia; paediatric thoracic surgery; Practice Guidelines as Topic; Reproducibility of Results; Virtual Reality

Bilateral Ultrasound-Guided Erector Spinae Plane Block for Pectus Excavatum Surgery: A Retrospective Propensity-Score Study - Fiorelli, Silvia; Menna, Cecilia; Andreetti, Claudio; Peritore, Valentina; Rocco, Monica; De Blasi, Roberto Alberto; Rendina, Erino Angelo; Massullo, Domenico; Ibrahim, Mohsen (Journal of Cardiothoracic and Vascular Anesthesia, 2022)
OBJECTIVE: Pectus excavatum (PE) repair is burdened by severe postoperative pain. This retrospective study aimed to determine whether the analgesic effect of ultrasound-guided erector spinae plane block (ESPB) plus standard intravenous analgesia (SIVA) might be superior to SIVA alone in pain control after PE surgical repair via Ravitch or Nuss technique. DESIGN: A retrospective cohort study. SETTING: At a university hospital. PARTICIPANTS: All participants were scheduled for surgical repair of PE. INTERVENTIONS: From January 2017 to December 2019, all patients who received ESPB plus SIVA or SIVA alone were investigated retrospectively. A 2:1 propensity-score matching analysis considering preoperative variables was used to compare analgesia efficacy in 2 groups. All patients received a 24-hour continuous infusion of tramadol, 0.1 mg/kg/h, and ketorolac, 0.05 mg/kg/h, via elastomeric pump, and morphine, 2 mg, intravenously as a rescue drug. The ESPB group received preoperative bilateral ESPB block. Postoperative pain, reported using a numerical rating scale at 1, 12, 24, and 48 hours after surgery; the number of required rescue doses; total postoperative morphine milligram equivalents consumption; and the incidence of postoperative nausea and vomit were analyzed. MEASUREMENT AND MAIN RESULTS: A total of 105 patients were identified for analysis. Propensity-score matching resulted in 38 patients in the SIVA group and 19 patients in the ESPB group. Postoperative pain, the number of rescue doses, and postoperative nausea and vomit incidences were lower in the ESPB group (p < 0.005). CONCLUSIONS: Erector spinae plane block may be an effective option for pain management after surgical repair of PE as part of a multimodal approach. This study showed good perioperative analgesia, opioid sparing, and reduced opioid-related adverse effects.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Analgesics, Opioid; Nerve Block; Ultrasonography, Interventional; Ravitch procedure; erector spinae plane block; Morphine Derivatives; pectus excavatum surgery; Postoperative Nausea and Vomiting; regional anesthesia; thoracic anesthesia

Intraoperative cryoanalgesia for managing pain after the Nuss procedure - Graves, Claire; Idowu, Olajire; Lee, Sang; Padilla, Benjamin; Kim, Sunghoon (Journal of Pediatric Surgery, 2017)
BACKGROUND: Cryoanalgesia prevents pain by freezing the affected peripheral nerve. We report the use of intraoperative cryoanalgesia during the Nuss procedure for pectus excavatum and describe our initial experience, modifications of technique, and lessons learned. MATERIALS AND METHODS: We retrospectively reviewed the medical records of patients who received cryoanalgesia during the Nuss procedure between June 1, 2015, and April 30, 2016, at our institutions and analyzed modifications in surgical technique during this early adoption period. RESULTS: Eight male and two female patients underwent the Nuss procedure with cryoanalgesia. The mean postoperative length of stay (LOS) was 2days (range 1-3). Average inpatient pain scores were 3.4, 3.2, and 4.6 on postoperative days 1-3, respectively (N=10, 7, and 2). At a 1-week postoperative visit, mean pain score was 1.1 (N=6). Compared to the preceding 15 Nuss patients at our institution, who were treated with a thoracic epidural, postoperative LOS was significantly shorter with cryoanalgesia (2.0±0.82 vs. 6.3±1.3days, P<0.001). We modified our technique for patient habitus and adopted single-lung ventilation for improved visualization. CONCLUSIONS: Cryoanalgesia may be the ideal pain management strategy for Nuss patients because it is effective and long lasting. Intraoperative application is easily integrated into the Nuss procedure. STUDY TYPE: Treatment study: case series; Evidence level IV.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Analgesia; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Nuss procedure; Pectus excavatum; Intercostal Nerves; Orthopedic Procedures; Cryoanalgesia; Thoracoscopy; Follow-Up Studies; Cryoprobe; Cryotherapy; Epidural analgesia; Intraoperative Care

Quantifying postoperative sleep loss associated with increased pain in children undergoing a modified Nuss operation - Many, Benjamin T.; Rizeq, Yazan K.; Kwon, Soyang; Vacek, Jonathan C.; Goldstein, Seth D.; Hunter, Catherine J.; Ghomrawi, Hassan; Abdullah, Fizan (Journal of Pediatric Surgery, 2020)
PURPOSE: The presence of pain may interrupt sleep and impede normal postoperative recovery; however, no prior studies have quantified sleep loss due to pain in children undergoing inpatient surgery. Wearable accelerometers objectively measure sleep patterns in children. We aimed to quantify sleep loss associated with patient reported pain scores after a Modified Nuss operation. METHODS: Ten patients undergoing Modified Nuss operations were recruited during their inpatient stay. Children wore an Actigraph GT3X-BT accelerometer postoperatively during their hospital stay. Hourly sleep minutes were recorded using the Actigraph between 10 pm and 6 am. Patient reported pain scores were abstracted from patient charts. Mixed linear regression models, adjusting for within-subject random effects, were estimated to quantify the association between hourly sleep minutes and patient reported pain scores. RESULTS: Patients were 30% female, with an average age of 15.7 years (range 13-22). The majority (70%) of patients were white non-Hispanic. All patients received a patient controlled analgesic pump. Average postoperative length of stay was 4.8 days (range 4.0-6.0; SD = 0.8). A total of 240 sleep hours and associated pain scores were analyzed. Patients slept on average 48 min per hour. Mixed model analysis predicted that a 1-point increase in pain score was associated with 2.5 min per hour less sleep time. CONCLUSION: Increases in patient-reported pain scores are associated with sleep loss after a Modified Nuss operation. Objectively quantifying sleep loss associated with postoperative pain using accelerometer data may help clinicians better understand their patient's level of pain control. Our findings provide the basis for future studies aimed at more accurately titrating pain medication to optimize sleep and speed up recovery. LEVEL OF EVIDENCE: Case Series Without Comparison Group, Level IV.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Funnel Chest; Pain, Postoperative; Treatment Outcome; Analgesics; Pectus excavatum; Pain; Pediatric surgery; Children; Accelerometers; Actigraphy; Plastic Surgery Procedures; Sleep; Sleep Wake Disorders; Wearable telemetry

Use of cryoanalgesia for pain management for the modified ravitch procedure in children - Pilkington, Mercedes; Harbaugh, Calista M.; Hirschl, Ronald B.; Geiger, James D.; Gadepalli, Samir K. (Journal of Pediatric Surgery, 2020)
BACKGROUND: Intercostal cryoablation(IC) for pain management in children undergoing Nuss Procedure has been previously described. We evaluated postoperative outcomes following Modified Ravitch procedure for pectus disorders comparing IC to thoracic epidural(TE). MATERIALS AND METHODS: Single-center retrospective review of pediatric patients (age < 21) undergoing Modified Ravitch procedure (January 2015-March 2019) with either IC(9), or TE(20) analgesia. Primary outcome was length of stay (LOS) and secondary outcomes were inpatient opioid use (in oral morphine equivalents per kilogram; OME/kg), pain scores on each postoperative day (POD), discharge prescriptions, and complications. Pairwise comparisons made with Mann-Whitney U test or Fisher Exact test as appropriate. Two-tailed p values <0.05 were considered significant. RESULTS: Patient characteristics were similar. LOS was shorter with IC compared to TE (4 days versus 6; p < 0.006). Postoperative opioid use was not significantly different (IC: 1.5 OME/kg versus TE: 1.1; p = 0.10). There was improved pain control on POD 2 in patients who underwent IC (median pain score 3 versus 4; p < 0.0004). There was no difference in discharge prescription (IC: 3.3 OME/kg; TE: 4.8; p = 0.19) or complication rate (IC: 55.6%, TE:50%; p = 1.0). CONCLUSIONS: IC during the Modified Ravitch reduced LOS compared to TE with improved pain control starting on POD 2, with similar narcotic utilization and complication rates. LEVEL OF EVIDENCE: Treatment Study, Level III (Retrospective comparative study).
Keywords: Humans; Adolescent; Adult; Young Adult; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Length of Stay; Orthopedic Procedures; Pain Management; Cryoanalgesia; Pain; Pediatric; Pectus; Cryotherapy; Ravitch; Thoracic

Comparing outcomes with thoracic epidural and intercostal nerve cryoablation after Nuss procedure - Harbaugh, Calista M.; Johnson, Kevin N.; Kein, Courtney E.; Jarboe, Marcus D.; Hirschl, Ronald B.; Geiger, James D.; Gadepalli, Samir K. (The Journal of Surgical Research, 2018)
BACKGROUND: This study aimed to evaluate postoperative outcomes after minimally invasive repair of pectus excavatum (Nuss procedure) using video-assisted intercostal nerve cryoablation (INC) compared to thoracic epidural (TE). MATERIALS AND METHODS: We performed a single center retrospective review of pediatric patients who underwent Nuss procedure with INC (n = 19) or TE (n = 13) from April 2015 to August 2017. Preoperative, intraoperative, and postoperative characteristics were collected. The primary outcome was length of stay (LOS) and secondary outcomes were intravenous and oral opioid use, pain scores, and complications. Opioids were converted to oral morphine milligram equivalents per kilogram (oral morphine equivalent [OME]/kg). Mann-Whitney U test was used for continuous and chi-squared analysis for categorical variables. RESULTS: There were no significant differences in patient characteristics, except Haller Index (INC: median [interquartile range] 4.3 [3.6-4.9]; TE: 3.2 [2.8-4.0]; P = 0.03). LOS was shorter with INC (INC: 3 [3-4] days; TE: 6 [5-7] days; P < 0.001). Opioid use was higher intraoperatively (INC: 1.08 [0.87-1.37] OME/kg; TE: 0.46 [0.37-0.67] OME/kg; P = 0.002) and unchanged postoperatively (INC: 1.78 [1.26-3.77] OME/kg; TE: 1.82 [1.05-3.37] OME/kg; P = 0.80), and prescription doses were lower at discharge in INC (INC: 30 [30-40] doses; TE: 42 [40-60] doses; P = 0.005). There was no significant difference in postoperative complications (INC: 42.1%; TE: 53.9%; P = 0.51). CONCLUSIONS: INC during Nuss procedure reduced LOS, shifting postoperative opioid use earlier during admission. This may reflect the need for improved early pain control until INC takes effect. Prospective evaluation after INC is needed to characterize long-term pain medication requirements.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Postoperative Complications; Pain management; Analgesia, Epidural; Epidural; Cryoablation; Michigan; Pectus; Pediatric surgery; Video-Assisted Surgery

Opioid use and length of stay following minimally invasive pectus excavatum repair in 436 patients - Benefits of an enhanced recovery pathway - Holmes, David M.; Polites, Stephanie F.; Roskos, Penny L.; Moir, Christopher R. (Journal of Pediatric Surgery, 2019)
PURPOSE: The purpose of this study was to determine outcomes of an enhanced recovery pathway (ERP) for minimally invasive repair of pectus excavatum (MIRPE) at a high volume center, hypothesizing it is associated with decreased opioid requirement and shorter hospital stay. METHODS: Patients were categorized into pre-ERP (1998-2006), transition (2007-2011), and ERP (2012-2017) cohorts. Data were abstracted from medical records. Univariate and multivariable analyses compared opioid utilization, length of stay (LOS), and complications between cohorts. Opioids were converted to morphine daily dose per kilogram (MEDD/kg). RESULTS: Of 436 patients, 186 were ERP, 104 were transition, and 146 were pre-ERP. ERP was associated with decreased hospital opioid utilization (mean MEDD/kg 0.5 ± 0.2 vs 0.7 ± 0.4 vs 0.7 ± 0.8 p < .001) and shorter median LOS (3 vs 4 vs 5 days, p < .001) despite equivalent pain scores at discharge (2.7 ± 0.1 vs 2.8 ± 0.2 vs 2.9 ± 0.3, p = .73). Most ERP patients (76%) had LOS ≤3 days. Differences in LOS between ERP, transition, and pre-ERP persisted on multivariable analysis after adjusting for confounding factors. Post-operative complications were rare and not different between groups (p > .05). CONCLUSIONS: Implementation of our ERP was associated with decreased opioid requirement and shorter hospital stay. ERPs are a valuable tool in pediatric surgery given the current emphasis on optimizing opioid and resource utilization. LEVELS OF EVIDENCE: Level III (Retrospective comparative study).
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally invasive repair; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesics, Opioid; Length of Stay; Patient Discharge; Thoracoplasty; Length of stay; Incidence; United States; Enhanced recovery protocol; Laparoscopy; Opioid utilization; Recovery of Function

Successful use of an enhanced recovery after surgery (ERAS) pathway to improve outcomes following the Nuss procedure for pectus excavatum - Wharton, Kristin; Chun, Young; Hunsberger, Joann; Jelin, Eric; Garcia, Alejandro; Stewart, Dylan (Journal of Pediatric Surgery, 2020)
PURPOSE: Pectus excavatum is a common chest wall deformity amenable to surgical correction, most commonly by a technique known as the Nuss Procedure. The surgery is associated with significant postoperative pain and lengthy hospital stays. We hypothesized that a standardized enhanced recovery after surgery (ERAS) pathway would result in significantly reduced length of stay (LOS) and reduced levels of postoperative pain without an increase in readmissions or emergency department (ED) visits. METHODS: We instituted a pectus excavatum ERAS program at a high-volume academic center. Our ERAS protocol standardized perioperative exercise and pharmacologic regimens, pre- and post-operative education, and early return to activity. We conducted a retrospective review of all patients undergoing the Nuss procedure from 2015 to 2018. ERAS was implemented at the mid-point of the study period, and pre- and post-protocol patients were compared in our analysis. The primary outcome measure was LOS. The secondary outcomes included pain scores, incidence of urinary retention, and readmissions or ED visits. RESULTS: One hundred nine patients were included in this study (51 patients pre-ERAS and 58 post-ERAS). The average length of hospitalization prior to implementation of ERAS was 3.49 and after the implementation 2.90 (p = 0.0007). The implementation of ERAS showed a trend of decreasing readmissions and emergency department visits, but this did not reach statistical significance. There was a statistically significant decrease in both requirement for urinary catheter placement and pain scores on postoperative day 0. CONCLUSIONS: Implementation of ERAS for the Nuss procedure leads to a significant reduction in LOS, early pain scores, and urinary catheter usage, without an increase in post-operative ED visits and hospital readmissions. An ERAS protocol should be utilized in this patient population. TYPE OF STUDY: Retrospective comparative study. TYPE OF EVIDENCE: Level III.
Keywords: Humans; Adolescent; Female; Infant, Newborn; Male; Young Adult; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Nuss procedure; Pectus excavatum; Length of Stay; Enhanced recovery after surgery (ERAS); Postoperative Period; Length of stay; Child, Preschool; Plastic Surgery Procedures; Enhanced Recovery After Surgery; Gabapentin; Infant; Patient Readmission

Cryoablation is associated with shorter length of stay and reduced opioid use in pectus excavatum repair - Rettig, R. Luke; Rudikoff, Andrew G.; Lo, Hoi Yee Annie; Shaul, Donald B.; Banzali, Franklin M.; Conte, Antonio Hernandez; Sydorak, Roman M. (Pediatric Surgery International, 2021)
PURPOSE: The use of intercostal nerve cryoablation (INC) is becoming increasingly common in patients undergoing pectus excavatum (PE) repair. This study sought to evaluate the use of INC compared to traditional use of thoracic epidural (TE). METHODS: A retrospective review of 79 patients undergoing PE repair with either INC or TE from May 2009 to December 2019 was conducted. The operations were performed by four surgeons who worked together at four different hospitals and have the same standardized practice. The primary outcome measure was hospital length of stay (LOS). Secondary variables included surgical time, total operating room time, operating room time cost, total hospital cost, inpatient opioid use, long-term opioid use after discharge, and postoperative complications. RESULTS: LOS decreased to 2.5 days in the INC group compared to 5 days in the TE group (p < 0.0001). Surgical time was increased in the INC group, but there was no difference in total OR time. The INC group experienced significantly lower hospital costs. Total hospital opioid administration was significantly lower in INC group, and there was a significant decrease in long-term opioid use in the INC group. CONCLUSIONS: INC is a newer modality that decreases LOS, controls pain, and results in overall cost savings. We recommend that INC be included in the current practice for postoperative pain control in PE patients undergoing Nuss procedure.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Pectus excavatum repair; Postoperative Complications; Operative Time; Enhanced recovery after surgery; Thoracic epidural

Epidural analgesia versus intravenous analgesia after minimally invasive repair of pectus excavatum in pediatric patients: a systematic review and meta-analysis - Heo, Min Hee; Kim, Ji Yeon; Kim, Jung Hyeon; Kim, Kyung Woo; Lee, Sang Il; Kim, Kyung-Tae; Park, Jang Su; Choe, Won Joo; Kim, Jun Hyun (Korean Journal of Anesthesiology, 2021)
BACKGROUND: Postoperative pain control after the minimally invasive repair of pectus excavatum (MIRPE) is essential, but there is a controversy about a better analgesic method between epidural and intravenous (IV) analgesia. This systematic review and meta-analysis aimed to compare the effect of epidural versus IV analgesia following MIRPE. METHODS: We searched PubMed, MEDLINE, EMBASE, Cochrane Central Register, and ClinicalTrials.gov for randomized controlled trials (RCTs) dated up to 31st May 2021. The primary outcome was the area under the curve (AUC) of the weighted mean visual analog scale (VAS) after MIRPE. The secondary outcomes were postoperative nausea, operation time, total operating room time, and postoperative length of hospital stay. RESULTS: Four RCTs involving 243 patients were finally included in this meta-analysis. The AUC of the weighted mean VAS was 343.62 in the epidural group and 375.24 in the IV group. The epidural group showed lower VAS than the IV group at 12 to 48 h after the surgery. Postoperative nausea, operation time and length of hospital stay was not different between two groups. The epidural group had a significantly longer total operating room time due to epidural catheter insertion time. CONCLUSIONS: Epidural analgesia after the MIRPE had a better analgesic effect than IV analgesia. However, IV analgesia may also be a viable option, and physicians should wisely choose analgesic modalities after MIRPE.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Pain Management; Analgesia, Epidural; Postoperative pain; Funnel chest; Epidural analgesia; Intravenous administration; Minimally invasive surgical procedures; Statistics; Systematic review

Intercostal cryoablation during Nuss procedure: A large volume single surgeon's experience and outcomes - Sun, Raphael C.; Mehl, Steven C.; Anbarasu, Centura R.; Portuondo, Jorge I.; Espinoza, Andres F.; Whitlock, Richard; Mazziotti, Mark V. (Journal of Pediatric Surgery, 2021)
BACKGROUND: Recent studies have shown intercostal cryoablation(IC) during the Nuss procedure decreases hospital length of stay(LOS) and opioid administration. However, few studies have also evaluated the risk of postoperative complications related to IC. METHODS: We performed a single center retrospective analysis of all patients who underwent Nuss procedure by one surgeon from 2/2016 to 2/2020, comparing intraoperative IC to other pain management modalities(non-IC). Primary outcomes were postoperative complications, hospital LOS, and opioid administration. Multivariate analysis was performed with outcomes reported as regression coefficients(RC) or odds ratios(OR) with 95% confidence interval. RESULTS: IC was associated with decreased hospital LOS (RC -1.91[-2.29 to -1.54], less hospital opioid administration (RC -4.28[-5.13 to -3.43]), and less discharge opioid administration (RC -3.82[-5.23 to -2.41]). With respect to postoperative complications, IC decreased the odds of urinary retention (OR 0.16[0.06 to 0.44]); however, increased the odds of slipped bars requiring reoperation (OR 36.65[5.04-266.39]). CONCLUSIONS: Our single surgeon experience controls for surgeon variability and demonstrates intraoperative IC for the Nuss procedure is an effective pain management modality that decreases hospital LOS and opioid use during hospitalization and at discharge; however, it is associated with increased odds of slipped bars requiring reoperation. LEVEL OF EVIDENCE: III.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Cryosurgery; Intercostal cryoablation; Nuss; Opioid; Abbreviations; Forced expiratory volume (FEV); Forced vital capacity (FVC); Haller index (HI); intercostal cryoablation (IC); interquartile ranges (IQR); length of stay (LOS); multiple polyester (p-dioxanone) sutures (PDS); odds ratio (OR); oral morphine equivalents (OME/kg); patient-controlled analgesia (PCA); peripheral nerve block (PNB); regression coefficient (RC); Surgeons; thoracic epidural (TE)

Epidural versus Patient-Controlled Analgesia after Pediatric Thoracotomy for Malignancy: A Preliminary Review - Gonzalez, Katherine W.; Dalton, Brian G.; Millspaugh, Daniel L.; Thomas, Priscilla G.; St Peter, Shawn David (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2016)
Introduction The use of thoracic epidural is standard in adult thoracotomy patients facilitating earlier mobilization, deep breathing, and minimizing narcotic effects. However, a recent randomized trial in pediatric patients who undergo repair of pectus excavatum suggests patient-controlled analgesia (PCA) produces a less costly, minimally invasive postoperative course compared with epidural. Given that thoracotomy is typically less painful than pectus bar placement, we compared the outcomes of epidural to PCA for pain management after pediatric thoracotomy. Methods A retrospective review of 17 oncologic thoracotomies was performed at a children's hospital from 2004 to 2013. Data points included operative details, epidural or PCA use, urinary catheterization, days to regular diet, days to oral pain regimen, postoperative pain scores, length of stay, and anesthesia charges. Patients were excluded if they did not have epidural or PCA following thoracotomy. Results Six thoracotomies were managed with an epidural and 11 with a PCA. Three epidural patients were opiate naïve compared with two with a PCA. The most common indication for thoracotomy was metastatic osteosarcoma (n = 13). When comparing epidural to PCA, there was no significant difference in days to removal of Foley catheter, regular diet, oral pain control, length of stay, or total operating room time. Postoperative pain scores were also comparable. The mean anesthesia charges were significantly higher in patients with an epidural than with a PCA. Conclusion Epidural catheter and PCA provided comparable pain relief and objective recovery course in children who underwent thoracotomy for oncologic disease; however, epidural catheter placement was associated with increased anesthesia charges, suggesting that PCA is a noninvasive, cost-effective alternative.
Keywords: Humans; Adolescent; Female; Male; Child; Pain, Postoperative; Retrospective Studies; Length of Stay; Analgesia, Patient-Controlled; Pain Measurement; Operative Time; Anesthesia, Epidural; Postoperative Care; Osteosarcoma; Pulmonary Blastoma; Sarcoma, Ewing; Thoracotomy

Liposomal Bupivacaine Injection in Nuss Procedure Allows Narcotic Avoidance and Improved Outcomes - Jeziorczak, Paul M.; Frenette, Riley S.; Aprahamian, Charles J. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2021)
Background: The Nuss procedure has provided a minimally invasive surgical solution for pectus excavatum with excellent long-term outcomes. However, opioid avoidance, cost reduction, and length of stay (LOS) still offer room for improvement. The focus of this study is to identify the impact of Bupivacaine liposome injectable suspension (Exparel) on outcomes. Methods: A retrospective review at a Pediatric specialty hospital from October 1, 2014 to December 31, 2019 was performed. All patients underwent a Nuss procedure (n = 19) for pectus excavatum. The cohort comprised a control group that did not use liposomal Bupivacaine (Standard, n = 9) and an interventional group that received liposomal Bupivacaine (n = 10). Nonparametric Wilcoxon rank-sum tests and chi-squared or Fisher's exact tests were used to assess significance (P < .05). Results: Overall, the entire population was 68.4% male and had an average age of 15 years. There was a significant difference between the Standard and Liposomal Bupivacaine groups for total cost ($60,746 versus $13,289), total Morphine Milligram Equivalents (MME) (282 versus 76.8 MME) and Epidural Catheter usage (100% versus 0%). There was also a significant difference between groups for LOS (5.00 days versus 3.00 days) and Foley catheter usage (100% versus 20%). Conclusions: There is a significant impact of liposomal Bupivacaine usage on epidural catheter avoidance and opioid administration correlating with a significantly decreased total cost and decreased LOS. While more study is necessary, liposomal Bupivacaine for Nuss procedure offers improvement of postoperative patient outcomes and drastic cost savings.
Keywords: Humans; Adolescent; Female; Male; Child; Pain, Postoperative; Retrospective Studies; Nuss procedure; Analgesics, Opioid; Length of Stay; Narcotics; Bupivacaine; Anesthetics, Local; cost reduction; liposomal bupivacaine; Liposomes; opioid avoidance

Development of a five point enhanced recovery protocol for pectus excavatum surgery - Downing, Lynsey; Ramjist, Joshua K.; Tyrrell, Aidan; Tsang, Maisie; Isaac, Lisa; Fecteau, Annie (Journal of Pediatric Surgery, 2023)
PURPOSE: We implemented and evaluated an Enhanced Recovery after Surgery (ERAS) protocol for Nuss procedures consisting of patient education, bowel management, pre/post-operative transitional pain service involvement, serratus anterior plane blocks and intercostal nerve cryoablation. METHODS: A 5-point ERAS protocol was implemented using multiple plan-do-study-act (PDSA) cycles. Data was collected prospectively for patients in the full ERAS protocol and retrospectively for previous patients. The primary outcome was length of stay (LOS). Secondary outcomes were opioid consumption, pain scores, protocol compliance and patient satisfaction. The impact of PDSA cycles and the ERAS protocol was quantified using statistical process control charts and Mann Whitney U test. RESULTS: A total of 53 patients were identified, 13 within the ERAS protocol and 40 prior to introduction. There was no difference in age, sex, or Haller index between the two cohorts. The median LOS was decreased by 3 days in the ERAS cohort (P = 0.00001). There was decreased opioid consumption on post-operative day 1 (1.47 vs 1.96 MME/kg, p = 0.009) and overall (3.12 vs 6.35 MME/kg, p = 0.0042) in the ERAS cohort. Median pain scores did not differ between cohorts. ERAS bundle element compliance was: education 92%, bowel management 100%, transitional pain involvement 100%, serratus block 100% and cryoablation 100%. The 1-month survey revealed that 92% of patients were satisfied with their experience. CONCLUSION: Our results demonstrate significant reduction in LOS and a trend to decreasing opioid consumption in hospital following ERAS protocol implementation and support the further application of ERAS protocols in pediatrics. LEVEL OF EVIDENCE: III - Retrospective comparative study.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Analgesics, Opioid; Length of Stay; Cryoablation; Pediatric surgery; Enhanced recovery after surgery; ERAS

Cost and outcomes of intercostal nerve cryoablation versus thoracic epidural following the Nuss procedure - Perez Holguin, Rolfy A.; DeAngelo, Noah; Sinha, Anjana; Shen, Chan; Tsai, Anthony Y. (Journal of Pediatric Surgery, 2023)
BACKGROUND: Pectus excavatum is the most common congenital chest wall abnormality, with the Nuss procedure being the most commonly performed repair. Pain control is the predominant factor in the postoperative treatment of these patients. This study aims to compare the cost and outcomes of intercostal nerve cryoablation (INC) and thoracic epidural (TE) in patients undergoing the Nuss procedure. METHODS: A retrospective chart review was conducted at our institution for all patients who underwent the Nuss procedure for pectus excavatum from 2002 to 2020. Patients were stratified by pain management strategy, INC vs. TE. Chi-square and Fisher's exact were used to compare categorical variables. Wilcoxon tests were used to evaluate continuous variables and costs. RESULTS: A total of 158 patients were identified. Of these, 80.4% (N = 127) were treated with epidural, while 19.6% (N = 31) were treated with intercostal nerve cryoablation. The INC group had lower rates of PCA use (35.5% vs. 93.7%, p < 0.001), lower total morphine milligram equivalent requirement (27.0 vs. 290.8, p < 0.001), and shorter length of stay (3.2 days vs. 5.3 days, p < 0.001) compared to the TE group. INC was also associated with longer operative times (153.0 min vs. 89.0 min, p < 0.001). The total hospitalization cost for the INC group was higher compared to the TE group ($24,742.5 vs $21,621.9, p = 0.001). CONCLUSIONS: In patients undergoing the Nuss procedure, compared to thoracic epidural, INC was associated with lower opioid use and shorter length of stay but at the cost of longer operative time and increased hospitalization cost. LEVEL OF EVIDENCE: Treatment Study, Level III.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Thoracic Wall; Thoracic epidural; Cost

A retrospective comparison of thoracic epidural infusion and multimodal analgesia protocol for pain management following the minimally invasive repair of pectus excavatum - Man, Janice Y.; Gurnaney, Harshad G.; Dubow, Scott R.; DiMaggio, Theresa J.; Kroeplin, Gina R.; Adzick, N. Scott; Muhly, Wallis T. (Paediatric Anaesthesia, 2017)
BACKGROUND: Pain management following minimally invasive repair of pectus excavatum is variable. We recently adopted a comprehensive multimodal analgesic protocol that standardizes perioperative analgesic management. We hypothesized that patients managed with this protocol would use more opioids postoperatively, have similar pain control, and shorter length of stay compared to patients managed with thoracic epidural infusion. AIMS: We retrospectively compared opioid consumption, pain scores, and length of stay between a cohort of patients managed with our multimodal analgesic protocol and a cohort managed with a thoracic epidural infusion. METHODS: This retrospective cohort comparison includes patients, 8 to 21 years of age, managed with either thoracic epidural infusion (n = 21) or multimodal analgesic protocol (n = 29) following minimally invasive repair of pectus excavatum from January 1, 2011 through September 15, 2015. The primary outcome, total daily opioid consumption in morphine equivalents, is presented as an average by postoperative day. Secondary outcomes included median daily pain score and length of stay. RESULTS: Patients were similar in age, weight, sex, and physical status. Patients managed with thoracic epidural infusion received less opioid (morphine equivalents-mg/kg) intraoperatively compared to multimodal analgesic protocol (difference of mean [95% confidence interval] 0.22 [0.16-0.28] P ≤ .01) but required more total opioid through postoperative day 3 (difference of mean [95% confidence interval] 1.2 [0.26-2.14] P = .01). We did not observe a difference in pain scores. Median length of stay was 1 day less in patients managed with multimodal analgesic protocol (difference of median [95% confidence interval] 1 [0.3-1.7] P = .003). CONCLUSION: Implementation of a standardized comprehensive multimodal analgesic protocol following minimally invasive repair of pectus excavatum resulted in equivalent analgesia with a modest reduction in length of stay when compared to thoracic epidural. We did not observe an opioid sparing effect in our thoracic epidural which may reflect technique variability.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Length of Stay; Analgesia, Patient-Controlled; Pain Management; Pain Measurement; Analgesia, Epidural; Analgesics, Non-Narcotic; Cohort Studies; acute pain; adolescent; child; opioids; quality improvement; Thoracic Vertebrae

Interventions with Music in PECTus excavatum treatment (IMPECT trial): a study protocol for a randomised controlled trial investigating the clinical effects of perioperative music interventions - Billar, Ryan J.; Kühlmann, A. Y. Rosalie; Schnater, J. Marco; Vlot, John; Tomas, Jeremy J. P.; Zijp, Gerda W.; Rad, Mandana; de Beer, Sjoerd A.; Stevens, Markus F.; Poley, Marten J.; van Rosmalen, Joost; Jeekel, Johannes F.; et al. (BMJ open, 2020)
INTRODUCTION: Pectus excavatum repair is associated with substantial postoperative pain, despite the use of epidural analgesia and other analgesic regimens. Perioperative recorded music interventions have been shown to alleviate pain and anxiety in adults, but evidence for children and adolescents is still lacking. This study protocol describes a randomised controlled trial that evaluates the effects of recorded music interventions on postoperative pain relief in children and adolescents after pectus excavatum repair. METHODS: A multicentre randomised controlled trial was set up comparing the effects of perioperative recorded music interventions in addition to standard care with those of standard care only in patients undergoing a Nuss procedure for pectus excavatum repair. One hundred and seventy subjects (12-18 years of age) will be included in three centres in the Netherlands. Patient inclusion has started in November 2018, and is ongoing. The primary outcome is self-reported perceived pain measured on the visual analogue scale. Secondary outcomes are anxiety level, analgesics consumption, vital parameters such as heart rate, blood pressure and respiratory rate, length of hospital stay, postoperative complications, quality of life and cost-effectiveness. ETHICS AND DISSEMINATION: This study is being conducted in accordance with the Declaration of Helsinki. The Medical Ethics Review Board of Erasmus University Medical Centre Rotterdam, The Netherlands, has approved this protocol. Results will be disseminated via peer-reviewed scientific journals and conference presentations. TRIAL REGISTRATION NUMBER: NL6863.
Keywords: Humans; Adolescent; Adult; Child; Funnel Chest; Pain, Postoperative; Analgesics, Opioid; pain management; Quality of Life; Randomized Controlled Trials as Topic; paediatric anaesthesia; paediatric thoracic surgery; Multicenter Studies as Topic; Music; Music Therapy; Netherlands

Intercostal nerve cryoablation versus thoracic epidural catheters for postoperative analgesia following pectus excavatum repair: Preliminary outcomes in twenty-six cryoablation patients - Keller, Benjamin A.; Kabagambe, Sandra K.; Becker, James C.; Chen, Y. Julia; Goodman, Laura F.; Clark-Wronski, Julianna M.; Furukawa, Kenneth; Stark, Rebecca A.; Rahm, Amy L.; Hirose, Shinjiro; Raff, Gary W. (Journal of Pediatric Surgery, 2016)
BACKGROUND: Multimodal pain management strategies are used for analgesia following pectus excavatum repair. However, the optimal regimen has not been identified. We describe our early experience with intercostal cryoablation for pain management in children undergoing the Nuss procedure and compare early cryoablation outcomes to our prior outcomes using thoracic epidural analgesia. METHODS: A multi-institutional, retrospective review of fifty-two patients undergoing Nuss bar placement with either intercostal cryoablation (n=26) or thoracic epidural analgesia (n=26) from March 2013 to January 2016 was conducted. The primary outcome was hospital length of stay. Secondary outcomes included telemetry unit monitoring time, total intravenous narcotic use, duration of intravenous narcotic use, and postoperative complications. RESULTS: Patients who underwent intercostal cryoablation had a significant reduction in the mean hospital length of stay, time in a monitored telemetry bed, total use of intravenous narcotics, and the duration of intravenous narcotic administration when compared to thoracic epidural patients. Cryoablation patients had a slightly higher rate of postoperative complications. CONCLUSION: Intercostal cryoablation is a promising technique for postoperative pain management in children undergoing repair of pectus excavatum. This therapy results in reduced time to hospital discharge, decreased intravenous narcotic utilization, and has eliminated epidurals from our practice. LEVEL OF EVIDENCE: Retrospective study - level III.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Pain management; Analgesia, Epidural; Cryoablation; Epidural analgesia

The Use of Cryoanalgesia in Minimally Invasive Repair of Pectus Excavatum: Lessons Learned - Parrado, Raphael; Lee, Justin; McMahon, Lisa E.; Clay, Conner; Powell, Jordan; Kang, Paul; Notrica, David M.; Ostlie, Daniel J.; Bae, Jae-O. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2019)
Introduction: Cryoanalgesia has been applied to minimally invasive repair of pectus excavatum (MIRPE). After implementation of cryoanalgesia at our institution, we had several cases of delayed postoperative pneumothorax. The purpose of this study was to critically evaluate the complications and efficacy of cryoanalgesia in MIRPE. Materials and Methods: We performed a single institution retrospective review of pediatric patients undergoing MIRPE from June 2017 to July 2018. Multimodal (MM) analgesia was used in all patients. In addition, most patients received either cryoanalgesia or elastomeric pain pumps (EPPs) as adjuncts to postoperative analgesia. Primary outcome was clinically significant late pneumothorax. Secondary outcomes included length of stay, pain scores, opiate use, and bar displacement requiring reoperation. Results: A total of 101 patients undergoing MIRPE were included: 45 had cryoanalgesia + MM, 45 EPP + MM, and 11 MM alone. Postoperative tube thoracostomy was placed in 5 patients with cryoanalgesia (4 pneumothorax; 1 effusion), 1 patient with EPP (1 pneumothorax), and none in MM alone (P = .25). Pain scores at discharge were similar in all groups. Cryoanalgesia patients received less overall inpatient opioids than other groups (P < .05). No patient required reoperation for bar displacement. Conclusion: Cryoanalgesia is an effective therapy for pain control in MIRPE. Because thermal injury can occur on the lung and chest wall with cryoanalgesia, we implemented techniques to limit and prevent this injury. Cryoanalgesia offers a safe alternative for postoperative analgesia with significant reduction in inpatient opioid requirement. Larger prospective studies are required to assess the long-term impact and complications of cryoanalgesia.
Keywords: Humans; Adolescent; Female; Male; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Orthopedic Procedures; Postoperative Complications; postoperative analgesia; minimally invasive repair of pectus excavatum; Follow-Up Studies; cryoanalgesia; Cryotherapy; Combined Modality Therapy; Pneumothorax

Intercostal Nerve Cryoablation is Associated with Reduced Opioid Use in Pediatric Oncology Patients - Chen, Stephanie Y.; Mack, Shale J.; Stein, James E.; Kelley-Quon, Lorraine I.; Kim, Eugene S. (The Journal of Surgical Research, 2023)
INTRODUCTION: Intercostal nerve cryoablation reduces postoperative pain in adults undergoing thoracotomy and children undergoing pectus excavatum repair. We hypothesize that cryoablation is associated with decreased post-thoracotomy pain and opioid use in pediatric oncology patients. METHODS: A single-center retrospective cohort study was performed for oncology patients who underwent thoracotomy from January 1, 2017 to May 31, 2021. Outcomes included postoperative opioid use measured in morphine milligram equivalents per kilogram (MME/kg), pain scores (scale 0-10), and opioid prescription at discharge. Univariable analysis compared patients who received cryoablation to patients who did not receive cryoablation. Multivariable regression analysis controlling for age and prior thoracotomy evaluated associations between cryoablation and postoperative pain. RESULTS: Overall, 32 patients (19 males:13 females) underwent thoracotomy with 16 who underwent >1 thoracotomy resulting in 53 thoracotomies included for analysis. Cryoablation was used in 14 of 53 (26.4%) thoracotomies. Throughout the postoperative hospitalization, patients receiving cryoablation during thoracotomy consumed less opioids compared to patients who did not receive cryoablation (median 0.38 MME/kg, interquartile range [IQR] 0.20-1.15 versus median 1.47 MME/kg, IQR 0.71-4.02, P < 0.01). Maximum pain scores were lower in cryoablation patients (median 6, IQR 5-8) than noncryoablation patients (median 8, IQR 6-10), with a significant difference observed on postoperative day 4 (P = 0.01). Cryoablation patients were also less frequently prescribed opioids at discharge (21.4% versus 58.97%, P = 0.02). Multivariable regression demonstrated that cryoablation was associated with 2.59 MME/kg less opioid use (95% confidence interval -4.56 to -0.63) and decreased likelihood of opioid prescription at discharge (adjusted odds ratio 0.14, 95% confidence interval 0.03-0.67). CONCLUSIONS: Cryoablation is significantly associated with decreased post-thoracotomy pain and opioid use in pediatric cancer patients and should be considered in postoperative pain regimens.
Keywords: Humans; Adult; Female; Male; Child; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Morphine; Postoperative pain; Opioid; Cryoablation; Pediatric surgery; Thoracotomy; Opioid-Related Disorders; Pediatric oncology

Perioperative anesthetic and surgical complications of the Nuss procedure - Umuroglu, Tumay; Bostancı, Korkut; Thomas, David Terence; Yuksel, Mustafa; Gogus, F. Yilmaz (Journal of Cardiothoracic and Vascular Anesthesia, 2013)
OBJECTIVE: The Nuss procedure is a chest wall remodeling surgery performed in patients with pectus excavatum. This study was performed to analyze perioperative surgical and anesthetic complications with the Nuss procedures. DESIGN: A retrospective analysis. SETTING: An academic hospital. PARTICIPANTS: Two hundred fourteen patients (children, adolescents, and adults) undergoing the Nuss procedure over 6 years. INTERVENTIONS: Patient age and sex, premorbid diseases, indications for surgery, patient position during the procedure, the length of surgery, time to hospital discharge, postoperative analgesia method, and the presence of perioperative complications were recorded. MEASUREMENTS: No mortality was observed. The overall complication rate was 18.7%, but the overall event rate was 42.6% (91 events in 40 patients). Intraoperative hypotension, tachycardia, and hypercapnia were the most common complications (4.7%), followed by postoperative ileus (3.2%), pneumothorax (right, left, or bilateral; 4.2%), lung parenchymal laceration (2.3%), and postoperative nausea and vomiting (2.3%). Two patients had an ulnar nerve palsy and 1 patient had a brachial nerve palsy as a result of surgical position. CONCLUSION: Although the Nuss procedure is reported to be minimally invasive, some serious complications concerning both surgery and anesthesia should not be overlooked.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Thoracic Surgical Procedures; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Length of Stay; Analgesia, Patient-Controlled; Postoperative Complications; Forced Expiratory Volume; Vital Capacity; Anesthesia, General; Intraoperative Complications; Perioperative Care; Preanesthetic Medication; Respiratory Function Tests; Supine Position

Effects of oxycodone pharmacogenetics on postoperative analgesia and related clinical outcomes in children: a pilot prospective study - Aruldhas, Blessed W.; Quinney, Sara K.; Packiasabapathy, Senthil; Overholser, Brian R.; Raymond, Olivia; Sivam, Sahana; Sivam, Inesh; Velu, Sanjana; Montelibano, Antoinette; Sadhasivam, Senthilkumar (Pharmacogenomics, 2023)
Background: Variability in the pharmacokinetics and pharmacodynamics of oxycodone in children undergoing surgery could be due to genetic polymorphisms. Materials & methods: The authors studied the association between clinical outcomes and pharmacogenes in children undergoing major surgery. A total of 89 children (35 undergoing pectus excavatum repair and 54 undergoing spinal fusion) were recruited. Results: OPRM1 SNP rs6902403 showed an association with maximum pain score and total morphine equivalent dose (p < 0.05). Other polymorphisms in OPRM1 SNP, PXR, COMT and ABCB1 were also shown to be associated with average morphine equivalent dose, length of hospital stay and maximum surgical pain (p < 0.05). Conclusion: This study demonstrates novel associations between the above pharmacogenes and oxycodone's pharmacokinetics as well as postoperative outcomes in children. Clinical trial registration: NCT03495388 (ClinicalTrials.gov).
Keywords: Humans; Analgesia; Child; Pain, Postoperative; Analgesics, Opioid; Prospective Studies; Morphine; analgesia; Oxycodone; ABCB1; children; COMT; CYP2D6; CYP3A4; hospital stay; OPRM1; oxycodone; pharmacogenetics; Pharmacogenetics; pharmacokinetics; PXR

Customized silicone implant for the correction of acquired and congenital chest wall deformities: A valuable option with pectus excavatum - Soccorso, Giampiero; Parikh, Dakshesh H.; Worrollo, Steve (Journal of Pediatric Surgery, 2015)
BACKGROUND: Surgical remodeling and correction of congenital and acquired chest wall deformities (CWD) is undertaken many times for cosmesis. Although reportedly minimally invasive, commonly used Nuss procedure for correction of pectus excavatum (PE) is not without complications. Nuss procedure is also not suitable for complex deformities and Poland syndrome cases. Insertion of custom-made silicone implants for the reconstruction of defects has been adopted from adult plastic reconstructive surgery as primary repair of CWD or rescue procedure for recurrence of PE after recurrence or residual deformity. METHODS: We present our experience with CWD reconstruction in children with customized silicone prosthesis made from a surgically implantable liquid silicone rubber (NuSil MED-4805, Ca). RESULTS: Since 2006 we treated 26 patients with CWD: six were children (age <17years, median 14.6) with PE. Implants were custom made for each patient's chest. The implants were inserted under general anesthesia. Postoperatively all patients were fully satisfied with the cosmetic result and subjective patient satisfaction remained excellent at follow-up in all the children. Only one child developed postoperative complications (seroma). CONCLUSIONS: Customized silicone implant for PE in the pediatric age is an alternative therapeutic method, as primary or rescue treatment, with equally good cosmetic outcome, fewer significant complications, less postoperative pain and a faster recovery.
Keywords: Humans; Adolescent; Adult; Female; Male; Child; Funnel Chest; Pain, Postoperative; Pectus excavatum; Postoperative Complications; Patient Satisfaction; Postoperative Period; Thoracic Wall; Recurrence; Children; Plastic Surgery Procedures; Chest wall deformity; Contraindications; Poland Syndrome; Prostheses and Implants; Prosthesis Design; Prosthesis Implantation; Silicone Elastomers; Silicone implant

Thoracic epidural-based Enhanced Recovery After Surgery (ERAS) pathway for Nuss repair of pectus excavatum shortened length of stay and decreased rescue intravenous opiate use - Cramm, Shannon L.; Luckhurst, Casey; Galls, Alexandra; Pietrantonio, Nicole; Doody, Daniel P.; Ryan, Daniel P.; Masiakos, Peter T. (Pediatric Surgery International, 2021)
BACKGROUND: PCA- and block-based enhanced recovery after surgery (ERAS) pathways have been shown to decrease hospital length of stay (HLOS) and opiate use following Nuss Repair for Pectus Excavatum (NRPE). No thoracic epidural-based ERAS pathway has demonstrated similar benefits. METHODS: In this pre-post single-center study, data were retrospectively collected for patients ≤ 21 years undergoing NRPE from May 2015 to August 2019. Univariate and multivariate methods were used to evaluate whether implementation of a thoracic epidural-based ERAS in April 2017 was associated with HLOS, opiate use, or pain scores. RESULTS: There were 110 patients: 35 pre- and 75 post-ERAS. HLOS decreased from median 4.8 (1.1) to 3.3 (0.6) days with ERAS (p < 0.001). Use of rescue intravenous opiates decreased from 35.3% pre- to 9.3% with ERAS (p = 0.013). When adjusted for baseline characteristics, ERAS was associated with a 1.3 ± 0.2 day decrease in HLOS and 0.188 times the odds of rescue intravenous opiate use (p = 0.011). CONCLUSIONS: Pain scores, ED visits, and readmissions did not change with ERAS (p > 0.05). Implementation of a thoracic epidural-based ERAS following NRPE was associated with decreased HLOS and need for any rescue intravenous opiates without a change in pain scores, ED visits, or readmission.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Length of Stay; Length of stay; Thoracic epidural; Enhanced Recovery After Surgery; ERAS; Opiate Alkaloids

A comparison of paravertebral nerve block catheters and thoracic epidural catheters for postoperative analgesia following the Nuss procedure for pectus excavatum repair - Hall Burton, Denise M.; Boretsky, Karen R. (Paediatric Anaesthesia, 2014)
INTRODUCTION: Thoracic epidurals (TE) have been advocated as a superior method for controlling postoperative pain after repair of pectus excavatum with a Nuss procedure. However, three recent reports of permanent neurologic injury after the Nuss procedure with concurrent TE analgesia have raised concerns about the safety of this combination. Paravertebral nerve blocks (PVNB) are used successfully for analgesia of the chest, but no studies are available comparing TE and PVNB catheters for postoperative analgesia in this patient population. This study was conducted to compare the efficacy of PVNB catheters with TE catheters for postoperative analgesia in pediatric patients undergoing the Nuss procedure. METHODS: We retrospectively reviewed the medical records of 20 adolescent males undergoing a thoracoscopic Nuss procedure with either bilateral PVNB catheters (n = 10) or TE catheter (n = 10) and compared postoperative opiate consumption and pain scores. RESULTS: There were no statistically significant differences between the groups with respect to demographics, opiate consumption measured in morphine equivalents, and pain scores. DISCUSSION: In this small series, bilateral PVNB catheters resulted in equivalent opioid consumption and pain scores when compared to TE for postoperative pain management in pediatric patients undergoing the Nuss procedure. Large prospective studies are needed to further compare the efficacy, incidence of side effects, and complications of TE and PVNB catheters for postoperative analgesia in this pediatric population.
Keywords: Humans; Adolescent; Male; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Pain Measurement; Analgesia, Epidural; Nerve Block; Morphine; Catheters; pediatrics; acute pain; anesthesia conduction; anesthesia, epidural; anesthesiology; bone diseases, developmental; Case-Control Studies; nerve block; pain, postoperative

Complications after Ravitch versus Nuss repair of pectus excavatum: A Society of Thoracic Surgeons (STS) General Thoracic Surgery Database analysis - Jawitz, Oliver K.; Raman, Vignesh; Thibault, Dylan; Yerokun, Babatunde; Zwischenberger, Brittany A.; Kosinski, Andrzej S.; Allen, Mark S.; Harpole, David H. (Surgery, 2021)
BACKGROUND: There are conflicting reports in the literature comparing outcomes after open Ravitch and minimally invasive Nuss procedures for pectus excavatum repair, and there is relatively little data available comparing the outcomes of these procedures performed by thoracic surgeons. METHODS: The 2010 to 2018 Society of Thoracic Surgeons General Thoracic Surgery Database was queried for patients age 12 or greater undergoing open or minimally invasive repair of pectus excavatum. Patients were stratified by operative approach. Multivariable logistic regression was performed with a composite outcome of 30-day complications. RESULTS: A total of 1,767 patients met inclusion criteria, including 1,017 and 750 patients who underwent minimally invasive pectus repair and open repair, respectively. Open repair patients were more likely to be American Society of Anesthesiologists (ASA) class III or greater (24% vs 14%; P < .001), have a history of prior cardiothoracic surgery (26% vs 14%; P < .001), and require longer operations (median 268 vs 185 minutes; P < .001). Open repair patients were more likely to require greater than 6 days of hospitalization (18% vs 7%; P < .001), undergo transfusion (7% vs 2%; P < .001), and be readmitted (8% vs 5%; P = .004). After adjustment, open repair was not associated with an increased risk of a composite of postoperative complications (odds ratio 0.99, 95% confidence interval 0.67-1.46). This finding persisted after propensity score matching (odds ratio 1.11, 95% confidence interval 0.74-1.67). CONCLUSION: Pectus excavatum repair procedure type was not associated with the risk of postoperative complications after adjustment. Further investigation is necessary to determine the impact of pectus excavatum repair type on recurrence and patient reported outcomes, including satisfaction, quality of life, and pain control.
Keywords: Humans; Adult; Female; Male; Young Adult; Thoracic Surgical Procedures; Funnel Chest; Retrospective Studies; Minimally Invasive Surgical Procedures; Patient Satisfaction; Quality of Life; Sternum; Risk Factors; Propensity Score

A comparison of parecoxib and thoracic epidural analgesia for postoperative analgesia following Nuss procedure - Yang, Wendy; Ming, Yung-Ching; Kau, Yi-Chuan; Liao, Chia-Chih; Tsai, Shih-Chang; Wong, Kit-Man; Wong, Shu-Yam; Lai, Jin-Yao (Journal of Pediatric Surgery, 2015)
BACKGROUND: The purpose of this study was to compare the results of thoracic epidural analgesia (TEA) and parecoxib in controlling postoperative pain after the Nuss procedure. METHODS: Between August 2005 and July 2014, 120 adolescents and adults underwent Nuss procedures and received either TEA or parecoxib for postoperative pain control. Demographic data, preoperative preparation times, visual analog scale (VAS) pain scores from postoperative day 1 to day 5, medical costs of pain control, days to Foley catheter removal, days to being able to sit up, days to being able to walk, days of hospital stay, nausea/vomiting scores, and complications related to pain control were compared. RESULTS: A total of 106 patients received TEA, and 14 received parecoxib. No between-group differences in demographics were observed. Patients in the parecoxib group had shorter preparation times (p<0.001), lower VAS pain scores from postoperative day 2 to day 5 (day 2, p=0.006; day 3, p=0.006; day 4, p<0.001; day 5, p<0.001), shorter hospital stays (p<0.001), lower pain control costs (p<0.001), and lower nausea/vomiting scores (p=0.046). CONCLUSIONS: For adolescents and adults undergoing the Nuss procedure, parecoxib affords better pain control efficacy, a shorter hospital stay, lower medical pain control costs, and fewer side effects compared with TEA.
Keywords: Humans; Adolescent; Adult; Female; Male; Young Adult; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Nuss procedure; Pectus excavatum; Length of Stay; Orthopedic Procedures; Pain Measurement; Analgesia, Epidural; Pain control; Injections, Intravenous; Thoracic epidural analgesia; Drug Administration Schedule; Cyclooxygenase 2 Inhibitors; Isoxazoles; Parecoxib

Long-term patient perception of pain control experience after participating in a trial between patient-controlled analgesia and epidural after pectus excavatum repair with bar placement - Gasior, Alessandra C.; Weesner, Kathryn A.; Knott, E. Marty; Poola, Ashwini; St Peter, Shawn D. (The Journal of Surgical Research, 2013)
BACKGROUND: Pain control is the dominant management issue after bar placement for pectus excavatum. We previously conducted a prospective, randomized trial comparing patient-controlled analgesia (PCA) to thoracic epidural (EPI) documenting similar objective outcomes. Our impression is that the subjective cognitive experience differs between the groups, which impacts trial results interpretation. Therefore, we conducted a survey to ascertain patient recollection and impression of their experience. METHODS: By telephone questionnaire, yes/no questions included early course recall, anxiety, if they would choose the same arm, do the operation again, or recommend it to friends. Qualitative questions included description, location, and time of peak pain. The graded question addressed severity of pain (1-5). RESULTS: We contacted 27 EPI and 38 PCA patients with a median follow-up of 3.2 y. The majority (~/= 85%) of both groups remembered the first 2 d. Mean pain severity was 3.0 in both groups (3 = bad, but tolerable). Description, location, and time of peak pain responses did not differ. Anxiety was reported by 30% of EPI group and 18% of PCA group (P = 0.37). Approximately 15% of both groups still think about the pain. No differences were seen in nausea, emesis, constipation, itching, or sleepiness. Most patients would choose the same group (87% PCA, 81% EPI, P = 0.73), have the operation again (87% PCA, 74% EPI, P = 0.21), and recommend the operation to friends (100% PCA, 96% EPI, P = 0.42). CONCLUSIONS: Long-term recall after repair of pectus excavatum with bar placement does not substantially differ between those managed with an epidural or PCA.
Keywords: Funnel Chest; Pain, Postoperative; Analgesics, Opioid; Orthopedic Procedures; Analgesia, Patient-Controlled; Prospective Studies; Patient Satisfaction; Analgesia, Epidural; Pain control; Epidural; Pediatric; Follow-Up Studies; Interviews as Topic; Oxycodone; Pain Threshold; PCA; Pectus bar; Time

Next day discharge after the Nuss procedure using intercostal nerve cryoablation, intercostal nerve blocks, and a perioperative ERAS pain protocol - DiFiore, John W.; Robertson, Jason O.; Chhabada, Surendrasingh; DeRoss, Anthony L.; Hossain, Mir S.; Rincon-Cruz, Lorena; Sung, Wai (Journal of Pediatric Surgery, 2022)
BACKGROUND: The Nuss procedure for pectus excavatum has historically been associated with significant postoperative pain, which has been the major factor contributing to hospital length of stay (LOS). METHODS: A single-institution, prospective study of 40 consecutive patients undergoing Nuss bar placement for pectus excavatum between November 2019 and January 2021 was conducted to assess the effectiveness of a multimodality pain management protocol. All patients received T3-T8 intercostal nerve cryoablation (INC), T3-T8 bupivacaine intercostal nerve blocks, Exparel at the skin incisions, and management with a perioperative analgesia regimen that minimized narcotic usage. The primary outcome was LOS. Secondary outcomes included opioid use, pain scores, and time to sensory recovery. RESULTS: 37/40 patients (92.5%) were discharged home on postoperative day (POD) 1, and 3/40 (7.5%) were discharged on POD 2 (mean LOS = 1.1 days). The median average postoperative pain score was 2/10. After eliminating IVPCA from our protocol, total oral morphine equivalent (OME) decreased by 73% (55.5 mg to 15 mg) with no change in pain scores or discharge timing. CONCLUSIONS: INC combined with bupivacaine intercostal nerve blocks and a pre- and post-hospital analgesia protocol facilitated discharge one day after the Nuss procedure, achieved excellent pain control, and eliminated the need for intravenous opioids.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Enhanced recovery after surgery (ERAS); Patient Discharge; Prospective Studies; Analgesia, Epidural; Intercostal nerve blocks; Nuss bar procedure

Successful Treatment of Persistent Pain After Pectus Excavatum Repair Using Paravertebral Nerve Radiofrequency Thermoablation - Ladenhauf, Hannah Noemi; Stundner, Ottokar; Likar, Rudolf; Schnöll, Jörg; Metzger, Roman P. (A & A Case Reports, 2017)
We present a case of a 25-year-old male patient suffering from severe prolonged pain after uneventful pectus excavatum repair that could be treated successfully by paravertebral nerve radiofrequency thermoablation. The patient was scheduled for a minimally invasive Nuss pectus excavatum repair. Surgical correction was performed under general anesthesia in combination with a thoracic peridural catheter. The immediate postoperative course was uneventful; however, the patient developed severe prolonged bilateral chest wall pain across segments T8 and T9. After failure of conservative treatment options, a specialized interventional anesthesiologist performed paravertebral nerve radiofrequency thermoablation of segment T9 bilaterally, after which the patient was pain free until scheduled removal of the pectus bar 3 years after placement.
Keywords: Humans; Adult; Male; Funnel Chest; Pain, Postoperative; Treatment Outcome; Minimally Invasive Surgical Procedures; Pain Measurement; Nerve Block; Orthopedic Fixation Devices; Ablation Techniques; Chronic Pain; Thoracic Nerves

Complex regional pain syndrome following the Nuss procedure for severe pectus excavatum - Chen, Yi-Ling; Chen, Liang-Cheng; Chen, Jen-Chih; Cheng, Yeung-Leung (Annals of Thoracic and Cardiovascular Surgery: Official Journal of the Association of Thoracic and Cardiovascular Surgeons of Asia, 2014)
Complex regional pain syndrome (CRPS) is not an uncommon complication after surgery, but has never been reported after the Nuss procedure for repairing pectus excavatum. A 22-year-old man with pectus excavatum had type I CRPS that developed 2 weeks after the Nuss procedure. He complained of persistent pain, hyperalgesia, weakness, edema, and color and temperature changes on right upper extremity. Following intensive rehabilitation, the degree of pain, weakness and edema were ameliorated. He recovered 6 months after surgery and the pectus bars were removed uneventfully 3 years after the repair.
Keywords: Humans; Male; Young Adult; Funnel Chest; Pain, Postoperative; Treatment Outcome; Orthopedic Procedures; Pain Measurement; Time Factors; Tomography, X-Ray Computed; Reflex Sympathetic Dystrophy; Remission Induction; Severity of Illness Index

Comparison of Ultrasonography-guided Bilateral Intercostal Nerve Blocks and Conventional Patient-controlled Intravenous Analgesia for Pain Control After the Nuss Procedure in Children: A Prospective Randomized Study - Luo, Mengqiang; Liu, Xiaoming; Ning, Li; Sun, Yuan; Cai, Ying; Shen, Sai'e (The Clinical Journal of Pain, 2017)
OBJECTIVES: Patients experience severe pain after pectus excavatum (PE) surgery. The aim of this prospective, randomized study was to compare analgesic effects of ultrasonography-guided bilateral intercostal nerve blocks (UG-ICNBs) with those of conventional patient-controlled intravenous analgesia (PCIA) on acute pain after the Nuss procedure for PE repair in children. METHODS: A prospective randomized study was performed in children with PE who were scheduled for the Nuss procedure. Participants were randomly assigned to receive either UG-ICNBs or PCIA for postoperative analgesia. Faces Pain Scale-Revised scores, opioid consumption, analgesia-associated side effects (respiratory depression, pruritus, nausea, vomiting) during the first 24 hours, and lengths of stay in the postanesthesia care unit (PACU) and hospital were recorded after the surgery. RESULTS: Sixty-two children undergoing the Nuss procedure were enrolled in the trial. Faces Pain Scale-Revised scores were significantly decreased in the UG-ICNBs group compared with the PCIA group for up to 6 hours after surgery. The opioid doses required in the PACU and during the first 24 hours after surgery were significantly greater in the PCIA group compared with the UG-ICNBs group. Accordingly, patients in the UG-ICNBs group showed a lower incidence of analgesia-associated side effects and faster PACU discharge compared with the PCIA group. CONCLUSIONS: Our study suggests that UG-ICNBs might be more effective than PCIA for postoperative analgesia in children who undergo the Nuss procedure for PE.
Keywords: Humans; Adolescent; Female; Male; Analgesia; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Intercostal Nerves; Analgesia, Patient-Controlled; Pain Management; Prospective Studies; Pain Measurement; Nerve Block; Follow-Up Studies; Child, Preschool; Administration, Intravenous; Double-Blind Method; Ultrasonography

Intercostal nerve cryoablation is associated with lower hospital cost during minimally invasive Nuss procedure for pectus excavatum - Aiken, Taylor J.; Stahl, Christopher C.; Lemaster, Deborah; Casias, Timothy W.; Walker, Benjamin J.; Nichol, Peter F.; Leys, Charles M.; Abbott, Daniel E.; Brinkman, Adam S. (Journal of Pediatric Surgery, 2021)
Minimally invasive repair of pectus excavatum (Nuss procedure) is associated with significant pain, and efforts to control pain impact resource utilization. Bilateral thoracic intercostal nerve cryoablation has been proposed as a novel technique to improve post-operative pain control, though the impact on hospital cost is unknown. METHODS: We conducted a retrospective study of patients undergoing a Nuss procedure from 2016 to 2019. Patients who received cryoablation were compared to those that received traditional pain control (patient-controlled analgesia or epidural). Outcome variables included postoperative opioid usage (milligram morphine equivalents, MME), length of stay (LOS), and hospital cost. RESULTS: Thirty-five of 73 patients studied (48%) received intercostal nerve cryoablation. LOS (1.0 vs 4.0 days, p < 0.01) and total hospital cost ($21,924 versus $23,694, p = 0.04) were decreased in the cryoablation cohort, despite longer operative time (152 vs 74 min, p < 0.01). Cryoablation was associated with decreased opioid usage (15.0 versus 148.6 MME, p < 0.01) during the 24 h following surgery and this persisted over the entire postoperative period, including discharge opioid prescription (112.5 vs 300.0 MME, p < 0.01). CONCLUSION: Bilateral intercostal nerve cryoablation is associated with decreased postoperative opioid usage and decreased resource utilization in pediatric patients undergoing a minimally invasive Nuss procedure for pectus excavatum. LEVEL OF EVIDENCE: Retrospective comparative study, level III.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Pectus excavatum; Cryosurgery; Intercostal Nerves; Pediatric; Cryoablation; Hospital cost; Hospital Costs; Minimally invasive Nuss procedure; Post-op pain

Continuous chest wall ropivacaine infusion for analgesia in children undergoing Nuss procedure: a comparison with thoracic epidural - Choudhry, Dinesh K.; Brenn, B. Randall; Sacks, Karen; Reichard, Kirk (Paediatric Anaesthesia, 2016)
BACKGROUND: Pain following Nuss procedure is severe and its management is challenging. Many different pain treatment modalities are currently being used, but none of them have been found to be ideal. AIM: In this retrospective review, we compare our current multimodal approach, which involves continuous ropivacaine infusion through chest wall catheters (CWC), intravenous patient-controlled analgesia (IV-PCA), and adjunctive medications (gabapentin and clonidine), with the technique that we used in the past, the thoracic epidural catheter (TEC). METHODS: Following IRB approval, we performed a retrospective analysis of data on 32 patients who underwent the Nuss procedure at our institution. All children were divided into two groups: TEC group: 0.2% ropivacaine and hydromorphone 10 mcg·ml(-1) epidural infusion (n = 15) and CWC group (with IV-PCA and adjuncts [gabapentin + clonidine]): 0.2% ropivacaine infusion and hydromorphone PCA, oral gabapentin, and transdermal clonidine patch (n = 17). RESULTS: Both the groups were demographically similar. Average numeric pain scores were higher in the CWC group only on the day of surgery (mean ± sd: 3.79 ± 1.58 vs 2.68 ± 1.30; 95% CI: -2.16 to -0.05). Pain scores on postoperative day 1 (mean ± sd: 3.40 ± 1.59 vs 3.35 ± 1.32; 95% CI: -1.11 to 1.01), day 2 (mean± sd: 3.39 ± 1.79 vs 2.99 ± 1.06; 95% CI: -1.50 to 0.70), and on the day of discharge (DOD) (mean± sd: 3.25 ± 1.84 vs 3.99 ± 1.28; 95% CI: -0.42 to 1.89) were comparable between the groups. The CWC group needed fewer changes in the therapeutic regimen to maintain acceptable pain relief, had lower incidence of nausea and vomiting, had shorter anesthesia time, total OR time, and hospital length of stay. CONCLUSION: TEC provided better analgesia following the Nuss procedure only on the day of surgery. On the subsequent days until discharge, pain scores were comparable. However, CWC offered other advantages: it was less labor intensive and had fewer side effects, shorter OR time, and shorter hospital stay.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Analgesics, Opioid; Analgesia, Patient-Controlled; Thoracic Wall; Morphine; Anesthetics, Local; pediatric; pain management; Anesthesia, Epidural; Gabapentin; Combined Modality Therapy; Amides; Amines; Clonidine; Cyclohexanecarboxylic Acids; gamma-Aminobutyric Acid; Infusions, Parenteral; multimodal approach; pectus repair; Ropivacaine

Effectiveness of one minute per level intercostal nerve cryoablation for postoperative analgesia after surgical correction of pectus excavatum - Zeineddin, Suhail; Goldstein, Seth D.; Linton, Samuel; DeBoer, Christopher; Alayleh, Amin; Ortiz, Irma; Sands, Laurie; Kujawa, Suzanne; Suresh, Santhanam; Ghomrawi, Hassan; Abdullah, Fizan (Journal of Pediatric Surgery, 2023)
PURPOSE: Intraoperative intercostal nerve cryoablation has emerged as a promising modality for postoperative analgesia following Surgical Correction of Pectus Excavatum (SCOPE). Most centers use two-minute cryoablation per level, although data from histologic and adult studies suggest the effectiveness of one-minute freezes. We aimed to describe our center's experience with one minute per level cryoablation. METHODS: A retrospective single institution review of patients undergoing SCOPE was performed to compare patients pre- and post-intercostal nerve cryoablation implementation. Cryoablation was performed as one minute for each of the thoracic intercostal nerves T3-T7. Multivariable regression analyses were conducted to compare the outcomes and cost between pre- and post-implementation groups. RESULTS: During the study period, 198 patients underwent SCOPE with one Nuss bar, receiving either intraoperative intercostal nerve cryoablation (Cryo, n = 100) or preoperative thoracic paravertebral catheters (NoCryo, n = 98). Surgical time was on average 9 min longer for the Cryo group (p<0.01). Median length of stay for the Cryo group was 3 days shorter compared to the NoCryo group (p<0.01). The Cryo group had a 19-fold and 5.6-fold reduction in average inpatient and total postoperative opioid usage, respectively (p<0.01). Total hospital costs were significantly lower in the Cryo group (p<0.01). Overall complication rate was not statistically significant different between the two groups. CONCLUSIONS: Intraoperative one minute per level cryoablation is a potent approach to postoperative analgesia for SCOPE patients that led to a shorter hospital length of stay, lower hospital costs, and decreased opioid use compared to conventional analgesia at our institution. Pediatric surgeons performing correction of chest wall deformities should consider offering this technique.
Keywords: Humans; Adult; Analgesia; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Cryoanalgesia; Thoracic Wall; Intercostal cryoablation; Nuss bar; Thoracoscopy; SCOPE

Are Foley catheters needed after minimally invasive repair of pectus excavatum? - Friske, Tyler C.; Sola, Richard; Yu, Yangyang R.; Jamal, Abdur R.; Rosenfeld, Eric; Zhu, Huirong; Mazziotti, Mark V.; St Peter, Shawn D.; Shah, Sohail R. (Surgery, 2018)
BACKGROUND: High narcotic requirements after minimally invasive repair of pectus excavatum (MIRPE) can increase the risk of urinary retention. Placement of intraoperative Foley catheters to minimize this risk is variable. This study determines the rate of urinary retention in this population to guide future practice. MATERIALS AND METHODS: We reviewed retrospectively all patients who underwent MIRPE from January 2012 to July 2016 at 2 academic children's hospitals. Data collected included demographics, BMI, severity of the pectus defect, postoperative pain management, and the incidence of urinary retention and urinary tract infection (UTI). RESULTS: Of 360 total patients who underwent MIRPE, 218 had an intraoperative Foley catheter. Patients with epidural pain control were more likely to receive a Foley catheter. The urinary retention rate was 34% for patients without an intraoperative Foley, and 1% in patients after removal of an intraoperatively placed Foley. Urinary retention was greater with an epidural compared with patient-controlled anesthesia (55% vs 26%, P = .002) in the no intraoperative Foley group. No urinary tract infections were identified. Epidural pain control was the only risk factor on multivariate analysis for retention in patients without an intraoperatively Foley catheter. CONCLUSION: Intraoperative Foley catheters obviate urinary retention without increasing the risk of urinary tract infection after MIRPE. These results will allow surgeons to better counsel patients regarding Foley placement.
Keywords: Humans; Adolescent; Female; Male; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Orthopedic Procedures; Postoperative Complications; Incidence; Risk Factors; Intraoperative Care; Urinary Catheterization; Urinary Retention; Urinary Tract Infections

Paravertebral regional blocks decrease length of stay following surgery for pectus excavatum in children - Loftus, Patrick D.; Elder, Craig T.; Russell, Katie W.; Spanos, Stephen P.; Barnhart, Douglas C.; Scaife, Eric R.; Skarda, David E.; Rollins, Michael D.; Meyers, Rebecka L. (Journal of Pediatric Surgery, 2016)
PURPOSE: Management of postoperative pain following repair of pectus excavatum has traditionally included thoracic epidural analgesia, narcotics, and benzodiazepines. We hypothesized that the use of intercostal or paravertebral regional blocks could result in decreased inpatient length of stay (LOS). METHODS: We conducted a retrospective cohort study of 137 patients (118 Nuss and 19 Ravitch - Nuss and Ravitch patients were analyzed separately) who underwent surgical repair of pectus excavatum with pain management via epidural, intercostal, or paravertebral analgesia from January 2009-December 2012. Measured outcomes included LOS, pain scores, benzodiazepine/narcotic requirements, emesis, professional fees, hospital cost, and total cost. RESULTS: In the Nuss patients, LOS was significantly reduced in the paravertebral group (p<0.005) and the intercostal group (p<0.005) compared to the epidural group, but was paradoxically countered by a nonsignificant increase in total cost (p=0.09). While benzodiazepine doses/day was not increased in the paravertebral group (p=0.08), an increase was seen in narcotic use (p<0.005). Despite increased narcotic use, no differences were seen in emesis between epidural and paravertebral use. Compared to epidural, pain scores were higher for both intercostal and paravertebral on day one (p<0.005), but equivalent for paravertebral on day three (p=0.62). The Ravitch group was too small for detailed independent statistical analysis but followed the same overall trend seen in the Nuss patients. CONCLUSION: Our use of paravertebral continuous infusion pain catheters for pectus excavatum repair was an effective alternative to epidural analgesia resulting in shorter LOS but not a decrease in overall cost.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Pectus excavatum; Analgesics, Opioid; Length of Stay; Pain management; Analgesia, Epidural; Length of stay; Nerve Block; Epidural; Catheters; Benzodiazepines; Infusions, Intravenous; Intercostal; Paravertebral

Freeze the pain away: The role of cryoanalgesia during a Nuss procedure - Sancheti, Manu (The Journal of Thoracic and Cardiovascular Surgery, 2016)
Keywords: Humans; Male; Analgesia; Funnel Chest; Pain, Postoperative; Intercostal Nerves; Orthopedic Procedures; Thoracoscopy; Cryotherapy

Cryoablation is associated with shorter length-of-stay and reduced opioid use after the Ravitch procedure - Rettig, R. Luke; Yang, Claire J.; Ashfaq, Adeel; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: The use of intercostal nerve cryoablation (INC) is becoming increasingly common in patients undergoing pectus repair. This study sought to evaluate the use of INC compared to traditional use of thoracic epidural (TE) in patients undergoing the modified Ravitch procedure. METHODS: A retrospective review of 37 patients undergoing the modified Ravitch repair with either INC or TE from March 2009 to July 2021 was conducted. The operations were performed by four surgeons who worked together at four different hospitals and have the same standardized practice. The primary outcome measure was hospital length of stay (LOS). Secondary variables included surgical time, total operating room time, operating room time cost, total hospital cost, inpatient opioid use, long term opioid use after discharge, and post-operative complications. RESULTS: LOS decreased to 2.8 days in the INC group compared to 6 days in the TE group (p<0.0001). Surgical time and total OR time was increased in the INC group. The INC group experienced significantly lower hospital costs (p<0.01). Total hospital opioid administration was significantly lower in INC group, and there was a significant decrease in long term opioid use in the INC group (p<0.0001). CONCLUSIONS: INC is a newer modality that decreases LOS, controls pain, and results in overall cost savings for patients undergoing the modified Ravitch procedure. We recommend that INC be included in the current practice for postoperative pain control in pectus disorder patients undergoing the modified Ravitch procedure.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Thoracic epidural; Modified Ravitch procedure

Implementation Science Fundamentals: Pediatric Surgery Enhanced Recovery After Surgery Protocol for Pectus Repair - Thompson, Allison R.; Glick, Hannah; Rubalcava, Nathan S.; Vernamonti, Jack P.; Speck, K. Elizabeth (The Journal of Surgical Research, 2023)
INTRODUCTION: Surgical repair of pectus excavatum and carinatum in children has historically been associated with severe postoperative pain and prolonged hospitalization. Enhanced Recovery After Surgery (ERAS) is a multidisciplinary, multimodal approach designed to fast-track surgical care. However, obstacles to implementation have led to very few within pediatric surgery. The aim of this study is to outline the process of development and implementation of an ERAS protocol for pectus surgical repair using fundamental principles of implementation science. METHODS: A multidisciplinary team of providers worked collaboratively to develop an ERAS protocol for surgical repair of pectus excavatum and carinatum and methods for identifying eligible patients. The surgical champion collaborated with all end users to review and revise the ERAS protocol, assessing all foreseeable barriers and facilitators prior to implementation. RESULTS: Our entire pediatric surgery team, nurses at every stage (clinic/preoperative/recovery/floor), physical therapy, and information technology contributed to the creation and implementation of an ERAS protocol with seven phases of care. The finalized version was implemented by end users focusing on four main areas: pain control, ambulation, diet, and education. Barriers and facilitators were continually addressed with an iterative process to improve the success of implementation. CONCLUSIONS: This is one of the first studies in children which details the step-by-step process of developing and implementing an ERAS protocol for pectus excavatum and carinatum. The process of development and implementation of an ERAS protocol as outlined in this manuscript can serve as a model for future ERAS protocols in pediatric surgery.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Length of Stay; Pectus; Pediatric surgery; Children; Enhanced recovery after surgery; Enhanced Recovery After Surgery; Implementation science; Implementation Science; Practice-Based Learning and Improvement; Specialties, Surgical

Extended pain relief achieved by analgesic-eluting biodegradable nanofibers in the Nuss procedure: in vitro and in vivo studies - Liu, Kuo-Sheng; Chen, Wei-Hsun; Lee, Cheng-Hung; Su, Yong-Fong; Liu, Shih-Jung (International Journal of Nanomedicine, 2018)
BACKGROUND: The most common complaint after the Nuss procedure is severe postoperative chest pain. The aim of this study was to evaluate the effectiveness of analgesic-eluting biodegradable nanofibers in pain relief after the Nuss procedure. MATERIALS AND METHODS: Poly(d,l)-lactide-co-glycolide, lidocaine, and ketorolac were dissolved in 1,1,1,3,3,3-hexafluoro-2-propanol. This solution was electrospun into a nanofibrous membrane. The elution method and high-performance chromatography were used to characterize the in vitro drug release. Stainless steel bars with and without coating of the analgesic-eluting nanofibrous membrane were implanted underneath the sternums of New Zealand white rabbits. The in vivo characteristics were further investigated. RESULTS: The in vitro study showed that the biodegradable nanofibers released high doses of lidocaine and ketorolac within 10 days. The in vivo study demonstrated high local and systemic concentrations of lidocaine and ketorolac. The serum creatinine level was unaffected. Animals that received implants of the analgesic-eluting nanofiber-coated stainless steel bar exhibited significantly greater food and water ingestion and physical activity than the control group did, indicating effective pain relief. CONCLUSION: The proposed analgesic-eluting biodegradable nanofibers contribute to the achievement of extended pain relief after the Nuss procedure, without obvious adverse effects, in an animal model.
Keywords: Animals; Humans; Thoracic Surgical Procedures; Pain, Postoperative; Analgesics; Nuss procedure; pectus excavatum; analgesic-eluting; Behavior, Animal; Biocompatible Materials; biodegradable; Drug Liberation; Ketorolac; Lidocaine; Membranes, Artificial; nanofibers; Nanofibers; Polylactic Acid-Polyglycolic Acid Copolymer; Rabbits; Spectroscopy, Fourier Transform Infrared; Stainless Steel

Paravertebral block for analgesia after pediatric thoracic surgery - Berde, Charles B.; Boretsky, Karen R.; Cravero, Joseph P. (Regional Anesthesia and Pain Medicine, 2014)
Keywords: Humans; Female; Male; Funnel Chest; Pain, Postoperative; Nerve Block; Ultrasonography, Interventional

Modified bar bending method of thoracoscopic nuss procedure on pectus excavatum: a retrospective single-center study - Han, Jichang; Mou, Yaru; Wang, Dongming; Xu, Qiongqian; Wang, Jian (BMC pediatrics, 2023)
BACKGROUND: Pectus excavatum (PE) is the most common disease of chest wall deformity, with an incidence of 1 in 300-400 births. Nuss procedure has proved to be the best surgical treatment method and has been widely used after clinical use for 30 years. We aimed to review the clinical data of pectus excavatum (PE) of thoracoscopic Nuss procedure adopted the Modified bar bending method of the six-point seven-section type, and compare it with the traditional curved bar bending method to explore the clinical application effect. METHODS: Forty-six cases of clinical data were summarized of children with PE who adopted the treatment of the Modified bar bending method of the six-point seven-section type from January 2019 to December 2021, and 51 cases were compared of PE children who adopted the treatment of traditional curved bar bending method from January 2016 to December 2018, including the data of age, gender, preoperative symptoms, symmetry, Haller index, operation time, bar bending time, intraoperative bleeding, postoperative complications, bar migration, postoperative effect evaluation, etc. RESULTS: The Procedure duration (P = 0.008), bar bending time (P < 0.001), and duration of postoperative pain (P < 0.001) were reduced significantly, and the incidence of bar migration after surgery was reduced as well by the modified bar bending method. There was no difference compared with traditional Nuss produce, like the incidence of evaluation of postoperative effects (Excellent, P = 0.93; Good, P = 0.80; Medium, P = 1.00; Poor, P = 1.00), bar migration (P = 1.00), postoperative complications (P = 1.00), Clavien- Dindo classification of surgical complications (I = 0.165; II = 1.00; IIIa = 1.00; IIIb = 1.00; VI = 1.00; V = 1.00), operative safety, and operative validity. CONCLUSION: Modified bar bending method of the six-point seven-section type, which is a kind of surgical method worth applying and popularizing, and the advantages of minimally procedure duration, bar bending time, and duration of postoperative pain, compared with the traditional bar bending method.
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Postoperative Complications; Thoracic Wall; Funnel chest; Pectus Excavatum

Standardization of clinical care pathway leads to sustained decreased length of stay following Nuss pectus repair: A multidisciplinary quality improvement initiative - Gurria, Juan P.; Simpson, Blair; Tuncel-Kara, Setenay; Bates, Christina; McKenna, Emily; Rogers, Tracy; Kraemer, Aimee; Platt, Michael; Mecoli, Marc; Garcia, Victor F.; Brown, Rebeccah L. (Journal of Pediatric Surgery, 2020)
BACKGROUND AND PURPOSE: Postoperatively, standardized clinical care pathways (SCCPs) help patients reach necessary milestones for discharge. The objective of this study was to achieve 90% compliance with a pectus specific SCCP within 9 months of implementation. We hypothesized that adherence to a pectus SCCP following the Nuss procedure would decrease postsurgical length of stay (LOS). METHODS: A multidisciplinary team implemented the pectus SCCP, including goals for mobility, lung recruitment, pain control, intake, and output. The full protocol included 42 components, tracked using chart reviews and a patient-directed checklist. The primary process measure was compliance with the pectus SCCP. The primary outcome measure was LOS; secondary outcomes were patient charges, patient satisfaction, and hospital readmission. RESULTS: Total study patients were n = 509: 159 patients pre-intervention, 350 patients post-intervention (80 implementation group; 270 sustain group). SCCP compliance data were collected on 164 patients post-intervention - 80 implementation, 84 sustain. LOS, ED visits, and hospital readmissions were recorded for all 509 patients. Mean LOS decreased from 4.5 days to 3.4 days, with >90% adherence to the pectus SCCP postintervention. There were no readmissions owing to pain despite earlier termination of epidural analgesia. Total patient charges decreased by 30% and patient satisfaction was high. CONCLUSION: Using quality improvement methodology with strict adherence to a pectus SCCP, we had significant reduction in LOS and patient charge without compromising effective postoperative pain management or patient satisfaction. TYPE OF STUDY: Clinical research; quality improvement. LEVEL OF EVIDENCE: V.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Length of Stay; Quality improvement; Length of stay; Clinical Protocols; Patient charge; Postoperative care; Quality Improvement; Standardized clinical care pathway

[Psychological prophylaxis training for coping with postoperative pain. Long-term effects] - Scheel, J.; Parthum, A.; Dimova, V.; Horn-Hofmann, C.; Meinfelder, F.; Carbon, R.; Grießinger, N.; Sittl, R.; Lautenbacher, S. (Schmerz (Berlin, Germany), 2014)
INTRODUCTION: The present study was performed to investigate the effect of multidimensional psychological prophylaxis training focusing on coping with cognitive-emotional pain on recovery within the first 12 months after surgery. The training included the following three components: (1) education about pain, analgesia and psychological aspects of coping with pain, (2) training for coping with pain and (3) body-centered relaxation. MATERIAL AND METHODS: In the study 48 young male patients (surgical correction of a chest malformation) were assessed 1 day before surgery, at discharge and 3, 6 and 12 months postoperatively concerning postoperative pain intensity and pain disability as well as pain anxiety, pain catastrophizing and pain hypervigilance. Additionally, 24 of these patients received training on cognitive-emotional coping with pain 1 day before surgery and 1-3 days after surgery (each session 1 h). RESULTS: The proportion of patients with clinically relevant improvement was significantly higher in the training group compared to the control group. This was the case for acute pain intensity (approximately 1 week after surgery), pain disability 3 months later and pain anxiety 12 months after surgery. CONCLUSION: The resurgence of pain anxiety after 12 months could only be found in the control group and could be due to the upcoming surgical removal of the transsternal metal implant. The prophylaxis training can therefore be seen as a protective factor for long-term management of surgery-related consequences and future pain experiences.
Keywords: Humans; Adolescent; Adult; Male; Young Adult; Funnel Chest; Pain, Postoperative; Pain Management; Pain Measurement; Patient Education as Topic; Follow-Up Studies; Anxiety; Catastrophization; Combined Modality Therapy; Adaptation, Psychological; Arousal; Cognitive Behavioral Therapy; Relaxation Therapy

A Novel Perioperative Multidose Methadone-Based Multimodal Analgesic Strategy in Children Achieved Safe and Low Analgesic Blood Methadone Levels Enabling Opioid-Sparing Sustained Analgesia With Minimal Adverse Effects - Sadhasivam, Senthilkumar; Aruldhas, Blessed W.; Packiasabapathy, Senthil; Overholser, Brian R.; Zhang, Pengyue; Zang, Yong; Renschler, Janelle S.; Fitzgerald, Ryan E.; Quinney, Sara K. (Anesthesia and Analgesia, 2021)
BACKGROUND: Intraoperative methadone, a long-acting opioid, is increasingly used for postoperative analgesia, although the optimal methadone dosing strategy in children is still unknown. The use of a single large dose of intraoperative methadone is controversial due to inconsistent reductions in total opioid use in children and adverse effects. We recently demonstrated that small, repeated doses of methadone intraoperatively and postoperatively provided sustained analgesia and reduced opioid use without respiratory depression. The aim of this study was to characterize pharmacokinetics, efficacy, and safety of a multiple small-dose methadone strategy. METHODS: Adolescents undergoing posterior spinal fusion (PSF) for idiopathic scoliosis or pectus excavatum (PE) repair received methadone intraoperatively (0.1 mg/kg, maximum 5 mg) and postoperatively every 12 hours for 3-5 doses in a multimodal analgesic protocol. Blood samples were collected up to 72 hours postoperatively and analyzed for R-methadone and S-methadone, 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidene (EDDP) metabolites, and alpha-1 acid glycoprotein (AAG), the primary methadone-binding protein. Peak and trough concentrations of enantiomers, total methadone, and AAG levels were correlated with clinical outcomes including pain scores, postoperative nausea and vomiting (PONV), respiratory depression, and QT interval prolongation. RESULTS: The study population included 38 children (10.8-17.9 years): 25 PSF and 13 PE patients. Median total methadone peak plasma concentration was 24.7 (interquartile range [IQR], 19.2-40.8) ng/mL and the median trough was 4.09 (IQR, 2.74-6.4) ng/mL. AAG concentration almost doubled at 48 hours after surgery (median = 193.9, IQR = 86.3-279.5 µg/mL) from intraoperative levels (median = 87.4, IQR = 70.6-115.8 µg/mL; P < .001), and change of AAG from intraoperative period to 48 hours postoperatively correlated with R-EDDP (P < .001) levels, S-EDDP (P < .001) levels, and pain scores (P = .008). Median opioid usage was minimal, 0.66 (IQR, 0.59-0.75) mg/kg morphine equivalents/d. No respiratory depression (95% Wilson binomial confidence, 0-0.09) or clinically significant QT prolongation (median = 9, IQR = -10 to 28 milliseconds) occurred. PONV occurred in 12 patients and was correlated with morphine equivalent dose (P = .005). CONCLUSIONS: Novel multiple small perioperative methadone doses resulted in safe and lower blood methadone levels, <100 ng/mL, a threshold previously associated with respiratory depression. This methadone dosing in a multimodal regimen resulted in lower blood methadone analgesia concentrations than the historically described minimum analgesic concentrations of methadone from an era before multimodal postoperative analgesia without postoperative respiratory depression and prolonged corrected QT (QTc). Larger studies are needed to further study the safety and efficacy of this methadone dosing strategy.
Keywords: Humans; Adolescent; Female; Male; Indiana; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Analgesics, Opioid; Prospective Studies; Pain Measurement; Postoperative Nausea and Vomiting; Risk Factors; Drug Administration Schedule; Perioperative Care; Age Factors; Drug Monitoring; Methadone; Predictive Value of Tests; Risk Assessment; Scoliosis; Spinal Fusion

Multimodal anesthesia with the addition of methadone is superior to epidural analgesia: A retrospective comparison of intraoperative anesthetic techniques and pain management for 124 pediatric patients undergoing the Nuss procedure - Singhal, Neil R.; Jones, John; Semenova, Janet; Williamson, Amber; McCollum, Katelyn; Tong, Dennis; Jerman, Jonathan; Notrica, David M.; Nguyen, Hayden (Journal of Pediatric Surgery, 2016)
BACKGROUND: The Nuss procedure corrects pectus excavatum by forceful displacement of the sternum with metal bars. Optimal pain management remains a challenge. Mutimodal anesthesia alleviates pain through blockade of multiple nociceptive and inflammatory pain receptors. METHODS: A retrospective chart review of anesthetic and postoperative mangement of 125 children undergoing the Nuss procedure was conducted. Anesthetic mangement strategies were analyzed in four groups: opioid during general anesthesia (GA), epidural with general anesthesia (Epidural), multimodal anesthesia (MM), and multimodal anesthesia with methadone (MM+M). Data collection included total opioid use (as equivalent milligrams of morphine (Mmg)), pain scores, length of stay (LOS), and adverse effects. RESULTS: Total opioid use varied by group (median, IQR (in Mg)): Epidural 213 [149, 293], GA 179 [134, 298], MM (150 [123, 281]), and MM+M (106 [87, 149]), as did severe pain (in minutes): Epidural (208 [73, 323]), GA (115 [7, 255]), MM (54 [0, 210]), and MM+M (49 [0, 151]). LOS was shortest for the MM+M group (MM+M=3.8+1.0days; MM=4.5+1.3days; GA=4.9+1.4days, Epidural=5.5+2.3days). CONCLUSION: Multimodal anesthesia is associated with less postoperative pain and shorter LOS compared to epidural or traditional anesthetic techniques for the Nuss procedure. Multimodal anesthesia with a single intraoperative dose of methadone was associated with lowest total opioid use, time with uncontrolled pain, and shortest LOS.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Length of Stay; Pain Management; Pain Measurement; Pain management; Anesthesia, Epidural; Anesthetics; Anesthesia, General; Methadone; Multimodal anesthesia

Introduction of a novel ultrasound-guided extrathoracic sub-paraspinal block for control of perioperative pain in Nuss procedure patients - Bryskin, Robert B.; Robie, Daniel K.; Mansfield, Frederick M.; Freid, Eugene B.; Sukumvanich, Siam (Journal of Pediatric Surgery, 2017)
BACKGROUND: A safe and effective method of multilevel thoracic pain control remains an elusive goal in patients undergoing the Nuss procedure. The aim of our study was to develop a nonopioid centered approach using a novel regional technique as part of a quality improvement initiative. METHODS: The proposed ultrasound-guided technique positions multi-perforated soaker catheter deep to the paraspinal muscles from T2 to T11. The project was conducted in two phases. First, a cadaveric dissection was performed to establish the pathway of spread of local anesthetic in vivo. Second, a pilot double blind randomized control project was conducted to evaluate effectiveness of the technique in ten patients and to derive parameters necessary for the definitive future study. Outcomes were evaluated based on the narcotic requirement, pain scores and functional measures. RESULTS: Placement of the catheters in two cadavers demonstrated reliable positioning in the subparaspinal tissue plane, and multilevel dye spread along the intercostal nerve path. In addition, a potential route of spread toward the paravertebral space along the canal accommodating dorsal ramus of the thoracic nerve was demonstrated. The pilot trial demonstrated a trend in decreased cumulative hydromorphone requirement in comparison to the control group at both 24h (0.19±0.09mg/kg vs. 0.13±0.08mg/kg p=0.72) and 48h (0.37±0.2mg/kg vs. 0.3±0.12mg/kg p=0.37). Functional performance ability was higher in the treatment group on both POD#1 (6.7±1.8 vs. 4.8±1 p=0.0495) and POD#2 (8.9±0.8 vs. 6.5±1.2 p=0.04). Pain scores were similar among the two groups (p=0.96). CONCLUSIONS: We describe a new technique to treat multilevel thoracic pain following the Nuss procedure that is reproducible, safe, allows diminished opioid use and enhances functional recovery.
Keywords: Humans; Adolescent; Female; Male; Thorax; Funnel Chest; Pain, Postoperative; Pectus excavatum; Analgesics, Opioid; Intercostal Nerves; Pain Management; Pain Measurement; Nerve Block; Ultrasonography, Interventional; Pain; Anesthesia; Postoperative pain; Catheters; Hydromorphone; Pilot Projects; Double-Blind Method; Cadaver; Chest pain; Intercostal Muscles; Nerve block; Recovery period

Subcutaneous local anesthetic infusion could eliminate use of epidural analgesia after the Nuss procedure - Kabagambe, Sandra K.; Goodman, Laura F.; Chen, Y. Julia; Keller, Benjamin A.; Becker, James C.; Raff, Gary W.; Stark, Rebecca A.; Stephenson, Jacob T.; Rahm, Amy; Farmer, Diana L.; Hirose, Shinjiro (Pain Management, 2018)
AIM: To compare outcomes of continuous subcutaneous infusion of local anesthetic and epidural analgesia following the Nuss procedure. PATIENTS & METHODS: A retrospective chart review compared patients managed with subcutaneous local anesthetic infusion (n = 12) versus thoracic epidural (n = 19) following the Nuss procedure from March 2013 to June 2015. RESULTS: There was no difference in hospital length of stay or days on intravenous narcotics. Epidural catheter placement prolonged operating room time (146.58 ± 28.30 vs 121.42 ± 21.98 min, p = 0.01). Average pain scores were slightly higher in the subcutaneous infusion group (3.72 ± 1.62 vs 2.35 ± 0.95, p = 0.02), but of negligible clinical significance. CONCLUSION: Continuous subcutaneous infusion of local anesthetic could eliminate the need for thoracic epidural for pain management after the Nuss procedure.
Keywords: Humans; Adolescent; Female; Male; Child; Funnel Chest; Pain, Postoperative; Treatment Outcome; Nuss procedure; Pain Management; Analgesia, Epidural; epidural; pectus excavatum; Anesthesia, Local; Anesthetics, Local; regional anesthesia; Infusions, Subcutaneous; pain management; Postoperative Care; Outcome Assessment, Health Care; subcutaneous infusion

Single shot intercostal block for pain management in pediatric patients undergoing the Nuss procedure: a double-blind, randomized, controlled study - Lukosiene, Laura; Macas, Andrius; Trepenaitis, Darius; Kalibatiene, Lina; Malcius, Dalius; Barauskas, Vidmantas (Journal of Pediatric Surgery, 2014)
PURPOSE: The aim of this study was to investigate the efficacy of a single shot intercostal block for pain control in pediatric patients undergoing the Nuss procedure. METHODS: A double-blind, randomized, controlled study was performed. Thirty patients received a single shot bilateral intercostal block with levobupivacaine (L group) and 30 patients with 0.9 % saline (S group). Standardized baseline analgesia was applied for all patients. Morphine consumption, pain scores, respiratory depression, nausea and vomiting, and urinary retention were recorded every 3h for 48h after surgery. RESULTS: The loading dose of morphine was lower (p<0.00001) in the L group. There were significantly lower morphine doses up to 6h after surgery and VAS scores up to 3h after surgery in the L group (p<0.001 and p=0.0003, respectively). The incidence of nausea and vomiting was lower in the L group (<0.00001). The incidence of urinary retention was lower in the L group (p=0.019). CONCLUSIONS: A single shot IB is an effective additional treatment for pediatric patients undergoing the Nuss procedure and results in the reduced consumption of morphine, less postoperative pain, and fewer opioid-related adverse effects.
Keywords: Humans; Adolescent; Female; Male; Funnel Chest; Pain, Postoperative; Treatment Outcome; Nuss procedure; Intercostal Nerves; Orthopedic Procedures; Pain Management; Pain Measurement; Nerve Block; Bupivacaine; Pediatric; Morphine; Anesthetics, Local; Preoperative Care; Postoperative pain; Intercostal block; Double-Blind Method; Injections; Levobupivacaine

A prospective randomized observer-blinded study to assess postoperative analgesia provided by an ultrasound-guided bilateral thoracic paravertebral block for children undergoing the Nuss procedure - Qi, Jiashan; Du, Bin; Gurnaney, Harshad; Lu, Peilin; Zuo, Yunxia (Regional Anesthesia and Pain Medicine, 2014)
BACKGROUND AND OBJECTIVES: This prospective, randomized, single-blinded study evaluates the effectiveness of the ultrasound-guided bilateral thoracic paravertebral (BTPV) block for providing postoperative pain control in children undergoing the Nuss procedure. METHODS: Thirty American Society of Anesthesiologists I-II children with pectus excavatum, scheduled for the Nuss procedure, were enrolled at West China Hospital of Sichuan University. The patients were randomly allocated into the BTPV block group or the control group. In the BTPV group, 0.25% ropivacaine 0.5 mL/kg with 1:200,000 epinephrine was injected under ultrasound guidance on each side at the level of the fifth thoracic vertebra. Postoperative pain was evaluated in both groups for the first 48 hours. Total opioid administered and cumulative attempts on the patient/parent-controlled intravenous analgesia (PCA) pump were recorded. Postoperative negative behavioral changes in the children were evaluated on postoperative days 1, 7, and 30, respectively, using the posthospital behavior questionnaire. RESULTS: The pain scores were significantly reduced in the postanesthesia care unit and for the first 48 hours postoperatively in the BTPV group compared to the control group (P < 0.01). The sufentanil use in the postanesthesia care unit was significantly greater in the control group [mean (SD), 0.2 (0) mcg/kg] compared to the BTPV group [mean (SD), 0.05 (0.06) mcg/kg] (P < 0.01). The postoperative sufentanil use was significantly higher in the control group during the first 24 hours (P < 0.01). Numbers of attempts on the PCA pump were significantly greater in the control group (P < 0.01). The posthospital behavior questionnaire score was lower in the BTPV group on day 1, day 7, and 1 month, respectively (P < 0.01). CONCLUSIONS: Ultrasound-guided BTPV block provides improved postoperative analgesia for children undergoing the Nuss procedure as compared with intravenous PCA and decreases the incidence of postoperative behavioral disturbance.
Keywords: Humans; Adolescent; Female; Male; Child; Funnel Chest; Pain, Postoperative; Prospective Studies; Nerve Block; Ultrasonography, Interventional; Child, Preschool; Blood Pressure; Heart Rate; Single-Blind Method

Bilateral ultrasound-guided erector spinae plane block for postoperative pain management in surgical repair of pectus excavatum via Ravitch technique - Fiorelli, Silvia; Leopizzi, Giulio; Saltelli, Giorgia; Andreetti, Claudio; Fiorelli, Alfonso; Peritore, Valentina; Rocco, Monica; Massullo, Domenico (Journal of Clinical Anesthesia, 2019)
Keywords: Humans; Adolescent; Adult; Male; Funnel Chest; Pain, Postoperative; Treatment Outcome; Orthopedic Procedures; Pain Measurement; Erector spinae plane block; Nerve Block; Ultrasonography, Interventional; Ravitch procedure; Anesthesia, Intravenous; Paraspinal Muscles; Pectus excavatum surgery; Regional anesthesia; Thoracic anesthesia

Use of transthoracic cryoanalgesia during the Nuss procedure - Kim, Sunghoon; Idowu, Olajire; Palmer, Barnard; Lee, Sang H. (The Journal of Thoracic and Cardiovascular Surgery, 2016)
Keywords: Humans; Adolescent; Male; Analgesia; Funnel Chest; Pain, Postoperative; Treatment Outcome; Intercostal Nerves; Orthopedic Procedures; Thoracoscopy; Cryotherapy; Cold Temperature; Equipment Design; Thoracoscopes

Bilateral Pecto-intercostal fascial plane nerve block with liposomal bupivacaine after modified Ravitch pectus excavatum repair: A case report - Migirov, Allan; Oweidat, Adeeb; Soliman, Loran Mounir; Ali Sakr Esa, Wael (Journal of Clinical Anesthesia, 2021)
Keywords: Humans; Funnel Chest; Pain, Postoperative; Anesthesia, Conduction; Nerve Block; Bupivacaine; Anterior intercostal nerve; Case report; Modified Ravich pectus excavatum repair; Open pectus excavatum repair; Pecto-intercostal plane nerve block

Case Report of Cryo Nerve Block in a Patient Undergoing Full Sternotomy: A Novel Approach to Pain Control in Cardiac Surgery - Caparrelli, David J. (A&A Practice, 2023)
We present the case of a 65-year-old man undergoing open-heart surgery through a full sternotomy with the use of bilateral intercostal cryo nerve block (cryoNB) as adjunctive therapy for postoperative analgesia. CryoNB has been previously demonstrated as safe and effective for pain control in thoracotomy procedures as well as bilaterally in adolescent patients with pectus excavatum undergoing Nuss procedure. Herein, we describe for the first time, the cryoNB procedure for postoperative pain management in a patient undergoing full sternotomy.
Keywords: Humans; Adolescent; Male; Pain, Postoperative; Pain Management; Nerve Block; Aged; Cardiac Surgical Procedures; Sternotomy

Bilateral erector spinae plane block using a programmed intermittent bolus technique for pain management after Nuss procedure - Yoshizaki, Mai; Murata, Hiroaki; Ogami-Takamura, Keiko; Hara, Tetsuya (Journal of Clinical Anesthesia, 2019)
Keywords: Humans; Male; Child; Funnel Chest; Pain, Postoperative; Nuss procedure; Pectus excavatum; Erector spinae plane block; Nerve Block; Anesthetics, Local; Programmed intermittent bolus

Pain Quality After Pediatric Pectus Excavatum Repair - Manworren, Renee C. B.; Di Franco, Maria Victoria; Mishra, Trishla; Kaduwela, Naomi (Pain Management Nursing: Official Journal of the American Society of Pain Management Nurses, 2022)
BACKGROUND: Neuropathic pain medications are included in multimodal postoperative analgesic strategies, but quality of perioperative pain is rarely assessed. AIMS: The purpose of this study was to describe adolescents' pain experiences after thoracoscopic pectus excavatum repair (Nuss procedure) using the Adolescent Pediatric Pain Tool. DESIGN: This prospective descriptive longitudinal study was designed to test the hypothesis that pain quality descriptors reported are consistent with neuropathic pain. METHODS: A convenience sample of 23 adolescents aged 12 to 17 years from a single urban, university affiliated, nonprofit children's hospital consented to self-report pain using the Adolescent Pediatric Pain Tool before and during hospitalization, and up to 14 months after Nuss procedure. Visual analytic techniques were used to analyze reported pain intensity, location, and affective, evaluative, sensory, and temporal qualities. RESULTS: Postoperative pain quality, intensity, number of sites, and surface area decreased over time. Word clouds illustrated that neuropathic sensory and temporal pain quality descriptors increased in frequency 2 to 6 weeks after surgery and were the predominant descriptors 2 to 4 months after surgery. Dot matrix charts illustrated an inconsistent relationship of pain quality and intensity with pain surface area. CONCLUSIONS: Pain quality should be assessed with valid, reliable, and developmentally appropriate tools. Visual analytics help illustrate pain quality at single points in time and longitudinally and may be helpful in guiding postoperative pain treatment.
Keywords: Humans; Adolescent; Child; Funnel Chest; Longitudinal Studies; Neuralgia; Pain, Postoperative; Retrospective Studies; Treatment Outcome

Postoperative pain following minimally invasive repair of pectus excavatum: A descriptive study - Ganescu, Olivia; Emil, Sherif; Saint-Martin, Christine; Guadagno, Elena; Laberge, Jean-Martin; LaRusso, Kathryn; Frigon, Chantal (Journal of Pediatric Surgery, 2022)
BACKGROUND: Minimally Invasive Repair of Pectus Excavatum (MIRPE) is associated with significant postoperative pain. The objective of our study was to characterize the severity and duration of this pain, and to investigate possible associations with pectus severity. METHODS: We conducted a retrospective cohort study of pediatric patients who underwent MIRPE from January 2014 to April 2018. Pectus excavatum (PE) severity was determined with 3 indices measured from computed tomography: Depression Index (DI), Correction Index (CI), and Haller index (HI). Mean pain scores for every 6-hour period and the presence of pain and intake of analgesics during follow-up were extracted from the medical record. RESULTS: The cohort included 57 patients with a mean age of 15.9 ± 1.3 years. All 3 severity indices were positively correlated, with a correlation coefficient of 0.8 between the DI and CI. The requirement for 2 bars was significantly associated with higher indices (95% CI:0.18-0.63, p = 0.01). Pain was managed with thoracic epidural analgesia for all but one patient. Growth linear modeling identified five different pain trajectory subgroups of patients up to post-operative day 5. None of the tested predictors (age, gender, body image, physical activity level, DI, CI, HI, difference deformity-epidural level) were significantly associated with class membership. Persistent pain at one-year follow-up was present in 18% of patients, all with severe deformity (DI≥0.8). CONCLUSION: Pain trajectory and intensity after MIRPE can be classified into discrete patterns but are not influenced by PE severity. Severe deformity seems to predict persistent pain at one year.
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Depression index; Level III; Minimally invasive repair; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Persistent post surgical pain; Post-operative pain; Retrospective Study; Severity deformity

Impact of Cryoablation on Pectus Excavatum Repair in Pediatric Patients - Clark, Rachael A.; Jacobson, Jillian C.; Singhal, Amogh; Alder, Adam C.; Chung, Dai H.; Pandya, Samir R. (Journal of the American College of Surgeons, 2022)
BACKGROUND: Minimally invasive repair of pectus excavatum (MIRPE) involves placement of a transthoracic, retrosternal support bar under thoracoscopic guidance. Despite its minimally invasive technical approach, postoperative pain is a significant morbidity that often results in increased length of stay. Multi-modal pain control strategies have been used in the past with limited success. Recently, the use of intraoperative intercostal nerve cryoablation (CA) has been added. In the present study, we aim to evaluate the effects of CA on postoperative pain control, opioid requirements, and perioperative outcomes. STUDY DESIGN: A single-center, retrospective chart review of all patients (less than 18 years old) who underwent MIRPE from 2009 to 2020 was performed. CA was started in June 2018. Data collection included demographics, preoperative characteristics, intraoperative findings, and postoperative outcomes. We hypothesized that CA would be associated with improved pain scores, lower doses of total inpatient opioid requirement, and shorter length of stay (LOS). RESULTS: One hundred sixty-one patients met inclusion criteria: 75 underwent intraoperative CA and 86 underwent MIRPE without CA (NCA group). CA significantly decreased median LOS from 4 days in NCA to 2 days; the use of CA was the only significant predictor of LOS on linear regression. CA was also associated with decreased total PCA, intravenous opioid, and oral opioid dosages. There was no difference in inpatient pain scores and a slight increase in mean procedure time. However, CA was associated with significantly decreased postoperative complications. CONCLUSIONS: The use of cryoablation during MIRPE significantly decreases LOS, perioperative opioid requirements, and postoperative complications, with a minimal increase in operative time. Cryoablation is an effective pain control modality in the surgical management of chest wall deformities in children.
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Postoperative Complications

Same day discharge for pectus excavatum-is it possible? - Rettig, R. Luke; Rudikoff, Andrew G.; Lo, Hoi Yee Annie; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: The use of intercostal nerve cryoablation (INC) has been an effective modality for treating pain in patients undergoing pectus excavatum (PE) repair. This study sought to evaluate if PE patients undergoing Nuss procedures with INC and intercostal nerve block (INB) could safely be discharged the same day of surgery. METHODS: A prospective study with IRB approval of 15 consecutive patients undergoing PE Nuss repair with INC, INB, and an enhanced recovery after surgery (ERAS) protocol was conducted. The primary outcome measure was hospital length of stay (LOS) in hours. Secondary variables included same day discharge, postoperative complications, emergency department (ED) visits, urgent care (UC) visits, opioid use, and return to the operating room (OR). RESULTS: LOS averaged 11.9 h amongst 15 patients. Ten patients (66.7%) went home on postoperative day (POD) 0, and the rest went home on POD 1. No patients stayed in the hospital due to pain. Reasons for failure to discharge included urinary retention, drowsiness, vomiting, and anxiety, but not pain. No patients were readmitted to the ED. One patient visited UC for constipation. One patient had bar migration requiring return to the OR for revision. Ten (66.7%) patients did not use opioids after discharge. CONCLUSIONS: Same day discharge is feasible and safe in PE patients undergoing Nuss procedure with INC and INB. INC with INB can adequately control pain without significant complications. Same day discharge can be safely considered for PE patients undergoing Nuss procedure with INC with INB. TYPE OF STUDY: Prognosis study LEVEL-OF-EVIDENCE RATING: Level II.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Intercostal nerve cryoablation; Enhanced recovery after surgery (ERAS); Patient Discharge; Pectus excavatum repair; Prospective Studies; Same day discharge

Percutaneous Cryoanalgesia: A New Strategy for Pain Management in Pectus Excavatum Surgery - Velayos, María; Alonso, Mercedes; Delgado-Miguel, Carlos; Estefanía-Fernández, Karla; Muñoz-Serrano, Antonio J.; Santamaría, Manuel V. López; Reinoso-Barbero, Francisco; De La Torre, Carlos A. (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2022)
INTRODUCTION: In recent years, pain protocols for pectus excavatum (PE) have incorporated cryoanalgesia through thoracoscopic approach. Since 2019, ultrasound-guided percutaneous cryoanalgesia (PCr) has been applied at our institution, either on the same day as the Nuss procedure or 48 hours before surgery. We carried out a preliminary retrospective review of patients with PE in whom PCr prior to surgery was performed at our institution between 2019 and 2021. MATERIALS AND METHODS: Two groups were evaluated: PCr on the same day (PCrSD) and PCr 48 hours before surgery (PCr48). Despite PCr, patients were treated with "patient-controlled analgesia" (PCA) with opioids for at least 24 hours, switching to conventional intravenous analgesia and oral analgesia in the following days. Demographic, clinical-radiological variables, PCA opioid use, pain grade according to the visual analog scale (VAS), and length of stay (LOS) were compared between the groups. A total of 20 patients were included (12 with PCrSD and 8 with PCr48), without significant differences in demographics or clinical-radiological variables. The overall median time of PCr was 65 minutes (55-127), with no differences between the groups. RESULTS: PCr48 group presented with significantly lower median number of hours of continuous PCA (24 vs. 32 hours; p = 0.031), lower median number of rescue boluses (11 vs. 18; p = 0.042), lower median VAS in the early postoperative hours (2 vs. 5.5; p = 0.043), and lower median LOS (3.5 vs. 5 days). CONCLUSION: PCr performed 48 hours prior to surgery is more effective in terms of PCA requirements, VAS, and LOS when compared with cryoanalgesia on the same day.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Analgesia, Patient-Controlled; Pain Management

Postoperative pain control following minimally invasive correction of pectus excavatum in pediatric patients: A systematic review - Archer, Victoria; Robinson, Tessa; Kattail, Deepa; Fitzgerald, Peter; Walton, J. Mark (Journal of Pediatric Surgery, 2020)
PURPOSE: Surgery for pectus excavatum is associated with significant postoperative pain. The aim of this study was to summarize the current literature regarding postoperative pain control for pediatric patients undergoing minimally invasive repair of pectus excavatum (MIRPE). METHODS: A systematic search of Medline, Embase, PubMed, CINAHL, Web of Science, and the Cochrane Library for randomized controlled trials (RCT) comparing methods of pain control in pediatric patients undergoing MIRPE was conducted. Studies were restricted to the English language. RESULTS: After screening 1304 references, 9 randomized control trials (RCTs) enrolling 485 patients were included. The average age was 11.9 years (±3.1). Pain scores were decreased with ropivacaine compared to bupivacaine-based epidurals. In studies comparing ketamine to opioid based patient-controlled anesthesia (PCA) pumps, the results were variable. Intercostal and paravertebral nerve blocks had decreased pain scores in 75% of the studies compared to opioid-based PCA. Opioid consumption was decreased in 50% of the trials assessing ketamine-based infusions and 75% of the studies comparing intercostal and paravertebral nerve blocks. Nausea was decreased in several of the ketamine-based infusion and intercostal and paravertebral nerve block studies. CONCLUSION: Ketamine-including infusions or paravertebral and intercostal nerve blocks may represent superior methods of postoperative pain control for MIRPE. Further work is needed to confirm results. LEVEL OF EVIDENCE: 2A [1].
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Analgesics; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesics, Opioid; Bupivacaine; Ketamine; MIRPE: minimally invasive repair of pectus excavatum; Pain; Pediatric; Postoperative

Intercostal Nerve Cryoablation in Minimally Invasive Repair of Pectus Excavatum: Effect on Pulmonary Function - Lai, Krista; Lee, Justin; Notrica, David M.; Egan, J. Craig; McMahon, Lisa E.; Molitor, Mark S.; Bae, Jae-O.; Ostlie, Daniel J.; Padilla, Benjamin E. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2022)
Introduction: Cryoablation of intercostal nerves is performed for pain control after minimally invasive repair of pectus excavatum (MIRPE). Cryoablation affects both sensory and motor neurons, resulting in temporary anesthesia to the chest wall and loss of intercostal motor function. The study objective is to determine the effect of cryoablation on incentive spirometry (IS) volumes, as a measure of pulmonary function, after MIRPE. Materials and Methods: A single-institution retrospective review of pediatric patients undergoing MIRPE was performed. All patients received a multimodal regimen (MMR) of analgesics postoperatively. Three groups were compared-cryoablation (CRYO), elastomeric pain pump (EPP), and MMR alone. The primary outcomes were postoperative IS volumes and IS volumes as a ratio of preoperative forced vital capacity (FVC). Secondary outcomes included pain scores, opioid use, length of stay (LOS), and infectious complications. Results: MIRPE was performed in 115 patients: 50 CRYO, 50 EPP, and 15 MMR alone. Groups were similar for demographics and pectus excavatum severity. Postoperative spirometry measurements were similar across groups: IS (CRYO 750 mL [500,961] versus EPP 750 mL [590,1019] versus MMR 696 mL [500,1037], P = .77); IS/FVC (CRYO 0.19 [0.14,0.26] versus EPP 0.20 [0.16,0.26] versus MMR 0.16 [0.15,0.24], P = .69). Although pain scores were also similar across groups, CRYO patients used less opioid (P < .05) and had shorter LOS (P < .05). Postoperative pneumonia was rare and similar across groups (P = 1.00). Conclusion: Intercostal nerve cryoablation during MIRPE does not adversely affect postoperative IS volumes or increase pneumonia rate, despite the temporary loss of motor innervation to intercostal muscles. Cryoablation provides effective pain control with less opioid use.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; MIRPE; Nuss; cryoablation; incentive spirometry; pectus; pulmonary function

Postoperative management of pediatric patients undergoing minimally invasive repair of pectus excavatum: Where are we now? - Kirupaharan, Sawmmiya; Briatico, Daniel; Robinson, Tessa; Fitzgerald, Peter; Walton, J. Mark (Journal of Pediatric Surgery, 2022)
PURPOSE: Minimally invasive repair of pectus excavatum (MIRPE) often leads to a painful and challenging recovery period. This study aims to describe the postoperative management of pediatric patients undergoing MIRPE and compare postoperative outcomes between patients using different routes of postoperative analgesia. METHODS: Retrospective chart review of pediatric patients who underwent MIRPE from July 2003 to September 2019 at a single pediatric tertiary care center. Data on pain management and course of hospital stay were ascertained. Descriptive statistics, Mann-Whitney U and Pearson Chi-Square tests were used to analyze data. A p-value <0.05 was considered significant. RESULTS: Of the 115 patients identified, 58 (50.4%) managed pain postoperatively using thoracic epidural and 57 (49.6%) used intravenous patient-controlled analgesia (IVPCA). The transition from the predominant use of epidural to IVPCA for MIRPE occurred between 2012 and 2013. Higher pain scores were reported by the IVPCA group at 6 h (p<0.001) and 12 h (p<0.001) postoperative. Patients using IVPCA had lower postoperative opioid consumption (p<0.001) and switched to oral opioids sooner than the epidural group (p<0.001). Fewer patients in the IVPCA group required urinary catheterization (p<0.001). Patients using IVPCA had a shorter hospital stay (4 days [IQR 4-5]) compared to the epidural group (5.5 [IQR 5-6]; p<0.001). Readmission was comparable at 3.48% in the total sample. CONCLUSION: Patients using intravenous patient-controlled analgesia reported higher pain scores however, this route of analgesia was associated with shorter hospital stay. Prospective studies designed to address moderator variables are required to confirm findings and develop standardized recovery protocols.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Analgesia, Patient-Controlled; Prospective Studies; MIRPE; Pain management; Quality improvement

Same-day discharge following the Nuss repair: A comparison - Rettig, R. Luke; Rudikoff, Andrew G.; Annie Lo, Hoi Yee; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: Intercostal Nerve Cryoablation (INC) has significantly improved pain control following the Nuss repair of pectus excavatum (PE). This study sought to evaluate patients undergoing the Nuss repair with INC compared to the Nuss repair with an ERAS protocol, INC, and intercostal nerve blocks (INB). METHODS: In June 2020, a new protocol was implemented involving surgery, anesthesia, nursing, physical therapy, and child life with the goal of safe same day discharge for patients undergoing the Nuss repair. They were compared to a control group who underwent the Nuss repair with INC alone in 2017-2019. The primary outcome measure was hospital length of stay (LOS) in hours, secondary outcomes were number of patients discharged on postoperative day (POD) 0, and returns to the emergency department (ED), urgent care (UC), and operating room (OR). RESULTS: The characteristics between the groups were the same (Table 1). The mean LOS was 11.8 h in the INB group versus 58.2 h in the INC group, p < 0.01. 10 of 15 patients in the INB group went home on POD 0 (average of 5.5 h postop), versus 0 patients in the INC only group, p < 0.01. Five patients in the INB stayed overnight. Two patients stayed owing to anxiety, one owing to urinary retention, one owing to nausea, and one owing to drowsiness. None stayed for pain control. Four patients in the INC group returned to the ED for pain control, versus 0 in the INB group, and 1 patient in the INB returned to UC for constipation. CONCLUSIONS: The majority of patients undergoing the Nuss repair of PE with a multidisciplinary regimen of pre and postoperative nursing education, precise intraoperative anesthesia care, performance of direct vision INB and INC, as well as careful surgery can go home on the day of surgery without adverse outcomes or unanticipated returns to the hospital. LEVEL-OF-EVIDENCE: Level II.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Intercostal nerve cryoablation; Enhanced recovery after surgery (ERAS); Patient Discharge; Pectus excavatum repair; Same day discharge; Anesthesia, Conduction; Intercostal nerve block

Pain Quality After Pediatric Pectus Excavatum Repair - Manworren, Renee C. B.; Di Franco, Maria Victoria; Mishra, Trishla; Kaduwela, Naomi (Pain Management Nursing: Official Journal of the American Society of Pain Management Nurses, 2022)
BACKGROUND: Neuropathic pain medications are included in multimodal postoperative analgesic strategies, but quality of perioperative pain is rarely assessed. AIMS: The purpose of this study was to describe adolescents' pain experiences after thoracoscopic pectus excavatum repair (Nuss procedure) using the Adolescent Pediatric Pain Tool. DESIGN: This prospective descriptive longitudinal study was designed to test the hypothesis that pain quality descriptors reported are consistent with neuropathic pain. METHODS: A convenience sample of 23 adolescents aged 12 to 17 years from a single urban, university affiliated, nonprofit children's hospital consented to self-report pain using the Adolescent Pediatric Pain Tool before and during hospitalization, and up to 14 months after Nuss procedure. Visual analytic techniques were used to analyze reported pain intensity, location, and affective, evaluative, sensory, and temporal qualities. RESULTS: Postoperative pain quality, intensity, number of sites, and surface area decreased over time. Word clouds illustrated that neuropathic sensory and temporal pain quality descriptors increased in frequency 2 to 6 weeks after surgery and were the predominant descriptors 2 to 4 months after surgery. Dot matrix charts illustrated an inconsistent relationship of pain quality and intensity with pain surface area. CONCLUSIONS: Pain quality should be assessed with valid, reliable, and developmentally appropriate tools. Visual analytics help illustrate pain quality at single points in time and longitudinally and may be helpful in guiding postoperative pain treatment.
Keywords: Humans; Adolescent; Child; Funnel Chest; Longitudinal Studies; Neuralgia; Pain, Postoperative; Retrospective Studies; Treatment Outcome

Postoperative pain following minimally invasive repair of pectus excavatum: A descriptive study - Ganescu, Olivia; Emil, Sherif; Saint-Martin, Christine; Guadagno, Elena; Laberge, Jean-Martin; LaRusso, Kathryn; Frigon, Chantal (Journal of Pediatric Surgery, 2022)
BACKGROUND: Minimally Invasive Repair of Pectus Excavatum (MIRPE) is associated with significant postoperative pain. The objective of our study was to characterize the severity and duration of this pain, and to investigate possible associations with pectus severity. METHODS: We conducted a retrospective cohort study of pediatric patients who underwent MIRPE from January 2014 to April 2018. Pectus excavatum (PE) severity was determined with 3 indices measured from computed tomography: Depression Index (DI), Correction Index (CI), and Haller index (HI). Mean pain scores for every 6-hour period and the presence of pain and intake of analgesics during follow-up were extracted from the medical record. RESULTS: The cohort included 57 patients with a mean age of 15.9 ± 1.3 years. All 3 severity indices were positively correlated, with a correlation coefficient of 0.8 between the DI and CI. The requirement for 2 bars was significantly associated with higher indices (95% CI:0.18-0.63, p = 0.01). Pain was managed with thoracic epidural analgesia for all but one patient. Growth linear modeling identified five different pain trajectory subgroups of patients up to post-operative day 5. None of the tested predictors (age, gender, body image, physical activity level, DI, CI, HI, difference deformity-epidural level) were significantly associated with class membership. Persistent pain at one-year follow-up was present in 18% of patients, all with severe deformity (DI≥0.8). CONCLUSION: Pain trajectory and intensity after MIRPE can be classified into discrete patterns but are not influenced by PE severity. Severe deformity seems to predict persistent pain at one year.
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Depression index; Level III; Minimally invasive repair; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Persistent post surgical pain; Post-operative pain; Retrospective Study; Severity deformity

Impact of Cryoablation on Pectus Excavatum Repair in Pediatric Patients - Clark, Rachael A.; Jacobson, Jillian C.; Singhal, Amogh; Alder, Adam C.; Chung, Dai H.; Pandya, Samir R. (Journal of the American College of Surgeons, 2022)
BACKGROUND: Minimally invasive repair of pectus excavatum (MIRPE) involves placement of a transthoracic, retrosternal support bar under thoracoscopic guidance. Despite its minimally invasive technical approach, postoperative pain is a significant morbidity that often results in increased length of stay. Multi-modal pain control strategies have been used in the past with limited success. Recently, the use of intraoperative intercostal nerve cryoablation (CA) has been added. In the present study, we aim to evaluate the effects of CA on postoperative pain control, opioid requirements, and perioperative outcomes. STUDY DESIGN: A single-center, retrospective chart review of all patients (less than 18 years old) who underwent MIRPE from 2009 to 2020 was performed. CA was started in June 2018. Data collection included demographics, preoperative characteristics, intraoperative findings, and postoperative outcomes. We hypothesized that CA would be associated with improved pain scores, lower doses of total inpatient opioid requirement, and shorter length of stay (LOS). RESULTS: One hundred sixty-one patients met inclusion criteria: 75 underwent intraoperative CA and 86 underwent MIRPE without CA (NCA group). CA significantly decreased median LOS from 4 days in NCA to 2 days; the use of CA was the only significant predictor of LOS on linear regression. CA was also associated with decreased total PCA, intravenous opioid, and oral opioid dosages. There was no difference in inpatient pain scores and a slight increase in mean procedure time. However, CA was associated with significantly decreased postoperative complications. CONCLUSIONS: The use of cryoablation during MIRPE significantly decreases LOS, perioperative opioid requirements, and postoperative complications, with a minimal increase in operative time. Cryoablation is an effective pain control modality in the surgical management of chest wall deformities in children.
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Postoperative Complications

Same day discharge for pectus excavatum-is it possible? - Rettig, R. Luke; Rudikoff, Andrew G.; Lo, Hoi Yee Annie; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: The use of intercostal nerve cryoablation (INC) has been an effective modality for treating pain in patients undergoing pectus excavatum (PE) repair. This study sought to evaluate if PE patients undergoing Nuss procedures with INC and intercostal nerve block (INB) could safely be discharged the same day of surgery. METHODS: A prospective study with IRB approval of 15 consecutive patients undergoing PE Nuss repair with INC, INB, and an enhanced recovery after surgery (ERAS) protocol was conducted. The primary outcome measure was hospital length of stay (LOS) in hours. Secondary variables included same day discharge, postoperative complications, emergency department (ED) visits, urgent care (UC) visits, opioid use, and return to the operating room (OR). RESULTS: LOS averaged 11.9 h amongst 15 patients. Ten patients (66.7%) went home on postoperative day (POD) 0, and the rest went home on POD 1. No patients stayed in the hospital due to pain. Reasons for failure to discharge included urinary retention, drowsiness, vomiting, and anxiety, but not pain. No patients were readmitted to the ED. One patient visited UC for constipation. One patient had bar migration requiring return to the OR for revision. Ten (66.7%) patients did not use opioids after discharge. CONCLUSIONS: Same day discharge is feasible and safe in PE patients undergoing Nuss procedure with INC and INB. INC with INB can adequately control pain without significant complications. Same day discharge can be safely considered for PE patients undergoing Nuss procedure with INC with INB. TYPE OF STUDY: Prognosis study LEVEL-OF-EVIDENCE RATING: Level II.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Intercostal nerve cryoablation; Enhanced recovery after surgery (ERAS); Patient Discharge; Pectus excavatum repair; Prospective Studies; Same day discharge

Percutaneous Cryoanalgesia: A New Strategy for Pain Management in Pectus Excavatum Surgery - Velayos, María; Alonso, Mercedes; Delgado-Miguel, Carlos; Estefanía-Fernández, Karla; Muñoz-Serrano, Antonio J.; Santamaría, Manuel V. López; Reinoso-Barbero, Francisco; De La Torre, Carlos A. (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2022)
INTRODUCTION: In recent years, pain protocols for pectus excavatum (PE) have incorporated cryoanalgesia through thoracoscopic approach. Since 2019, ultrasound-guided percutaneous cryoanalgesia (PCr) has been applied at our institution, either on the same day as the Nuss procedure or 48 hours before surgery. We carried out a preliminary retrospective review of patients with PE in whom PCr prior to surgery was performed at our institution between 2019 and 2021. MATERIALS AND METHODS: Two groups were evaluated: PCr on the same day (PCrSD) and PCr 48 hours before surgery (PCr48). Despite PCr, patients were treated with "patient-controlled analgesia" (PCA) with opioids for at least 24 hours, switching to conventional intravenous analgesia and oral analgesia in the following days. Demographic, clinical-radiological variables, PCA opioid use, pain grade according to the visual analog scale (VAS), and length of stay (LOS) were compared between the groups. A total of 20 patients were included (12 with PCrSD and 8 with PCr48), without significant differences in demographics or clinical-radiological variables. The overall median time of PCr was 65 minutes (55-127), with no differences between the groups. RESULTS: PCr48 group presented with significantly lower median number of hours of continuous PCA (24 vs. 32 hours; p = 0.031), lower median number of rescue boluses (11 vs. 18; p = 0.042), lower median VAS in the early postoperative hours (2 vs. 5.5; p = 0.043), and lower median LOS (3.5 vs. 5 days). CONCLUSION: PCr performed 48 hours prior to surgery is more effective in terms of PCA requirements, VAS, and LOS when compared with cryoanalgesia on the same day.
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Analgesia, Patient-Controlled; Pain Management

Postoperative pain control following minimally invasive correction of pectus excavatum in pediatric patients: A systematic review - Archer, Victoria; Robinson, Tessa; Kattail, Deepa; Fitzgerald, Peter; Walton, J. Mark (Journal of Pediatric Surgery, 2020)
PURPOSE: Surgery for pectus excavatum is associated with significant postoperative pain. The aim of this study was to summarize the current literature regarding postoperative pain control for pediatric patients undergoing minimally invasive repair of pectus excavatum (MIRPE). METHODS: A systematic search of Medline, Embase, PubMed, CINAHL, Web of Science, and the Cochrane Library for randomized controlled trials (RCT) comparing methods of pain control in pediatric patients undergoing MIRPE was conducted. Studies were restricted to the English language. RESULTS: After screening 1304 references, 9 randomized control trials (RCTs) enrolling 485 patients were included. The average age was 11.9 years (±3.1). Pain scores were decreased with ropivacaine compared to bupivacaine-based epidurals. In studies comparing ketamine to opioid based patient-controlled anesthesia (PCA) pumps, the results were variable. Intercostal and paravertebral nerve blocks had decreased pain scores in 75% of the studies compared to opioid-based PCA. Opioid consumption was decreased in 50% of the trials assessing ketamine-based infusions and 75% of the studies comparing intercostal and paravertebral nerve blocks. Nausea was decreased in several of the ketamine-based infusion and intercostal and paravertebral nerve block studies. CONCLUSION: Ketamine-including infusions or paravertebral and intercostal nerve blocks may represent superior methods of postoperative pain control for MIRPE. Further work is needed to confirm results. LEVEL OF EVIDENCE: 2A [1].
Keywords: Humans; Adolescent; Child; Funnel Chest; Pain, Postoperative; Analgesics; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesics, Opioid; Bupivacaine; Ketamine; MIRPE: minimally invasive repair of pectus excavatum; Pain; Pediatric; Postoperative

Intercostal Nerve Cryoablation in Minimally Invasive Repair of Pectus Excavatum: Effect on Pulmonary Function - Lai, Krista; Lee, Justin; Notrica, David M.; Egan, J. Craig; McMahon, Lisa E.; Molitor, Mark S.; Bae, Jae-O.; Ostlie, Daniel J.; Padilla, Benjamin E. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2022)
Introduction: Cryoablation of intercostal nerves is performed for pain control after minimally invasive repair of pectus excavatum (MIRPE). Cryoablation affects both sensory and motor neurons, resulting in temporary anesthesia to the chest wall and loss of intercostal motor function. The study objective is to determine the effect of cryoablation on incentive spirometry (IS) volumes, as a measure of pulmonary function, after MIRPE. Materials and Methods: A single-institution retrospective review of pediatric patients undergoing MIRPE was performed. All patients received a multimodal regimen (MMR) of analgesics postoperatively. Three groups were compared-cryoablation (CRYO), elastomeric pain pump (EPP), and MMR alone. The primary outcomes were postoperative IS volumes and IS volumes as a ratio of preoperative forced vital capacity (FVC). Secondary outcomes included pain scores, opioid use, length of stay (LOS), and infectious complications. Results: MIRPE was performed in 115 patients: 50 CRYO, 50 EPP, and 15 MMR alone. Groups were similar for demographics and pectus excavatum severity. Postoperative spirometry measurements were similar across groups: IS (CRYO 750 mL [500,961] versus EPP 750 mL [590,1019] versus MMR 696 mL [500,1037], P = .77); IS/FVC (CRYO 0.19 [0.14,0.26] versus EPP 0.20 [0.16,0.26] versus MMR 0.16 [0.15,0.24], P = .69). Although pain scores were also similar across groups, CRYO patients used less opioid (P < .05) and had shorter LOS (P < .05). Postoperative pneumonia was rare and similar across groups (P = 1.00). Conclusion: Intercostal nerve cryoablation during MIRPE does not adversely affect postoperative IS volumes or increase pneumonia rate, despite the temporary loss of motor innervation to intercostal muscles. Cryoablation provides effective pain control with less opioid use.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; MIRPE; Nuss; cryoablation; incentive spirometry; pectus; pulmonary function

Postoperative management of pediatric patients undergoing minimally invasive repair of pectus excavatum: Where are we now? - Kirupaharan, Sawmmiya; Briatico, Daniel; Robinson, Tessa; Fitzgerald, Peter; Walton, J. Mark (Journal of Pediatric Surgery, 2022)
PURPOSE: Minimally invasive repair of pectus excavatum (MIRPE) often leads to a painful and challenging recovery period. This study aims to describe the postoperative management of pediatric patients undergoing MIRPE and compare postoperative outcomes between patients using different routes of postoperative analgesia. METHODS: Retrospective chart review of pediatric patients who underwent MIRPE from July 2003 to September 2019 at a single pediatric tertiary care center. Data on pain management and course of hospital stay were ascertained. Descriptive statistics, Mann-Whitney U and Pearson Chi-Square tests were used to analyze data. A p-value <0.05 was considered significant. RESULTS: Of the 115 patients identified, 58 (50.4%) managed pain postoperatively using thoracic epidural and 57 (49.6%) used intravenous patient-controlled analgesia (IVPCA). The transition from the predominant use of epidural to IVPCA for MIRPE occurred between 2012 and 2013. Higher pain scores were reported by the IVPCA group at 6 h (p<0.001) and 12 h (p<0.001) postoperative. Patients using IVPCA had lower postoperative opioid consumption (p<0.001) and switched to oral opioids sooner than the epidural group (p<0.001). Fewer patients in the IVPCA group required urinary catheterization (p<0.001). Patients using IVPCA had a shorter hospital stay (4 days [IQR 4-5]) compared to the epidural group (5.5 [IQR 5-6]; p<0.001). Readmission was comparable at 3.48% in the total sample. CONCLUSION: Patients using intravenous patient-controlled analgesia reported higher pain scores however, this route of analgesia was associated with shorter hospital stay. Prospective studies designed to address moderator variables are required to confirm findings and develop standardized recovery protocols.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Analgesia, Patient-Controlled; Prospective Studies; MIRPE; Pain management; Quality improvement

Same-day discharge following the Nuss repair: A comparison - Rettig, R. Luke; Rudikoff, Andrew G.; Annie Lo, Hoi Yee; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: Intercostal Nerve Cryoablation (INC) has significantly improved pain control following the Nuss repair of pectus excavatum (PE). This study sought to evaluate patients undergoing the Nuss repair with INC compared to the Nuss repair with an ERAS protocol, INC, and intercostal nerve blocks (INB). METHODS: In June 2020, a new protocol was implemented involving surgery, anesthesia, nursing, physical therapy, and child life with the goal of safe same day discharge for patients undergoing the Nuss repair. They were compared to a control group who underwent the Nuss repair with INC alone in 2017-2019. The primary outcome measure was hospital length of stay (LOS) in hours, secondary outcomes were number of patients discharged on postoperative day (POD) 0, and returns to the emergency department (ED), urgent care (UC), and operating room (OR). RESULTS: The characteristics between the groups were the same (Table 1). The mean LOS was 11.8 h in the INB group versus 58.2 h in the INC group, p < 0.01. 10 of 15 patients in the INB group went home on POD 0 (average of 5.5 h postop), versus 0 patients in the INC only group, p < 0.01. Five patients in the INB stayed overnight. Two patients stayed owing to anxiety, one owing to urinary retention, one owing to nausea, and one owing to drowsiness. None stayed for pain control. Four patients in the INC group returned to the ED for pain control, versus 0 in the INB group, and 1 patient in the INB returned to UC for constipation. CONCLUSIONS: The majority of patients undergoing the Nuss repair of PE with a multidisciplinary regimen of pre and postoperative nursing education, precise intraoperative anesthesia care, performance of direct vision INB and INC, as well as careful surgery can go home on the day of surgery without adverse outcomes or unanticipated returns to the hospital. LEVEL-OF-EVIDENCE: Level II.
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Intercostal nerve cryoablation; Enhanced recovery after surgery (ERAS); Patient Discharge; Pectus excavatum repair; Same day discharge; Anesthesia, Conduction; Intercostal nerve block

Intraoperative intercostal nerve cryoablation During the Nuss procedure reduces length of stay and opioid requirement: A randomized clinical trial - Graves, Claire E.; Moyer, Jarrett; Zobel, Michael J.; Mora, Roberto; Smith, Derek; O'Day, Maura; Padilla, Benjamin E. (Journal of Pediatric Surgery, 2019)
PURPOSE: Minimally-invasive repair of pectus excavatum by the Nuss procedure is associated with significant postoperative pain, prolonged hospital stay, and high opiate requirement. We hypothesized that intercostal nerve cryoablation during the Nuss procedure reduces hospital length of stay (LOS) compared to thoracic epidural analgesia. DESIGN: This randomized clinical trial evaluated 20 consecutive patients undergoing the Nuss procedure for pectus excavatum between May 2016 and March 2018. Patients were randomized evenly via closed-envelope method to receive either cryoanalgesia or thoracic epidural analgesia. Patients and physicians were blinded to study arm until immediately preoperatively. SETTING: Single institution, UCSF-Benioff Children's Hospital. PARTICIPANTS: 20 consecutive patients were recruited from those scheduled for the Nuss procedure. Exclusion criteria were age < 13 years, chest wall anomaly other than pectus excavatum, previous repair or other thoracic surgery, and chronic use of pain medications. MAIN OUTCOMES AND MEASURES: Primary outcome was postoperative LOS. Secondary outcomes included total operative time, total/daily opioid requirement, inpatient/outpatient pain score, and complications. Primary outcome data were analyzed by the Mann-Whitney U-test for nonparametric continuous variables. Other continuous variables were analyzed by two-tailed t-test, while categorical data were compared via Chi-squared test, with alpha = 0.05 for significance. RESULTS: 20 patients were randomized to receive either cryoablation (n = 10) or thoracic epidural (n = 10). Mean operating room time was 46.5 min longer in the cryoanalgesia group (p = 0.0001). Median LOS decreased by 2 days in patients undergoing cryoablation, to 3 days from 5 days (Mann-Whitney U, p = 0.0001). Cryoablation patients required significantly less inpatient opioid analgesia with a mean decrease of 416 mg oral morphine equivalent per patient (p = 0.0001), requiring 52%-82% fewer milligrams on postoperative days 1-3 (p < 0.01 each day). There was no difference in mean pain score between the groups at any point postoperatively, up to one year, and no increased incidence of neuropathic pain in the cryoablation group. No complications were noted in the cryoablation group; among patients with epidurals, one patient experienced a symptomatic pneumothorax and another had urinary retention. CONCLUSIONS AND RELEVANCE: Intercostal nerve cryoablation during the Nuss procedure decreases hospital length of stay and opiate requirement versus thoracic epidural analgesia, while offering equivalent pain control. TYPE OF STUDY: Treatment study. LEVEL OF EVIDENCE: Level I.
Cited By :55 Cited By :55 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Humanos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgésicos Opioides/uso terapéutico; Criocirugía; Criocirugía/métodos; Nervios Intercostales/cirugía; Criocirugía/efectos adversos; Tiempo de Internación/estadística & datos numéricos; Procedimientos Ortopédicos/efectos adversos; Criocirugía/estadística & datos numéricos; Procedimientos Ortopédicos/estadística & datos numéricos; Procedimientos Ortopédicos/métodos; Funnel Chest; Pain, Postoperative; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Orthopedic Procedures; Thoracoscopic

Percutaneous Cryoanalgesia: A New Strategy for Pain Management in Pectus Excavatum Surgery - Velayos, María; Alonso, Mercedes; Delgado-Miguel, Carlos; Estefanía-Fernández, Karla; Muñoz-Serrano, Antonio J.; Santamaría, Manuel V. López; Reinoso-Barbero, Francisco; De La Torre, Carlos A. (European Journal of Pediatric Surgery: Official Journal of Austrian Association of Pediatric Surgery ... [et Al] = Zeitschrift Fur Kinderchirurgie, 2022)
INTRODUCTION: In recent years, pain protocols for pectus excavatum (PE) have incorporated cryoanalgesia through thoracoscopic approach. Since 2019, ultrasound-guided percutaneous cryoanalgesia (PCr) has been applied at our institution, either on the same day as the Nuss procedure or 48 hours before surgery. We carried out a preliminary retrospective review of patients with PE in whom PCr prior to surgery was performed at our institution between 2019 and 2021. MATERIALS AND METHODS: Two groups were evaluated: PCr on the same day (PCrSD) and PCr 48 hours before surgery (PCr48). Despite PCr, patients were treated with "patient-controlled analgesia" (PCA) with opioids for at least 24 hours, switching to conventional intravenous analgesia and oral analgesia in the following days. Demographic, clinical-radiological variables, PCA opioid use, pain grade according to the visual analog scale (VAS), and length of stay (LOS) were compared between the groups. A total of 20 patients were included (12 with PCrSD and 8 with PCr48), without significant differences in demographics or clinical-radiological variables. The overall median time of PCr was 65 minutes (55-127), with no differences between the groups. RESULTS: PCr48 group presented with significantly lower median number of hours of continuous PCA (24 vs. 32 hours; p = 0.031), lower median number of rescue boluses (11 vs. 18; p = 0.042), lower median VAS in the early postoperative hours (2 vs. 5.5; p = 0.043), and lower median LOS (3.5 vs. 5 days). CONCLUSION: PCr performed 48 hours prior to surgery is more effective in terms of PCA requirements, VAS, and LOS when compared with cryoanalgesia on the same day.
Cited By :1 Cited By :1 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Estudios Retrospectivos; Humanos; Manejo del Dolor; Tórax en Embudo/cirugía; Analgésicos Opioides; Tórax en Embudo; Analgesia Controlada por el Paciente; Dolor Postoperatorio; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Analgesia, Patient-Controlled; Pain Management

Same day discharge for pectus excavatum-is it possible? - Rettig, R. Luke; Rudikoff, Andrew G.; Lo, Hoi Yee Annie; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: The use of intercostal nerve cryoablation (INC) has been an effective modality for treating pain in patients undergoing pectus excavatum (PE) repair. This study sought to evaluate if PE patients undergoing Nuss procedures with INC and intercostal nerve block (INB) could safely be discharged the same day of surgery. METHODS: A prospective study with IRB approval of 15 consecutive patients undergoing PE Nuss repair with INC, INB, and an enhanced recovery after surgery (ERAS) protocol was conducted. The primary outcome measure was hospital length of stay (LOS) in hours. Secondary variables included same day discharge, postoperative complications, emergency department (ED) visits, urgent care (UC) visits, opioid use, and return to the operating room (OR). RESULTS: LOS averaged 11.9 h amongst 15 patients. Ten patients (66.7%) went home on postoperative day (POD) 0, and the rest went home on POD 1. No patients stayed in the hospital due to pain. Reasons for failure to discharge included urinary retention, drowsiness, vomiting, and anxiety, but not pain. No patients were readmitted to the ED. One patient visited UC for constipation. One patient had bar migration requiring return to the OR for revision. Ten (66.7%) patients did not use opioids after discharge. CONCLUSIONS: Same day discharge is feasible and safe in PE patients undergoing Nuss procedure with INC and INB. INC with INB can adequately control pain without significant complications. Same day discharge can be safely considered for PE patients undergoing Nuss procedure with INC with INB. TYPE OF STUDY: Prognosis study LEVEL-OF-EVIDENCE RATING: Level II.
Cited By :4 Cited By :4 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Funnel Chest; Pain, Postoperative; Retrospective Studies; Intercostal nerve cryoablation; Enhanced recovery after surgery (ERAS); Patient Discharge; Pectus excavatum repair; Prospective Studies; Same day discharge

Impact of Cryoablation on Pectus Excavatum Repair in Pediatric Patients - Clark, Rachael A.; Jacobson, Jillian C.; Singhal, Amogh; Alder, Adam C.; Chung, Dai H.; Pandya, Samir R. (Journal of the American College of Surgeons, 2022)
BACKGROUND: Minimally invasive repair of pectus excavatum (MIRPE) involves placement of a transthoracic, retrosternal support bar under thoracoscopic guidance. Despite its minimally invasive technical approach, postoperative pain is a significant morbidity that often results in increased length of stay. Multi-modal pain control strategies have been used in the past with limited success. Recently, the use of intraoperative intercostal nerve cryoablation (CA) has been added. In the present study, we aim to evaluate the effects of CA on postoperative pain control, opioid requirements, and perioperative outcomes. STUDY DESIGN: A single-center, retrospective chart review of all patients (less than 18 years old) who underwent MIRPE from 2009 to 2020 was performed. CA was started in June 2018. Data collection included demographics, preoperative characteristics, intraoperative findings, and postoperative outcomes. We hypothesized that CA would be associated with improved pain scores, lower doses of total inpatient opioid requirement, and shorter length of stay (LOS). RESULTS: One hundred sixty-one patients met inclusion criteria: 75 underwent intraoperative CA and 86 underwent MIRPE without CA (NCA group). CA significantly decreased median LOS from 4 days in NCA to 2 days; the use of CA was the only significant predictor of LOS on linear regression. CA was also associated with decreased total PCA, intravenous opioid, and oral opioid dosages. There was no difference in inpatient pain scores and a slight increase in mean procedure time. However, CA was associated with significantly decreased postoperative complications. CONCLUSIONS: The use of cryoablation during MIRPE significantly decreases LOS, perioperative opioid requirements, and postoperative complications, with a minimal increase in operative time. Cryoablation is an effective pain control modality in the surgical management of chest wall deformities in children.
RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Adolescente; Estudios Retrospectivos; Humanos; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Adolescent; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Tórax en Embudo; Analgésicos Opioides/uso terapéutico; Criocirugía; Criocirugía/métodos; Complicaciones Posoperatorias/cirugía; Criocirugía/efectos adversos; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Tórax en Embudo/complicaciones; Tórax en Embudo/tratamiento farmacológico; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Postoperative Complications

Same-day discharge following the Nuss repair: A comparison - Rettig, R. Luke; Rudikoff, Andrew G.; Annie Lo, Hoi Yee; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)
PURPOSE: Intercostal Nerve Cryoablation (INC) has significantly improved pain control following the Nuss repair of pectus excavatum (PE). This study sought to evaluate patients undergoing the Nuss repair with INC compared to the Nuss repair with an ERAS protocol, INC, and intercostal nerve blocks (INB). METHODS: In June 2020, a new protocol was implemented involving surgery, anesthesia, nursing, physical therapy, and child life with the goal of safe same day discharge for patients undergoing the Nuss repair. They were compared to a control group who underwent the Nuss repair with INC alone in 2017-2019. The primary outcome measure was hospital length of stay (LOS) in hours, secondary outcomes were number of patients discharged on postoperative day (POD) 0, and returns to the emergency department (ED), urgent care (UC), and operating room (OR). RESULTS: The characteristics between the groups were the same (Table 1). The mean LOS was 11.8 h in the INB group versus 58.2 h in the INC group, p < 0.01. 10 of 15 patients in the INB group went home on POD 0 (average of 5.5 h postop), versus 0 patients in the INC only group, p < 0.01. Five patients in the INB stayed overnight. Two patients stayed owing to anxiety, one owing to urinary retention, one owing to nausea, and one owing to drowsiness. None stayed for pain control. Four patients in the INC group returned to the ED for pain control, versus 0 in the INB group, and 1 patient in the INB returned to UC for constipation. CONCLUSIONS: The majority of patients undergoing the Nuss repair of PE with a multidisciplinary regimen of pre and postoperative nursing education, precise intraoperative anesthesia care, performance of direct vision INB and INC, as well as careful surgery can go home on the day of surgery without adverse outcomes or unanticipated returns to the hospital. LEVEL-OF-EVIDENCE: Level II.
Cited By :1 Cited By :1 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Estudios Retrospectivos; Humanos; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Dolor Postoperatorio/etiología; Tórax en Embudo; Alta del Paciente; Anestesia de Conducción; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Intercostal nerve cryoablation; Enhanced recovery after surgery (ERAS); Patient Discharge; Pectus excavatum repair; Same day discharge; Anesthesia, Conduction; Intercostal nerve block

Cryoanalgesia is Associated With Decreased Postoperative Opioid Use in Minimally Invasive Repair of Pectus Excavatum - Arshad, Seyed A.; Ferguson, Dalya M.; Garcia, Elisa I.; Hebballi, Nutan B.; Buchanan, Allison C.; Tsao, KuoJen (The Journal of Surgical Research, 2022)
BACKGROUND: Postoperative pain control is challenging after pectus excavatum repair. We aimed to understand the impact that cryoanalgesia had on opioid utilization and outcomes of pediatric patients undergoing minimally invasive repair of pectus excavatum (MIRPE). METHODS: A single-center retrospective cohort study was conducted of all patients (< 18 y) who underwent MIRPE (2011-2019). Patients receiving cryoanalgesia were compared to those who did not. The primary outcome was total postoperative, inpatient, opioid use, measured as milligrams of oral morphine equivalents per kilogram (OME/kg). Univariate and multivariable analyses were performed. RESULTS: Of 35 patients, 20 received cryoanalgesia (57%). Baseline characteristics were similar. Patients who received cryoanalgesia had a lower opioid requirement: median 2.3 mg OME/kg (IQR 1.2-3.1), versus 4.9 mg OME/kg (IQR 2.9-5.8), P < 0.001. Accounting for receipt of cryoanalgesia, epidural, and/or patient-controlled analgesia, cryoanalgesia was associated with a 3.3 mg OME/kg reduction in opioid use (P < 0.001). Median length of stay (LOS) was shorter in cryoanalgesia patients: 3.1 d (IQR 2.3-3.4), versus 5.1 d (IQR 4.3-5.4), P < 0.001. Complications within 90 d were similar between groups. CONCLUSIONS: Cryoanalgesia is an effective adjunctive pain control modality for patients undergoing MIRPE. Use of cryoanalgesia was associated with lower postoperative opioid requirements and shorter LOS, without increased short-term complications, and should be considered for enhanced recovery after MIRPE.
Cited By :2 Cited By :2 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Estudios Retrospectivos; Humanos; Niño; Tórax en Embudo/cirugía; Analgésicos Opioides; Dolor Postoperatorio/etiología; Dolor Postoperatorio/prevención & control; Tórax en Embudo; Analgésicos Opioides/uso terapéutico; Dolor Postoperatorio/cirugía; Procedimientos Quirúrgicos Mínimamente Invasivos/efectos adversos; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryoanalgesia; Length of stay; Minimally invasive repair of pectus excavatum; Pain control

Outcomes Using Cryoablation for Postoperative Pain Control in Children Following Minimally Invasive Pectus Excavatum Repair - Sujka, Joseph; Benedict, Leo Andrew; Fraser, Jason D.; Aguayo, Pablo; Millspaugh, Daniel L.; St Peter, Shawn D. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2018)
PURPOSE: Pain is the main factor that determines the postoperative course for patients undergoing pectus bar placement. Cryoablation of the intercostal nerves has been suggested to mitigate this pain. We instituted a protocol for using intercostal cryoablation and report our early results compared to our immediately previous cohort. MATERIALS AND METHODS: A retrospective study was conducted on patients undergoing minimally invasive repair for pectus excavatum between January 1, 2017, and August 21, 2017. Demographic data, anthropometrics, operative times, type and duration of patient analgesia, and postoperative length of stay were collected. Descriptive statistics were performed with all means reported ± standard deviations. Comparisons between groups were analyzed on STATA using T-tests with a P value <.05 determined as significant. RESULTS: Twenty-eight patients were treated for pectus excavatum during the study period with 9 (32%) undergoing cryoablation. Mean number of rib spaces ablated was 5 ± 0.53 with no reported intraoperative complications. Mean operative time was 30 minutes longer in the cryoablation group (P = .00). Days to only oral pain medication was shorter in the cryoablation group, (1.22 ± 0.66 day versus 2.63 ± 0.68 day, P = .00). Length of stay, in days, was shorter in the cryoablation group (1.4 ± 0.72 days versus 4.0 ± 1.0 days, P = .00). There were no reported complications from cryoablation or bar placement during the study period. Days to discontinuation of oral narcotics were less in the cryoablation group (8.2 ± 7.0 versus 18.2 ± 10.4, P = .00). CONCLUSION: Cryoablation after pectus bar placement dramatically decreases narcotic usage and postoperative length of stay.
Cited By :19 Cited By :19 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Tórax en Embudo/cirugía; Adolescent; Female; Male; Criocirugía/métodos; Dolor Postoperatorio/cirugía; Nervios Intercostales/cirugía; Tempo Operativo; Tiempo de Internación/estadística & datos numéricos; Analgésicos/uso terapéutico; Estudios de Cohortes; Narcóticos/uso terapéutico; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics; Minimally Invasive Surgical Procedures; Cryosurgery; Intercostal Nerves; Length of Stay; Operative Time; Cohort Studies; cryoablation; epidural; minimally invasive; Narcotics; patient-controlled anesthesia; pectus excavatum; Only Child

Thoracoscopic cryoanalgesia: A new strategy for postoperative pain control in minimally invasive pectus excavatum repair - Cadaval Gallardo, C.; Martínez, J.; Bellía-Munzon, G.; Nazar, M.; Sanjurjo, D.; Toselli, L.; Martínez-Ferro, M. (Cirugia Pediatrica: Organo Oficial De La Sociedad Espanola De Cirugia Pediatrica, 2020)
OBJECTIVE: Recent publications report early discharge and low opioid requirements after minimally invasive pectus excavatum repair treated with bilateral intercostal nerve cryoablation. Our aim is to report our initial experience with this technique. MATERIAL AND METHODS: Retrospective analysis of medical records of patients undergoing bilateral thoracoscopic cryoanalgesia during minimally invasive pectus excavatum repair within our institution from September 2018 to March 2019. TECHNIQUE: A cryoprobe was applied at -70 ºC for 2 minutes each from the 3rd to the 7th intercostal nerves bilaterally under thoracoscopic control. Postoperative pain was assessed using a visual analogue scale (VAS). RESULTS: Twenty-one patients were included. Ninety percent were male, the mean age being 15.2 ± 4.29 years, and the mean weight being 53.6 ± 15.33 kg. The average Haller index was 5.1 ± 2.97, and the mean repair index was 37.6 ± 13.77%. The mean number of implants introduced was 2.55 ± 0.74. The mean duration of cryoanalgesia was 39.9 ± 21.1. No patients received epidural anesthesia. Mean postoperative stay was 1.64 ± 0.73 days. Seventy-one percent of the patients required 1 dose of opioids at the most for postoperative pain control. According to the VAS, the average pain score on postoperative days 1, 3, 7, and 21 was 2.55, 2.01, 0.5, and 0.06, respectively. CONCLUSIONS: Bilateral thoracoscopic cryoanalgesia during minimally invasive pectus excavatum repair leads to early discharge and good postoperative pain control in all cases. Cryoanalgesia has become our treatment of choice for pain control in the thoracoscopic repair of pectus excavatum.
RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Nervios Intercostales; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Toracoscopía/métodos; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Young Adult; Criocirugía/métodos; Dolor Postoperatorio/cirugía; Tiempo de Internación; Adulto Joven; Analgésicos Opioides/administración & dosificación; Dimensión del Dolor; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Length of Stay; Pain Measurement; Cryoanalgesia; Thoracoscopy; Minimally invasive pectus excavatum repair; Intercostal nerve; Nerve cryoablation; Postoperative pain

Intercostal Nerve Cryoablation in Minimally Invasive Repair of Pectus Excavatum: Effect on Pulmonary Function - Lai, Krista; Lee, Justin; Notrica, David M.; Egan, J. Craig; McMahon, Lisa E.; Molitor, Mark S.; Bae, Jae-O.; Ostlie, Daniel J.; Padilla, Benjamin E. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2022)
Introduction: Cryoablation of intercostal nerves is performed for pain control after minimally invasive repair of pectus excavatum (MIRPE). Cryoablation affects both sensory and motor neurons, resulting in temporary anesthesia to the chest wall and loss of intercostal motor function. The study objective is to determine the effect of cryoablation on incentive spirometry (IS) volumes, as a measure of pulmonary function, after MIRPE. Materials and Methods: A single-institution retrospective review of pediatric patients undergoing MIRPE was performed. All patients received a multimodal regimen (MMR) of analgesics postoperatively. Three groups were compared-cryoablation (CRYO), elastomeric pain pump (EPP), and MMR alone. The primary outcomes were postoperative IS volumes and IS volumes as a ratio of preoperative forced vital capacity (FVC). Secondary outcomes included pain scores, opioid use, length of stay (LOS), and infectious complications. Results: MIRPE was performed in 115 patients: 50 CRYO, 50 EPP, and 15 MMR alone. Groups were similar for demographics and pectus excavatum severity. Postoperative spirometry measurements were similar across groups: IS (CRYO 750 mL [500,961] versus EPP 750 mL [590,1019] versus MMR 696 mL [500,1037], P = .77); IS/FVC (CRYO 0.19 [0.14,0.26] versus EPP 0.20 [0.16,0.26] versus MMR 0.16 [0.15,0.24], P = .69). Although pain scores were also similar across groups, CRYO patients used less opioid (P < .05) and had shorter LOS (P < .05). Postoperative pneumonia was rare and similar across groups (P = 1.00). Conclusion: Intercostal nerve cryoablation during MIRPE does not adversely affect postoperative IS volumes or increase pneumonia rate, despite the temporary loss of motor innervation to intercostal muscles. Cryoablation provides effective pain control with less opioid use.
RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; MIRPE; Nuss; cryoablation; incentive spirometry; pectus; pulmonary function

Limited cryoablation reduces hospital stay and opioid consumption compared to thoracic epidural analgesia after minimally invasive repair of pectus excavatum - Song, Seung Hwan; Moon, Duk Hwan; Shim, Yon Hee; Jung, Hyunjoo; Lee, Sungsoo (Medicine, 2022)
pain following minimally invasive repair of pectus excavatum (MIRPE) is a critical concern that leads to a prolonged hospital stay and high doses of opiates administered to the patients. This study aimed to evaluate the efficacy of intraoperative cryoanalgesia (cryoablation of the intercostal nerves) during MIRPE. We retrospectively analyzed the data of 64 patients who underwent MIRPE and received cryoanalgesia or epidural analgesia between January 2019 and January 2021. The oral morphine milligram equivalent (MME) was used to calculate the dosage of opioid agents. The median age was 15 years (range, 4-33 years). The median postoperative hospital stay was 4 days (range, 2-6 days), with a median oral MME consumption of 45 mg (ranging from 0 to 1360 mg). Cryoanalgesia was performed in 38 patients, and epidural analgesia was administered to the remaining 26 patients. The cryoanalgesia group had a significantly lesser pain score, shorter postoperative hospital stay and lower oral MME consumption than the epidural analgesia group (5 vs 2; P < .001, 3 days vs 5 days; P < .001, 19 mg vs 634 mg; P < .001). Cryoanalgesia appears to reduce postoperative hospital stay and opioid consumption compared with epidural analgesia. The outcomes of this study indicate that cryoanalgesia might be a safe and effective method for pain control following MIRPE.
Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Adolescente; Estudios Retrospectivos; Humanos; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Analgesia Epidural/métodos; Adolescent; Tórax en Embudo; Analgésicos Opioides/uso terapéutico; Criocirugía; Criocirugía/métodos; Dolor Postoperatorio/cirugía; Tiempo de Internación; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Length of Stay; Analgesia, Epidural

Intercostal cryoablation during Nuss procedure: A large volume single surgeon's experience and outcomes - Sun, Raphael C.; Mehl, Steven C.; Anbarasu, Centura R.; Portuondo, Jorge I.; Espinoza, Andres F.; Whitlock, Richard; Mazziotti, Mark V. (Journal of Pediatric Surgery, 2021)
BACKGROUND: Recent studies have shown intercostal cryoablation(IC) during the Nuss procedure decreases hospital length of stay(LOS) and opioid administration. However, few studies have also evaluated the risk of postoperative complications related to IC. METHODS: We performed a single center retrospective analysis of all patients who underwent Nuss procedure by one surgeon from 2/2016 to 2/2020, comparing intraoperative IC to other pain management modalities(non-IC). Primary outcomes were postoperative complications, hospital LOS, and opioid administration. Multivariate analysis was performed with outcomes reported as regression coefficients(RC) or odds ratios(OR) with 95% confidence interval. RESULTS: IC was associated with decreased hospital LOS (RC -1.91[-2.29 to -1.54], less hospital opioid administration (RC -4.28[-5.13 to -3.43]), and less discharge opioid administration (RC -3.82[-5.23 to -2.41]). With respect to postoperative complications, IC decreased the odds of urinary retention (OR 0.16[0.06 to 0.44]); however, increased the odds of slipped bars requiring reoperation (OR 36.65[5.04-266.39]). CONCLUSIONS: Our single surgeon experience controls for surgeon variability and demonstrates intraoperative IC for the Nuss procedure is an effective pain management modality that decreases hospital LOS and opioid use during hospitalization and at discharge; however, it is associated with increased odds of slipped bars requiring reoperation. LEVEL OF EVIDENCE: III.
Cited By :11 Cited By :11 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Estudios Retrospectivos; Humanos; Tórax en Embudo/cirugía; Dolor Postoperatorio/epidemiología; Dolor Postoperatorio/etiología; Tórax en Embudo; Criocirugía; Dolor Postoperatorio/cirugía; Cirujanos; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Cryosurgery; Intercostal cryoablation; Nuss; Opioid; Abbreviations; Forced expiratory volume (FEV); Forced vital capacity (FVC); Haller index (HI); intercostal cryoablation (IC); interquartile ranges (IQR); length of stay (LOS); multiple polyester (p-dioxanone) sutures (PDS); odds ratio (OR); oral morphine equivalents (OME/kg); patient-controlled analgesia (PCA); peripheral nerve block (PNB); regression coefficient (RC); Surgeons; thoracic epidural (TE)

Postoperative pain control modalities for pectus excavatum repair: A prospective observational study of cryoablation compared to results of a randomized trial of epidural vs patient-controlled analgesia - Dekonenko, Charlene; Dorman, Robert M.; Duran, Yara; Juang, David; Aguayo, Pablo; Fraser, Jason D.; Oyetunji, Tolulope A.; Snyder, Charles L.; Holcomb, George W.; Millspaugh, Daniel L.; St Peter, Shawn D. (Journal of Pediatric Surgery, 2020)
BACKGROUND: Pain following bar placement for pectus excavatum is the dominant factor post-operatively and determines length of stay (LOS). We recently adopted intercostal cryoablation as our preferred method of pain control following minimally invasive pectus excavatum repair. We compared the outcomes of cryoablation to results of a recently concluded trial of epidural (EPI) and patient-controlled analgesia (PCA) protocols. METHODS: We conducted a prospective observational study of patients undergoing bar placement for pectus excavatum using intercostal cryoablation. Results are reported and compared with those of a randomized trial comparing EPI with PCA. Comparisons of medians were performed using Kruskal-Wallis H tests with alpha 0.05. RESULTS: Thirty-five patients were treated with cryoablation compared to 32 epidural and 33 PCA patients from the trial. Cryoablation was associated with longer operating time (101 min, versus 58 and 57 min for epidural and PCA groups, p < 0.01), resulted in less time to pain control with oral medication (21 h, versus 72 and 67 h, p < 0.01), and decreased LOS (1 day, versus 4.3 and 4.2 days, p < 0.01). CONCLUSION: Intercostal cryoablation during minimally invasive pectus excavatum repair reduces LOS and perioperative opioid consumption compared with both EPI and PCA. LEVEL OF EVIDENCE: II.
Cited By :30 Cited By :30 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Dolor Postoperatorio/terapia; Humanos; Tórax en Embudo/cirugía; Analgesia Epidural; Estudios Prospectivos; Criocirugía/efectos adversos; Analgesia Controlada por el Paciente; Tiempo de Internación/estadística & datos numéricos; Funnel Chest; Pain, Postoperative; Cryosurgery; Length of Stay; Analgesia, Patient-Controlled; Prospective Studies; Analgesia, Epidural; Cryoanalgesia; Minimally invasive pectus excavatum repair; Cryoablation

Cryoanalgesia in Patients Undergoing Nuss Repair of Pectus Excavatum: Technique Modification and Early Results - Morikawa, Nicole; Laferriere, Nicole; Koo, Sylvia; Johnson, Sidney; Woo, Russell; Puapong, Devin (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2018)
PURPOSE: The Nuss procedure for surgical correction of pectus excavatum often causes severe postoperative pain. Cryoanalgesia of intercostal nerves is an alternative modality for pain control. We describe our modification of the cryoICE™ probe that allows for nerve ablation through the ipsilateral chest along with early results utilizing this technique. METHODS: To allow for ipsilateral nerve ablation, a 20-French chest tube was cut and secured to the cryoICE probe, thus providing insulation for the malleable end of the probe. A 3-year retrospective review of patients undergoing Nuss repair at our institution was performed. Patients who received cryoanalgesia (cryo, n = 6) were compared with a historical control cohort who did not receive cryoanalgesia (nocryo, n = 13) during Nuss repair. Hospital length of stay, postoperative narcotic requirement (PNR), and highest postoperative pain score were collected. RESULTS: Both cohorts were similar regarding age, BMI, and pectus index. The cryo group had a significantly less PNR (6.4 versus 17.9 doses, P = .05) and was discharged on average >1 day earlier than nocryo patients (3.7 versus 2.2 days, P = .01). No complications occurred in either group. CONCLUSIONS: Our technique modification simplifies previously described approaches to intercostal nerve cryoablation. Patients undergoing this adjunct benefit with less PNR and a faster discharge time.
Cited By :15 Cited By :15 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Adolescente; Crioanestesia/instrumentación; Crioanestesia/métodos; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/prevención & control; Criocirugía/métodos; Nervios Intercostales/cirugía; Estudios de Seguimiento; Procedimientos Ortopédicos; Criocirugía/instrumentación; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Nuss procedure; Cryosurgery; Intercostal Nerves; Orthopedic Procedures; pectus excavatum; Follow-Up Studies; pain management; cryoanalgesia; Cryoanesthesia

Comparing outcomes with thoracic epidural and intercostal nerve cryoablation after Nuss procedure - Harbaugh, Calista M.; Johnson, Kevin N.; Kein, Courtney E.; Jarboe, Marcus D.; Hirschl, Ronald B.; Geiger, James D.; Gadepalli, Samir K. (The Journal of Surgical Research, 2018)
BACKGROUND: This study aimed to evaluate postoperative outcomes after minimally invasive repair of pectus excavatum (Nuss procedure) using video-assisted intercostal nerve cryoablation (INC) compared to thoracic epidural (TE). MATERIALS AND METHODS: We performed a single center retrospective review of pediatric patients who underwent Nuss procedure with INC (n = 19) or TE (n = 13) from April 2015 to August 2017. Preoperative, intraoperative, and postoperative characteristics were collected. The primary outcome was length of stay (LOS) and secondary outcomes were intravenous and oral opioid use, pain scores, and complications. Opioids were converted to oral morphine milligram equivalents per kilogram (oral morphine equivalent [OME]/kg). Mann-Whitney U test was used for continuous and chi-squared analysis for categorical variables. RESULTS: There were no significant differences in patient characteristics, except Haller Index (INC: median [interquartile range] 4.3 [3.6-4.9]; TE: 3.2 [2.8-4.0]; P = 0.03). LOS was shorter with INC (INC: 3 [3-4] days; TE: 6 [5-7] days; P < 0.001). Opioid use was higher intraoperatively (INC: 1.08 [0.87-1.37] OME/kg; TE: 0.46 [0.37-0.67] OME/kg; P = 0.002) and unchanged postoperatively (INC: 1.78 [1.26-3.77] OME/kg; TE: 1.82 [1.05-3.37] OME/kg; P = 0.80), and prescription doses were lower at discharge in INC (INC: 30 [30-40] doses; TE: 42 [40-60] doses; P = 0.005). There was no significant difference in postoperative complications (INC: 42.1%; TE: 53.9%; P = 0.51). CONCLUSIONS: INC during Nuss procedure reduced LOS, shifting postoperative opioid use earlier during admission. This may reflect the need for improved early pain control until INC takes effect. Prospective evaluation after INC is needed to characterize long-term pain medication requirements.
Cited By :28 Cited By :28 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/prevención & control; Nervios Intercostales/cirugía; Analgésicos Opioides/administración & dosificación; Procedimientos Quirúrgicos Mínimamente Invasivos; Complicaciones Posoperatorias/epidemiología; Criocirugía/estadística & datos numéricos; Analgesia Epidural/estadística & datos numéricos; Cirugía Asistida por Video; Michigan/epidemiología; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Postoperative Complications; Pain management; Analgesia, Epidural; Epidural; Cryoablation; Michigan; Pectus; Pediatric surgery; Video-Assisted Surgery

Intraoperative cryoanalgesia for managing pain after the Nuss procedure - Graves, Claire; Idowu, Olajire; Lee, Sang; Padilla, Benjamin; Kim, Sunghoon (Journal of Pediatric Surgery, 2017)
BACKGROUND: Cryoanalgesia prevents pain by freezing the affected peripheral nerve. We report the use of intraoperative cryoanalgesia during the Nuss procedure for pectus excavatum and describe our initial experience, modifications of technique, and lessons learned. MATERIALS AND METHODS: We retrospectively reviewed the medical records of patients who received cryoanalgesia during the Nuss procedure between June 1, 2015, and April 30, 2016, at our institutions and analyzed modifications in surgical technique during this early adoption period. RESULTS: Eight male and two female patients underwent the Nuss procedure with cryoanalgesia. The mean postoperative length of stay (LOS) was 2days (range 1-3). Average inpatient pain scores were 3.4, 3.2, and 4.6 on postoperative days 1-3, respectively (N=10, 7, and 2). At a 1-week postoperative visit, mean pain score was 1.1 (N=6). Compared to the preceding 15 Nuss patients at our institution, who were treated with a thoracic epidural, postoperative LOS was significantly shorter with cryoanalgesia (2.0±0.82 vs. 6.3±1.3days, P<0.001). We modified our technique for patient habitus and adopted single-lung ventilation for improved visualization. CONCLUSIONS: Cryoanalgesia may be the ideal pain management strategy for Nuss patients because it is effective and long lasting. Intraoperative application is easily integrated into the Nuss procedure. STUDY TYPE: Treatment study: case series; Evidence level IV.
Cited By :39 Cited By :39 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Nervios Intercostales; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Female; Male; Young Adult; Dolor Postoperatorio/diagnóstico; Dolor Postoperatorio/prevención & control; Adulto Joven; Crioterapia/métodos; Estudios de Seguimiento; Procedimientos Ortopédicos; Analgesia/métodos; Cuidados Intraoperatorios/métodos; Toracoscopía; Analgesia; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Nuss procedure; Pectus excavatum; Intercostal Nerves; Orthopedic Procedures; Pain Management; Cryoanalgesia; Thoracoscopy; Follow-Up Studies; Cryoprobe; Cryotherapy; Epidural analgesia; Intraoperative Care

Cryoablation is associated with shorter length of stay and reduced opioid use in pectus excavatum repair - Rettig, R. Luke; Rudikoff, Andrew G.; Lo, Hoi Yee Annie; Shaul, Donald B.; Banzali, Franklin M.; Conte, Antonio Hernandez; Sydorak, Roman M. (Pediatric Surgery International, 2021)
PURPOSE: The use of intercostal nerve cryoablation (INC) is becoming increasingly common in patients undergoing pectus excavatum (PE) repair. This study sought to evaluate the use of INC compared to traditional use of thoracic epidural (TE). METHODS: A retrospective review of 79 patients undergoing PE repair with either INC or TE from May 2009 to December 2019 was conducted. The operations were performed by four surgeons who worked together at four different hospitals and have the same standardized practice. The primary outcome measure was hospital length of stay (LOS). Secondary variables included surgical time, total operating room time, operating room time cost, total hospital cost, inpatient opioid use, long-term opioid use after discharge, and postoperative complications. RESULTS: LOS decreased to 2.5 days in the INC group compared to 5 days in the TE group (p < 0.0001). Surgical time was increased in the INC group, but there was no difference in total OR time. The INC group experienced significantly lower hospital costs. Total hospital opioid administration was significantly lower in INC group, and there was a significant decrease in long-term opioid use in the INC group. CONCLUSIONS: INC is a newer modality that decreases LOS, controls pain, and results in overall cost savings. We recommend that INC be included in the current practice for postoperative pain control in PE patients undergoing Nuss procedure.
Cited By :9 Cited By :9 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Adulto; Adolescent; Adult; Female; Male; Young Adult; Criocirugía/métodos; Nervios Intercostales/cirugía; Adulto Joven; Analgésicos Opioides/administración & dosificación; Complicaciones Posoperatorias; Tempo Operativo; Tiempo de Internación/estadística & datos numéricos; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Pectus excavatum repair; Postoperative Complications; Operative Time; Enhanced recovery after surgery; Thoracic epidural

Next day discharge after the Nuss procedure using intercostal nerve cryoablation, intercostal nerve blocks, and a perioperative ERAS pain protocol - DiFiore, John W.; Robertson, Jason O.; Chhabada, Surendrasingh; DeRoss, Anthony L.; Hossain, Mir S.; Rincon-Cruz, Lorena; Sung, Wai (Journal of Pediatric Surgery, 2022)
BACKGROUND: The Nuss procedure for pectus excavatum has historically been associated with significant postoperative pain, which has been the major factor contributing to hospital length of stay (LOS). METHODS: A single-institution, prospective study of 40 consecutive patients undergoing Nuss bar placement for pectus excavatum between November 2019 and January 2021 was conducted to assess the effectiveness of a multimodality pain management protocol. All patients received T3-T8 intercostal nerve cryoablation (INC), T3-T8 bupivacaine intercostal nerve blocks, Exparel at the skin incisions, and management with a perioperative analgesia regimen that minimized narcotic usage. The primary outcome was LOS. Secondary outcomes included opioid use, pain scores, and time to sensory recovery. RESULTS: 37/40 patients (92.5%) were discharged home on postoperative day (POD) 1, and 3/40 (7.5%) were discharged on POD 2 (mean LOS = 1.1 days). The median average postoperative pain score was 2/10. After eliminating IVPCA from our protocol, total oral morphine equivalent (OME) decreased by 73% (55.5 mg to 15 mg) with no change in pain scores or discharge timing. CONCLUSIONS: INC combined with bupivacaine intercostal nerve blocks and a pre- and post-hospital analgesia protocol facilitated discharge one day after the Nuss procedure, achieved excellent pain control, and eliminated the need for intravenous opioids.
Cited By :2 Cited By :2 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Estudios Retrospectivos; Humanos; Nervios Intercostales; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural; Analgésicos Opioides; Tórax en Embudo; Criocirugía; Dolor Postoperatorio/cirugía; Tiempo de Internación; Estudios Prospectivos; Alta del Paciente; Funnel Chest; Pain, Postoperative; Retrospective Studies; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal nerve cryoablation; Intercostal Nerves; Length of Stay; Enhanced recovery after surgery (ERAS); Patient Discharge; Prospective Studies; Analgesia, Epidural; Nerve Block; Intercostal nerve blocks; Nuss bar procedure

Intercostal nerve cryoablation versus thoracic epidural catheters for postoperative analgesia following pectus excavatum repair: Preliminary outcomes in twenty-six cryoablation patients - Keller, Benjamin A.; Kabagambe, Sandra K.; Becker, James C.; Chen, Y. Julia; Goodman, Laura F.; Clark-Wronski, Julianna M.; Furukawa, Kenneth; Stark, Rebecca A.; Rahm, Amy L.; Hirose, Shinjiro; Raff, Gary W. (Journal of Pediatric Surgery, 2016)
BACKGROUND: Multimodal pain management strategies are used for analgesia following pectus excavatum repair. However, the optimal regimen has not been identified. We describe our early experience with intercostal cryoablation for pain management in children undergoing the Nuss procedure and compare early cryoablation outcomes to our prior outcomes using thoracic epidural analgesia. METHODS: A multi-institutional, retrospective review of fifty-two patients undergoing Nuss bar placement with either intercostal cryoablation (n=26) or thoracic epidural analgesia (n=26) from March 2013 to January 2016 was conducted. The primary outcome was hospital length of stay. Secondary outcomes included telemetry unit monitoring time, total intravenous narcotic use, duration of intravenous narcotic use, and postoperative complications. RESULTS: Patients who underwent intercostal cryoablation had a significant reduction in the mean hospital length of stay, time in a monitored telemetry bed, total use of intravenous narcotics, and the duration of intravenous narcotic administration when compared to thoracic epidural patients. Cryoablation patients had a slightly higher rate of postoperative complications. CONCLUSION: Intercostal cryoablation is a promising technique for postoperative pain management in children undergoing repair of pectus excavatum. This therapy results in reduced time to hospital discharge, decreased intravenous narcotic utilization, and has eliminated epidurals from our practice. LEVEL OF EVIDENCE: Retrospective study - level III.
Cited By :58 Cited By :58 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Adolescente; Estudios Retrospectivos; Femenino; Humanos; Masculino; Dolor Postoperatorio/tratamiento farmacológico; Tórax en Embudo/cirugía; Analgesia Epidural/métodos; Adolescent; Female; Male; Criocirugía/métodos; Dolor Postoperatorio/cirugía; Nervios Intercostales/cirugía; Analgésicos Opioides/administración & dosificación; Funnel Chest; Pain, Postoperative; Retrospective Studies; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Pain management; Analgesia, Epidural; Cryoablation; Epidural analgesia

Intercostal nerve cryoablation is associated with lower hospital cost during minimally invasive Nuss procedure for pectus excavatum - Aiken, Taylor J.; Stahl, Christopher C.; Lemaster, Deborah; Casias, Timothy W.; Walker, Benjamin J.; Nichol, Peter F.; Leys, Charles M.; Abbott, Daniel E.; Brinkman, Adam S. (Journal of Pediatric Surgery, 2021)
Minimally invasive repair of pectus excavatum (Nuss procedure) is associated with significant pain, and efforts to control pain impact resource utilization. Bilateral thoracic intercostal nerve cryoablation has been proposed as a novel technique to improve post-operative pain control, though the impact on hospital cost is unknown. METHODS: We conducted a retrospective study of patients undergoing a Nuss procedure from 2016 to 2019. Patients who received cryoablation were compared to those that received traditional pain control (patient-controlled analgesia or epidural). Outcome variables included postoperative opioid usage (milligram morphine equivalents, MME), length of stay (LOS), and hospital cost. RESULTS: Thirty-five of 73 patients studied (48%) received intercostal nerve cryoablation. LOS (1.0 vs 4.0 days, p < 0.01) and total hospital cost ($21,924 versus $23,694, p = 0.04) were decreased in the cryoablation cohort, despite longer operative time (152 vs 74 min, p < 0.01). Cryoablation was associated with decreased opioid usage (15.0 versus 148.6 MME, p < 0.01) during the 24 h following surgery and this persisted over the entire postoperative period, including discharge opioid prescription (112.5 vs 300.0 MME, p < 0.01). CONCLUSION: Bilateral intercostal nerve cryoablation is associated with decreased postoperative opioid usage and decreased resource utilization in pediatric patients undergoing a minimally invasive Nuss procedure for pectus excavatum. LEVEL OF EVIDENCE: Retrospective comparative study, level III.
Cited By :11 Cited By :11 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Estudios Retrospectivos; Humanos; Nervios Intercostales; Niño; Dolor Postoperatorio/tratamiento farmacológico; Resultado del Tratamiento; Tórax en Embudo/cirugía; Dolor Postoperatorio/etiología; Tórax en Embudo; Criocirugía; Dolor Postoperatorio/cirugía; Costos de Hospital; Procedimientos Quirúrgicos Mínimamente Invasivos; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Pectus excavatum; Cryosurgery; Intercostal Nerves; Pediatric; Cryoablation; Hospital cost; Hospital Costs; Minimally invasive Nuss procedure; Post-op pain

The Use of Cryoanalgesia in Minimally Invasive Repair of Pectus Excavatum: Lessons Learned - Parrado, Raphael; Lee, Justin; McMahon, Lisa E.; Clay, Conner; Powell, Jordan; Kang, Paul; Notrica, David M.; Ostlie, Daniel J.; Bae, Jae-O. (Journal of Laparoendoscopic & Advanced Surgical Techniques. Part A, 2019)
Introduction: Cryoanalgesia has been applied to minimally invasive repair of pectus excavatum (MIRPE). After implementation of cryoanalgesia at our institution, we had several cases of delayed postoperative pneumothorax. The purpose of this study was to critically evaluate the complications and efficacy of cryoanalgesia in MIRPE. Materials and Methods: We performed a single institution retrospective review of pediatric patients undergoing MIRPE from June 2017 to July 2018. Multimodal (MM) analgesia was used in all patients. In addition, most patients received either cryoanalgesia or elastomeric pain pumps (EPPs) as adjuncts to postoperative analgesia. Primary outcome was clinically significant late pneumothorax. Secondary outcomes included length of stay, pain scores, opiate use, and bar displacement requiring reoperation. Results: A total of 101 patients undergoing MIRPE were included: 45 had cryoanalgesia + MM, 45 EPP + MM, and 11 MM alone. Postoperative tube thoracostomy was placed in 5 patients with cryoanalgesia (4 pneumothorax; 1 effusion), 1 patient with EPP (1 pneumothorax), and none in MM alone (P = .25). Pain scores at discharge were similar in all groups. Cryoanalgesia patients received less overall inpatient opioids than other groups (P < .05). No patient required reoperation for bar displacement. Conclusion: Cryoanalgesia is an effective therapy for pain control in MIRPE. Because thermal injury can occur on the lung and chest wall with cryoanalgesia, we implemented techniques to limit and prevent this injury. Cryoanalgesia offers a safe alternative for postoperative analgesia with significant reduction in inpatient opioid requirement. Larger prospective studies are required to assess the long-term impact and complications of cryoanalgesia.
Cited By :11 Cited By :11 Export Date: 8 December 2022 Export Date: 8 December 2022 | RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Adolescente; Dolor Postoperatorio/terapia; Estudios Retrospectivos; Femenino; Humanos; Masculino; Niño; Resultado del Tratamiento; Tórax en Embudo/cirugía; Adolescent; Female; Male; Dolor Postoperatorio/diagnóstico; Analgésicos Opioides/uso terapéutico; Procedimientos Quirúrgicos Mínimamente Invasivos; Complicaciones Posoperatorias/epidemiología; Complicaciones Posoperatorias/etiología; Complicaciones Posoperatorias/prevención & control; Crioterapia/efectos adversos; Crioterapia/métodos; Estudios de Seguimiento; Neumotórax/epidemiología; Neumotórax/etiología; Neumotórax/prevención & control; Procedimientos Ortopédicos; Terapia Combinada; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Treatment Outcome; Minimally Invasive Surgical Procedures; Analgesics, Opioid; Orthopedic Procedures; Postoperative Complications; postoperative analgesia; minimally invasive repair of pectus excavatum; Follow-Up Studies; cryoanalgesia; Cryotherapy; Combined Modality Therapy; Pneumothorax; Learning

Effectiveness of one minute per level intercostal nerve cryoablation for postoperative analgesia after surgical correction of pectus excavatum - Zeineddin, Suhail; Goldstein, Seth D.; Linton, Samuel; DeBoer, Christopher; Alayleh, Amin; Ortiz, Irma; Sands, Laurie; Kujawa, Suzanne; Suresh, Santhanam; Ghomrawi, Hassan; Abdullah, Fizan (Journal of Pediatric Surgery, 2023)
PURPOSE: Intraoperative intercostal nerve cryoablation has emerged as a promising modality for postoperative analgesia following Surgical Correction of Pectus Excavatum (SCOPE). Most centers use two-minute cryoablation per level, although data from histologic and adult studies suggest the effectiveness of one-minute freezes. We aimed to describe our center's experience with one minute per level cryoablation. METHODS: A retrospective single institution review of patients undergoing SCOPE was performed to compare patients pre- and post-intercostal nerve cryoablation implementation. Cryoablation was performed as one minute for each of the thoracic intercostal nerves T3-T7. Multivariable regression analyses were conducted to compare the outcomes and cost between pre- and post-implementation groups. RESULTS: During the study period, 198 patients underwent SCOPE with one Nuss bar, receiving either intraoperative intercostal nerve cryoablation (Cryo, n = 100) or preoperative thoracic paravertebral catheters (NoCryo, n = 98). Surgical time was on average 9 min longer for the Cryo group (p<0.01). Median length of stay for the Cryo group was 3 days shorter compared to the NoCryo group (p<0.01). The Cryo group had a 19-fold and 5.6-fold reduction in average inpatient and total postoperative opioid usage, respectively (p<0.01). Total hospital costs were significantly lower in the Cryo group (p<0.01). Overall complication rate was not statistically significant different between the two groups. CONCLUSIONS: Intraoperative one minute per level cryoablation is a potent approach to postoperative analgesia for SCOPE patients that led to a shorter hospital length of stay, lower hospital costs, and decreased opioid use compared to conventional analgesia at our institution. Pediatric surgeons performing correction of chest wall deformities should consider offering this technique.
RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Humans; Adult; Analgesia; Child; Funnel Chest; Pain, Postoperative; Retrospective Studies; Minimally Invasive Surgical Procedures; Nuss procedure; Pectus excavatum; Analgesics, Opioid; Cryosurgery; Intercostal Nerves; Cryoanalgesia; Thoracic Wall; Intercostal cryoablation; Nuss bar; Thoracoscopy; SCOPE

Crioanalgesia toracoscópica: nueva estrategia para el control del dolor postoperatorio en cirugía del pectus excavatum - Cadaval Gallardo, C; Martínez, J; Bellía-Munzon, G; Nazar, M; Sanjurjo, D; Toselli, L; Martínez-Ferro, M (Cir. pediátr, 2020)
Introducción: Publicaciones recientes reportaron el alta temprana y bajos requerimientos de opioides para el control del dolor postope-ratorio en la reparación mínimamente invasiva del pectus excavatumtras crioablación bilateral de nervios intercostales. Nuestro objetivo es describir nuestra experiencia inicial con esta técnica. Material y métodos: Análisis retrospectivo de historias clínicas de pacientes sometidos a crioanalgesia toracoscópica bilateral durante la reparación mínimamente invasiva del pectus excavatum en nuestra institución desde septiembre de 2018 a marzo de 2019. Técnica: Se aplicó una criosonda a -70°C bajo visión toracoscópica durante 2 minutos del 3º al 7º espacio intercostal, de manera bilateral. El dolor postoperatorio fue evaluado con una Escala Visual Analógica. Resultados: Se incluyeron 21 pacientes, de los cuales el 90% era de sexo masculino con una edad media de 15,2 ± 4,29 años y un peso de 53,6 ± 15,33 kg. El índice de Haller promedio fue de 5,1 ± 2,97 y el índice de corrección de 37,6 ± 13,77%. El número promedio de implantes fue de 2,55 ± 0,74. La duración media de la crioanalgesia fue de 39,9 ± 21,1 minutos. Ninguno recibió anestesia peridural. El tiempo de internación postquirúrgico fue de 1,64 ± 0,73. La necesidad de rescate con opiáceos fue menor a 1 dosis en el 71,3%. La puntuación de dolor en los días postoperatorios 1, 3, 7 y 21 fue, en promedio, de 2,55; 2,01; 0,5 y 0,06, respectivamente. Conclusiones: El empleo de la crioanalgesia toracoscópica bilateral permitió el alta hospitalaria temprana y buen control del dolor postoperatorio en todos los casos, convirtiéndose en el método analgésico de elección en nuestra práctica clínica
RAYYAN-INCLUSION: {"Maria"=>"Included", "Jorge Andres"=>"Included"}
Keywords: Adolescente; Cirugía Torácica/métodos; Crioanestesia/instrumentación; Crioanestesia/métodos; Crioanestesia/tendencias; Dolor Postoperatorio/terapia; Estudios Retrospectivos; Femenino; Humanos; Manejo del Dolor; Masculino; Nervios Intercostales; Niño; Procedimientos Quirúrgicos Mínimamente Invasivos/métodos; Toracoscopía/métodos

Percutaneous Cryoanalgesia: A New Strategy for Pain Management in Pectus Excavatum Surgery. - Velayos, María; Alonso, Mercedes; Delgado-Miguel, Carlos; Estefanía-Fernández, Karla; Muñoz-Serrano, Antonio J.; Santamaría, Manuel V. López; Reinoso-Barbero, Francisco; De La Torre, Carlos A. (European Journal of Pediatric Surgery, 2022)

Nuss procedure for Pectus excavatum repair: critical appraisal of the evidence - Araújo, Maria Elizete De Almeida; Penha, Anderson Da Paz; Westphal, Fernando Luiz; Silva, Marcus Tolentino; Galvão, Taís Freire (Revista do Colégio Brasileiro de Cirurgiões, 2014)
Objective: To evaluate the effectiveness and safety of correction of pectus excavatum by the Nuss technique based on the available scientific evidence.Methods: We conducted an evidence synthesis following systematic processes of search, selection, extraction and critical appraisal. Outcomes were classified by importance and had their quality assessed by the Grading of Recommendations Assessment, Development and Evaluation (GRADE).Results: The process of selection of items led to the inclusion of only one systematic review, which synthesized the results of nine observational studies comparing the Nuss and Ravitch procedures. The evidence found was rated as poor and very poor quality. The Nuss procedure has increased the incidence of hemothorax (RR = 5.15; 95% CI: 1.07; 24.89), pneumothorax (RR = 5.26; 95% CI: 1.55; 17.92) and the need for reintervention (RR = 4.88; 95% CI: 2.41; 9.88) when compared to the Ravitch. There was no statistical difference between the two procedures in outcomes: general complications, blood transfusion, hospital stay and time to ambulation. The Nuss operation was faster than the Ravitch (mean difference [MD] = -69.94 minutes, 95% CI: -139.04, -0.83).Conclusion: In the absence of well-designed prospective studies to clarify the evidence, especially in terms of aesthetics and quality of life, surgical indication should be individualized and the choice of the technique based on patient preference and experience of the team. , Objetivo: avaliar a efetividade e segurança da correção de pectus excavatum, através da técnica de Nuss, com base nas evidências científicas disponíveis.Métodos: realizou-se uma síntese de evidências seguindo processos sistemáticos de busca, seleção, extração e avaliação crítica. Os desfechos foram classificados pela importância e tiveram sua qualidade avaliada pela ferramenta Grading of Recommendations Assessment, Development and Evaluation (GRADE).Resultados: O processo de seleção dos artigos culminou na inclusão de apenas uma revisão sistemática, a qual sintetizou os resultados de nove estudos observacionais comparando o procedimento de Nuss e ao de Ravitch. A evidência encontrada foi classificada como baixa e muito baixa qualidade. O procedimento de Nuss causou maior incidência de hemotórax (RR=5,15; IC95%: 1,07; 24,89), pneumotórax (RR=5,26; IC95%: 1,55; 17,92) e necessidade de reintervenção operatória (RR=4,88; IC95%: 2,41; 9,88) quando comparado ao de Ravitch. Não houve diferença estatística entre os dois procedimentos nos desfechos: complicações gerais, transfusão de sangue, tempo de hospitalização e tempo para deambulação. A operação de Nuss foi mais rápida que a de Ravitch (diferença média [MD] = -69,94 minutos; IC95%: -139,04, -0,83).Conclusão: Na ausência de estudos prospectivos bem delineados para clarificar a evidência, sobretudo quanto à estética e à qualidade de vida, a indicação operatória deve ser individualizada e a escolha da técnica baseada na preferência do paciente e experiência da equipe.

Pectus excavatum and carinatum - Cobben, Jan M.; Oostra, Roelof-Jan; Van Dijk, Fleur S. (European Journal of Medical Genetics, 2014)

Current Concepts in the Etiology and Pathogenesis of Pectus Excavatum in Humans—A Systematic Review - David, Vlad Laurentiu (Journal of Clinical Medicine, 2022)
Pectus excavatum (PE) is the most common deformity of the chest wall and is characterized by the posterior depression of the sternum and the lower costal cartilages. To date, the etiology of PE in humans remains enigmatic. Several etiologic hypotheses have been proposed over the past two centuries. However, most of them have been scientifically dismissed and now have only historic value. In this systematic review, we assess scientific publications of the past two centuries addressing the issue of the origin of PE in humans. We present and discuss the histologic, genetic, biomechanical, and experimental scientific achievements that contributed to the clarification of its etiology and pathogenesis. With no clear consensus over the exact mechanism, most recent studies agree that the primordial defect leading the deformation of the anterior chest wall in PE is related to the costal hyaline cartilage structure and function. Further studies on this subject must be carried out. Genetic studies seem to be the most promising way to understand the exact mechanism of PE’s origin and pathogenesis.

Nuss procedure for Pectus excavatum repair: critical appraisal of the evidence - Araújo, Maria Elizete De Almeida; Penha, Anderson Da Paz; Westphal, Fernando Luiz; Silva, Marcus Tolentino; Galvão, Taís Freire (Revista do Colégio Brasileiro de Cirurgiões, 2014)
Objective: To evaluate the effectiveness and safety of correction of pectus excavatum by the Nuss technique based on the available scientific evidence.Methods: We conducted an evidence synthesis following systematic processes of search, selection, extraction and critical appraisal. Outcomes were classified by importance and had their quality assessed by the Grading of Recommendations Assessment, Development and Evaluation (GRADE).Results: The process of selection of items led to the inclusion of only one systematic review, which synthesized the results of nine observational studies comparing the Nuss and Ravitch procedures. The evidence found was rated as poor and very poor quality. The Nuss procedure has increased the incidence of hemothorax (RR = 5.15; 95% CI: 1.07; 24.89), pneumothorax (RR = 5.26; 95% CI: 1.55; 17.92) and the need for reintervention (RR = 4.88; 95% CI: 2.41; 9.88) when compared to the Ravitch. There was no statistical difference between the two procedures in outcomes: general complications, blood transfusion, hospital stay and time to ambulation. The Nuss operation was faster than the Ravitch (mean difference [MD] = -69.94 minutes, 95% CI: -139.04, -0.83).Conclusion: In the absence of well-designed prospective studies to clarify the evidence, especially in terms of aesthetics and quality of life, surgical indication should be individualized and the choice of the technique based on patient preference and experience of the team. , Objetivo: avaliar a efetividade e segurança da correção de pectus excavatum, através da técnica de Nuss, com base nas evidências científicas disponíveis.Métodos: realizou-se uma síntese de evidências seguindo processos sistemáticos de busca, seleção, extração e avaliação crítica. Os desfechos foram classificados pela importância e tiveram sua qualidade avaliada pela ferramenta Grading of Recommendations Assessment, Development and Evaluation (GRADE).Resultados: O processo de seleção dos artigos culminou na inclusão de apenas uma revisão sistemática, a qual sintetizou os resultados de nove estudos observacionais comparando o procedimento de Nuss e ao de Ravitch. A evidência encontrada foi classificada como baixa e muito baixa qualidade. O procedimento de Nuss causou maior incidência de hemotórax (RR=5,15; IC95%: 1,07; 24,89), pneumotórax (RR=5,26; IC95%: 1,55; 17,92) e necessidade de reintervenção operatória (RR=4,88; IC95%: 2,41; 9,88) quando comparado ao de Ravitch. Não houve diferença estatística entre os dois procedimentos nos desfechos: complicações gerais, transfusão de sangue, tempo de hospitalização e tempo para deambulação. A operação de Nuss foi mais rápida que a de Ravitch (diferença média [MD] = -69,94 minutos; IC95%: -139,04, -0,83).Conclusão: Na ausência de estudos prospectivos bem delineados para clarificar a evidência, sobretudo quanto à estética e à qualidade de vida, a indicação operatória deve ser individualizada e a escolha da técnica baseada na preferência do paciente e experiência da equipe.

Implementation of a Cryoablation-based Pain Management Protocol for Pectus Excavatum - Cockrell, Hannah C.; Hrachovec, Jennifer; Schnuck, Jamie; Nchinda, Nzuekoh; Meehan, John (Journal of Pediatric Surgery, 2023)

Implementation of a Cryoablation-based Pain Management Protocol for Pectus Excavatum - Cockrell, Hannah C.; Hrachovec, Jennifer; Schnuck, Jamie; Nchinda, Nzuekoh; Meehan, John (Journal of Pediatric Surgery, 2023)

The physiologic impact of pectus excavatum repair - Obermeyer, Robert J.; Cohen, Nina S.; Jaroszewski, Dawn E. (Seminars in Pediatric Surgery, 2018)

Camargo_M .docx (Google Docs)
EFECTIVIDAD DE LA CRIOABLACIÓN EN EL MANEJO DE DOLOR POSTOPERATORIO POSTERIOR A PROCEDIMIENTO DE NUSS: REVISIÓN SISTEMÁTICA. MARIA ISABEL CRISTINA CAMARGO AREYANES UNIVERSIDAD DEL ROSARIO ESCUELA DE MEDICINA Y CIENCIAS DE LA SALUD UNIVERSIDAD CES FACULTAD DE MEDICINA ESPECIA...
https://doi.org/10.3390/jcm11051241

Pectus excavatum: historical background, clinical picture, preoperative evaluation and criteria for operation - Kelly, Robert E. (Seminars in Pediatric Surgery, 2008)

Camargo_M .docx (Google Docs)
EFECTIVIDAD DE LA CRIOABLACIÓN EN EL MANEJO DE DOLOR POSTOPERATORIO POSTERIOR A PROCEDIMIENTO DE NUSS: REVISIÓN SISTEMÁTICA. MARIA ISABEL CRISTINA CAMARGO AREYANES UNIVERSIDAD DEL ROSARIO ESCUELA DE MEDICINA Y CIENCIAS DE LA SALUD UNIVERSIDAD CES FACULTAD DE MEDICINA ESPECIA...
https://doi.org/10.1016/j.athoracsur.2021.07.051

The Severity of Pectus Excavatum Defect Is Associated With Impaired Cardiopulmonary Function - Zens, Tiffany J.; Casar Berazaluce, Alejandra M.; Jenkins, Todd M.; Hardie, William; Alsaied, Tarek; Tretter, Justin T.; Moore, Ryan; Foster, Karla; Fleck, Robert J.; Hanke, Rachel E.; Colvin, Brandon E.; Garrison, Aaron P.; et al. (The Annals of Thoracic Surgery, 2022)

Comparison of the Nuss versus Ravitch procedure for pectus excavatum repair: an updated meta-analysis - Mao, Yong Zhong; Tang, ShaoTao; Li, Shuai (Journal of Pediatric Surgery, 2017)

Outcomes, quality of life, and long-term results after pectus repair from around the globe - Kelly, Robert E.; Daniel, Antarius (Seminars in Pediatric Surgery, 2018)

Use of transthoracic cryoanalgesia during the Nuss procedure - Kim, Sunghoon; Idowu, Olajire; Palmer, Barnard; Lee, Sang H. (The Journal of Thoracic and Cardiovascular Surgery, 2016)

Epidural analgesia versus patient-controlled intravenous analgesia for pain following intra-abdominal surgery in adults - Salicath, Jon H; Yeoh, Emily Cy; Bennett, Michael H (Cochrane Database of Systematic Reviews, 2018)

Bloqueo paravertebral - Theissen, A.; Marret, E.; Sultan, W.; Niccolai, P.; Raucoules-Aimé, M. (EMC - Anestesia-Reanimación, 2014)

Postoperative epidural analgesia versus systemic analgesia for thoraco-lumbar spine surgery in children - Guay, Joanne; Suresh, Santhanam; Kopp, Sandra; Johnson, Rebecca L (Cochrane Database of Systematic Reviews, 2019)

Diagnosis and treatment of acute appendicitis: 2020 update of the WSES Jerusalem guidelines - Di Saverio, Salomone; Podda, Mauro; De Simone, Belinda; Ceresoli, Marco; Augustin, Goran; Gori, Alice; Boermeester, Marja; Sartelli, Massimo; Coccolini, Federico; Tarasconi, Antonio; De’ Angelis, Nicola; Weber, Dieter G.; et al. (World Journal of Emergency Surgery, 2020)
Abstract Background and aims Acute appendicitis (AA) is among the most common causes of acute abdominal pain. Diagnosis of AA is still challenging and some controversies on its management are still present among different settings and practice patterns worldwide. In July 2015, the World Society of Emergency Surgery (WSES) organized in Jerusalem the first consensus conference on the diagnosis and treatment of AA in adult patients with the intention of producing evidence-based guidelines. An updated consensus conference took place in Nijemegen in June 2019 and the guidelines have now been updated in order to provide evidence-based statements and recommendations in keeping with varying clinical practice: use of clinical scores and imaging in diagnosing AA, indications and timing for surgery, use of non-operative management and antibiotics, laparoscopy and surgical techniques, intra-operative scoring, and peri-operative antibiotic therapy. Methods This executive manuscript summarizes the WSES guidelines for the diagnosis and treatment of AA. Literature search has been updated up to 2019 and statements and recommendations have been developed according to the GRADE methodology. The statements were voted, eventually modified, and finally approved by the participants to the consensus conference and by the board of co-authors, using a Delphi methodology for voting whenever there was controversy on a statement or a recommendation. Several tables highlighting the research topics and questions, search syntaxes, and the statements and the WSES evidence-based recommendations are provided. Finally, two different practical clinical algorithms are provided in the form of a flow chart for both adults and pediatric (< 16 years old) patients. Conclusions The 2020 WSES guidelines on AA aim to provide updated evidence-based statements and recommendations on each of the following topics: (1) diagnosis, (2) non-operative management for uncomplicated AA, (3) timing of appendectomy and in-hospital delay, (4) surgical treatment, (5) intra-operative grading of AA, (6) ,management of perforated AA with phlegmon or abscess, and (7) peri-operative antibiotic therapy.

Acute appendicitis: proposal of a new comprehensive grading system based on clinical, imaging and laparoscopic findings - Gomes, Carlos Augusto; Sartelli, Massimo; Di Saverio, Salomone; Ansaloni, Luca; Catena, Fausto; Coccolini, Federico; Inaba, Kenji; Demetriades, Demetrios; Gomes, Felipe Couto; Gomes, Camila Couto (World Journal of Emergency Surgery, 2015)

Acute appendicitis: proposal of a new comprehensive grading system based on clinical, imaging and laparoscopic findings - Gomes, Carlos Augusto; Sartelli, Massimo; Di Saverio, Salomone; Ansaloni, Luca; Catena, Fausto; Coccolini, Federico; Inaba, Kenji; Demetriades, Demetrios; Gomes, Felipe Couto; Gomes, Camila Couto (World Journal of Emergency Surgery, 2015)

Appendicitis - Prystowsky, Jay B.; Pugh, Carla M.; Nagle, Alex P. (Current Problems in Surgery, 2005)

Early versus delayed (interval) appendicectomy for the management of appendicular abscess and phlegmon: a systematic review and meta-analysis - Akingboye, Akinfemi A.; Mahmood, Fahad; Zaman, Shafquat; Wright, Jenny; Mannan, Fatima; Mohamedahmed, Ali Yasen Y. (Langenbeck's Archives of Surgery, 2021)

A Retrospective Analysis of Conservative Management Versus Early Surgical Intervention in Appendicular Lump - Das, Bhupati Bhusan; Nayak, Kedar Nath; Mohanty, Sujit Kumar; Sahoo, Ashok Kumar (Cureus, 2022)

Implications of bacteriological study in complicated and uncomplicated acute appendicitis - Cimpean, Sorin; Barranquero, Alberto Gonzalez; Surdeanu, Ion; Cadiere, Benjamin; Cadiere, Guy-Bernard (Annals of Coloproctology, 2022)

The Peritoneum: Beyond the Tissue – A Review - Isaza-Restrepo, Andres; Martin-Saavedra, Juan S.; Velez-Leal, Juan L.; Vargas-Barato, Felipe; Riveros-Dueñas, Rafael (Frontiers in Physiology, 2018)
Background: Despite its complexity, the peritoneum is usually underestimated in classical medical texts simply as the surrounding tissue (serous membrane) of the gut. Novel findings on physiology and morphology of the peritoneum and mesothelial cell exist but they are usually focused or limited to Continuous Ambulatory Peritoneal Dialysis research and practice. This review aims to expose, describe and analyze the most recent evidence on the peritoneum’s morphology, embryology and physiology., Materials and Methods: A literature review was performed on Pubmed and MEDLINE. With no limit of publication date, original papers and literature reviews about the peritoneum, the peritoneal cavity, peritoneal fluid, and mesothelial cells were included (n = 72)., Results: Peritoneum develops in close relationship to the gut from an early period in embryogenesis. Analyzing together the development of the primitive gut and the surrounding mesothelium helps understanding that the peritoneal cavity, the mesenteries and other structures can be considered parts of the peritoneum. However, some authors consider that structures like the mesenteries are different to the peritoneum. The mesothelial cell has a complex ultrastructural organization with intercellular junctions and apical microvilli. This complexity is further proven by the large array of functions like selective fluid and cell transport; physiological protective barrier; immune induction, modulation, and inhibition; tissue repair and scarring; preventing adhesion and tumoral dissemination; cellular migration; and the epithelial-mesenchymal transition capacity., Conclusion: Recent evidence on the anatomy, histology, and physiology of the peritoneum, shows that this structure is more complex than a simple serous membrane. These results call for a new conceptualization of peritoneum, and highlight the need of adequate research for identifying clinical relevance of this knowledge.

Epidemiology, Pathophysiology, and Treatment of Diverticulitis - Strate, Lisa L.; Morris, Arden M. (Gastroenterology, 2019)

Emergency Presentations of Diverticulitis - Meara, Michael P.; Alexander, Colleen M. (Surgical Clinics of North America, 2018)

2020 update of the WSES guidelines for the management of acute colonic diverticulitis in the emergency setting - Sartelli, Massimo; Weber, Dieter G.; Kluger, Yoram; Ansaloni, Luca; Coccolini, Federico; Abu-Zidan, Fikri; Augustin, Goran; Ben-Ishay, Offir; Biffl, Walter L.; Bouliaris, Konstantinos; Catena, Rodolfo; Ceresoli, Marco; et al. (World Journal of Emergency Surgery, 2020)
Abstract Acute colonic diverticulitis is one of the most common clinical conditions encountered by surgeons in the acute setting. An international multidisciplinary panel of experts from the World Society of Emergency Surgery (WSES) updated its guidelines for management of acute left-sided colonic diverticulitis (ALCD) according to the most recent available literature. The update includes recent changes introduced in the management of ALCD. The new update has been further integrated with advances in acute right-sided colonic diverticulitis (ARCD) that is more common than ALCD in select regions of the world.

Randomized clinical trial of antibiotics in acute uncomplicated diverticulitis13 - for the AVOD Study Group; Chabok, A; Påhlman, L; Hjern, F; Haapaniemi, S; Smedh, K (British Journal of Surgery, 2012)
Abstract Background The standard of care for acute uncomplicated diverticulitis today is antibiotic treatment, although there are no controlled studies supporting this management. The aim was to investigate the need for antibiotic treatment in acute uncomplicated diverticulitis, with the endpoint of recovery without complications after 12 months of follow-up. Methods This multicentre randomized trial involving ten surgical departments in Sweden and one in Iceland recruited 623 patients with computed tomography-verified acute uncomplicated left-sided diverticulitis. Patients were randomized to treatment with (314 patients) or without (309 patients) antibiotics. Results Age, sex, body mass index, co-morbidities, body temperature, white blood cell count and C-reactive protein level on admission were similar in the two groups. Complications such as perforation or abscess formation were found in six patients (1·9 per cent) who received no antibiotics and in three (1·0 per cent) who were treated with antibiotics (P = 0·302). The median hospital stay was 3 days in both groups. Recurrent diverticulitis necessitating readmission to hospital at the 1-year follow-up was similar in the two groups (16 per cent, P = 0·881). Conclusion Antibiotic treatment for acute uncomplicated diverticulitis neither accelerates recovery nor prevents complications or recurrence. It should be reserved for the treatment of complicated diverticulitis. Registration number: NCT01008488 (http://www.clinicaltrials.gov).

A systematic review and meta-analysis of outpatient treatment for acute diverticulitis - Van Dijk, S. T.; Bos, K.; De Boer, M. G. J.; Draaisma, W. A.; Van Enst, W. A.; Felt, R. J. F.; Klarenbeek, B. R.; Otte, J. A.; Puylaert, J. B. C. M.; Van Geloven, A. A. W.; Boermeester, M. A. (International Journal of Colorectal Disease, 2018)

From Open to Bedside Percutaneous Tracheostomy - Kidane, Biniam; Pierre, Andrew F. (Thoracic Surgery Clinics, 2018)

Failure of Abdominal Wall Closure - Zolin, Samuel J.; Rosen, Michael J. (Surgical Clinics of North America, 2021)

Failure of Abdominal Wall Closure - Zolin, Samuel J.; Rosen, Michael J. (Surgical Clinics of North America, 2021)

Updated guideline for closure of abdominal wall incisions from the European and American Hernia Societies - Deerenberg, Eva B; Henriksen, Nadia A; Antoniou, George A; Antoniou, Stavros A; Bramer, Wichor M; Fischer, John P; Fortelny, Rene H; Gök, Hakan; Harris, Hobart W; Hope, William; Horne, Charlotte M; Jensen, Thomas K; et al. (British Journal of Surgery, 2022)
Abstract Background Incisional hernia is a frequent complication of abdominal wall incision. Surgical technique is an important risk factor for the development of incisional hernia. The aim of these updated guidelines was to provide recommendations to decrease the incidence of incisional hernia. Methods A systematic literature search of MEDLINE, Embase, and Cochrane CENTRAL was performed on 22 January 2022. The Scottish Intercollegiate Guidelines Network instrument was used to evaluate systematic reviews and meta-analyses, RCTs, and cohort studies. The GRADE approach (Grading of Recommendations, Assessment, Development and Evaluation) was used to appraise the certainty of the evidence. The guidelines group consisted of surgical specialists, a biomedical information specialist, certified guideline methodologist, and patient representative. Results Thirty-nine papers were included covering seven key questions, and weak recommendations were made for all of these. Laparoscopic surgery and non-midline incisions are suggested to be preferred when safe and feasible. In laparoscopic surgery, suturing the fascial defect of trocar sites of 10 mm and larger is advised, especially after single-incision laparoscopic surgery and at the umbilicus. For closure of an elective midline laparotomy, a continuous small-bites suturing technique with a slowly absorbable suture is suggested. Prophylactic mesh augmentation after elective midline laparotomy can be considered to reduce the risk of incisional hernia; a permanent synthetic mesh in either the onlay or retromuscular position is advised. Conclusion These updated guidelines may help surgeons in selecting the optimal approach and location of abdominal wall incisions.

Importancia del conocimiento anatómico del espacio extraperitoneal y su utilidad en los abordajes quirúrgicos - Ramírez-Giraldo, Camilo; Luque-Bernal, Ricardo Miguel; Buitrago-Rincón, María Camila (Revista Colombiana de Cirugía, 2023)
Introducción. El espacio extraperitoneal, se define como el segmento topográfico ubicado entre el peritoneo parietal internamente y la fascia transversalis externamente. Como resultado del desarrollo y consolidación de la cirugía laparoscópica, en particular de la herniorrafia inguinal por esta vía, se ha presentado un renovado y creciente interés en esta área anatómica, debido a la importancia de su conocimiento detallado en la cirugía de mínima invasión. Métodos. Se hizo una revisión narrativa de la literatura para presentar una información actualizada y detallada sobre la anatomía del espacio extraperitoneal y su importancia en diferentes procedimientos quirúrgicos realizados actualmente. Resultados. Por fuera del espacio peritoneal, se encuentran las áreas anatómicas externas al peritoneo parietal, que incluyen la preperitoneal y la retroperitoneal. Mediante la laparoscopia, se pueden localizar en estos espacios cinco triángulos anatómicos, además de la corona mortis y el triángulo supra vesical. Conclusión. El conocimiento del espacio extraperitoneal es de gran importancia para el cirujano general, teniendo en cuenta los múltiples procedimientos que requieren el abordaje de esta área topográfica.

Inguinal Hernia - Miller, Heidi J. (Surgical Clinics of North America, 2018)

Acute Pancreatitis: A Review - Mederos, Michael A.; Reber, Howard A.; Girgis, Mark D. (JAMA, 2021)

Small Bowel Obstruction - Bower, Katie Love; Lollar, Daniel I.; Williams, Sharon L.; Adkins, Farrell C.; Luyimbazi, David T.; Bower, Curtis E. (Surgical Clinics of North America, 2018)

Bologna guidelines for diagnosis and management of adhesive small bowel obstruction (ASBO): 2017 update of the evidence-based guidelines from the world society of emergency surgery ASBO working group - Ten Broek, Richard P. G.; Krielen, Pepijn; Di Saverio, Salomone; Coccolini, Federico; Biffl, Walter L.; Ansaloni, Luca; Velmahos, George C.; Sartelli, Massimo; Fraga, Gustavo P.; Kelly, Michael D.; Moore, Frederick A.; Peitzman, Andrew B.; et al. (World Journal of Emergency Surgery, 2018)

Surgical Techniques for Parastomal Hernia Repair: A Systematic Review of the Literature - Hansson, Birgitta M.E.; Slater, Nicholas J.; Van Der Velden, Arjan Schouten; Groenewoud, Hans M.M.; Buyne, Otmar R.; De Hingh, Ignace H.J.T.; Bleichrodt, Rob P. (Annals of Surgery, 2012)

Parastomal Hernia Repair - Shah, Nilay R.; Craft, Randall O.; Harold, Kristi L. (Surgical Clinics of North America, 2013)

European Hernia Society classification of parastomal hernias - Śmietański, M.; Szczepkowski, M.; Alexandre, J. A.; Berger, D.; Bury, K.; Conze, J.; Hansson, B.; Janes, A.; Miserez, M.; Mandala, V.; Montgomery, A.; Morales Conde, S.; et al. (Hernia, 2014)

Nueva técnica para reparación de hernia paraestomal: «Técnica IVO» - Carbonell Tatay, Fernando; Trallero Anoro, Marta; Campos Máñez, Jorge; Caballero Soto, María; García Fadrique, Alfonso; Martínez Blasco, Amparo; Estevan Estevan, Rafael (REVISTA HISPANOAMERICANA DE HERNIA, 2017)
Introducción: La hernia paraestomal o estomal es una complicación a largo plazo de los estomas que limita la calidad de vida de los pacientes. No está establecido cuál es la mejor técnica ni la mejor vía de abordaje para su reparación. Describimos una nueva técnica usada en casos de eventración paraestomal con eventración de línea media asociada o sin ella. Material y métodos: Fueron intervenidos 15 pacientes con esta técnica (9 con colostomía y 6 con urostomía), que se realiza con abordaje abierto y que combina el uso de una malla intraperitoneal (IPST®) y una separación de componentes con malla de polipropileno supraaponeurótica y nuevas inserciones musculares.Esta técnica ha sido desarrollada por el Servicio de Cirugía del Instituto Valenciano de Oncología (IVO), por lo que los autores la han denominado «Técnica IVO para reparación de hernia paraestomal». Resultados: La estancia media fue 5.6 días. Dos pacientes (13.3 %) presentaron un seroma de herida. No hubo casos de infección de herida quirúrgica, necrosis cutánea ni recidiva de la eventración. El seguimiento medio fue de 16 meses (2-48 meses).Conclusiones: La técnica IVO es segura y reproducible, y permite cerrar los defectos sin tensión, restablecer la biomecánica de la pared y reforzar la zona paraestomal y la línea media. Es necesario un mayor número de casos y mayor tiempo de seguimiento para evaluar su defi nitiva efi cacia a largo plazo.

Nueva técnica para reparación de hernia paraestomal: «Técnica IVO» - Carbonell Tatay, Fernando; Trallero Anoro, Marta; Campos Máñez, Jorge; Caballero Soto, María; García Fadrique, Alfonso; Martínez Blasco, Amparo; Estevan Estevan, Rafael (REVISTA HISPANOAMERICANA DE HERNIA, 2017)
Introducción: La hernia paraestomal o estomal es una complicación a largo plazo de los estomas que limita la calidad de vida de los pacientes. No está establecido cuál es la mejor técnica ni la mejor vía de abordaje para su reparación. Describimos una nueva técnica usada en casos de eventración paraestomal con eventración de línea media asociada o sin ella. Material y métodos: Fueron intervenidos 15 pacientes con esta técnica (9 con colostomía y 6 con urostomía), que se realiza con abordaje abierto y que combina el uso de una malla intraperitoneal (IPST®) y una separación de componentes con malla de polipropileno supraaponeurótica y nuevas inserciones musculares.Esta técnica ha sido desarrollada por el Servicio de Cirugía del Instituto Valenciano de Oncología (IVO), por lo que los autores la han denominado «Técnica IVO para reparación de hernia paraestomal». Resultados: La estancia media fue 5.6 días. Dos pacientes (13.3 %) presentaron un seroma de herida. No hubo casos de infección de herida quirúrgica, necrosis cutánea ni recidiva de la eventración. El seguimiento medio fue de 16 meses (2-48 meses).Conclusiones: La técnica IVO es segura y reproducible, y permite cerrar los defectos sin tensión, restablecer la biomecánica de la pared y reforzar la zona paraestomal y la línea media. Es necesario un mayor número de casos y mayor tiempo de seguimiento para evaluar su defi nitiva efi cacia a largo plazo.

Major Abdominal Trauma - Brenner, Megan; Hicks, Christopher (Emergency Medicine Clinics of North America, 2018)

Detection of Anastomotic Leakage Following Elective Colonic Surgery: Results of the Prospective Biomarkers and Anastomotic Leakage (BALL) Study - Su'a, Bruce; Milne, Tony; Jaung, Rebekah; Jin, James Z.; Svirskis, Darren; Bissett, Ian P.; Eglinton, Tim; Hill, Andrew G. (Journal of Surgical Research, 2022)

Management of Colorectal Anastomotic Leak - Thomas, Michael; Margolin, David (Clinics in Colon and Rectal Surgery, 2016)

Management of Colorectal Anastomotic Leak - Thomas, Michael; Margolin, David (Clinics in Colon and Rectal Surgery, 2016)

Role of the triad of procalcitonin, C-reactive protein, and white blood cell count in the prediction of anastomotic leak following colorectal resections - El Zaher, Haidi Abd; Ghareeb, Waleed M.; Fouad, Ahmed M.; Madbouly, Khaled; Fathy, Hamada; Vedin, Tomas; Edelhamre, Marcus; Emile, Sameh H.; Faisal, Mohammed (World Journal of Surgical Oncology, 2022)
Abstract Purpose The enhanced recovery after surgery (ERAS) program expedites patient recovery after major surgery. This study aimed to investigate the role of the triad of procalcitonin (PCT), C-reactive protein (CRP), and white blood cells (WBC) trajectories as a predictive biomarker for the anastomotic leak (AL) after colorectal surgery. Method Patients who had colorectal anastomosis were prospectively included. Postoperative clinical and laboratory parameters and outcomes were collected and analyzed. The 5-day trajectories of PCT, CRP, and WBC were evaluated. Based on the trajectory of the three biomarkers, we compared patients with and without AL as detected during the first 30 days after surgery using the area under receiver operator characteristic curves (AUC) for logistic estimation. Results This study included 205 patients, of whom 56% were men and 43.9% were women with a mean age of 56.4 ± 13.1 years. Twenty-two patients (10.7%) had AL; 77.3% underwent surgery, and 22.7% were treated with drainage and antibiotics. Procalcitonin was the best predictor for AL compared to CRP and WBC at three days postoperatively (AUC: 0.84, 0.76, 0.66, respectively). On day 5, a cutoff value of 4.93 ng/mL for PCT had the highest sensitivity, specificity, and negative predictive value. The predictive power of PCT was substantially improved when combined with either CRP or WBC, or both (AUC: 0.92, 0.92, 0.93, respectively). Conclusion The 5-day trajectories of combined CRP, PCT, and WBC had a better predictive power for AL than the isolated daily measurements. Combining the three parameters may be a reliable predictor of early patient discharge, which would be highly beneficial to ERAS programs.

Guías basadas en la evidencia para el uso de traqueostomía en el paciente crítico - Raimondi, N.; Vial, M.R.; Calleja, J.; Quintero, A.; Cortés Alban, A.; Celis, E.; Pacheco, C.; Ugarte, S.; Añón, J.M.; Hernández, G.; Vidal, E.; Chiappero, G.; et al. (Medicina Intensiva, 2017)

Tracheostomy Emergencies - Bontempo, Laura J.; Manning, Sara L. (Emergency Medicine Clinics of North America, 2019)

Surgery of the trachea and bronchi - Grillo, Hermes C. (BC Decker, 2004)

From Open to Bedside Percutaneous Tracheostomy - Frcsc, Biniam Kidane

Superior mesenteric artery syndrome: Diagnosis and management - Oka, Akihiko; Awoniyi, Muyiwa; Hasegawa, Nobuaki; Yoshida, Yuri; Tobita, Hiroshi; Ishimura, Norihisa; Ishihara, Shunji (World Journal of Clinical Cases, 2023)

Wilkie’s syndrome - Farina, Renato; Foti, Pietro Valerio; Cocuzza, Giuseppe; Costanzo, Valeria; Costanzo, Giuliana; Conti, Alessandro; Torcitto, Alfredo; Pennisi, Monica (Journal of Ultrasound, 2017)

Tubes and Drains - ClinicalKey

Development of the human pancreas and its vasculature — An integrated review covering anatomical, embryological, histological, and molecular aspects - Henry, Brandon Michael; Skinningsrud, Bendik; Saganiak, Karolina; Pękala, Przemysław A.; Walocha, Jerzy A.; Tomaszewski, Krzysztof A. (Annals of Anatomy - Anatomischer Anzeiger, 2019)

Acute pancreatitis - Boxhoorn, Lotte; Voermans, Rogier P; Bouwense, Stefan A; Bruno, Marco J; Verdonk, Robert C; Boermeester, Marja A; Van Santvoort, Hjalmar C; Besselink, Marc G (The Lancet, 2020)

Aggressive or Moderate Fluid Resuscitation in Acute Pancreatitis - de-Madaria, Enrique; Buxbaum, James L.; Maisonneuve, Patrick; García García De Paredes, Ana; Zapater, Pedro; Guilabert, Lucía; Vaillo-Rocamora, Alicia; Rodríguez-Gandía, Miguel Á.; Donate-Ortega, Jesús; Lozada-Hernández, Edgard E.; Collazo Moreno, Alan J.R.; Lira-Aguilar, Alba; et al. (New England Journal of Medicine, 2022)

A critical evaluation of laboratory tests in acute pancreatitis - Yadav, Dhiraj; Agarwal, N.; Pitchumoni, C.S. (The American Journal of Gastroenterology, 2002)

Acute Pancreatitis: Diagnosis and Treatment - Szatmary, Peter; Grammatikopoulos, Tassos; Cai, Wenhao; Huang, Wei; Mukherjee, Rajarshi; Halloran, Chris; Beyer, Georg; Sutton, Robert (Drugs, 2022)

2019 WSES guidelines for the management of severe acute pancreatitis - Leppäniemi, Ari; Tolonen, Matti; Tarasconi, Antonio; Segovia-Lohse, Helmut; Gamberini, Emiliano; Kirkpatrick, Andrew W.; Ball, Chad G.; Parry, Neil; Sartelli, Massimo; Wolbrink, Daan; Van Goor, Harry; Baiocchi, Gianluca; et al. (World Journal of Emergency Surgery, 2019)

Imaging guidelines for acute pancreatitis: when and when not to image - Rocha, Ana Paola Campos; Schawkat, Khoschy; Mortele, Koenraad J. (Abdominal Radiology, 2020)

Management of Enterocutaneous Fistula: A Review - Ghimire, Pradeep (Journal of Nepal Medical Association, 2022)
Enterocutaneous fistula is any communication between bowel and skin or atmosphere outside the body. It can be classified by various means by etiology, organ of origin, etc. Enterocutaneous fistula can occur after any gastrointestinal surgery where there is some trauma during surgery or other associated causes such as malignancy, inflammatory bowel disease, foreign body, etc. Enterocutaneous fistula needs a multidisciplinary approach as its management is a very tedious and complex process. Sepsis, malnutrition, and dyselectrolytemia are three key factors during the management of enterocutaneous fistula, so these should be properly addressed for better and efficient outcomes. There is excess fistula effluent which should be replaced adequately in high output fistula. The nutrition of the patient plays a vital role in the success of enterocutaneous fistula management so if the patient can tolerate oral or enteral feeding should be commenced as soon as possible otherwise parenteral nutrition should be advised. Wound care should be done aggressively, proper skincare, timely drainage of any localised abscesses should be done. Patients should be properly resuscitated and stabilised before any definitive investigations and management. Surgical therapy can be staged and should not be rushed which results in failure of this complex disease process.

Treatment Strategies in 135 Consecutive Patients with Enterocutaneous Fistulas - Visschers, Ruben G. J.; Damink, Steven W. M. Olde; Winkens, Bjorn; Soeters, Peter B.; Van Gemert, Wim G. (World Journal of Surgery, 2008)
Abstract Background Enterocutaneous fistulas (ECF) pose a major challenge to every gastrointestinal (GI) surgeon. Based on earlier studies, a standardized treatment guideline was implemented. The focus of the present study was to assess that guideline and determine prognostic factors for outcome of patients with ECF, and to define a more detailed therapeutic approach including the convalescence time before restorative surgery. Methods All patients with ECF treated between 1990 and 2005 were included. Management consisted of controlling Sepsis, Optimization of nutritional state, Wound care, assessment of fistula Anatomy, Timing of surgery, and Surgical strategy (the SOWATS guideline). Prognostic factors were assessed by way of multiple logistic regression analysis. Results A total of 135 patients were treated at our unit. Overall closure was achieved in 118 patients (87.4%). Restorative operations for fistula closure were performed after a median of 53 days (range: 4–270 days). Restorative operations were successful in 97/107 patients (90.7%). Thirteen patients (9.6%) died. An abdominal wall defect was the most predominant negative prognostic factor for spontaneous closure (odds ratio [OR] = 0.195, confidence interval [CI] 0.052–0.726, p = 0.015). A strong relation was found between preoperative albumin level and surgical closure ( p < 0.001) and mortality ( p < 0.001). Conclusions Application of the SOWATS guideline allowed a favorable outcome after a short convalescence period. Abdominal wall defects and preoperative hypoalbuminemia are important prognostic variables.

ASPEN‐FELANPE Clinical Guidelines: Nutrition Support of Adult Patients With Enterocutaneous Fistula - Kumpf, Vanessa J.; De Aguilar‐Nascimento, Jose Eduardo; Diaz‐Pizarro Graf, Jose Ignacio; Hall, Amber M.; McKeever, Liam; Steiger, Ezra; Winkler, Marion F.; Compher, Charlene W.; FELANPE; American Society for Parenteral and Enteral Nutrition (Journal of Parenteral and Enteral Nutrition, 2017)
Background: The management of patients with enterocutaneous fistula (ECF) requires an interdisciplinary approach and poses a significant challenge to physicians, wound/stoma care specialists, dietitians, pharmacists, and other nutrition clinicians. Guidelines for optimizing nutrition status in these patients are often vague, based on limited and dated clinical studies, and typically rely on individual institutional or clinician experience. Specific nutrient requirements, appropriate route of feeding, role of immune‐enhancing formulas, and use of somatostatin analogues in the management of patients with ECF are not well defined. The purpose of this clinical guideline is to develop recommendations for the nutrition care of adult patients with ECF. Methods: A systematic review of the best available evidence to answer a series of questions regarding clinical management of adults with ECF was undertaken and evaluated using concepts adopted from the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) Working Group. An anonymous consensus process was used to develop the clinical guideline recommendations prior to peer review and approval by the ASPEN Board of Directors and by FELANPE. Questions: In adult patients with enterocutaneous fistula: (1) What factors best describe nutrition status? (2) What is the preferred route of nutrition therapy (oral diet, enteral nutrition, or parenteral nutrition)? (3) What protein and energy intake provide best clinical outcomes? (4) Is fistuloclysis associated with better outcomes than standard care? (5) Are immune‐enhancing formulas associated with better outcomes than standard formulas? (6) Does the use of somatostatin or somatostatin analogue provide better outcomes than standard medical therapy? (7) When is home parenteral nutrition support indicated?

TERAPIA NUTRICIA EN FÍSTULA ENTEROCUTÁNEA; DE LA BASE FISIOLÓGICA AL - Rodríguez Cano, Ameyalli Mariana (NUTRICION HOSPITALARIA, 2014)

Treatment of enterocutaneous fistula: a systematic review and meta-analysis - Gefen, R.; Garoufalia, Z.; Zhou, P.; Watson, K.; Emile, S. H.; Wexner, S. D. (Techniques in Coloproctology, 2022)

Treatment of enterocutaneous fistula: a systematic review and meta-analysis - Gefen, R.; Garoufalia, Z.; Zhou, P.; Watson, K.; Emile, S. H.; Wexner, S. D. (Techniques in Coloproctology, 2022)

Surgical Wound Misclassification: A Multicenter Evaluation - Levy, Shauna M.; Lally, Kevin P.; Blakely, Martin L.; Calkins, Casey M.; Dassinger, Melvin S.; Duggan, Eileen; Huang, Eunice Y.; Kawaguchi, Akemi L.; Lopez, Monica E.; Russell, Robert T.; St Peter, Shawn D.; Streck, Christian J.; et al. (Journal of the American College of Surgeons, 2015)

Surgical Wound Misclassification: A Multicenter Evaluation - Levy, Shauna M.; Lally, Kevin P.; Blakely, Martin L.; Calkins, Casey M.; Dassinger, Melvin S.; Duggan, Eileen; Huang, Eunice Y.; Kawaguchi, Akemi L.; Lopez, Monica E.; Russell, Robert T.; St Peter, Shawn D.; Streck, Christian J.; et al. (Journal of the American College of Surgeons, 2015)

Surgical Site Infections - Young, Pang Y.; Khadaroo, Rachel G. (Surgical Clinics of North America, 2014)

Stevens DL et al (Clin Infect Dis 2014; 59:147–59) (Clinical Infectious Diseases, 2015)

Practice Guidelines for the Diagnosis and Management of Skin and Soft Tissue Infections: 2014 Update by the Infectious Diseases Society of America - Stevens, Dennis L.; Bisno, Alan L.; Chambers, Henry F.; Dellinger, E. Patchen; Goldstein, Ellie J. C.; Gorbach, Sherwood L.; Hirschmann, Jan V.; Kaplan, Sheldon L.; Montoya, Jose G.; Wade, James C. (Clinical Infectious Diseases, 2014)
A panel of national experts was convened by the Infectious Diseases Society of America (IDSA) to update the 2005 guidelines for the treatment of skin and soft tissue infections (SSTIs). The panel's recommendations were developed to be concordant with the recently published IDSA guidelines for the treatment of methicillin-resistant Staphylococcus aureus infections. The focus of this guideline is the diagnosis and appropriate treatment of diverse SSTIs ranging from minor superficial infections to life-threatening infections such as necrotizing fasciitis. In addition, because of an increasing number of immunocompromised hosts worldwide, the guideline addresses the wide array of SSTIs that occur in this population. These guidelines emphasize the importance of clinical skills in promptly diagnosing SSTIs, identifying the pathogen, and administering effective treatments in a timely fashion.

Two-year results of the randomized clinical trial DILALA comparing laparoscopic lavage with resection as treatment for perforated diverticulitis - Kohl, A; Rosenberg, J; Bock, D; Bisgaard, T; Skullman, S; Thornell, A; Gehrman, J; Angenete, E; Haglind, E (British Journal of Surgery, 2018)
Abstract Background Traditionally, perforated diverticulitis with purulent peritonitis was treated with resection and colostomy (Hartmann's procedure), with inherent complications and risk of a permanent stoma. The DILALA (DIverticulitis – LAparoscopic LAvage versus resection (Hartmann's procedure) for acute diverticulitis with peritonitis) and other randomized trials found laparoscopic lavage to be a feasible and safe alternative. The medium-term follow-up results of DILALA are reported here. Methods Patients were randomized during surgery after being diagnosed with Hinchey grade III perforated diverticulitis at diagnostic laparoscopy. The primary outcome was the proportion of patients with one or more secondary operations from 0 to 24 months after the index procedure in the laparoscopic lavage versus Hartmann's procedure groups. The trial was registered as ISRCTN82208287. Results Forty-three patients were randomized to laparoscopic lavage and 40 to Hartmann's procedure. Patients in the lavage group had a 45 per cent reduced risk of undergoing one or more operations within 24 months (relative risk 0·55, 95 per cent c.i. 0·36 to 0·84; P = 0·012) and had fewer operations (ratio 0·51, 95 per cent c.i. 0·31 to 0·87; P = 0·024) compared with those in the Hartmann's group. No difference was found in mean number of readmissions (1·37 versus 1·50; P = 0·221) or mortality between patients randomized to laparoscopic lavage or Hartmann's procedure. Three patients in the lavage group and nine in the Hartmann's group had a colostomy at 24 months. Conclusion Laparoscopic lavage is a better option for perforated diverticulitis with purulent peritonitis than open resection and colostomy.

Laparoscopic Lavage vs Primary Resection for Acute Perforated Diverticulitis: Long-term Outcomes From the Scandinavian Diverticulitis (SCANDIV) Randomized Clinical Trial - Azhar, Najia; Johanssen, Anette; Sundström, Tove; Folkesson, Joakim; Wallon, Conny; Kørner, Hartvig; Blecic, Ljiljana; Forsmo, Håvard Mjørud; Øresland, Tom; Yaqub, Sheraz; Buchwald, Pamela; Schultz, Johannes Kurt; et al. (JAMA Surgery, 2021)

Laparoscopic peritoneal lavage versus sigmoidectomy for perforated diverticulitis with purulent peritonitis: three-year follow-up of the randomised LOLA trial - Hoek, Vincent T.; Edomskis, Pim P.; Stark, Pieter W.; Lambrichts, Daniel P. V.; Draaisma, Werner A.; Consten, Esther C. J.; Lange, Johan F.; Bemelman, Willem A.; The LADIES trial collaborators; Hop, W C; Opmeer, B C; Reitsma, J B; et al. (Surgical Endoscopy, 2022)
Abstract Background This study aimed to compare laparoscopic lavage and sigmoidectomy as treatment for perforated diverticulitis with purulent peritonitis during a 36 month follow-up of the LOLA trial. Methods Within the LOLA arm of the international, multicentre LADIES trial, patients with perforated diverticulitis with purulent peritonitis were randomised between laparoscopic lavage and sigmoidectomy. Outcomes were collected up to 36 months. The primary outcome of the present study was cumulative morbidity and mortality. Secondary outcomes included reoperations (including stoma reversals), stoma rates, and sigmoidectomy rates in the lavage group. Results Long-term follow-up was recorded in 77 of the 88 originally included patients, 39 were randomised to sigmoidectomy (51%) and 38 to laparoscopic lavage (49%). After 36 months, overall cumulative morbidity (sigmoidectomy 28/39 (72%) versus lavage 32/38 (84%), p = 0·272) and mortality (sigmoidectomy 7/39 (18%) versus lavage 6/38 (16%), p = 1·000) did not differ. The number of patients who underwent a reoperation was significantly lower for lavage compared to sigmoidectomy (sigmoidectomy 27/39 (69%) versus lavage 17/38 (45%), p = 0·039). After 36 months, patients alive with stoma in situ was lower in the lavage group (proportion calculated from the Kaplan–Meier life table, sigmoidectomy 17% vs lavage 11%, log-rank p = 0·0268). Eventually, 17 of 38 (45%) patients allocated to lavage underwent sigmoidectomy. Conclusion Long-term outcomes showed that laparoscopic lavage was associated with less patients who underwent reoperations and lower stoma rates in patients alive after 36 months compared to sigmoidectomy. No differences were found in terms of cumulative morbidity or mortality. Patient selection should be improved to reduce risk for short-term complications after which lavage could still be a valuable treatment option. Graphical abstract

Hartmann's procedure versus sigmoidectomy with primary anastomosis for perforated diverticulitis with purulent or faecal peritonitis (LADIES): a multicentre, parallel-group, randomised, open-label, superiority trial - Lambrichts, Daniël P V; Vennix, Sandra; Musters, Gijsbert D; Mulder, Irene M; Swank, Hilko A; Hoofwijk, Anton G M; Belgers, Eric H J; Stockmann, Hein B A C; Eijsbouts, Quirijn A J; Gerhards, Michael F; Van Wagensveld, Bart A; Van Geloven, Anna A W; et al. (The Lancet Gastroenterology & Hepatology, 2019)

Long-term outcomes of Hartmann’s procedure versus primary anastomosis for generalized peritonitis due to perforated diverticulitis: follow-up of a prospective multicenter randomized trial (DIVERTI) - Loire, M.; Bridoux, V.; Mege, D.; Mathonnet, M.; Mauvais, F.; Massonnaud, C.; Regimbeau, J. M.; Tuech, J. J. (International Journal of Colorectal Disease, 2021)

Long-term Outcome of Surgery Versus Conservative Management for Recurrent and Ongoing Complaints After an Episode of Diverticulitis: 5-year Follow-up Results of a Multicenter Randomized Controlled Trial (DIRECT-Trial) - Bolkenstein, Hendrike E.; Consten, Esther C. J.; Van Der Palen, Job; Van De Wall, Bryan J. M.; Broeders, Ivo A. M. J.; Bemelman, Willem A.; Lange, Johan F.; Boermeester, Marja A.; Draaisma, Werner A. (Annals of Surgery, 2019)
Objective: The aim of this study was to establish whether surgical or conservative treatment leads to a higher quality of life (QoL) in patients with recurring diverticulitis and/or ongoing complaints. Summary of Background Data: The 6 months’ results of the DIRECT trial, a randomized trial comparing elective sigmoidectomy with conservative management in patients with recurring diverticulitis (>2 episodes within 2 years) and/or ongoing complaints (>3 months) after an episode of diverticulitis, demonstrated a significantly higher QoL after elective sigmoidectomy. The aim of the present study was to evaluate QoL at 5-year follow-up. Methods: From January 2010 to June 2014, 109 patients were randomized to either elective sigmoidectomy (N = 53) or conservative management (N = 56). In the present study, the primary outcome was QoL measured by the Gastrointestinal Quality of Life Index (GIQLI) at 5-year follow-up. Secondary outcome measures were SF-36 score, Visual Analogue Score (VAS) pain score, EuroQol-5D-3L (EQ-5D-3L) score, morbidity, mortality, perioperative complications, and long-term operative outcome. Results: At 5-year follow-up, mean GIQLI score was significantly higher in the operative group [118.2 (SD 21.0)] than the conservative group [108.5 (SD 20.0)] with a mean difference of 9.7 (95% confidence interval 1.7–17.7). All secondary QoL outcome measures showed significantly better results in the operative group, with a higher SF-36 physical ( P = 0.030) and mental score ( P = 0.010), higher EQ5D score ( P = 0.016), and a lower VAS pain score ( P = 0.011). Twenty-six (46%) patients in the conservative group ultimately required surgery due to severe ongoing complaints. Of the operatively treated patients, 8 (11%) patients had anastomotic leakage and reinterventions were required in 11 (15%) patients. Conclusion: Consistent with the short-term results of the DIRECT trial, elective sigmoidectomy resulted in a significantly increased QoL at 5-year follow-up compared with conservative management in patients with recurring diverticulitis and/or ongoing complaints. Surgeons should counsel these patients for elective sigmoidectomy weighing superior QoL, less pain, and lower risk of new recurrences against the complication risk of surgery.

When Critical View of Safety Fails: A Practical Perspective on Difficult Laparoscopic Cholecystectomy - Alius, Catalin; Serban, Dragos; Bratu, Dan Georgian; Tribus, Laura Carina; Vancea, Geta; Stoica, Paul Lorin; Motofei, Ion; Tudor, Corneliu; Serboiu, Crenguta; Costea, Daniel Ovidiu; Serban, Bogdan; Dascalu, Ana Maria; et al. (Medicina, 2023)
The incidence of common bile duct injuries following laparoscopic cholecystectomy (LC) remains three times higher than that following open surgery despite numerous attempts to decrease intraoperative incidents by employing better training, superior surgical instruments, imaging techniques, or strategic concepts. This paper is a narrative review which discusses from a contextual point of view the need to standardise the surgical approach in difficult laparoscopic cholecystectomies, the main strategic operative concepts and techniques, complementary visualisation aids for the delineation of anatomical landmarks, and the importance of cognitive maps and algorithms in performing safer LC. Extensive research was carried out in the PubMed, Web of Science, and Elsevier databases using the terms ”difficult cholecystectomy”, ”bile duct injuries”, ”safe cholecystectomy”, and ”laparoscopy in acute cholecystitis”. The key content and findings of this research suggest there is high intersocietal variation in approaching and performing LC, in the use of visualisation aids, and in the application of safety concepts. Limited papers offer guidelines based on robust data and a timid recognition of the human factors and ergonomic concepts in improving the outcomes associated with difficult cholecystectomies. This paper highlights the most relevant recommendations for dealing with difficult laparoscopic cholecystectomies.

Colecistectomía segura: ¿Qué es y cómo hacerla? ¿Cómo lo hacemos nosotros? - Chama Naranjo, Alfredo; Farell Rivas, Jorge; Cuevas Osorio, Victor José (Revista Colombiana de Cirugía, 2021)
La colecistectomía laparoscópica es uno de los procedimientos más realizados a nivel mundial. La técnica laparoscópica se considera el estándar de oro para la resolución de la patología de la vesícula biliar secundaria a litiasis, y aunque es un procedimiento seguro, no se encuentra exenta de complicaciones. La complicación más grave es la lesión de la vía biliar, que, aunque es poco frecuente, con una incidencia de 0,2 a 0,4%, conduce a una disminución en la calidad de vida y contribuye a un aumento en la morbi-mortalidad. El objetivo de este artículo es reportar nuestra técnica quirúrgica, enfatizando los principios del programa de cultura para una colecistectomía segura, propuesta y descrita por the Society of American Gastrointestinal and Endoscopic Surgeons (SAGES), para minimizar los riesgos y obtener un resultado quirúrgico satisfactorio.

Safe laparoscopic cholecystectomy: Adoption of universal culture of safety in cholecystectomy - Gupta, Vishal; Jain, Gaurav (World Journal of Gastrointestinal Surgery, 2019)

Critical Decisions in the Management of Thoracic Trauma - Schellenberg, Morgan; Inaba, Kenji (Emergency Medicine Clinics of North America, 2018)

Western Trauma Association Critical Decisions in Trauma: Penetrating chest trauma - Karmy-Jones, Riyad; Namias, Nicholas; Coimbra, Raul; Moore, Ernest E.; Schreiber, Martin; McIntyre, Robert; Croce, Martin; Livingston, David H.; Sperry, Jason L.; Malhotra, Ajai K.; Biffl, Walter L. (Journal of Trauma and Acute Care Surgery, 2014)

Chest drain and thoracotomy for chest trauma - Bertoglio, Pietro; Guerrera, Francesco; Viti, Andrea; Terzi, Alberto Claudio; Ruffini, Enrico; Lyberis, Paraskevas; Filosso, Pier Luigi (Journal of Thoracic Disease, 2019)

Observing pneumothoraces: The 35-millimeter rule is safe for both blunt and penetrating chest trauma - Bou Zein Eddine, Savo; Boyle, Kelly A.; Dodgion, Christopher M.; Davis, Christopher S.; Webb, Travis P.; Juern, Jeremy S.; Milia, David J.; Carver, Thomas W.; Beckman, Marshall A.; Codner, Panna A.; Trevino, Colleen; De Moya, Marc A. (Journal of Trauma and Acute Care Surgery, 2019)
BACKGROUND As more pneumothoraxes (PTX) are being identified on chest computed tomography (CT), the empiric trigger for tube thoracostomy (TT) versus observation remains unclear. We hypothesized that PTX measuring 35 mm or less on chest CT can be safely observed in both penetrating and blunt trauma mechanisms. METHODS A retrospective review was conducted of all patients diagnosed with PTX by chest CT between January 2011 and December 2016. Patients were excluded if they had an associated hemothorax, an immediate TT (TT placed before the initial chest CT), or if they were on mechanical ventilation. Size of PTX was quantified by measuring the radial distance between the parietal and visceral pleura/mediastinum in a line perpendicular to the chest wall on axial imaging of the largest air pocket. Based on previous work, a cutoff of 35 mm on the initial CT was used to dichotomize the groups. Failure of observation was defined as the need for a delayed TT during the first week. A univariate analysis was performed to identify predictors of failure in both groups, and multivariate analysis was constructed to assess the independent impact of PTX measurement on the failure of observation while controlling for demographics and chest injuries. RESULTS Of the 1,767 chest trauma patients screened, 832 (47%) had PTX, and of those meeting inclusion criteria, 257 (89.0%) were successfully observed until discharge. Of those successfully observed, 247 (96%) patients had a measurement of 35 mm or less. The positive predictive value for 35 mm as a cutoff was 90.8% to predict successful observation. In the univariant analyses, rib fractures ( p = 0.048), Glasgow Coma Scale ( p = 0.012), and size of the PTX (≤35 mm or >35 mm) ( P < 0.0001) were associated with failed observation. In multivariate analysis, PTX measuring 35 mm or less was an independent predictor of successful observation (odds ratio, 0.142; 95% confidence interval, 0.047–0.428)] for the combined blunt and penetrating trauma patients. CONCLUSION A 35-mm cutoff is safe as a general guide with only 9% of stable patients failing initial observation regardless of mechanism. LEVEL OF EVIDENCE Therapeutic, level III.

Occult Pneumothorax in Trauma Patients: Development of an Objective Scoring System - De Moya, Marc A.; Seaver, Christopher; Spaniolas, Konstantinos; Inaba, Kenji; Nguyen, Michael; Veltman, Yevgeniy; Shatz, David; Alam, Hasan B.; Pizano, Louis (Journal of Trauma: Injury, Infection & Critical Care, 2007)

Perforated and bleeding peptic ulcer: WSES guidelines - Tarasconi, Antonio; Coccolini, Federico; Biffl, Walter L.; Tomasoni, Matteo; Ansaloni, Luca; Picetti, Edoardo; Molfino, Sarah; Shelat, Vishal; Cimbanassi, Stefania; Weber, Dieter G.; Abu-Zidan, Fikri M.; Campanile, Fabio C.; et al. (World Journal of Emergency Surgery, 2020)
Abstract Background Peptic ulcer disease is common with a lifetime prevalence in the general population of 5–10% and an incidence of 0.1–0.3% per year. Despite a sharp reduction in incidence and rates of hospital admission and mortality over the past 30 years, complications are still encountered in 10–20% of these patients. Peptic ulcer disease remains a significant healthcare problem, which can consume considerable financial resources. Management may involve various subspecialties including surgeons, gastroenterologists, and radiologists. Successful management of patients with complicated peptic ulcer (CPU) involves prompt recognition, resuscitation when required, appropriate antibiotic therapy, and timely surgical/radiological treatment. Methods The present guidelines have been developed according to the GRADE methodology. To create these guidelines, a panel of experts was designed and charged by the board of the WSES to perform a systematic review of the available literature and to provide evidence-based statements with immediate practical application. All the statements were presented and discussed during the 5th WSES Congress, and for each statement, a consensus among the WSES panel of experts was reached. Conclusions The population considered in these guidelines is adult patients with suspected complicated peptic ulcer disease. These guidelines present evidence-based international consensus statements on the management of complicated peptic ulcer from a collaboration of a panel of experts and are intended to improve the knowledge and the awareness of physicians around the world on this specific topic. We divided our work into the two main topics, bleeding and perforated peptic ulcer, and structured it into six main topics that cover the entire management process of patients with complicated peptic ulcer, from diagnosis at ED arrival to post-discharge antimicrobial therapy, to provide an up-to-date, easy-to-use tool that can help physicians and surgeons during the decision-making process.

Comparison of Glasgow-Blatchford score and full Rockall score systems to predict clinical outcomes in patients with upper gastrointestinal bleeding - Mokhtare, Marjan; Bozorgi, Vida; Agah, Shahram; Nikkhah, Mehdi; Faghihi, Amirhossein; Boghratian, Amirhossein; Shalbaf, Neda; Khanlari, Abbas; Seifmanesh, Hamidreza (Clinical and Experimental Gastroenterology, 2016)

Sepsis and septic shock - Cecconi, Maurizio; Evans, Laura; Levy, Mitchell; Rhodes, Andrew (The Lancet, 2018)

The Pathogenesis of Sepsis and Potential Therapeutic Targets - Huang, Min; Cai, Shaoli; Su, Jingqian (International Journal of Molecular Sciences, 2019)
Sepsis is defined as “a life-threatening organ dysfunction caused by a host’s dysfunctional response to infection”. Although the treatment of sepsis has developed rapidly in the past few years, sepsis incidence and mortality in clinical treatment is still climbing. Moreover, because of the diverse manifestations of sepsis, clinicians continue to face severe challenges in the diagnosis, treatment, and management of patients with sepsis. Here, we review the recent development in our understanding regarding the cellular pathogenesis and the target of clinical diagnosis of sepsis, with the goal of enhancing the current understanding of sepsis. The present state of research on targeted therapeutic drugs is also elaborated upon to provide information for the treatment of sepsis.

Sepsis-induced immunosuppression: mechanisms, diagnosis and current treatment options - Liu, Di; Huang, Si-Yuan; Sun, Jian-Hui; Zhang, Hua-Cai; Cai, Qing-Li; Gao, Chu; Li, Li; Cao, Ju; Xu, Fang; Zhou, Yong; Guan, Cha-Xiang; Jin, Sheng-Wei; et al. (Military Medical Research, 2022)
Abstract Sepsis is a common complication of combat injuries and trauma, and is defined as a life-threatening organ dysfunction caused by a dysregulated host response to infection. It is also one of the significant causes of death and increased health care costs in modern intensive care units. The use of antibiotics, fluid resuscitation, and organ support therapy have limited prognostic impact in patients with sepsis. Although its pathophysiology remains elusive, immunosuppression is now recognized as one of the major causes of septic death. Sepsis-induced immunosuppression is resulted from disruption of immune homeostasis. It is characterized by the release of anti-inflammatory cytokines, abnormal death of immune effector cells, hyperproliferation of immune suppressor cells, and expression of immune checkpoints. By targeting immunosuppression, especially with immune checkpoint inhibitors, preclinical studies have demonstrated the reversal of immunocyte dysfunctions and established host resistance. Here, we comprehensively discuss recent findings on the mechanisms, regulation and biomarkers of sepsis-induced immunosuppression and highlight their implications for developing effective strategies to treat patients with septic shock.

Trauma-Induced Coagulopathy - Feliciano, David V.; Mattox, Kenneth L.; Moore, Ernest E. (Trauma, 9e, 2020)

The Utility of Thromboelastography to Guide Blood Product Transfusion - Schmidt, Amy E; Israel, Anna Karolina; Refaai, Majed A (American Journal of Clinical Pathology, 2019)
Abstract Objectives To provide an overview of the clot viscoelastic testing technology and to describe its utility in guiding blood product transfusions. Methods A case scenario will be discussed as well as interpretation of thromboelastography (TEG) tracings. In addition, literature examining the utility of viscoelastic testing in guiding patient management and blood product transfusions will be reviewed. Results TEG/rotational thromboelastometry (ROTEM) is useful in evaluating clot kinetics in trauma and acutely bleeding patients. TEG/ROTEM parameters are reflective of values measured using standard coagulation assays; however, TEG/ROTEM parameters are more rapidly available and more costly. TEG and ROTEM are used in three main settings: cardiac surgery, liver transplantation, and trauma to assess global hemostasis and administration of blood products. Conclusions TEG/ROTEM can be helpful in guiding resuscitation and blood product transfusion. Several studies have demonstrated a reduction in transfusion of blood components with TEG/ROTEM; however, other studies have suggested that TEG/ROTEM is not clinically effective in guiding transfusion.

Viscoelastic Methods of Blood Clotting Assessment – A Multidisciplinary Review - Benes, Jan; Zatloukal, Jan; Kletecka, Jakub (Frontiers in Medicine, 2015)

metamedian: An R Package for Meta-Analyzing Studies Reporting Medians - Sean McGrath; XiaoFei Zhao; Omer Ozturk; Stephan Katzenschlager; Russell Steele; Andrea Benedetti (Research Synthesis Methods, 2024)

Infectious complications of intercostal nerve cryoablation mediated by perioperative hypothermia during pediatric Nuss procedure - Bundrant, Nikkida T.; Sayrs, Lois W.; Ostlie, Daniel; Lee, Justin; Egan, Craig; Molitor, Mark; Notrica, David; Padilla, Benjamin (Journal of Pediatric Surgery, 2022)

Impact of Cryoanalgesia Use During Minimally Invasive Pectus Excavatum Repair on Hospital Days and Total Hospital Costs Among Pediatric Patients - Hegde, Brittany N.; Avritscher, Elenir; Arshad, Seyed A.; Garcia, Elisa I.; Hebballi, Nutan B.; Broussard, Maryam; Tsao, KuoJen (Journal of Pediatric Surgery, 2023)

Prevention of Central-Line Associated Bloodstream Infections - Selby, Laura M.; Rupp, Mark E.; Cawcutt, Kelly A. (Infectious Disease Clinics of North America, 2021)

Prevention of Central Line–Associated Bloodstream Infections - Bell, Taison; O’Grady, Naomi P. (Infectious Disease Clinics of North America, 2017)

Diagnosis and treatment of catheter-related bloodstream infection: Clinical guidelines of the Spanish Society of Infectious Diseases and Clinical Microbiology and (SEIMC) and the Spanish Society of Spanish Society of Intensive and Critical Care Medicine and Coronary Units (SEMICYUC) - Chaves, F.; Garnacho-Montero, J.; Del Pozo, J.L.; Bouza, E.; Capdevila, J.A.; De Cueto, M.; Domínguez, M.Á.; Esteban, J.; Fernández-Hidalgo, N.; Fernández Sampedro, M.; Fortún, J.; Guembe, M.; et al. (Medicina Intensiva, 2018)

Epidural analgesia versus patient-controlled intravenous analgesia for pain following intra-abdominal surgery in adults - Salicath, Jon H; Yeoh, Emily Cy; Bennett, Michael H (Cochrane Database of Systematic Reviews, 2018)

Intercostal nerve cryoablation therapy for the repair of pectus excavatum: a systematic review - Eldredge, R. Scott; McMahon, Lisa (Frontiers in Surgery, 2023)
Introduction The minimally invasive repair of pectus excavatum (PE) is a painful procedure that can result in long-term hospitalization and opioid use. To mitigate the length of stay and opioid consumption, many different analgesia strategies have been implemented. The aim of this study is to review the use and patient outcomes of intercostal nerve cryoablation (INC) during PE repair reported in the literature. Methods An unfunded literature search using PubMed identifying articles discussing INC during PE repair from 1946 to 1 July 2023 was performed. Articles were included if they discussed patient outcomes with INC use during PE repair. Articles were excluded if they were reviews/meta-analyses, editorials, or not available in English. Each article was reviewed for bias by analyzing the study methods, data analysis, patient selection, and patient follow-up. Articles comparing outcomes of INC were considered significant if p -value was <0.05. Results A total of 34 articles were included in this review that described INC use during pectus repair. Most supported a decreased hospital length of stay and opioid use with INC. Overall, INC was associated with fewer short-term and long-term complications. However, the researchers reported varied results of total hospital costs with the use of INC. Conclusion The review was limited by a paucity of prospective studies and low number of patients who received INC. Despite this, the present data support INC as a safe and effective analgesic strategy during the repair of PE.

Are We Ready for Cryoablation in Children Undergoing Nuss Procedures? - Chidambaran, Vidya; Garcia, Victor F.; Brown, Rebeccah L. (Anesthesia & Analgesia, 2022)

Same day discharge for pectus excavatum—is it possible? - Rettig, R. Luke; Rudikoff, Andrew G.; Lo, Hoi Yee Annie; Lee, Constance W.; Vazquez, Walter D.; Rodriguez, Karen; Shaul, Donald B.; Conte, Antonio Hernandez; Banzali, Franklin M.; Sydorak, Roman M. (Journal of Pediatric Surgery, 2022)